A comparison of opposition control in turbulent boundary layer and turbulent channel flow - Stroh, Alexander; Frohnapfel, Bettina; Schlatter, Philipp; Hasegawa, Y. (Physics of Fluids, 2015)
A comparison between classical opposition control applied in the configuration of a fully developed turbulent channel flow and applied locally in a spatially developing turbulent boundary layer is presented. It is found that the control scheme yields similar drag reduction rates if compared at the same friction Reynolds numbers. However, a detailed analysis of the dynamical contributions to the skin friction coefficient reveals significant differences in the mechanism behind the drag reduction. While drag reduction in turbulent channel flow is entirely based on the attenuation of the Reynolds shear stress, the modification of the spatial flow development is essential for the turbulent boundary layer in terms of achievable drag reduction. It is shown that drag reduction due to this spatial development contribution becomes more pronounced with increasing Reynolds number (up to Reτ = 660, based on friction velocity and boundary layer thickness) and even exceeds drag reduction due to attenuation of the Reynolds shear stress. In terms of an overall energy balance, it is found that opposition control is less efficient in the turbulent boundary layer due to the inherently larger fluctuation intensities in the near wall region.
CRIS-Team Scopus Importer:2023-03-21

Actuator line simulations of a Joukowsky and Tjæreborg rotor using spectral element and finite volume methods - Kleusberg, E.; Sarmast, S.; Schlatter, Philipp; Ivanell, Stefan; Henningson, D. S. (Journal of Physics: Conference Series, 2016)
The wake structure behind a wind turbine, generated by the spectral element code Nek5000, is compared with that from the finite volume code EllipSys3D. The wind turbine blades are modeled using the actuator line method. We conduct the comparison on two different setups. One is based on an idealized rotor approximation with constant circulation imposed along the blades corresponding to Glauert's optimal operating condition, and the other is the Tjffireborg wind turbine. The focus lies on analyzing the differences in the wake structures entailed by the different codes and corresponding setups. The comparisons show good agreement for the defining parameters of the wake such as the wake expansion, helix pitch and circulation of the helical vortices. Differences can be related to the lower numerical dissipation in Nek5000 and to the domain differences at the rotor center. At comparable resolution Nek5000 yields more accurate results. It is observed that in the spectral element method the helical vortices, both at the tip and root of the actuator lines, retain their initial swirl velocity distribution for a longer distance in the near wake. This results in a lower vortex core growth and larger maximum vorticity along the wake. Additionally, it is observed that the break down process of the spiral tip vortices is significantly different between the two methods, with vortex merging occurring immediately after the onset of instability in the finite volume code, while Nek5000 simulations exhibit a 2-3 radii period of vortex pairing before merging.
CRIS-Team Scopus Importer:2023-03-21

Adaptive mesh refinement for steady flows in Nek5000 - Offermans, Nicolas; Peplinski, A.; Marin, O.; Schlatter, Philipp (Computers & Fluids, 2020)
Adaptive mesh refinement is performed in the framework of the spectral element method augmented by approaches to error estimation and control. The h-refinement technique is used for adapting the mesh, where selected grid elements are split by a quadtree (2D) or octree (3D) structure. Continuity between parent–child elements is enforced by high-order interpolation of the solution across the common faces. Parallel mesh partitioning and grid management respectively, are taken care of by the external libraries ParMETIS and p4est. Two methods are considered for estimating and controlling the error of the solution. The first error estimate is local and based on the spectral properties of the solution on each element. This method gives a local measure of the L2-norm of the solution over the entire computational domain. The second error estimate uses the dual-weighted residuals method — it is based on and takes into account both the local properties of the solution and the global dependence of the error in the solution via an adjoint problem. The objective of this second approach is to optimize the computation of a given functional of physical interest. The simulations are performed by using the code Nek5000 and three steady-state test cases are studied: a two-dimensional lid-driven cavity at Re=7,500, a two-dimensional flow past a cylinder at Re=40, and a three-dimensional lid-driven cavity at Re=2,000 with a moving lid tilted by an angle of 30∘. The efficiency of both error estimators is compared in terms of refinement patterns and accuracy on the functional of interest. In the case of the adjoint error estimators, the trend on the error of the functional is shown to be correctly represented up to a multiplicative constant.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Adjoint error estimators; Error indicators; Mesh optimization; Spectral methods

A description of turbulence intensity profiles for boundary layers with adverse pressure gradient - Drozdz, Artur; Elsner, Witold; Niegodajew, Pawel; Vinuesa, Ricardo; Orlu, Ramis; Schlatter, Philipp (European Journal of Mechanics B-Fluids, 2020)
The paper presents an extension of the diagnostic-plot scaling (Alfredsson et al., 2012) of the turbulence-intensity profiles for the outer region of adverse-pressure-gradient (APG) turbulent boundary layers (TBLs). An extended formula including the shape factor is proposed, which allows the diagnostic-plot scaling to be used in strong APGs at high Reynolds numbers. The validity of the new formulation is verified using several available databases. We demonstrate that the new formula allows to scale profiles in cases where the Clauser–Rotta pressure-gradient parameter β is below 14 even in presence of very strong flow-history effects. In order to extend the scaling to the near-wall region of TBLs the adapted complete difference function is proposed. The proposed scaling yields a unified description of the turbulence-intensity profiles regardless of their flow history (as opposed to other previously proposed scalings), and is valid for a wider range of cases not only for the outer but also for the inner region.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Pressure gradient; Streamwise Reynolds stress scaling; Turbulent boundary layer

Adjoint optimization of natural convection problems: differentially heated cavity - Saglietti, Clio; Schlatter, Philipp; Monokrousos, Antonios; Henningson, Dan S. (Theoretical and Computational Fluid Dynamics, 2017)
Optimization of natural convection-driven flows may provide significant improvements to the performance of cooling devices, but a theoretical investigation of such flows has been rarely done. The present paper illustrates an efficient gradient-based optimization method for analyzing such systems. We consider numerically the natural convection-driven flow in a differentially heated cavity with three Prandtl numbers (Pr= 0.15 - 7 ) at super-critical conditions. All results and implementations were done with the spectral element code Nek5000. The flow is analyzed using linear direct and adjoint computations about a nonlinear base flow, extracting in particular optimal initial conditions using power iteration and the solution of the full adjoint direct eigenproblem. The cost function for both temperature and velocity is based on the kinetic energy and the concept of entransy, which yields a quadratic functional. Results are presented as a function of Prandtl number, time horizons and weights between kinetic energy and entransy. In particular, it is shown that the maximum transient growth is achieved at time horizons on the order of 5 time units for all cases, whereas for larger time horizons the adjoint mode is recovered as optimal initial condition. For smaller time horizons, the influence of the weights leads either to a concentric temperature distribution or to an initial condition pattern that opposes the mean shear and grows according to the Orr mechanism. For specific cases, it could also been shown that the computation of optimal initial conditions leads to a degenerate problem, with a potential loss of symmetry. In these situations, it turns out that any initial condition lying in a specific span of the eigenfunctions will yield exactly the same transient amplification. As a consequence, the power iteration converges very slowly and fails to extract all possible optimal initial conditions. According to the authors’ knowledge, this behavior is illustrated here for the first time.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Adjoint optimization; Arnoldi method; Differentially heated cavity; Natural convection; Power iterations

Advances in Direct and Large-Eddy Simulations - Marchioli, Cristian; García-Villalba, Manuel; Salvetti, Maria Vittoria; Schlatter, Philipp (Flow Turbulence and Combustion, 2024)
CRIS-Team Scopus Importer:2024-01-19

Adverse-Pressure-Gradient Effects on Turbulent Boundary Layers: Statistics and Flow-Field Organization - Sanmiguel Vila, Carlos; Orlu, Ramis; Vinuesa, Ricardo; Schlatter, Philipp; Ianiro, Andrea; Discetti, Stefano (Flow Turbulence and Combustion, 2017)
This manuscripts presents a study on adverse-pressure-gradient turbulent boundary layers under different Reynolds-number and pressure-gradient conditions. In this work we performed Particle Image Velocimetry (PIV) measurements supplemented with Large-Eddy Simulations in order to have a dataset covering a range of displacement-thickness-based Reynolds-number 2300 <Re 34000 and values of the Clauser pressure-gradient parameter β up to 2.4. The spatial resolution limits of PIV for the estimation of turbulence statistics have been overcome via ensemble-based approaches. A comparison between ensemble-correlation and ensemble Particle Tracking Velocimetry was carried out to assess the uncertainty of the two methods. The effects of β, Re and of the pressure-gradient history on turbulence statistics were assessed. A modal analysis via Proper Orthogonal Decomposition was carried out on the flow fields and showed that about 20% of the energy contribution corresponds to the first mode, while 40% of the turbulent kinetic energy corresponds to the first four modes with no appreciable dependence on β and Re within the investigated range. The topology of the spatial modes shows a dependence on the Reynolds number and on the pressure-gradient strength, in line with the results obtained from the analysis of the turbulence statistics. The contribution of the modes to the Reynolds stresses and the turbulence production was assessed using a truncated low-order reconstruction with progressively larger number of modes. It is shown that the outer peaks in the Reynolds-stress profiles are mostly due to large-scale structures in the outer part of the boundary layer.
CRIS-Team Scopus Importer:2023-03-21
Keywords: PIV; POD; PTV; Wall turbulence

Aerodynamic Effects of Uniform Blowing and Suction on a NACA4412 Airfoil - Atzori, Marco; Vinuesa, Ricardo; Fahland, Georg; Stroh, Alexander; Gatti, Davide; Frohnapfel, Bettina; Schlatter, Philipp (Flow Turbulence and Combustion, 2020)
We carried out high-fidelity large-eddy simulations to investigate the effects of uniform blowing and uniform suction on the aerodynamic efficiency of a NACA4412 airfoil at the moderate Reynolds number based on chord length and incoming velocity of Rec= 200 , 000. We found that uniform blowing applied at the suction side reduces the aerodynamics efficiency, while uniform suction increases it. This result is due to the combined impact of blowing and suction on skin friction, pressure drag and lift. When applied to the pressure side, uniform blowing improves aerodynamic efficiency. The Reynolds-number dependence of the relative contributions of pressure and friction to the total drag for the reference case is analysed via Reynolds-averaged Navier–Stokes simulations up to Rec= 10 , 000 , 000. The results suggest that our conclusions on the control effect can tentatively be extended to a broader range of Reynolds numbers.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Active flow control; Aerodynamics; Turbulence simulation; Wing section

Aerodynamic free-flight conditions in wind tunnel modelling through reduced-order wall inserts - Tabatabaei, Narges; Orlu, Ramis; Vinuesa, Ricardo; Schlatter, Philipp (Fluids, 2021)
Parallel sidewalls are the standard bounding walls in wind tunnels when making a wind tunnel model for free-flight condition. The consequence of confinement in wind tunnel tests, known as wall-interference, is one of the main sources of uncertainty in experimental aerodynamics, limiting the realizability of free-flight conditions. Although this has been an issue when designing transonic wind tunnels and/or in cases with large blockage ratios, even subsonic wind tunnels at low-blockage-ratios might require wall corrections if a good representation of free-flight conditions is intended. In order to avoid the cumbersome streamlining methods especially for subsonic wind tunnels, a sensitivity analysis is conducted in order to investigate the effect of inclined sidewalls as a reduced-order wall insert in the airfoil plane. This problem is investigated via Reynolds-averaged Navier–Stokes (RANS) simulations, and a NACA4412 wing at the angles of attack between 0 and 11 degrees at a moderate Reynolds number (400 k) is considered. The simulations are validated with well-resolved large-eddy simulation (LES) results and experimental wind tunnel data. Firstly, the wall-interference contribution in aerodynamic forces, as well as the local pressure coefficients, are assessed. Furthermore, the isolated effect of confinement is analyzed independent of the boundary-layer growth. Secondly, wall-alignment is modified as a calibration parameter in order to reduce wall-interference based on the aforementioned assessment. In the outlined method, we propose the use of linear inserts to account for the effect of wind tunnel walls, which are experimentally simple to realize. The use of these inserts in subsonic wind tunnels with moderate blockage ratio leads to very good agreement between free-flight and wind tunnel data, while this approach benefits from simple manufacturing and experimental realization.
CRIS-Team Scopus Importer:2023-03-21
Keywords: CFD; Confinement; Free-flight; Insert wall; RANS; Wall interference; Wind tunnel

A High-Fidelity Flow Solver for Unstructured Meshes on Field-Programmable Gate Arrays: Design, Evaluation, and Future Challenges - Karp, Martin; Podobas, Artur; Kenter, Tobias; Jansson, Niclas; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (ACM International Conference Proceeding Series, 2022)
The impending termination of Moore's law motivates the search for new forms of computing to continue the performance scaling we have grown accustomed to. Among the many emerging Post-Moore computing candidates, perhaps none is as salient as the Field-Programmable Gate Array (FPGA), which offers the means of specializing and customizing the hardware to the computation at hand. In this work, we design a custom FPGA-based accelerator for a computational fluid dynamics (CFD) code. Unlike prior work - which often focuses on accelerating small kernels - we target the entire Poisson solver on unstructured meshes based on the high-fidelity spectral element method (SEM) used in modern state-of-the-art CFD systems. We model our accelerator using an analytical performance model based on the I/O cost of the algorithm. We empirically evaluate our accelerator on a state-of-the-art Intel Stratix 10 FPGA in terms of performance and power consumption and contrast it against existing solutions on general-purpose processors (CPUs). Finally, we propose a data movement-reducing technique where we compute geometric factors on the fly, which yields significant (700+ Gflop/s) single-precision performance and an upwards of 2x reduction in runtime for the local evaluation of the Laplace operator. We end the paper by discussing the challenges and opportunities of using reconfigurable architecture in the future, particularly in the light of emerging (not yet available) technologies.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Conjugate gradient method; Field-programmable gate array; High-level synthesis; Spectral element method

A low-dissipative, scale-selective discretization scheme for the Navier-Stokes equations - Vuorinen, Ville; Larmi, Martti; Schlatter, Philipp; Fuchs, L.; Boersma, B. J. (Computers & Fluids, 2012)
A new Scale-Selective Discretization (SSD) procedure for the Navier-Stokes equations is proposed. The aim is to reduce the numerical dissipation of already existing numerical schemes to make the SSD scheme easily implementable to the existing CFD codes. In particular, the new procedure is designed to decrease the dissipation errors arising from the discretization of the convection term using upwind-biased convection schemes. Such dissipative errors reduce the quality of high-fidelity simulation approaches in fluid dynamics such as Large-Eddy Simulations (LES). The new discretization procedure is based on separating small and large scales of the flow using a high-pass filter. As a first pre-processing step the convecting velocity field u i is decomposed into a rapidly fluctuating part ui' using the high-pass filter and a smooth part ui-ui'. After this the derivatives involving ui-ui' may be discretized with a centered scheme whereas the derivatives involving ui' can be discretized using an upwind method. The new procedure is tested in Navier-Stokes simulations by implementing the method into a second order accurate incompressible finite volume code based on the fractional step method. The numerical tests on the 2D lid-driven cavity at laminar conditions Re=2500 imply that the new method clearly improves the quality of the simulations. At Re=10,000 the SSD scheme captures the post-critical state of the cavity flow. The advantages of the new method are quantitatively assessed by studying a 2D temporally evolving shear layer. The results imply that the SSD scheme significantly reduces the numerical diffusion in contrast to the conventional upwind-biased schemes. Results from marginally resolved turbulent channel flow at Re τ=590 imply that the new scheme can be used for 3D simulations. © 2012 Elsevier Ltd.
CRIS-Team Scopus Importer:2023-03-21
Keywords: High-pass filtering; Large-Eddy Simulation; Scale-separation

A method to correct third and fourth order moments in turbulent flows - Talamelli, Alessandro; Segalini, Antonio; Orlu, Ramis; Schlatter, Philipp; Alfredsson, P. Henrik (Journal of Physics: Conference Series, 2011)
It is well known that spatial averaging, resulting from the finite size of a hot-wire probe, significantly affects the accuracy of such measurements in turbulent flows close to the wall. Here, a theoretical model which describes the effect of the spatial filtering of hot-wire probes on the third and fourth order moments of the streamwise velocity is presented. The model, which is based on the three (four) point velocity correlation function for the third (fourth) order moment, shows that the filtering can be related to a characteristic length scale which is an equivalent of the Taylor transverse micro-scale for the second order moment. The capacity of the model to accurately describe the attenuation is validated against direct numerical simulation (DNS) data of a zero pressure-gradient turbulent boundary layer. The DNS data allow the filtering effect to be appraised for different wire lengths and for the different moments. A procedure, based on the developed model, to correct the measured moments in turbulent flows is finally presented. The method is applied by combining the response of two single hot-wire sensors with different wire lengths. The technique has also been validated against spatially averaged DNS data showing a good capacity to reconstruct the actual profiles over the entire height of the boundary layer except, for the third order moment, in the region where the latter is close to zero.
CRIS-Team Scopus Importer:2023-03-21

A method to estimate turbulence intensity and transverse Taylor microscale in turbulent flows from spatially averaged hot-wire data - Segalini, Antonio; Orlu, Ramis; Schlatter, Philipp; Alfredsson, P. Henrik; Rueedi, Jean-Daniel; Talamelli, Alessandro (Experiments in Fluids, 2011)
A new approach to evaluate turbulence intensity and transverse Taylor microscale in turbulent flows is presented. The method is based on a correction scheme that compensates for probe resolution effects and is applied by combining the response of two single hot-wire sensors with different wire lengths. Even though the technique, when compared to other correction schemes, requires two independent measurements, it provides, for the same data, an estimate of the spanwise Taylor microscale. The method is here applied to streamwise turbulence intensity distributions of turbulent boundary layer flows but it is applicable generally in any turbulent flow. The technique has been firstly validated against spatially averaged DNS data of a zero pressure-gradient turbulent boundary layer showing a good capacity to reconstruct the actual profiles and to predict a qualitatively correct and quantitatively agreeing transverse Taylor microscale over the entire height of the boundary layer. Finally, the proposed method has been applied to available higher Reynolds number data from recent boundary layer experiments where an estimation of the turbulence intensity and of the Taylor microscale has been performed. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-21

An adverse-pressure-gradient turbulent boundary layer with nearly constant up to - Pozuelo, Ramon; Li, Qiang; Schlatter, Philipp; Vinuesa, Ricardo (Journal of Fluid Mechanics, 2022)
In this study, a new well-resolved large-eddy simulation of an incompressible near-equilibrium adverse-pressure-gradient (APG) turbulent boundary layer (TBL) over a flat plate is presented. In this simulation, we have established a near-equilibrium APG over a wide Reynolds-number range. In this so-called region of interest, the Rotta-Clauser pressure-gradient parameter exhibits an approximately constant value of around 1.4, and the Reynolds number based on momentum thickness reaches. To the best of the authors' knowledge, this is to date the highest achieved for a near-equilibrium APG TBL under an approximately constant moderate APG. We evaluated the self-similarity of the outer region using two scalings, namely the Zagarola-Smits and an alternative scaling based on edge velocity and displacement thickness. Our results reveal that outer-layer similarity is achieved, and the viscous scaling collapses the near-wall region of the mean flow in agreement with classical theory. Spectral analysis reveals that the APG displaces some small-scale energy from the near-wall to the outer region, an effect observed for all the components of the Reynolds-stress tensor, which becomes more evident at higher Reynolds numbers. In general, the effects of the APG are more noticeable at lower Reynolds numbers. For instance, the outer peak of turbulent-kinetic-energy (TKE) production is less prominent at higher. Although the scale separation increases with in zero-pressure-gradient TBLs, this effect becomes accentuated by the APG. Despite the reduction of the outer TKE production at higher Reynolds numbers, the mechanisms of energisation of large scales are still present.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulence simulation; turbulent boundary layers

A new high-order method for simulating turbulent pipe flow - Lenaers, Peter; Schlatter, Philipp; Brethouwer, Geert; Johansson, Arne V. (Springer Proceedings in Physics, 2016)
CRIS-Team Scopus Importer:2023-03-21

A new high-order method for the accurate simulation of incompressible wall-bounded flows - Lenaers, Peter; Schlatter, Philipp; Brethouwer, Geert; Johansson, Arne V. (ERCOFTAC Series, 2015)
A new high-order method for the accurate simulation of incompressible wall-bounded flows is presented. In stream- and spanwise direction the discretisation is performed by standard Fourier series, while in wall-normal direction the method combines high-order collocated compact finite differences with the influence matrix method to calculate the pressure boundary conditions that render the velocity field divergence-free. The main advantage over Chebyshev collocation is that in wall normal direction, the grid can be chosen freely and thus excessive clustering near the wall is avoided. Both explicit and implicit discretisations of the viscous terms are described, with the implicit method being more complex, but also having a wider range of applications. The method is validated by simulating fully turbulent channel flow at friction Reynolds number Reτ=395, and comparing our data with existing numerical results. The results show excellent agreement proving that the method simulates all physical processes correctly.
CRIS-Team Scopus Importer:2023-03-21

A new high-order method for the simulation of incompressible wall-bounded turbulent flows - Lenaers, Peter; Schlatter, Philipp; Brethouwer, Geert; Johansson, Arne V. (Journal of Computational Physics, 2014)
A new high-order method for the accurate simulation of incompressible wall-bounded flows is presented. In the stream- and spanwise directions the discretisation is performed by standard Fourier series, while in the wall-normal direction the method combines high-order collocated compact finite differences with the influence matrix method to calculate the pressure boundary conditions that render the velocity field exactly divergence-free. The main advantage over Chebyshev collocation is that in wall-normal direction, the grid can be chosen freely and thus excessive clustering near the wall is avoided. This can be done while maintaining the high-order approximation as offered by compact finite differences. The discrete Poisson equation is solved in a novel way that avoids any full matrices and thus improves numerical efficiency. Both explicit and implicit discretisations of the viscous terms are described, with the implicit method being more complex, but also having a wider range of applications. The method is validated by simulating two-dimensional Tollmien-Schlichting waves, forced transition in turbulent channel flow, and fully turbulent channel flow at friction Reynolds number Reτ = 395, and comparing our data with analytical and existing numerical results. In all cases, the results show excellent agreement showing that the method simulates all physical processes correctly. © 2014 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Collocated grid; Compact finite differences; High-order; Incompressible wall-bounded turbulent flows; Influence matrix method

A new perspective on skin-friction contributions in adverse-pressure-gradient turbulent boundary layers - Atzori, Marco; Mallor, Fermín; Pozuelo, Ramón; Fukagata, Koji; Vinuesa, Ricardo; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2023)
For adverse-pressure-gradient turbulent boundary layers, the study of integral skin-friction contributions still poses significant challenges. Beyond questions related to the integration boundaries and the derivation procedure, which have been thoroughly investigated in the literature, an important issue is how different terms should be aggregated. The nature of these flows, which exhibit significant in-homogeneity in the streamwise direction, usually results in cancellation between several contributions with high absolute values. We propose a formulation of the identity derived by Fukagata et al. (2002), which we obtained from the convective form of the governing equations. A new skin-friction contribution is defined, considering wall-tangential convection and pressure gradient together. This contribution is related to the evolution of the dynamic pressure in the mean flow. The results of the decomposition are examined for a broad range of pressure-gradient conditions and different flow-control strategies. We found that the new formulation of the identity allows to readily identify the different regimes of near-equilibrium conditions and approaching separation. It also provides a more effective description of control effects. A similar aggregation between convection and pressure-gradient terms is also possible for any other decomposition where in-homogeneity contributions are considered explicitly.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Adverse pressure gradients; Skin friction; Turbulent boundary layers

A NEW POINT OF VIEW ON SKIN-FRICTION CONTRIBUTIONS IN ADVERSE-PRESSURE-GRADIENT TURBULENT BOUNDARY LAYERS - Atzori, Marco; Stroh, Alexander; Gatti, Davide; Fukagata, Koji; Vinuesa, Ricardo; Schlatter, Philipp (12th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2022, 2022)
Skin-friction decompositions such as the so-called FIK identity (Fukagata et al., 2002) are useful tools in identifying relevant contributions to the friction, but may also lead to results difficult to interpret when the total friction is recovered from cancellation of multiple terms with large values. We propose a new formulation of the FIK contributions related to streamwise inhomogeneity, which is derived from the convective form of the momentum equation and using the concept of dynamic pressure. We examine turbulent boundary layers subjected to various pressure-gradient conditions, including cases with drag-reducing control. The new formulation distinguishes more precisely the roles of the free-stream pressure distribution, wall-normal convection, and turbulent fluctuations. Our results allow to identify different regimes in adverse-pressure-gradient turbulent boundary layers, corresponding to different proportions of the various contributions, and suggest a possible direction towards studying the onset of mean separation.
CRIS-Team Scopus Importer:2023-03-21

A numerical study of the unstratified and stratified Ekman layer - Deusebio, Enrico; Brethouwer, G.; Schlatter, Philipp; Lindborg, E. (Journal of Fluid Mechanics, 2014)
We study the turbulent Ekman layer at moderately high Reynolds number, 1600 < Re = δEG/nu < 3000, using direct numerical simulations (DNS). Here, δE = √2v/f is the laminar Ekman layer thickness, G the geostrophic wind, ν the kinematic viscosity and f is the Coriolis parameter. We present results for both neutrally, moderately and strongly stably stratified conditions. For unstratified cases, large-scale roll-like structures extending from the outer region down to the wall are observed. These structures have a clear dominant frequency and could be related to periodic oscillations or instabilities developing near the low-level jet. We discuss the effect of stratification and Re on one-point and two-point statistics. In the strongly stratified Ekman layer we observe stable co-existing large-scale laminar and turbulent patches appearing in the form of inclined bands, similar to other wall-bounded flows. For weaker stratification, continuously sustained turbulence strongly affected by buoyancy is produced. We discuss the scaling of turbulent length scales, height of the Ekman layer, friction velocity, veering angle at the wall and heat flux. The boundary-layer thickness, the friction velocity and the veering angle depend on Lf/uτ, where uτ is the friction velocity and L the Obukhov length scale, whereas the heat fluxes appear to scale with L+=Luτ/ν.
CRIS-Team Scopus Importer:2023-03-21
Keywords: atmospheric flows; turbulent boundary layers; turbulent flows

An uncertainty-quantification framework for assessing accuracy, sensitivity, and robustness in computational fluid dynamics - Rezaeiravesh, Saleh; Vinuesa, R.; Schlatter, Philipp (Journal of Computational Science, 2022)
Combining different existing uncertainty quantification (UQ) techniques, a framework is obtained to assess a set of metrics in computational physics problems, in general, and computational fluid dynamics (CFD), in particular. The metrics include accuracy, sensitivity and robustness of the simulator's outputs with respect to uncertain inputs and parameters. These inputs and parameters are divided into two groups: based on the variation of the first group (e.g. numerical/computational parameters such as grid resolution), a computer experiment is designed, the data of which may become uncertain due to the parameters of the second group (e.g. finite time-averaging). To construct a surrogate model based on uncertain data, Gaussian process regression (GPR) with observation-dependent (heteroscedastic) noise is used. To estimate the propagated uncertainties in the simulator's outputs from the first group of parameters, a probabilistic version of the polynomial chaos expansion (PCE) is employed Global sensitivity analysis is performed using probabilistic Sobol indices. To illustrate its capabilities, the framework is applied to the scale-resolving simulations of turbulent channel and lid-driven cavity flows using the open-source CFD solver Nek5000. It is shown that at wall distances where the time-averaging uncertainty is high, the quantities of interest are also more sensitive to numerical/computational parameters. In particular for high-fidelity codes such as Nek5000, a thorough assessment of the results’ accuracy and reliability is crucial. The detailed analyses and the resulting conclusions can enhance our insight into the influence of different factors on physics simulations, in particular the simulations of high-Reynolds-number turbulent flows including wall turbulence.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Combined uncertainties; Computational fluid dynamics; Gaussian process regression; Polynomial chaos expansion; Uncertainty quantification

Applying Bayesian optimization with Gaussian process regression to computational fluid dynamics problems - Morita, Y.; Rezaeiravesh, Saleh; Tabatabaei, Narges; Vinuesa, Ricardo; Fukagata, Koji; Schlatter, Philipp (Journal of Computational Physics, 2022)
Bayesian optimization (BO) based on Gaussian process regression (GPR) is applied to different CFD (computational fluid dynamics) problems which can be of practical relevance. The problems are i) shape optimization in a lid-driven cavity to minimize or maximize the energy dissipation, ii) shape optimization of the wall of a channel flow in order to obtain a desired pressure-gradient distribution along the edge of the turbulent boundary layer formed on the other wall, and finally, iii) optimization of the controlling parameters of a spoiler-ice model to attain the aerodynamic characteristics of the airfoil with an actual surface ice. The diversity of the optimization problems, independence of the optimization approach from any adjoint information, the ease of employing different CFD solvers in the optimization loop, and more importantly, the relatively small number of the required flow simulations reveal the flexibility, efficiency, and versatility of the BO-GPR approach in CFD applications. It is shown that to ensure finding the global optimum of the design parameters of the size up to 8, less than 90 executions of the CFD solvers are needed. Furthermore, it is observed that the number of flow simulations does not significantly increase with the number of design parameters. The associated computational cost of these simulations can be affordable for many optimization cases with practical relevance.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Bayesian optimization; Computational fluid dynamics; Gaussian process regression; Spoiler-ice model; Turbulent boundary layers

Appraisal of cavity hot-wire probes for wall-shear-stress measurements - Perez, Adalberto; Orlu, Ramis; Talamelli, Alessandro; Schlatter, Philipp (Experiments in Fluids, 2022)
Flush-mounted cavity hot-wire probes have emerged as an alternative to classical hot-wire probes mounted several diameters above the surface for wall-shear stress measurements. They aim at increasing the frequency response and accuracy by circumventing the well-known issue of heat transfer to the substrate that hot-wire and hot-film probes possess. Their use, however, depends on the assumption that the cavity does not influence the flow field. In this study, we show that this assumption does not hold, and that turbulence statistics are modified by the presence of the cavity with sizes that are practically in use. The mean velocity and fluctuations increase near the cavity while the shear stress decreases in its surroundings, all seemingly stemming from the fact that the no-slip condition is not present anymore and that flow reversal occurs. Overall, the energy spectra and the probability density function of the wall shear stress fluctuations indicate a change of nature of turbulence by the presence of the cavity.
CRIS-Team Scopus Importer:2023-03-21

Aspect ratio effect on particle transport in turbulent duct flows - Noorani, A.; Vinuesa, Ricardo; Brandt, L.; Schlatter, Philipp (Physics of Fluids, 2016)
The dynamics of dilute micron-sized spherical inertial particles in turbulent duct flows is studied by means of direct numerical simulations of the carrier phase turbulence with one-way coupled Lagrangian particles. The geometries are a square and a rectangular duct with width-to-height aspect ratio AR of 3 operating at Reτ,c = 360 (based on the centerplane friction velocity and duct half-height). The present study is designed to determine the effect of turbulence-driven secondary motion on the particle dynamics. Our results show that a weak cross-flow secondary motion significantly changes the cross-sectional map of the particle concentration, mean velocity, and fluctuations. As the geometry of the duct is widened from AR = 1 to 3, the secondary vortex on the horizontal wall significantly expands in the spanwise direction, and although the kinetic energy of the secondary flow increases close to the corner, it decays towards the duct centreplane in the AR = 3 case so as the turbulent carrier phase approaches the behavior in spanwise-periodic channel flows, a fact that significantly affects the particle statistics. In the square duct the particle concentration in the viscous sublayer is maximum at the duct centreplane, whereas the maximum is found closer to the corner, at a distance of |z/h| ≈ 1.25 from the centreplane, in the AR = 3 case. Interestingly the centreplane concentration in the rectangular duct is around 3 times lower than that in the square duct. Moreover, a second peak in the accumulation distribution is found right at the corners for both ducts. At this location the concentration increases with particle inertia. The secondary motion changes also the cross-stream map of the particle velocities significantly in comparison to the fluid flow statistics. These directly affect the particle velocity fluctuations such that multiple peaks appear near the duct walls for the particle streamwise and wall-normal velocity fluctuations.
CRIS-Team Scopus Importer:2023-03-21

Aspect ratio effects in turbulent duct flows studied through direct numerical simulation - Vinuesa, Ricardo; Noorani, Azad; Lozano-Duran, Adrian; El Khoury, George K.; Schlatter, Philipp; Fischer, Paul F.; Nagib, Hassan M. (Journal of Turbulence, 2014)
Three-dimensional effects in turbulent duct flows, i.e., sidewall boundary layers and secondary motions, are studied by means of direct numerical simulation (DNS). The spectral element code Nek5000 is used to compute turbulent duct flows with aspect ratios 1-7 (at Reb,c = 2800, Re τ,c ≃ 180) and aspect ratio 1 (at Reb,c = 5600, Reτ,c ≃ 330), in streamwise-periodic boxes of length 25h. The total number of grid points ranges from 28 to 145 million, and the pressure gradient is adjusted iteratively in order to keep the same bulk Reynolds number in the centreplane with changing aspect ratio. Turbulence is initiated via a trip forcing active during the initial stages of the simulation, and the statistical convergence of the data is discussed both in terms of transient approach and averaging period. Spanwise variations in wall shear, mean-flow profiles, and turbulence statistics are analysed as a function of aspect ratio, and also compared with the spanwise-periodic channel (as idealisation of an infinite aspect ratio duct). The computations show good agreement with experimental measurements carried out in parallel at the Illinois Institute of Technology (IIT) in Chicago, and highlight the relevance of sidewall boundary layers and secondary vortices in the physics of the duct flow. The rich array of secondary vortices extending throughout the upper and lower walls of the duct, and their dependence on Reynolds number and aspect ratio, had not been reported in the literature before. © 2014 Taylor and Francis.
CRIS-Team Scopus Importer:2023-03-21
Keywords: direct numerical simulation; secondary motions; secondary vortices/motions; three-dimensional flows; turbulent duct flow; wall turbulence

Assessment of direct numerical simulation data of turbulent boundary layers - Schlatter, Philipp; Orlu, Ramis (Journal of Fluid Mechanics, 2010)
Statistics obtained from seven different direct numerical simulations (DNSs) pertaining to a canonical turbulent boundary layer (TBL) under zero pressure gradient are compiled and compared. The considered data sets include a recent DNS of a TBL with the extended range of Reynolds numbers Reθ = 500-4300. Although all the simulations relate to the same physical flow case, the approaches differ in the applied numerical method, grid resolution and distribution, inflow generation method, boundary conditions and box dimensions. The resulting comparison shows surprisingly large differences not only in both basic integral quantities such as the friction coefficient cf or the shape factor H12, but also in their predictions of mean and fluctuation profiles far into the sublayer. It is thus shown that the numerical simulation of TBLs is, mainly due to the spatial development of the flow, very sensitive to, e.g. proper inflow condition, sufficient settling length and appropriate box dimensions. Thus, a DNS has to be considered as a numerical experiment and should be the subject of the same scrutiny as experimental data. However, if a DNS is set up with the necessary care, it can provide a faithful tool to predict even such notoriously difficult flow cases with great accuracy. © 2010 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulence simulation; turbulent boundary layers

Assessment of uncertainties in hot-wire anemometry and oil-film interferometry measurements for wall-bounded turbulent flows - Rezaeiravesh, Saleh; Vinuesa, Ricardo; Liefvendahl, Mattias; Schlatter, Philipp (European Journal of Mechanics B-Fluids, 2018)
In this study, the sources of uncertainty of hot-wire anemometry (HWA) and oil-film interferometry (OFI) measurements are assessed. Both statistical and classical methods are used for the forward and inverse problems, so that the contributions to the overall uncertainty of the measured quantities can be evaluated. The correlations between the parameters are taken into account through the Bayesian inference with error-in-variable (EiV) model. In the forward problem, very small differences were found when using Monte Carlo (MC), Polynomial Chaos Expansion (PCE) and linear perturbation methods. In flow velocity measurements with HWA, the results indicate that the estimated uncertainty is lower when the correlations among parameters are considered, than when they are not taken into account. Moreover, global sensitivity analyses with Sobol indices showed that the HWA measurements are most sensitive to the wire voltage, and in the case of OFI the most sensitive factor is the calculation of fringe velocity. The relative errors in wall-shear stress, friction velocity and viscous length are 0.44%, 0.23% and0.22%, respectively. Note that these values are lower than the ones reported in other wall-bounded turbulence studies. Note that in most studies of wall-bounded turbulence the correlations among parameters are not considered, and the uncertainties from the various parameters are directly added when determining the overall uncertainty of the measured quantity. In the present analysis we account for these correlations, which may lead to a lower overall uncertainty estimate due to error cancellation Furthermore, our results also indicate that the crucial aspect when obtaining accurate inner-scaled velocity measurements is the wind-tunnel flow quality, which is more critical than the accuracy in wall-shear stress measurements.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Hot-wire anemometry; Oil-film interferometry; Uncertainty quantification; Wall-bounded turbulence

AUTOMATIC ESTIMATION OF INITIAL TRANSIENT IN A TURBULENT FLOW TIME SERIES - Xavier, Donnatella; Rezaeiravesh, Saleh; Vinuesa, Ricardo; Schlatter, Philipp (World Congress in Computational Mechanics and ECCOMAS Congress, 2022)
An automatic method is proposed for the removal of the initialization bias that is intrinsic to the output of any statistically stationary simulation. The general techniques based on optimization approaches such as Beyhaghi et al. [1] following the Marginal Standard Error Rules (MSER) method of White et al. [16] were observed to be highly sensitive to the fluctuations in a time series and resulted in frequent overprediction of the length of the initial truncation. As fluctuations are an innate part of turbulence data, these techniques performed poorly on turbulence quantities, meaning that the local minima was often wrongly interpreted as the minimum variance in the time series and resulted in different transient point predictions for any increments to the sample size. This limitation was overcome by considering the finite difference of the slope of the variance computed in the optimization algorithm. The start of the zero slope region was considered as the initial transient truncation point. This modification to the standard approach eliminated the sensitivity of the scheme, and led to consistent estimates of the transient truncation point, provided that the finite difference time interval was chosen large enough to cover the fluctuations in the time series. Therefore, the step size for the finite difference slope was computed using both visual inspection of the time series and trial and error. We propose the Augmented Dickey-Fuller test as an automatic and reliable method to determine the truncation point, from which the time series is considered stationary and without an initialization bias.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Initial transient; Stationarity; Time series; Turbulent flow; Variance

Autoregressive models for quantification of time-averaging uncertainties in turbulent flows - Xavier, Donnatella; Rezaeiravesh, Saleh; Schlatter, Philipp (Physics of Fluids, 2024)
Autoregressive models (ARMs) can be powerful tools for quantifying uncertainty in the time averages of turbulent flow quantities. This is because ARMs are efficient estimators of the autocorrelation function (ACF) of statistically stationary turbulence processes. In this study, we demonstrate a method for order selection of ARMs that uses the integral timescale of turbulence. A crucial insight into the operating principles of the ARM in terms of the time span covered by the product of model order and spacing between samples is provided, which enables us to develop computationally efficient implementations of ARM-based uncertainty estimators. This approach facilitates the quantification of uncertainty in downsampled time series and on a series of autocorrelated batch means with minimal loss of accuracy. Furthermore, a method for estimating uncertainties in second-order moments using first-order uncertainties is discussed. These techniques are applied to the time series data of turbulent flow a) through a plane channel and b) over periodic hills. Additionally, we illustrate the potential of ARMs in generating synthetic turbulence time series. Our study presents autoregressive models as intuitive and powerful tools for turbulent flows, paving the way for further applications in the field.
CRIS-Team Scopus Importer:2024-10-18

A vorticity stretching diagnostic for turbulent and transitional flows - Malm, Johan; Schlatter, Philipp; Sandham, Neil D. (Theoretical and Computational Fluid Dynamics, 2012)
Vorticity stretching in wall-bounded turbulent and transitional flows has been investigated by means of a new diagnostic measure, denoted by, designed to pick up regions with large amounts of vorticity stretching. It is based on the maximum vorticity stretching component in every spatial point, thus yielding a three-dimensional scalar field. The measure was applied in four different flows with increasing complexity: (a) the near-wall cycle in an asymptotic suction boundary layer (ASBL), (b) K-type transition in a plane channel flow, (c) fully turbulent channel flow at Re t = 180 and (d) a complex turbulent three-dimensional separated flow. Instantaneous data show that the coherent structures associated with intense vorticity stretching in all four cases have the shape of flat 'pancake' structures in the vicinity of high-speed streaks, here denoted 'h-type' events. The other event found is of 'l-type', present on top of an unstable low-speed streak. These events (l-type) are further thought to be associated with the exponential growth of streamwise vorticity in the turbulent nearwall cycle. It was found that the largest occurrence of vorticity stretching in the fully turbulent wall-bounded flows is present at a wall-normal distance of y + = 6.5, i.e. in the transition between the viscous sublayer and buffer layer. The associated structures have a streamwise length of ̃200-300 wall units. In K-type transition, the measure accurately locates the regions of interest, in particular the formation of high-speed streaks near thewall (h-type) and the appearance of the hairpin vortex (l-type). In the turbulent separated flow, the structures containing large amounts of vorticity stretching increase in size and magnitude in the shear layer upstream of the separation bubble but vanish in the backflow region itself. Overall, the measure proved to be useful in showing growing instabilities before they develop into structures, highlighting the mechanisms creating high shear region on a wall and showing turbulence creation associated with instantaneous separations. © Springer-Verlag 2011.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Laminar-turbulent transition; Turbulent flows; Vorticity stretching

A vorticity stretching diagnostic for turbulent flows - Malm, Johan; Schlatter, Philipp; Sandham, Neil D. (7th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2011, 2011)
Vorticity stretching in wall-bounded turbulent and transitional flows has been investigated by means of a new diagnostic, designed to pick up regions with large amounts of vorticity stretching. It was found that the largest occurrence of vorticity stretching in fully turbulent channel flows is present at a wall-normal distance of y+ = 6.5, i.e. in the transition between the viscous sublayer and the buffer region. Instantaneous data showed that the coherent structures associated with these stretching events have the shape of flat ‘pancake structures’ in the vicinity of high-speed streaks, here denoted ‘h-type’ events. The other event found, also studied in an asymptotic suction boundary layer, is the ‘l-type’ event present on top of an unstable low-speed streak. These events are further thought to be associated with the exponential growth of streamwise vorticity in the turbulent near-wall cycle.
CRIS-Team Scopus Importer:2023-03-21

Backflow events under the effect of secondary flow of Prandtl's first kind - Chin, R. C.; Vinuesa, Ricardo; Orlu, R.; Cardesa, J.; Noorani, A.; Chong, M. S.; Schlatter, Philipp (Physical Review Fluids, 2020)
A study of the backflow events in the flow through a toroidal pipe at friction Reynolds number Reτ≈ 650 is performed and compared with the results in a straight turbulent pipe flow at Reτ≈ 500. The statistics and topological properties of the backflow events are analysed and discussed. Conditionally averaged flow fields in the vicinity of the backflow event are obtained, and the results for the torus show a similar streamwise wall-shear stress topology which varies considerably for the azimuthal wall-shear stress when compared to the pipe flow. In the region around the backflow events, critical points are observed. The comparison between the toroidal pipe and its straight counterpart also shows fewer backflow events and critical points in the torus. This is attributed to the secondary flow of Prandtl's first kind present in the toroidal pipe, which is responsible for the convection of momentum from the inner to the outer bend through the core of the pipe, and back from outer bend to the inner bend along the azimuthal direction. These results indicate that backflow events and critical points are genuine features of wall-bounded turbulence, and are not artefacts of specific boundary or inflow conditions in simulations and/or measurement uncertainties in experiments
CRIS-Team Scopus Importer:2023-03-21

Bayesian Optimisation with Gaussian Process Regression Applied to Fluid Problems - Rezaeiravesh, Saleh; Morita, Yuki; Tabatabaei, Narges; Vinuesa, Ricardo; Fukagata, Koji; Schlatter, Philipp (Springer Proceedings in Physics, 2021)
Bayesian optimisation based on Gaussian process regression (GPR) is an efficient gradient-free algorithm widely used in various fields of data sciences to find global optima. Based on a recent study by the authors, Bayesian optimisation is shown to be applicable to optimisation problems based on simulations of different fluid flows. Examples range from academic to more industrially-relevant cases. As a main conclusion, the number of flow simulations required in Bayesian optimisation was found not to exponentially grow with the dimensionality of the design parameters (hence, no curse of dimensionality). Here, the Bayesian optimisation method is outlined and its application to the shape optimisation of a two-dimensional lid-driven cavity flow is detailed.
CRIS-Team Scopus Importer:2023-03-21

Bayesian Optimization of Wall-Normal Blowing and Suction-Based Flow Control of a NACA 4412 Wing Profile - Mallor, Fermin; Semprini-Cesari, Giacomo; Mukha, Timofey; Rezaeiravesh, Saleh; Schlatter, Philipp (Flow Turbulence and Combustion, 2023)
Active flow-control techniques have shown promise for achieving high levels of drag reduction. However, these techniques are often complex and involve multiple tunable parameters, making it challenging to optimize their efficiency. Here, we present a Bayesian optimization (BO) approach based on Gaussian process regression to optimize a wall-normal blowing and suction control scheme for a NACA 4412 wing profile at two angles of attack: 5 and 11 ∘ , corresponding to cruise and high-lift scenarios, respectively. An automated framework is developed by linking the BO code to the CFD solver OpenFOAM. RANS simulations (validated against high-fidelity LES and experimental data) are used in order to evaluate the different flow cases. BO is shown to provide rapid convergence towards a global maximum, even when the complexity of the response function is increased by introducing a model for the cost of the flow control actuation. The importance of considering the actuation cost is highlighted: while some cases yield a net drag reduction (NDR), they may result in an overall power increase. Furthermore, optimizing for NDR or net power reduction (NPR) can lead to significantly different actuation strategies. Finally, by considering losses and efficiencies representative of real-world applications, still a significant NPR is achieved in the 11 ∘ case, while net power reduction is only marginally positive in the 5 ∘ case.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Bayesian optimization; Drag reduction; Flow control; Gaussian process regression; Turbulence

Bifurcation and stability analysis of a jet in cross-flow: Onset of global instability at a low velocity ratio - Ilak, Milos; Schlatter, Philipp; Bagheri, Shervin; Henningson, Dan S. (Journal of Fluid Mechanics, 2012)
We study direct numerical simulations (DNS) of a jet in cross-flow at low values of the jet-to-cross-flow velocity ratio R. We observe that, as the ratio R increases, the flow evolves from simple periodic vortex shedding (a limit cycle) to more complicated quasi-periodic behaviour, before finally becoming turbulent, as seen in the simulation of Bagheri et al. (J. Fluid. Mech., vol. 624, 2009b, pp. 33-44). The value of R at which the first bifurcation occurs for our numerical set-up is found, and shedding of hairpin vortices characteristic of a shear layer instability is observed. We focus on this first bifurcation, and find that a global linear stability analysis predicts well the frequency and initial growth rate of the nonlinear DNS at the critical value of R and that good qualitative predictions about the dynamics can still be made at slightly higher values of R where multiple unstable eigenmodes are present. In addition, we compute the adjoint global eigenmodes, and find that the overlap of the direct and the adjoint eigenmode, also known as a wavemaker, provides evidence that the source of the first instability lies in the shear layer just downstream of the jet. © 2012 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21
Keywords: absolute/convective instability; bifurcation; jets

Bypass transition and spot nucleation in boundary layers - Kreilos, Tobias; Khapko, Taras; Schlatter, Philipp; Duguet, Yohann; Henningson, Dan S.; Eckhardt, Bruno (Physical Review Fluids, 2016)
The spatiotemporal aspects of the transition to turbulence are considered in the case of a boundary-layer flow developing above a flat plate exposed to free-stream turbulence. Combining results on the receptivity to free-stream turbulence with the nonlinear concept of a transition threshold, a physically motivated model suggests a spatial distribution of spot nucleation events. To describe the evolution of turbulent spots a probabilistic cellular automaton is introduced, with all parameters directly obtained from numerical simulations of the boundary layer. The nucleation rates are then combined with the cellular automaton model, yielding excellent quantitative agreement with the statistical characteristics for different free-stream turbulence levels. We thus show how the recent theoretical progress on transitional wall-bounded flows can be extended to the much wider class of spatially developing boundary-layer flows.
CRIS-Team Scopus Importer:2023-03-21

Bypass transition delay using oscillations of spanwise wall velocity - Negi, Prabal S.; Mishra, Maneesh; Schlatter, Philipp; Skote, Martin (Physical Review Fluids, 2019)
Large eddy simulations are performed to investigate the possibility of bypass transition delay in spatially developing boundary layers. An open loop wall control mechanism is employed which consists of either spatial or temporal oscillations of the spanwise wall velocity. Both spatial and temporal oscillations show a delay in the sharp rise in skin friction coefficient which is characteristic of laminar-turbulent transition. An insight into the mechanism is offered based on a secondary filtering of the continuous Orr-Sommerfeld-Squire (OSQ) modes provided by the Stokes layer, and it is shown that the control mechanism selectively affects the low-frequency penetrating modes of the OSQ spectrum. This perspective clarifies the limitations of the mechanism's capability to create transition delay. Furthermore, we extend the two-mode model of bypass transition proposed by T. Zaki and P. Durbin [J. Fluid Mech. 531, 85 (2005)JFLSA70022-112010.1017/S0022112005003800] to cases with wall control and illustrate the selective action of the wall oscillations on the penetrating mode in this simplified case.
CRIS-Team Scopus Importer:2023-03-21

Bypass transition in boundary layers as an activated process - Kreilos, Tobias; Khapko, Taras; Schlatter, Philipp; Duguet, Yohann; Henningson, Dan S.; Eckhardt, Bruno (Proceedings - 15th European Turbulence Conference, ETC 2015, 2015)
We consider the spatio-temporal aspects of the transition to turbulence in a boundary layer above a flat plate exposed to free-stream turbulence. Combining results from the receptivity to free-stream turbulence with the observation of a double threshold from transition studies in e.g. pipe flow we arrive at a physically motivated prediction for the spatial distribution of nucleation events in boundary layers. We use a cellular automaton to implement a complete model for the spatial and temporal evolution of turbulent patches and show that the model reproduces the statistical features of the boundary layer remarkably well. The success of the modeling shows that bypass transition occurs as a spatiotemporally activated process, where transition is triggered by critical fluctuations imported from the free-stream turbulence.
CRIS-Team Scopus Importer:2023-03-21

Characterisation of backflow events over a wing section - Vinuesa, Ricardo; Orlu, Ramis; Schlatter, Philipp (Journal of Turbulence, 2017)
Rare backflow (negative wall-shear stress) events have recently been found and quantified in the near-wall region of canonical wall-bounded turbulent flows. Although their existence and correlation with large-scale events have been established beyond numerical and measurement technique uncertainties, their occurrence at numerically high Reynolds numbers is still rare (less than 1 per thousand and 1 per million at the wall and beyond the viscous sublayer, respectively). To better quantify these rare events, the turbulent boundary layer developing over the suction side of a wing section, experiencing an increasing adverse pressure gradient (APG) without separation along its chord c, is considered in the present work. We find that the backflow level of 0.06% documented in turbulent channels and zero-pressure-gradient (ZPG) turbulent boundary layers is already exceeded on the suction side for x/c > 0.3, at friction Reynolds numbers three times lower, while close to the trailing edge the backflow level reaches 30%. Conditional analysis of extreme events indicates that for increasing Clauser pressure-gradient parameters (reaching β ≃ 35), the flow reaches a state in which the extreme events are more likely aligned with or against the freestream, and that the otherwise strong spanwise component of the wall-shear stress reduces towards the vicinity of the trailing edge. Backflow events subjected to moderate up to strong APG conditions (0.6 < β < 4.1) exhibit an average width of Δz+ ≃ 20, and an average lifetime of Δt+ ≃ 2. This directly connects with the findings by Lenaers et al., and implies that there is a connection between high-Re ZPG and strong APG conditions.
CRIS-Team Scopus Importer:2023-03-21
Keywords: adverse pressure gradient; backflow; separation; Turbulent boundary layers; wings

Characterisation of the steady, laminar incompressible flow in toroidal pipes covering the entire curvature range - Canton, Jacopo; Orlu, Ramis; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2017)
This work is concerned with a detailed investigation of the steady (laminar), incompressible flow inside bent pipes. In particular, a toroidal pipe is considered in an effort to isolate the effect of the curvature, δ, on the flow features, and to compare the present results to available correlations in the literature. More than 110 000 numerical solutions are computed, without any approximation, spanning the entire curvature range, 0 ≤ δ ≤ 1, and for bulk Reynolds numbers Re up to 7 000, where the flow is known to be unsteady. Results show that the Dean number De provides a meaningful non-dimensional group only below very strict limits on the curvature and the Dean number itself. For δ>10−6 and De > 10, in fact, not a single flow feature is found to scale well with the Dean number. These considerations are also valid for quantities, such as the Fanning friction factor, that were previously considered Dean-number dependent only. The flow is therefore studied as a function of two equally important, independent parameters: the curvature of the pipe and the Reynolds number. The analysis shows that by increasing the curvature the flow is fundamentally changed. Moderate to high curvatures are not only quantitatively, but also qualitatively different from low δ cases. A complete description of some of the most relevant flow quantities is provided. Most notably the friction factor f for laminar flow in curved pipes by Ito [J. Basic Eng. 81:123–134 (1959)] is reproduced, the influence of the curvature on f is quantified and the scaling is discussed. A complete database including all the computed solutions is available at www.flow.kth.se.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Bent pipes; Dean number; Friction factor

Characterization of the massively separated wake behind a square cylinder by means of direct numerical simulation - Vinuesa, Ricardo; Schlatter, Philipp; Henningson, Dan S. (Springer Proceedings in Physics, 2016)
The massively separated wake behind a wall-mounted square cylinder is investigated by means of direct numerical simulation (DNS). The effect of inflow conditions is assessed by considering two different cases with matching momentum thickness Reynolds numbers Reθ ≃ 1000 at the location of the cylinder: one with a fully-turbulent boundary layer as inflow condition, and another one with a laminar boundary layer. The main simulation is performed by using the spectral element code Nek5000. While in the laminar-inflow simulation the horseshoe vortex forming around the cylinder can be observed in the instantaneous flow fields, this is not the case in the turbulent-inflow simulation. Besides, the streaks in the turbulent case become greatly attenuated on both sides of the obstacle. By analyzing the Reynolds shear stress uv, we show that this is due to the modulation of the horseshoe vortex by the turbulence from the incoming boundary layer.
CRIS-Team Scopus Importer:2023-03-21

Characterization of the secondary flow in hexagonal ducts - Marin, Oana; Vinuesa, Ricardo; Obabko, A. V.; Schlatter, Philipp (Physics of Fluids, 2016)
In this work we report the results of DNSs and LESs of the turbulent flow through hexagonal ducts at friction Reynolds numbers based on centerplane wall shear and duct half-height Reτ,c ≃ 180, 360, and 550. The evolution of the Fanning friction factor f with Re is in very good agreement with experimental measurements. A significant disagreement between the DNS and previous RANS simulations was found in the prediction of the in-plane velocity, and is explained through the inability of the RANS model to properly reproduce the secondary flow present in the hexagon. The kinetic energy of the secondary flow integrated over the cross-sectional area ≪K≫yz decreases with Re in the hexagon, whereas it remains constant with Re in square ducts at comparable Reynolds numbers. Close connection between the values of Reynolds stress on the horizontal wall close to the corner and the interaction of bursting events between the horizontal and inclined walls is found. This interaction leads to the formation of the secondary flow, and is less frequent in the hexagon as Re increases due to the 120° aperture of its vertex, whereas in the square duct the 90° corner leads to the same level of interaction with increasing Re. Analysis of turbulence statistics at the centerplane and the azimuthal variance of the mean flow and the fluctuations shows a close connection between hexagonal ducts and pipe flows, since the hexagon exhibits near-axisymmetric conditions up to a distance of around 0.15DH measured from its center. Spanwise distributions of wall-shear stress show that in square ducts the 90° corner sets the location of a high-speed streak at a distance zv+ ≃ 50 from it, whereas in hexagons the 120° aperture leads to a shorter distance of zv+ ≃ 38. At these locations the root mean square of the wall-shear stresses exhibits an inflection point, which further shows the connections between the near-wall structures and the large-scale motions in the outer flow.
CRIS-Team Scopus Importer:2023-03-21

Characterization of the secondary flow in turbulent rectangular ducts with varying aspect ratio - Vinuesa, Ricardo; Schlatter, Philipp; Nagib, Hassan M. (9th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2015, 2015)
Direct numerical simulations of turbulent duct flows with width-to-height ratios 1, 3, 5, 7 and 10, at a friction Reynolds number Reτ,c, 180, are carried out with the spectral element code Nek5000. The aim of these simulations is to gain insight into the kinematics and dynamics of Prandtl's secondary flow of second kind, and its impact on the flow physics of wall-bounded turbulence. The secondary flow is characterized in terms of the cross-plane mean kinetic energy K = (V2 + W2)/2, and its variation in the spanwise direction of the flow. Our results show that averaging times of at least 3,000 time units are required to reach a converged state of the secondary flow, which extends up to z∗ ≈ 5h from the side walls. We also show that if the duct is not wide enough to accommodate the whole extent of the secondary flow, then its structure is modified by means of a different spanwise distribution of energy. The kinetic energy of the secondary flow for z∗ > 5h in aspect ratios 7 and 10 exhibits a decaying level of energy, and the rate of decay is approximately (Kyz) ∼ TA-1. This is the same rate of decay observed in a spanwise-periodic simulation, which suggests that at the core, (K)yz behaves as a random variable with zero mean, with rate of decay consistent with central limit theorem theory. Non-stationary effects of the secondary flow may persist into the core for all the aspect ratios we have run so far, and may interact with the dynamics of the nominally homogeneous flow that would exist in a channel. The non-stationary effects will be presented and further discussed in the Symposium. Note that these conclusions are limited to the low Reynolds number range under consideration, and additional data will be necessary to assess Reynolds number effects.
CRIS-Team Scopus Importer:2023-03-21

Characterization of turbulent coherent structures in square duct flow - Atzori, Marco; Vinuesa, Ricardo; Lozano-Duran, Adrian; Schlatter, Philipp (Journal of Physics: Conference Series, 2018)
This work is aimed at a first characterization of coherent structures in turbulent square duct flows. Coherent structures are defined as connected components in the domain identified as places where a quantity of interest (such as Reynolds stress or vorticity) is larger than a prescribed non-uniform threshold. Firstly, we qualitatively discuss how a percolation analysis can be used to assess the effectiveness of the threshold function, and how it can be affected by statistical uncertainty. Secondly, various physical quantities that are expected to play an important role in the dynamics of the secondary flow of Prandtl's second kind are studied. Furthermore, a characterization of intense Reynolds-stress events in square duct flow, together with a comparison of their shape for analogous events in channel flow at the same Reynolds number, is presented.
CRIS-Team Scopus Importer:2023-03-21

Coherent structures and dominant frequencies in a turbulent three-dimensional diffuser - Malm, Johan; Schlatter, Philipp; Henningson, Dan S. (Journal of Fluid Mechanics, 2012)
Dominant frequencies and coherent structures are investigated in a turbulent, three-dimensional and separated diffuser flow at Re= 10000 (based on bulk velocity and inflow-duct height), where mean flow characteristics were first studied experimentally by Cherry, Elkins and Eaton (Intl J. Heat Fluid Flow, vol. 29, 2008, pp. 803-811) and later numerically by Ohlsson etal.(J. Fluid Mech., vol. 650, 2010, pp. 307-318). Coherent structures are educed by proper orthogonal decomposition (POD) of the flow, which together with time probes located in the flow domain are used to extract frequency information. The present study shows that the flow contains multiple phenomena, well separated in frequency space. Dominant large-scale frequencies in a narrow band St = fh/ub ∈ [0. 0092, 0. 014] (where h is the inflow-duct height and u-b is the bulk velocity), yielding time periods T* = Tu b/h∈ [70, 110] , are deduced from the time signal probes in the upper separated part of the diffuser. The associated structures identified by the POD are large streaks arising from a sinusoidal oscillating motion in the diffuser. Their individual contributions to the total kinetic energy, dominated by the mean flow, are, however, small. The reason for the oscillating movement in this low-frequency range is concluded to be the confinement of the flow in this particular geometric set-up in combination with the high Reynolds number and the large separated zone on the top diffuser wall. Based on this analysis, it is shown that the bulk of the streamwise root mean square (r.m.s.) value arises due to large-scale motion, which in turn can explain the appearance of two or more peaks in the streamwise r.m.s. value. The weak secondary flow present in the inflow duct is shown to survive into the diffuser, where it experiences an imbalance with respect to the upper expanding corners, thereby giving rise to the asymmetry of the mean separated region in the diffuser. © 2012 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21
Keywords: jets; separated flows; turbulence simulation

Coherent structures in the turbulent stepped cylinder flow at ReD=5000 - Massaro, Daniele; Peplinski, Adam; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2023)
The coherent structures arising in the turbulent flow around a three-dimensional stepped (or step) cylinder are studied through direct numerical simulation. This geometry is widespread in many applications and the junction substantially modifies the wake behaviour, generating three main cells. The mechanisms of vortex connections on the junction are difficult to be captured and interpreted. We thus use a high-order spectral-element methodology (SEM), and the adaptive mesh refinement technique (AMR) to adequately resolve each region of the domain, capturing the smallest turbulent scales. In this way, we can analyse the vortical interactions on the junction via the λ2-criterion and understand the evolution of the train of hairpins, which appears only when the cylinder shear layer gets unstable. Together with the hairpins, four horseshoe and edge vortices coexist on the flat junction surface. A complete picture of the vortices’ evolution in time is provided. To extract the large-scale, and most energetic, structures in the wake we perform a three-dimensional proper orthogonal decomposition (POD) of the flow. The first six POD modes correspond to three travelling modes which identify the large (L), the small (S) and the modulation (N) cells. The ReD trend shows that these cells persist at higher Reynolds numbers with a larger separation between the vortex shedding frequencies fN and fL. At the same time, the downwash POD mode gets less strong with a more intense and localised modulation region which affects a more extended portion of the large cylinder wake.
CRIS-Team Scopus Importer:2023-05-12
Keywords: Coherent structures; Modal analysis; Stepped cylinder; Vortex dynamics

Coherent structures in turbulent boundary layers over an airfoil - Atzori, Marco; Vinuesa, Ricardo; Lozano-Durán, Adrián; Schlatter, Philipp (Journal of Physics: Conference Series, 2020)
This preliminary study is concerned with the identification of three-dimensional coherent structures, defined as intense Reynolds-stress events, in the turbulent boundary layer developing over the suction side of a NACA4412 airfoil at a Reynolds number based on the chord lenght and the incoming velocity of Rec = 200, 000. The scientific interest for such flows originates from the non-uniform adverse pressure gradient that affects the boundary-layer development. Firstly, we assess different methods to identify the turbulent-non-turbulent interface, in order to exclude the irrotational region from the analysis. Secondly, we evaluate the contribution of the considered coherent structures to the enhanced wall-normal velocity, characteristic of adverse pressure gradients. Our results show that it is necessary to limit the detection of coherent structures to the turbulent region of the domain, and that the structures reveal qualitative differences between the contributions of intense events to the wall-normal velocity in adverse-pressure-gradient and zero-pressure-gradient turbulent boundary layers.
CRIS-Team Scopus Importer:2023-03-21

Comment on "evolution of wall shear stress with Reynolds number in fully developed turbulent channel flow experiments" - Orlu, R.; Schlatter, Philipp (Physical Review Fluids, 2020)
The recent study by Gubian et al. [Phys. Rev. Fluids 4, 074606 (2019)2469-990X10.1103/PhysRevFluids.4.074606], based on a new wall-shear-stress sensor in a low-Reynolds-number Re turbulent channel flow, came to the surprising conclusion that the magnitude of the fluctuating wall-shear stress τw,rms+ reaches an asymptotic value of 0.44 beyond the friction Reynolds number Reτ≈600. This statement is at odds with results from well-established direct numerical simulation (DNS) results that exceed the authors' highest Reynolds number by up to a factor of 5 while exhibiting a clear Reynolds-number dependence. Furthermore, they claim that "prior estimates of these quantities did not resolve the full range of wall-shear-stress fluctuations, which extended beyond 10 standard deviations above the mean."This contradicts high-quality DNS results and calls for a more in-depth explanation, which is given in the present Comment. We shows that the measurements by Gubian et al. suffer from spatial-resolution issues among others, which when accounted for invalidate the statements made of an asymptotic state at Reτ≈600 and resurrects the Reynolds-number dependence of τw,rms+ for which DNS evidence exists exceeding Reτ≈600 by an order of magnitude.
CRIS-Team Scopus Importer:2023-03-21

Comparison of experiments and simulations for zero pressure gradient turbulent boundary layers at moderate Reynolds numbers - Orlu, Ramis; Schlatter, Philipp (Experiments in Fluids, 2013)
A detailed comparison between recent direct numerical simulation (DNS) and experiments of a turbulent boundary layer under zero pressure gradient at Re θ = 2,500 and 4,000 (based on the free-stream velocity and momentum-loss thickness) is presented. The well-resolved DNS is computed in a long spatial domain (Schlatter and Örlü in J Fluid Mech 659:116, 2010a), including the disturbance strip, while the experiments consist of single hot-wire probe and oil-film interferometry measurements. Remarkably, good agreement is obtained for integral quantities such as skin friction and shape factor, as well as mean and fluctuating streamwise velocity profiles, higher-order moments and probability density distributions. The agreement also extends to spectral/structural quantities such as the amplitude modulation of the small scales by the large-scale motion and temporal spectral maps throughout the boundary layer. Differences within the inner layer observed for statistical and spectral quantities could entirely be removed by spatially averaging the DNS to match the viscous-scaled length of the hot-wire sensor, thereby explaining observed differences solely by insufficient spatial resolution of the hot-wire sensor. For the highest Reynolds number, Re θ = 4,000, the experimental data exhibit a more pronounced secondary spectral peak in the outer region (y/δ 99 = 0.1) related to structures with length on the order of 5-7 boundary layer thicknesses, which is weaker and slightly moved towards lower temporal periods in the DNS. The cause is thought to be related to the limited spanwise box size which constrains the growth of the very large structures. In the light of the difficulty to obtain "canonical" flow conditions, both in DNS and the wind tunnel where effects such as boundary treatment, pressure gradient and turbulence tripping need to be considered, the present cross-validation of the data sets, at least for the present Re θ -range, provides important reference data for future studies and highlights the importance of taking spatial resolution effects into account when comparing experiment and DNS. For the considered flow, the present data also provide quantitative guidelines on what level of accuracy can be expected for the agreement between DNS and experiments. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-21

Comparison of SGS models for passive scalar mixing in turbulent channel flows - Li, Qiang; Schlatter, Philipp; Henningson, Dan S. (ERCOFTAC Series, 2011)
CRIS-Team Scopus Importer:2023-03-21

Complexity of localised coherent structures in a boundary-layer flow - Khapko, Taras; Duguet, Yohann; Kreilos, Tobias; Schlatter, Philipp; Eckhardt, Bruno; Henningson, Dan S. (European Physical Journal E, 2014)
We study numerically transitional coherent structures in a boundary-layer flow with homogeneous suction at the wall (the so-called asymptotic suction boundary layer ASBL). The dynamics restricted to the laminar-turbulent separatrix is investigated in a spanwise-extended domain that allows for robust localisation of all edge states. We work at fixed Reynolds number and study the edge states as a function of the streamwise period. We demonstrate the complex spatio-temporal dynamics of these localised states, which exhibits multistability and undergoes complex bifurcations leading from periodic to chaotic regimes. It is argued that in all regimes the dynamics restricted to the edge is essentially low-dimensional and non-extensive. © 2014 EDP Sciences, SIF, Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-21

Computing Optimal Forcing Using Laplace Preconditioning - Brynjell-Rahkola, M.; Tuckerman, L. S.; Schlatter, Philipp; Henningson, D. S. (Communications in Computational Physics, 2017)
For problems governed by a non-normal operator, the leading eigenvalue of the operator is of limited interest and a more relevant measure of the stability is obtained by considering the harmonic forcing causing the largest system response. Various methods for determining this so-called optimal forcing exist, but they all suffer from great computational expense and are hence not practical for large-scale problems. In the present paper a new method is presented, which is applicable to problems of arbitrary size. The method does not rely on timestepping, but on the solution of linear systems, in which the inverse Laplacian acts as a preconditioner. By formulating the search for the optimal forcing as an eigenvalue problem based on the resolvent operator, repeated system solves amount to power iterations, in which the dominant eigenvalue is seen to correspond to the energy amplification in a system for a given frequency, and the eigenfunction to the corresponding forcing function. Implementation of the method requires only minor modifications of an existing timestepping code, and is applicable to any partial differential equation containing the Laplacian, such as the Navier-Stokes equations. We discuss the method, first, in the context of the linear Ginzburg-Landau equation and then, the two-dimensional lid-driven cavity flow governed by the Navier-Stokes equations. Most importantly, we demonstrate that for the lid-driven cavity, the optimal forcing can be computed using a factor of up to 500 times fewer operator evaluations than the standard method based on exponential timestepping.
CRIS-Team Scopus Importer:2023-03-21
Keywords: eigenvalue problem; Ginzburg-Landau equation; Hydrodynamic stability; iterative methods; Laplace preconditioner; lid-driven cavity flow; optimal forcing

Contribution of Reynolds-stress structures to the secondary flow in turbulent ducts - Atzori, Marco; Vinuesa, Ricardo; Lozano-Durán, Adrián; Schlatter, Philipp (11th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2019, 2019)
The present work is aimed at evaluating the contribution to the secondary flow in duct flow with square and rectangular cross section from three-dimensional coherent structures, defined as intense Reynolds-stress events. The contribution to a certain mean quantity is defined as the ensemble average over the detected coherent structures, weighted with their own occupied volume fraction. Our analysis unveils that the contribution to the cross-stream components of the mean velocity is either very similar to the same contribution in channel flow, or almost negligible in respect to the contribution from the portion of the domain not occupied by coherent structures. These results suggest that the most intense events are not directly responsible for the secondary flow.
CRIS-Team Scopus Importer:2023-03-21

Control effects on coherent structures in a non-uniform adverse-pressure-gradient boundary layer - Atzori, Marco; Vinuesa, Ricardo; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2022)
We examine the effects of three basic but effective control strategies, namely uniform blowing, uniform suction, and body-force damping, on the intense Reynolds-stress events in the turbulent boundary layer (TBL) developing on the suction side of a NACA4412 airfoil. This flow is subjected to a non-uniform adverse pressure gradient (APG), which substantially modifies its turbulence statistics with respect to a zero-pressure-gradient (ZPG) boundary layer, and it also changes how control strategies affect the flow. The strong APG results in intense events that are shorter and more often detached from the wall than in ZPG TBLs. In a quadrant analysis, ejections remain the most relevant structures, but sweeps become more important than in ZPG TBLs, a fact that results in a lower contribution to the wall-normal velocity from intense Reynolds-stress events. Control effects are relatively less important on intense events than on the turbulent statistics. Uniform blowing has an impact similar to that of an even more intense APG, while uniform suction has more complex effects, most likely due to the particular behavior of the wall-normal velocity component near the wall. Body-force damping also reduces the probability of occurrence of very-large attached structures and that of intense events in the proximity of the actuation region. Our results show that intense Reynolds-stress events are robust features of the flow. If control strategies do not target directly these structures, their effects on the strong events is less pronounced than the effects on the mean flow.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Coherent structures; Flow control; Turbulent boundary layers

Convergence of numerical simulations of turbulent wall-bounded flows and mean cross-flow structure of rectangular ducts - Vinuesa, Ricardo; Prus, Cezary; Schlatter, Philipp; Nagib, Hassan M. (Meccanica, 2016)
Convergence criteria for direct numerical simulations of turbulent channel and duct flows are proposed. The convergence indicator for channels is defined as the deviation of the nondimensional total shear-stress profile with respect to a linear profile, whereas the one for the duct is based on a nondimensional streamwise momentum balance at the duct centerplane. We identify the starting (TS) and averaging times (TA) necessary to obtain sufficiently converged statistics, and also find that optimum convergence rates are achieved when the spacing in time between individual realizations is below Δ t+= 17. The in-plane structure of the flow in turbulent ducts is also assessed by analyzing square ducts at Reτ , c≃ 180 and 360 and rectangular ducts with aspect ratios 3 and 10 at Reτ , c≃ 180. Identification of coherent vortices shows that near-wall streaks are located in all the duct cases at a wall-normal distance of y+≃ 40 as in Pinelli et al. (J Fluid Mech 644:107–122, 2010). We also find that large-scale motions play a crucial role in the streamline pattern of the secondary flow, whereas near-wall structures highly influence the streamwise vorticity pattern. These conclusions extend the findings by Pinelli et al. to other kinds of large-scale motions in the flow through the consideration of wider ducts. They also highlight the complex and multiscale nature of the secondary flow of second kind in turbulent duct flows.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Convergence; Direct numerical simulation; Secondary flow; Turbulent structures; Wall-bounded turbulence

Convolutional-network models to predict wall-bounded turbulence from wall quantities - Guastoni, Luca; Guemes, Alejandro; Ianiro, Andrea; Discetti, Stefano; Schlatter, Philipp; Azizpour, Hossein; Vinuesa, Ricardo (Journal of Fluid Mechanics, 2021)
Two models based on convolutional neural networks are trained to predict the two-dimensional instantaneous velocity-fluctuation fields at different wall-normal locations in a turbulent open-channel flow, using the wall-shear-stress components and the wall pressure as inputs. The first model is a fully convolutional neural network (FCN) which directly predicts the fluctuations, while the second one reconstructs the flow fields using a linear combination of orthonormal basis functions, obtained through proper orthogonal decomposition (POD), and is hence named FCN-POD. Both models are trained using data from direct numerical simulations at friction Reynolds numbers and 550. Being able to predict the nonlinear interactions in the flow, both models show better predictions than the extended proper orthogonal decomposition (EPOD), which establishes a linear relation between the input and output fields. The performance of the models is compared based on predictions of the instantaneous fluctuation fields, turbulence statistics and power-spectral densities. FCN exhibits the best predictions closer to the wall, whereas FCN-POD provides better predictions at larger wall-normal distances. We also assessed the feasibility of transfer learning for the FCN model, using the model parameters learned from the dataset to initialize those of the model that is trained on the dataset. After training the initialized model at the new, our results indicate the possibility of matching the reference-model performance up to, with and of the original training data. We expect that these non-intrusive sensing models will play an important role in applications related to closed-loop control of wall-bounded turbulence.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulence simulation

Correcting hot-wire spatial resolution effects in third- and fourth-order velocity moments in wall-bounded turbulence - Talamelli, Alessandro; Segalini, Antonio; Orlu, Ramis; Schlatter, Philipp; Alfredsson, P. Henrik (Experiments in Fluids, 2013)
Spatial averaging, resulting from the finite size of a hot-wire probe, significantly affects the accuracy of velocity measurements in turbulent flows close to walls. Here, we extend the theoretical model, introduced in Segalini et al. (Meas Sci Technol 22:104508, 2011) quantifying the effect of a linear spatial filter of hot-wire probes on the mean and the variance of the streamwise velocity in turbulent wall-bounded flows, to describe the effect of the spatial filtering on the third- and fourth-order moments of the same velocity component. The model, based on the three-(four) point velocity-correlation function for the third-(fourth-) order moment, shows that the filtering can be related to a characteristic length scale which is an equivalent of the Taylor transverse microscale for the second-order moment. The capacity of the model to accurately describe the attenuation is validated against direct numerical simulation (DNS) data of a zero pressure-gradient turbulent boundary layer. The DNS data allow the filtering effect to be appraised for different wire lengths and for the different moments. The model shows good accuracy except for the third-order moment in the region where a zero-crossing of the third-order function is observed and where the equations become ill-conditioned. An "a posteriori" correction procedure, based on the developed model, to correct the measured third- and fourth-order velocity moments is also presented. This procedure, based on combining the measured data by two single hot-wire sensors with different wire lengths, is a natural extension of the one introduced by Segalini et al. (Exp Fluids 51:693-700, 2011) to evaluate both the turbulence intensity and the transverse Taylor microscale in turbulent flows. The technique is validated against spatially averaged simulation data showing a good capacity to correct the actual profiles over the entire height of the boundary layer except, as expected, for the third-order moment in the region where the latter exhibits a zero-crossing. Moreover, the proposed method has been tested on experimental data from turbulent pipe flow experiments. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-21

Correction to: Techniques for Turbulence Tripping of Boundary Layers in RANS Simulations (Flow, Turbulence and Combustion, (2022), 108, 3, (661-682), 10.1007/s10494-021-00296-5) - Tabatabaei, Narges; Vinuesa, Ricardo; Orlu, Ramis; Schlatter, Philipp (Flow Turbulence and Combustion, 2022)
The original article has been corrected.
CRIS-Team Scopus Importer:2023-03-21

Critical Point for Bifurcation Cascades and Featureless Turbulence - Canton, Jacopo; Rinaldi, Enrico; Orlu, Ramis; Schlatter, Philipp (Physical Review Letters, 2020)
In this Letter we show that a bifurcation cascade and fully sustained turbulence can share the phase space of a fluid flow system, resulting in the presence of competing stable attractors. We analyze the toroidal pipe flow, which undergoes subcritical transition to turbulence at low pipe curvatures (pipe-to-torus diameter ratio) and supercritical transition at high curvatures, as was previously documented. We unveil an additional step in the bifurcation cascade and provide evidence that, in a narrow range of intermediate curvatures, its dynamics competes with that of sustained turbulence emerging through subcritical transition mechanisms.
CRIS-Team Scopus Importer:2023-03-21

Decomposition of the mean friction drag in adverse-pressure-gradient turbulent boundary layers - Fan, Yitong; Li, Weipeng; Atzori, Marco; Pozuelo, Ramon; Schlatter, Philipp; Vinuesa, Ricardo (Physical Review Fluids, 2020)
In this study, we exploit the Renard-Deck identity [J. Fluid Mech. 790, 339 (2016)10.1017/jfm.2016.12] to decompose the mean friction drag in adverse-pressure-gradient turbulent boundary layers (APG-TBLs) into three components, associated with viscous dissipation, turbulence kinetic energy production, and spatial growth of the flow, respectively. We consider adverse-pressure-gradient turbulent boundary layers developing on flat plates and airfoils, with friction Reynolds numbers in the range 200<Reτ<2000, and with Rotta-Clauser pressure-gradient parameters (β) ranging from 0 to 50. The effects of Reynolds number, adverse pressure gradient, and the pressure-gradient history on the contributing components are individually investigated, and special attention is paid to the comparisons with zero-pressure-gradient turbulent boundary layers (ZPG-TBLs). Our results indicate that the inner peaks of the dissipation and production terms are located at y+≈6 and y+≈16.5, respectively, and their outer peaks scale with the 99% boundary-layer thickness (δ99), i.e., y/δ99≈0.7 and 0.53, respectively. These results are independent of the friction Reynolds number, the magnitude of β, and its development history. Moreover, the spatial-growth component is negative in the investigated APG-TBLs, and its magnitude increases with β.
CRIS-Team Scopus Importer:2023-03-21

Decomposition of the mean friction drag on an NACA4412 airfoil under uniform blowing/suction - Fan, Yitong; Atzori, Marco; Vinuesa, Ricardo; Gatti, Davide; Schlatter, Philipp; Li, Weipeng (Journal of Fluid Mechanics, 2022)
The application of drag-control strategies on canonical wall-bounded turbulence, such as periodic channel and zero- or adverse-pressure-gradient boundary layers, raises the question on how to distinguish consistently the origin of control effects under different reference conditions. We employ the RD identity (Renard & Deck, J. Fluid Mech., vol. 790, 2016, pp. 339-367) to decompose the mean friction drag and investigate the control effects of uniform blowing and suction applied to an NACA4412 airfoil at chord Reynolds numbers and. The connection of the drag reduction/increase by using blowing/suction with the turbulence statistics (including viscous dissipation, turbulence kinetic energy production and spatial growth of the flow) across the boundary layer, subjected to adverse or favourable pressure gradients, is examined. We found that the inner and outer peaks of the contributions associated with the friction-drag generation show good scaling with either inner or outer units, respectively. They are also independent of the Reynolds number, control scheme and intensity of the blowing/suction. The small- and large-scale structures are separated with an adaptive scale-decomposition method, namely the empirical mode decomposition (EMD), which aims to analyse the scale-specific contribution of turbulent motions to friction-drag generation. Results unveil that blowing on the suction side of the airfoil is able to enhance the contribution of large-scale motions and to suppress that of small scales; however, suction behaves contrarily. The contributions related to cross-scale interactions remain almost unchanged with different control strategies.
CRIS-Team Scopus Importer:2023-03-21
Keywords: boundary layer control; drag reduction

Direct numerical simulation of a turbulent 90° bend pipe flow - Wang, Zhixin; Orlu, Ramis; Schlatter, Philipp; Chung, Yongmann M. (International Journal of Heat and Fluid Flow, 2018)
Direct numerical simulation (DNS) has been performed for a spatially developing 90° bend pipe flow to investigate the unsteady flow motions downstream of the bend. A recycling method is implemented to generate a fully-developed turbulent inflow condition. The Reynolds number of the pipe flow is ReD=5300 and the bend curvature is γ=0.4. A long straight pipe section (40D) is attached in the downstream of the bend to allow the flow to develop. Flow oscillations downstream of the bend are measured using several methods, and the corresponding oscillation frequencies are estimated. It is found that different characteristic frequencies are obtained from various flow measurements. The stagnation point movement and single-point velocity measurements may not be good measures to determine the swirl-switching frequency. The oscillations of the lateral pressure force on the pipe wall and half-sided mass flow rate are proposed to be a more unambiguous measure of the unsteady flow motions downstream of the bend.
CRIS-Team Scopus Importer:2023-03-21
Keywords: 90 degrees bend; Conditional averaging; Curved pipe; DNS; Swirl switching; Turbulent pipe flow

Direct numerical simulation of a turbulent boundary layer with passive scalar transport - Li, Qiang; Schlatter, Philipp; Brandt, Luca; Henningson, Dan S. (ERCOFTAC Series, 2010)
A fully-resolved direct numerical simulation (DNS) of a spatially developing turbulent boundary layer with passive scalars over a flat plate under zero pressure gradient (ZPG) has been carried out using a spectral method with about 40M grid points. The highest Reynolds number based on the momentum thickness and free-stream velocity is Reθ = 850 and the molecular Prandtl numbers for the scalars range from 0.2 to 2.0. The intermittent region near the boundary-layer edge was identified by investigating the high-order moments and PDF. In addition, it was found that the streamwise velocity is similar to the scalar distribution at Pr = 0.71 with isoscalar wall boundary condition. Far away from the wall, the two quantities become less correlated.
CRIS-Team Scopus Importer:2023-03-21

Direct numerical simulation of a zero-pressure-gradient turbulent boundary layer with passive scalars up to Prandtl number Pr = 6 - Balasubramanian, Arivazhagan G.; Guastoni, Luca; Schlatter, Philipp; Vinuesa, Ricardo (Journal of Fluid Mechanics, 2023)
The objective of the present study is to provide a numerical database of thermal boundary layers and to contribute to the understanding of the dynamics of passive scalars at different Prandtl numbers. In this regard, a direct numerical simulation (DNS) of an incompressible zero-pressure-gradient turbulent boundary layer is performed with the Reynolds number based on momentum thickness ranging up to. Four passive scalars, characterized by the Prandtl numbers are simulated using the pseudo-spectral code SIMSON (Chevalier et al., SIMSON: A pseudo-spectral solver for incompressible boundary layer flows. Tech. Rep. TRITA-MEK 2007:07. KTH Mechanics, Stockholm, Sweden, 2007). To the best of our knowledge, the present DNS provides the thermal boundary layer with the highest Prandtl number available in the literature. It corresponds to that of water at, when the fluid temperature is considered as a passive scalar. Turbulence statistics for the flow and thermal fields are computed and compared with available numerical simulations at similar Reynolds numbers. The mean flow and scalar profiles, root-mean-squared velocity and scalar fluctuations, turbulent heat flux, turbulent Prandtl number and higher-order statistics agree well with the numerical data reported in the literature. Furthermore, the pre-multiplied two-dimensional spectra of the velocity and of the passive scalars are computed, providing a quantitative description of the energy distribution at the different length scales for various wall-normal locations. The energy distribution of the heat-flux fields at the wall is concentrated on longer temporal structures with increasing Prandtl number. This is due to the thinner thermal boundary layer as thermal diffusivity decreases and, thereby, the longer temporal structures exhibit a different footprint at the wall.
CRIS-Team Scopus Importer:2023-12-08
Keywords: turbulent boundary layers

Direct numerical simulation of flow over dissimilar, randomly distributed roughness elements: A systematic study on the effect of surface morphology on turbulence - Forooghi, Pourya; Stroh, Alexander; Schlatter, Philipp; Frohnapfel, Bettina (Physical Review Fluids, 2018)
Direct numerical simulations are used to investigate turbulent flow in rough channels, in which topographical parameters of the rough wall are systematically varied at a fixed friction Reynolds number of 500, based on a mean channel half-height h and friction velocity. The utilized roughness generation approach allows independent variation of moments of the surface height probability distribution function [thus root-mean-square (rms) surface height, skewness, and kurtosis], surface mean slope, and standard deviation of the roughness peak sizes. Particular attention is paid to the effect of the parameter Δ defined as the normalized height difference between the highest and lowest roughness peaks. This parameter is used to understand the trends of the investigated flow variables with departure from the idealized case where all roughness elements have the same height (Δ=0). All calculations are done in the fully rough regime and for surfaces with high slope (effective slope equal to 0.6-0.9). The rms roughness height is fixed for all cases at 0.045h and the skewness and kurtosis of the surface height probability density function vary in the ranges -0.33 to 0.67 and 1.9 to 2.6, respectively. The goal of the paper is twofold: first, to investigate the possible effect of topographical parameters on the mean turbulent flow, Reynolds, and dispersive stresses particularly in the vicinity of the roughness crest, and second, to investigate the possibility of using the wall-normal turbulence intensity as a physical parameter for parametrization of the flow. Such a possibility, already suggested for regular roughness in the literature, is here extended to irregular roughness.
CRIS-Team Scopus Importer:2023-03-21

Direct numerical simulation of separated flow in a three-dimensional diffuser - Ohlsson, Johan; Schlatter, Philipp; Fischer, Paul F.; Henningson, Dan S. (Journal of Fluid Mechanics, 2010)
A direct numerical simulation (DNS) of turbulent flow in a three-dimensional diffuser at Re = 10000 (based on bulk velocity and inflow-duct height) was performed with a massively parallel high-order spectral element method running on up to 32768 processors. Accurate inflow condition is ensured through unsteady trip forcing and a long development section. Mean flow results are in good agreement with experimental data by Cherry et al. (Intl J. Heat Fluid Flow, vol. 29, 2008, pp. 803-811), in particular the separated region starting from one corner and gradually spreading to the top expanding diffuser wall. It is found that the corner vortices induced by the secondary flow in the duct persist into the diffuser, where they give rise to a dominant low-speed streak, due to a similar mechanism as the lift-up effect in transitional shear flows, thus governing the separation behaviour. Well-resolved simulations of complex turbulent flows are thus possible even at realistic Reynolds numbers, providing accurate and detailed information about the flow physics. The available Reynolds stress budgets provide valuable references for future development of turbulence models. Copyright © Cambridge University Press 2010.
CRIS-Team Scopus Importer:2023-03-21

Direct numerical simulation of the flow around a wall-mounted square cylinder under various inflow conditions - Vinuesa, Ricardo; Schlatter, Philipp; Malm, Johan; Mavriplis, Catherine; Henningson, Dan S. (Journal of Turbulence, 2015)
The flow around a wall-mounted square cylinder of side d is investigated by means of direct numerical simulation (DNS). The effect of inflow conditions is assessed by considering two different cases with matching momentum-thickness Reynolds numbers Reθ ≃ 1000 at the obstacle: the first case is a fullyturbulent zero pressure gradient boundary layer, and the second one is a laminar boundary layer with prescribed Blasius inflow profile further upstream. An auxiliary simulation carried out with the pseudo-spectral Fourier-Chebyshev code SIMSON is used to obtain the turbulent time-dependent inflow conditions which are then fed into the main simulation where the actual flow around the cylinder is computed. This main simulation is performed, for both laminar and turbulent-inflows, with the spectral-element method code Nek5000. In both cases the wake is completely turbulent, and we find the same Strouhal number St ≃ 0.1, although the two wakes exhibit structural differences for x > 3d downstream of the cylinder. Transition to turbulence is observed in the laminar-inflow case, induced by the recirculation bubble produced upstream of the obstacle, and in the turbulent-inflow simulation the streamwise fluctuations modulate the horseshoe vortex. The wake obtained in our laminar-inflow case is in closer agreement with reference particle image velocimetry measurements of the same geometry, revealing that the experimental boundary layer was not fully turbulent in that dataset, and highlighting the usefulness of DNS to assess the quality of experimental inflow conditions.
CRIS-Team Scopus Importer:2023-03-21
Keywords: direct numerical simulation; separated flows; square-cylinder flow; three-dimensional flows; wall turbulence

Direct numerical simulation of the flow around a wing section at moderate Reynolds number - Hosseini, S. M.; Vinuesa, Ricardo; Schlatter, Philipp; Hanifi, Ardeshir; Henningson, D. S. (International Journal of Heat and Fluid Flow, 2016)
A three-dimensional direct numerical simulation has been performed to study the turbulent flow around the asymmetric NACA4412 wing section at a moderate chord Reynolds number of Rec=400,000, with an angle of attack of AoA=5∘. The mesh was optimized to properly resolve all relevant scales in the flow, and comprises around 3.2 billion grid points. The incompressible spectral-element Navier–Stokes solver Nek5000 was used to carry out the simulation. An unsteady volume force is used to trip the flow to turbulence on both sides of the wing at 10% of the chord. Full turbulence statistics are computed in addition to collection of time history data in selected regions. The Reynolds numbers on the suction side reach Reτ ≃ 373 and Reθ=2,800 with the pressure-gradient parameter ranging from β ≈ 0.0 to β ≈ 85. Similarly, on the pressure side, the Reynolds numbers reach Reτ ≈ 346 and Reθ=818 while β changes from β ≈ 0.0 to β≈−0.25. The effect of adverse pressure gradients on the mean flow is consistent with previous observations, namely a steeper incipient log law, a more prominent wake region and a lower friction. The turbulence kinetic energy profiles show a progressively larger inner peak for increasing pressure gradient, as well as the emergence and development of an outer peak with stronger APGs. The present simulation shows the potential of high-order (spectral) methods in simulating complex external flows at moderately high Reynolds numbers.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Incipient separation; NACA4412; Pressure gradient; Turbulent boundary layer; Vortex shedding; Wake

Direct numerical simulation of the flow around a wing section at moderate Reynolds numbers - Hosseini, Seyed M.; Vinuesa, Ricardo; Schlatter, Philipp; Hanifi, Ardeshir; Henningson, Dan S. (Proceedings - 15th European Turbulence Conference, ETC 2015, 2015)
A three dimensional direct numerical simulation has been performed to study the flow around the asymmetric NACA-4412 wing at a moderate chord Reynolds number (Rec = 400, 000) with an angle of attack of 5◦. The flow case under investigation poses numerous challenges for a numerical method due to the wide range of scales and complicated flow physics induced by the geometry. The mesh is optimized and well resolved to account for such varying scales in the flow. An unsteady volume force is used to trip the flow to turbulence on both sides of the wing at 10% chord. Full turbulent statistics are computed on the fly to further investigate the complicated flow features around the wing. The present simulation shows the potential of high-order methods in simulating complex external flows at moderately high Reynolds numbers.
CRIS-Team Scopus Importer:2023-03-21

Direct numerical simulation of the flow around a wing section using high-order parallel spectral methods - Vinuesa, Ricardo; Hosseini, Seyed M.; Hanifi, Ardeshir; Henningson, Dan S.; Schlatter, Philipp (9th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2015, 2015)
The results of a DNS of the flow around a wing section represented by a NACA4412 profile, with Rec = 400,000 and 5° angle of attack, are presented in this study. The high-order spectral element code Nek5000 is used for the computations. An initial RANS simulation is used to define the velocity boundary conditions, and to design the computational mesh. The agreement between spanwise- and time-averaged fields from the DNS and the RANS simulation is excellent. The mean flow and several components of the Reynolds stress tensor at x/c = 0.4 (β = 0.53) and 0.8 (β = 4.54) are compared with the ZPG boundary layer computed by Schlatter & Orlu (2010). In both cases, the friction Reynolds number is roughly matched (330 and 450), and as expected the Reg values from the wing (720 and 1,800) are larger than the ones from the ZPG case (612 and 1,007). The APG leads to a steeper log law, a more prominent wake region and a larger U+e. The tangential turbulence intensity exhibits a stronger inner peak, and starts to develop an outer peak. We also show that the impact on the spanwise component is significant, and also on the wall-normal intensity and the Reynolds shear stress for stronger pressure gradients, especially in the outer region.
CRIS-Team Scopus Importer:2023-03-21

DIRECT NUMERICAL SIMULATION OF TURBULENT FLOW AROUND 3D STEPPED CYLINDER WITH ADAPTIVE MESH REFINEMENT - Massaro, Daniele; Peplinski, Adam; Schlatter, Philipp (12th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2022, 2022)
In the present study, we investigate the turbulent three-dimensional flow around a stepped cylinder, namely two cylinders of different diameters joint at one extremity. We perform a direct numerical simulation with the spectral element code Nek5000 that uses a high order spatial discretisation (the polynomial order is p = 7). The adaptive mesh refinement technique is employed in the error-driven meshing procedure, allowing an adequately refined mesh everywhere. We consider the Reynolds number ReD = 1000, based on the large cylinder diameter and the uniform inflow velocity. We compare our results with the previous experimental campaign by Morton & Yarusevych (2014b). The results agree very well and we can identify the three main wake regions: the S, N and L cell with a Strouhal number StS = 0.408, StN = 0.188 and StL = 0.201 respectively. The instantaneous mean flow properties are studied showing that the junction dynamics is more similar to the previous laminar studies at ReD = 150 rather than at higher ReD = 3900. Moreover, proper orthogonal decomposition is used to detect the most energetic coherent structures, that resemble the three wake cells.
CRIS-Team Scopus Importer:2023-03-21

Direct numerical simulation of turbulent pipe flow at moderately high reynolds numbers - El Khoury, George K.; Schlatter, Philipp; Noorani, Azad; Fischer, Paul F.; Brethouwer, Geert; Johansson, Arne V. (Flow Turbulence and Combustion, 2013)
Fully resolved direct numerical simulations (DNSs) have been performed with a high-order spectral element method to study the flow of an incompressible viscous fluid in a smooth circular pipe of radius R and axial length 25R in the turbulent flow regime at four different friction Reynolds numbers Re τ = 180, 360, 550 and 1,000. The new set of data is put into perspective with other simulation data sets, obtained in pipe, channel and boundary layer geometry. In particular, differences between different pipe DNS are highlighted. It turns out that the pressure is the variable which differs the most between pipes, channels and boundary layers, leading to significantly different mean and pressure fluctuations, potentially linked to a stronger wake region. In the buffer layer, the variation with Reynolds number of the inner peak of axial velocity fluctuation intensity is similar between channel and boundary layer flows, but lower for the pipe, while the inner peak of the pressure fluctuations show negligible differences between pipe and channel flows but is clearly lower than that for the boundary layer, which is the same behaviour as for the fluctuating wall shear stress. Finally, turbulent kinetic energy budgets are almost indistinguishable between the canonical flows close to the wall (up to y + ≈ 100), while substantial differences are observed in production and dissipation in the outer layer. A clear Reynolds number dependency is documented for the three flow configurations. © 2013 Springer Science+Business Media Dordrecht.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Boundary layers; Channels; Direct numerical simulation; Pipes; Wall turbulence

Direct numerical simulations of bypass transition over distributed roughness - Von Deyn, Lars H.; Forooghi, Pourya; Frohnapfel, Bettina; Schlatter, Philipp; Hanifi, Ardeshir; Henningson, Dan S. (AIAA Journal, 2020)
Bypass transition in a boundary layer subjected to freestream turbulence and distributed surface roughness is studied numerically. The distributed surface roughness is reproduced with an immersed boundary technique, and the freestream turbulence is artificially generated by a superposition of eigenmodes of the Orr–Sommerfeld and Squire equations. Both an undisturbed laminar inflow and a disturbed inflow with freestream turbulence are studied. In either case a parametric study on the effects of the roughness size and density is carried out. The simulations reveal that the presence of roughness induces streaks in the laminar flow. When the freestream is turbulent, both roughness height and density show an impact on the onset of transition. The superposition of surface roughness and freestream turbulence causes amplified streaks. As a result, the streak instability occurs earlier within the boundary layer. The results show good qualitative and quantitative agreement to both experimental and numerical studies available in the literature.
CRIS-Team Scopus Importer:2023-03-21

Direct numerical simulations of stratified open channel flows - Deusebio, E.; Schlatter, Philipp; Brethouwer, G.; Lindborg, E. (Journal of Physics: Conference Series, 2011)
We carry out numerical simulations of wall-bounded stably stratified flows. We mainly focus on how stratification affects the near-wall turbulence at moderate Reynolds numbers, i.e. Reτ = 360. A set of fully-resolved open channel flow simulations is performed, where a stable stratification has been introduced through a negative heat flux at the lower wall. In agreement with previous studies, it is found that turbulence cannot be sustained for h/L values higher than 1.2, where L is the so-called Monin-Obukhov length and h is the height of the open channel. For smaller values, buoyancy does not re-laminarize the flow, but nevertheless affects the wall turbulence. Near-wall streaks are weakly affected by stratification, whereas the outer modes are increasingly damped as we move away from the wall. A decomposition of the wall-normal velocity is proposed in order to separate the gravity wave and turbulent flow fields. This method has been tested both for open channel and full channel flows. Gravity waves are likely to develop and to dominate close to the upper boundary (centerline for full channel). However, their intensity is weaker in the open channel, possibly due to the upper boundary condition. Moreover, the presence of internal gravity waves can also be deduced from a correlation analysis, which reveals (together with spanwise spectra) a narrowing of the outer structures as the stratification is increased.
CRIS-Team Scopus Importer:2023-03-21

Direct numerical simulations of turbulent flow through porous channels and ducts - Samanta, Arghya; Vinuesa, Ricardo; Lashgari, Iman; Schlatter, Philipp; Brandt, Luca (Proceedings - 15th European Turbulence Conference, ETC 2015, 2015)
Direct numerical simulations of the fully developed turbulent flow through a porous channel and duct are performed based on the spectral element code Nek5000. The volume-averaged Navier-Stokes (VANS) equations are implemented in order to describe the flow in the composite medium. The numerical simulations of the VANS equations are carried out at a constant value of the bulk Reynolds number when the porosity, or equivalently, the permeability of the medium varies successively. The mean and turbulent energy budgets are computed and the effect of porosity on the secondary flow in a duct is examined.
CRIS-Team Scopus Importer:2023-03-21

Direct numerical simulations of turbulent pipe flow up to - Yao, Jie; Rezaeiravesh, Saleh; Schlatter, Philipp; Hussain, Fazle (Journal of Fluid Mechanics, 2023)
Well-resolved direct numerical simulations (DNS) have been performed of the flow in a smooth circular pipe of radius and axial length at friction Reynolds numbers up to using the pseudo-spectral code OPENPIPEFLOW. Various turbulence statistics are documented and compared with other DNS and experimental data in pipes as well as channels. Small but distinct differences between various datasets are identified. The friction factor overshoots by and undershoots by the Prandtl friction law at low and high ranges, respectively. In addition, in our results is slightly higher than in Pirozzoli et al. (J. Fluid Mech., vol. 926, 2021, A28), but matches well the experiments in Furuichi et al. (Phys. Fluids, vol. 27, issue 9, 2015, 095108). The log-law indicator function, which is nearly indistinguishable between pipe and channel up to, has not yet developed a plateau farther away from the wall in the pipes even for the cases. The wall shear stress fluctuations and the inner peak of the axial turbulence intensity - which grow monotonically with - are lower in the pipe than in the channel, but the difference decreases with increasing. While the wall value is slightly lower in the channel than in the pipe at the same, the inner peak of the pressure fluctuation shows negligible differences between them. The Reynolds number scaling of all these quantities agrees with both the logarithmic and defect-power laws if the coefficients are properly chosen. The one-dimensional spectrum of the axial velocity fluctuation exhibits a dependence at an intermediate distance from the wall - also seen in the channel. In summary, these high-fidelity data enable us to provide better insights into the flow physics in the pipes as well as the similarity/difference among different types of wall turbulence.
CRIS-Team Scopus Importer:2023-03-21
Keywords: pipe flow; turbulence simulation; turbulent boundary layers

Direct numerical simulations of variable-aspect-ratio turbulent duct flows at low to moderate reynolds numbers - Vinuesa, Ricardo; Noorani, Azad; Lozano-Durán, Adrián; El Khoury, George; Schlatter, Philipp; Fischer, Paul F.; Nagib, Hassan M. (International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2013, 2013)
Three-dimensional effects in turbulent duct flows, i.e., side-wall boundary layers and secondary motions, are studied by means of direct numerical simulations (DNS). The spectral element code Nek5000 is used to compute turbulent duct flows with aspect ratios 1 to 7 (at Reb, c = 2800, Reτ 180) and 1 (at Reb, c = 5600, Reτ 330) in streamwiseperiodic boxes of length 25h. The total number of grid points ranges from 28 to 145 million, and the fluid kinematic viscosity n was adjusted iteratively in order to keep the same bulk Reynolds number at the centerplane with changing aspect ratio. Spanwise variations in wall shear, mean-flow profiles and turbulence statistics are analyzed with aspect ratio, and also compared with the 2D channel. These computations show good agreement with experimental measurements carried out at IIT in parallel, and reinforces one important conclusion: the conditions obtained in the core region of a high-aspect-ratio duct cannot exactly be reproduced by spanwise-periodic DNSs of turbulent channel flows.
CRIS-Team Scopus Importer:2023-03-21

Distributed Percolation Analysis for Turbulent Flows - Friederici, Anke; Köpp, Wiebke; Atzori, Marco; Vinuesa, Ricardo; Schlatter, Philipp; Weinkauf, Tino (2019 IEEE 9th Symposium on Large Data Analysis and Visualization, LDAV 2019, 2019)
Percolation analysis is a valuable tool to study the statistical properties of turbulent flows. It is based on computing the percolation function for a derived scalar field, thereby quantifying the relative volume of the largest connected component in a superlevel set for a decreasing threshold. We propose a novel memory-distributed parallel algorithm to finely sample the percolation function. It is based on a parallel version of the union-find algorithm interleaved with a global synchronization step for each threshold sample. The efficiency of this algorithm stems from the fact that operations in-between threshold samples can be freely reordered, are mostly local and thus require no inter-process communication. Our algorithm is significantly faster than previous algorithms for this purpose, and is neither constrained by memory size nor number of compute nodes compared to the conceptually related algorithm for extracting augmented merge trees. This makes percolation analysis much more accessible in a large range of scenarios. We explore the scaling of our algorithm for different data sizes, number of samples and number of MPI processes. We demonstrate the utility of percolation analysis using large turbulent flow data sets.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Computing methodologies; Discrete mathematics; Distributed algorithms; Distributed computing methodologies; Graph theory; Mathematics of computing; Paths and connectivity problems

DNS of a spatially developing turbulent boundary layer with passive scalar transport - Li, Qiang; Schlatter, Philipp; Brandt, Luca; Henningson, Dan S. (International Journal of Heat and Fluid Flow, 2009)
A direct numerical simulation (DNS) of a spatially developing turbulent boundary layer over a flat plate under zero pressure gradient (ZPG) has been carried out. The evolution of several passive scalars with both isoscalar and isoflux wall boundary condition are computed during the simulation. The Navier-Stokes equations as well as the scalar transport equation are solved using a fully spectral method. The highest Reynolds number based on the free-stream velocity U∞ and momentum thickness θ is Reθ = 830, and the molecular Prandtl numbers are 0.2, 0.71 and 2. To the authors' knowledge, this Reynolds number is to date the highest with such a variety of scalars. A large number of turbulence statistics for both flow and scalar fields are obtained and compared when possible to existing experimental and numerical simulations at comparable Reynolds number. The main focus of the present paper is on the statistical behaviour of the scalars in the outer region of the boundary layer, distinctly different from the channel-flow simulations. Agreements as well as discrepancies are discussed while the influence of the molecular Prandtl number and wall boundary conditions is also highlighted. A Pr scaling for various quantities is proposed in outer scalings. In addition, spanwise two-point correlation and instantaneous fields are employed to investigate the near-wall streak spacing and the coherence between the velocity and the scalar fields. Probability density functions (PDF) and joint probability density functions (JPDF) are shown to identify the intermittency both near the wall and in the outer region of the boundary layer. The present simulation data will be available online for the research community. © 2009 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct numerical simulation (DNS); Passive scalar; Prandtl number; Turbulent boundary layer

DNS of spatially-developing three-dimensional turbulent boundary layers - Schlatter, Philipp; Brandt, Luca (ERCOFTAC Series, 2010)
CRIS-Team Scopus Importer:2023-03-21

DNS of three-dimensional separation in turbulent diffuser flows - Ohlsson, Johan; Schlatter, Philipp; Fischer, Paul F.; Henningson, Dan S. (Springer Proceedings in Physics, 2009)
The spectral-element method (SEM), is a high-order numerical method with the ability to accurately simulate fluid flows in complex geometries. SEM has opened the possibility to study – in great detail – fluid phenomena known to be very sensitive to discretization errors, e.g. flows undergoing pressureinduced separation [4]. Recently, Cherry et al. [1] performed experiments using Magnetic Resonance Velocimetry (MRV) of turbulent diffuser flow exhibiting unsteady three-dimensional separation at Re = 10 000 based on bulk velocity and height of the inflow duct. Two geometries with different opening angles were investigated and it was found that the flow was extremely sensitive to slight changes in the geometrical setup. To understand this sensitivity and to analyze its causes, we present a direct numerical simulation (DNS) of one of these cases (denoted by “Diffuser 1“ in [1]) by means of the SEM. Here, we focus on careful analysis of mean flow results in order to assess the quality of the simulation data.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct Numerical Simulation; Discretization Error; Friction Reynolds Number; Geometrical Setup; Magnetic Resonance Velocimetry

Drag reduction in spatially developing turbulent boundary layers by blowing at constant mass-flux - Kametani, Yukinori; Orlii, Ramis; Fukagata, Koji; Schlatter, Philipp (9th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2015, 2015)
A series of large-eddy simulations of spatially developing turbulent boundary layers with uniform blowing at moderate Reynolds numbers (based on free-stream velocity, U∞ and momentum thickness, θ) up to Reθ ∼ 2500 were performed with the special focus on the effect of intermittent (separated in streamwise direction) blowing sections. The number of blowing sections, N, investigated is set to be 3, 6, 20, 30 and compared to N = 1, which constitutes the reference case, while the total wall-mass flux is constrained to be the same for all considered cases, corresponding to a blowing amplitude of 0.1% of U∞ for the reference case. Results indicate that the reference case provides a net-energy saving rate of around 18%, which initially decreases at most 2 percentage points for N = 3 but recovers with increasing N. The initial reduction of the drag reduction is due to the shorter streamwise length of intermittent blowing sections. The physical decomposition of the skin friction drag through the FIK identity (Fukagata et at, 2002), shows that the distribution of all components over each blowing section has similar trends, resulting in similar averaged values over the whole control region.
CRIS-Team Scopus Importer:2023-03-21

Drag reduction in spatially developing turbulent boundary layers by spatially intermittent blowing at constant mass-flux - Kametani, Yukinori; Fukagata, Koji; Orlu, Ramis; Schlatter, Philipp (Journal of Turbulence, 2016)
A series of large-eddy simulations of spatially developing turbulent boundary layers with uniform blowing at moderate Reynolds numbers (based on free-stream velocity, U∞, and momentum thickness, θ) up to Reθ ≈ 2500 were performed with the special focus on the effect of intermittent (separated in streamwise direction) blowing sections. The number of blowing sections, N, investigated is set to be 3, 6, 20, 30 and compared to N = 1, which constitutes the reference case, while the total wall-mass flux is constrained to be the same for all considered cases, corresponding to a blowing amplitude of 0.1% of U∞ for the reference case. Results indicate that the reference case provides a net-energy saving rate of around 18%, which initially decreases at most 2% points for N = 3 but recovers with increasing N, where the initial reduction of the drag reduction is found to be related to the shorter streamwise length of the intermittent blowing sections. The physical decomposition of the skin friction drag through the Fukagata-Iwamoto-Kasagi (FIK) identity shows that the distribution of all components over each blowing section has similar trends, resulting in similar averaged values over the whole control region.
CRIS-Team Scopus Importer:2023-03-21
Keywords: blowing; flow control; Turbulent boundary layer

Dynamic Resource Management for In-Situ Techniques Using MPI-Sessions - Ju, Yi; Huber, Dominik; Perez, Adalberto; Ulbl, Philipp; Markidis, Stefano; Schlatter, Philipp; Schulz, Martin; Schreiber, Martin; Laure, Erwin (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2025)
The computational power of High-Performance Computing (HPC) systems increases continuously and rapidly. Data-intensive applications are designed to leverage the high computational capacity of HPC resources and typically generate a large amount of data for traditional post-processing data analytics. However, the HPC systems’ in-/output (IO) subsystem develops relatively slowly, and the storage capacity is limited. This could lead to limited actual performance and scientific discovery. In-situ techniques are a partial remedy to these problems by reducing or avoiding the data flow through the IO subsystem to/from the storage. However, in current practice, asynchronous in-situ techniques with static resource management often allocate separate computing resources for executing in-situ task(s), which remain idle if no in-situ work is at hand. In the present work, we target improving the efficiency of computing resource usage by launching and releasing necessary additional computing resources for in-situ task(s). Our approach is based on extensions for MPI Sessions that enable the required dynamic resource management. In this paper, we propose a basic and an advanced in-situ techniques with dynamic resource management enabled by MPI Sessions, their implementations on two real-world use cases, and a critical analysis of the experimental results.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Dynamic resource management; HPC; In-situ; MPI Session

Edge manifold as a Lagrangian coherent structure in a high-dimensional state space - Beneitez, Miguel; Duguet, Yohann; Schlatter, Philipp; Henningson, Dan S. (Physical Review Research, 2020)
Dissipative dynamical systems characterized by two basins of attraction are found in many physical systems, notably in hydrodynamics where laminar and turbulent regimes can coexist. The state space of such systems is structured around a dividing manifold called the edge, which separates trajectories attracted by the laminar state from those reaching the turbulent state. We apply here concepts and tools from Lagrangian data analysis to investigate this edge manifold. This approach is carried out in the state space of autonomous arbitrarily high-dimensional dissipative systems, in which the edge manifold is reinterpreted as a Lagrangian coherent structure (LCS). Two different diagnostics, finite-time Lyapunov exponents and Lagrangian descriptors, are used and compared with respect to their ability to identify the edge and their scalability. Their properties are illustrated on several low-order models of subcritical transition of increasing dimension and complexity, as well on well-resolved simulations of the Navier-Stokes equations in the case of plane Couette flow. They allow for a mapping of the global structure of both the state space and the edge manifold based on quantitative information. Both diagnostics can also be used to generate efficient bisection algorithms to approach asymptotic edge states, which outperform classical edge tracking.
CRIS-Team Scopus Importer:2023-03-21

Edge state modulation by mean viscosity gradients - Rinaldi, Enrico; Schlatter, Philipp; Bagheri, Shervin (Journal of Fluid Mechanics, 2018)
Motivated by the relevance of edge state solutions as mediators of transition, we use direct numerical simulations to study the effect of spatially non-uniform viscosity on their energy and stability in minimal channel flows. What we seek is a theoretical support rooted in a fully nonlinear framework that explains the modified threshold for transition to turbulence in flows with temperature-dependent viscosity. Consistently over a range of subcritical Reynolds numbers, we find that decreasing viscosity away from the walls weakens the streamwise streaks and the vortical structures responsible for their regeneration. The entire self-sustained cycle of the edge state is maintained on a lower kinetic energy level with a smaller driving force, compared to a flow with constant viscosity. Increasing viscosity away from the walls has the opposite effect. In both cases, the effect is proportional to the strength of the viscosity gradient. The results presented highlight a local shift in the state space of the position of the edge state relative to the laminar attractor with the consequent modulation of its basin of attraction in the proximity of the edge state and of the surrounding manifold. The implication is that the threshold for transition is reduced for perturbations evolving in the neighbourhood of the edge state in the case that viscosity decreases away from the walls, and vice versa.
CRIS-Team Scopus Importer:2023-03-21
Keywords: nonlinear dynamical systems; nonlinear instability; transition to turbulence

Edge states as mediators of bypass transition in boundary-layer flows - Khapko, T.; Kreilos, Tobias; Schlatter, Philipp; Duguet, Y.; Eckhardt, Bruno; Henningson, D. S. (Journal of Fluid Mechanics, 2016)
The concept of edge states is investigated in the asymptotic suction boundary layer in relation to the receptivity process to noisy perturbations and the nucleation of turbulent spots. Edge tracking is first performed numerically, without imposing any discrete symmetry, in a large computational domain allowing for full spatial localisation of the perturbation velocity. The edge state is a three-dimensional localised structure recurrently characterised by a single low-speed streak that experiences erratic bursts and planar shifts. This recurrent streaky structure is then compared with predecessors of individual spot nucleation events, triggered by non-localised initial noise. The present results suggest a nonlinear picture, rooted in dynamical systems theory, of the nucleation process of turbulent spots in boundary-layer flows, in which the localised edge state plays the role of state-space mediator.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Boundary layers; nonlinear dynamical systems; transition to turbulence

Edge tracking in spatially developing boundary layer flows - Beneitez, Miguel; Duguet, Yohann; Schlatter, Philipp; Henningson, Dan S. (Journal of Fluid Mechanics, 2019)
Recent progress in understanding subcritical transition to turbulence is based on the concept of the edge, the manifold separating the basins of attraction of the laminar and the turbulent state. Originally developed in numerical studies of parallel shear flows with a linearly stable base flow, this concept is adapted here to the case of a spatially developing Blasius boundary layer. Longer time horizons fundamentally change the nature of the problem due to the loss of stability of the base flow due to Tollmien-Schlichting (TS) waves. We demonstrate, using a moving box technique, that efficient long-time tracking of edge trajectories is possible for the parameter range relevant to bypass transition, even if the asymptotic state itself remains out of reach. The flow along the edge trajectory features streak switching observed for the first time in the Blasius boundary layer. At long enough times, TS waves co-exist with the coherent structure characteristic of edge trajectories. In this situation we suggest a reinterpretation of the edge as a manifold dividing the state space between the two main types of boundary layer transition, i.e. bypass transition and classical transition.
CRIS-Team Scopus Importer:2023-03-21
Keywords: boundary layer stability; nonlinear dynamical systems; transition to turbulence

Editorial of Special Issue (SI) on “Large-scale control of wall-bounded flow” - Örlü, Ramis; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2025)
CRIS-Team Scopus Importer:2025-05-30

Effect of adverse pressure gradients on turbulent wing boundary layers - Tanarro, A.; Vinuesa, Ricardo; Schlatter, Philipp (Journal of Fluid Mechanics, 2019)
The characteristics of turbulent boundary layers (TBLs) subjected to adverse pressure gradients are analysed through well-resolved large-eddy simulations. The geometries under study are the NACA0012 and NACA4412 wing sections, at and angle of attack, respectively, both of them at a Reynolds number based on inflow velocity and chord length of. The turbulence statistics show that adverse pressure gradients (APGs) have a significant effect on the mean velocity, velocity fluctuations and turbulent kinetic energy budget, and this effect is more prominent on the outer region of the boundary layer. Furthermore, the effect of flow history is assessed by means of an integrated Clauser pressure-gradient parameter (Vinuesa etA al., Flow Turbul. Combust., vol.A 99, 2017, pp. 565-587), through the study of cases with matching local values of and the friction Reynolds number to isolate this effect. Our results show a noticeable effect of the flow history on the outer region, however the differences in the near-wall peak of the tangential velocity fluctuations appear to be mostly produced by the local APG magnitude. The one-dimensional power-spectral density shows energetic small scales in the outer region of APG TBLs, whereas these energetic scales do not appear in zero-pressure-gradient (ZPG) TBLs, suggesting that small scales near the wall are advected towards the outer layer by the APG. Moreover, the linear coherence spectra show that the spectral outer peak of high-Reynolds-number ZPG TBLs is highly correlated with the near-wall region (Baars etA al., J.A Fluid Mech., vol.A 823, 2017, R2), unlike APG TBLs which do not show such a correlation. This result, together with the different two-dimensional spectra of APG and high-Reynolds-number ZPG TBLs, suggests different energisation mechanisms due to APG and increase in Reynolds number. To the authors' knowledge, this is the first in-depth analysis of the TBL characteristics over wings, including detailed single-point statistics, spectra and coherence.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulence simulation

Effect of uniform blowing/suction in a turbulent boundary layer at moderate Reynolds number - Kametani, Yukinori; Fukagata, Koji; Orlu, Ramis; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2015)
A number of well-resolved large-eddy simulations (LES) of a spatially evolving turbulent boundary layer with uniform blowing or suction is performed in order to investigate the effect on skin friction drag as well as turbulence statistics and spectral composition at moderate Reynolds numbers up to Reθ=2500, based on the free-stream velocity and the momentum-loss thickness. The amplitude of uniform blowing or suction is set to be 0.1% of the free-stream velocity with different streamwise ranges of the controlled region.The boundary layer is thickened by blowing and thinned by suction. The Reynolds shear and normal stresses are increased by blowing and decreased by suction, most prominently, in the outer region. Through spectral analysis of the streamwise velocity and cross-spectra of the Reynolds shear stress, the enhancement and reduction of the fluctuation energy in the outer region by blowing and suction are found, respectively. It is also found that the emergence of a second peak in the outer region is promoted by blowing, while it is inhibited in the case of suction.In spite of the weak amplitude of the control, more than 10% of drag reduction and enhancement are achieved by means of blowing and suction, respectively. In the case of blowing, where drag reduction is achieved, the mean drag reduction rate increases as the blowing region extends because the local reduction rate, i.e.the streamwise gradient of the mean drag reduction rate, grows in the streamwise direction. The net-energy saving rate and the control gain have the same trends. It is found that a more effective skin friction drag reduction and control efficiency can be achieved with a wider control region that starts at a more upstream location.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Drag reduction; Large-eddy simulation; Turbulent boundary layer

Effects of Different Friction Control Techniques on Turbulence Developing Around Wings - Atzori, M.; Vinuesa, R.; Gatti, D.; Stroh, A.; Frohnapfel, B.; Schlatter, Philipp (Springer, 2020)
Developing efficient flow control techniques remain a challenging task due to the complexity of turbulent flows in industrial applications, a relevant example of which are turbulent boundary layers (TBL) subjected to pressure gradients. In the present study, we employ high-fidelity numerical simulations to assess the impact of different control strategies on the flow around a NACA4412 airfoil at a Reynolds number Rec=200,000 based on the chord length c and the inflow velocity U∞. The choice of this specific study case is motivated by the relatively weak dependence of the pressure distribution around the airfoil on the Reynolds number [6], which allows distinguishing the effects of increasing Reynolds number and those of the non-uniform adverse pressure gradient (APG).
CRIS-Team Scopus Importer:2023-03-21

Effects of modelling, resolution and anisotropy of subgrid-scales on large eddy simulations of channel flow - Rasam, Amin; Brethouwer, G.; Schlatter, Philipp; Li, Q.; Johansson, A. V. (Journal of Turbulence, 2011)
In this paper, the effect of subgrid-scale (SGS) modelling, grid resolution and anisotropy of the subgrid-scales on large eddy simulation (LES) is investigated. LES of turbulent channel flow is performed at Reτ = 934, based on friction velocity and channel half width, for a wide range of resolutions. The dynamic Smagorinsky model (DS), the highpass filtered dynamic Smagorinsky model (HPF) based on the variational multiscale method and the recent explicit algebraic model (EA), which accounts for the anisotropy of the SGS stresses are considered. The first part of the paper is focused on the resolution effects on LES, where the performances of the three SGS models at different resolutions are compared to direct numerical simulation (DNS) results. The results show that LES using eddy viscosity SGS models is very sensitive to resolution. At coarse resolutions, LES with the DS and the HPF models deviate considerably from DNS, whereas LES with the EA model still gives reasonable results. Further analysis shows that the two former models do not accurately predict the SGS dissipation near the wall, while the latter does, even at coarse resolutions. In the second part, the effect of SGS modelling on LES predictions of near-wall and outer-layer turbulent structures is discussed. It is found that different models predict near-wall turbulent structures of different sizes. Analysis of the spectra shows that although near-wall scales are not resolved at coarse resolutions, large-scale motions can be reasonably captured in LES using all the tested models. © 2010 Taylor & Francis.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Channel flow; Large eddy simulation; Resolution effects; Subgrid-scale modelling; Subgridscale anisotropy

Effects of rapid spanwise rotation on turbulent channel flow with a passive scalar - Brethouwer, Geert; Schlatter, Philipp; Johansson, Arne V. (7th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2011, 2011)
Direct numerical simulations of fully developed turbulent channel flow including a passive scalar rotating about the spanwise axis have been performed. The mean bulk Reynolds number, Reb = Ubh/ν ≥ 20000, where Ub is the bulk mean velocity and h the channel half width, is higher than in previous simulations and the rotation rate covers a wide range. At moderate rotation rates, turbulence on the stable channel side is significantly less damped than in DNS at lower Reb. At high rotation rates we observe re-occurring, quasi-periodic instabilities on the stable channel side. Between these events the turbulence is weak, but during the instability events the wall shear stress and turbulence intensity are much stronger. The instabilities are caused by structures resembling Tollmien-Schlichting (TS) waves that at some instant rapidly grow, then become unstable and finally break down into intense turbulence. After some time the TS waves form again and the process repeats itself in a periodic-like manner. Mean scalar profiles are also strongly affected by rotation and large scalar fluctuations are found on the border of the stable and unstable channel side. The turbulent Prandtl/Schmidt number of the scalar is much less than unity if there is rotation. Predicting scalar transport in rotating channel flow will therefore pose a challenge to turbulence models.
CRIS-Team Scopus Importer:2023-03-21

Enabling Adaptive Mesh Refinement for Spectral-Element Simulations of Turbulence Around Wing Sections - Tanarro, Alvaro; Mallor, Fermin; Offermans, Nicolas; Peplinski, Adam; Vinuesa, Ricardo; Schlatter, Philipp (Flow Turbulence and Combustion, 2020)
The implementation of adaptive mesh refinement (AMR) in the spectral-element method code Nek5000 is used for the first time on the well-resolved large-eddy simulation of the turbulent flow over wings. In particular, the flow over a NACA4412 profile with a 5 ∘ angle of attack at chord-based Reynolds number Re c= 200 , 000 is analyzed in the present work and compared with a previous conformal simulation used as baseline. The mesh, starting from a coarse resolution, is progressively and automatically refined by means of AMR, which allows for high resolution near the wall and wake whereas significantly larger elements are used in the far-field. The resulting mesh, which remains unchanged in the production runs (i.e. AMR is used to create the final mesh, which is then fixed), is of higher resolution than those in previous conformal cases, and it allows for the use of larger computational domains, avoiding the use of precursor RANS simulations to determine the boundary conditions. This is achieved with, approximately, 2 times lower total number of grid points if the same spanwise length is used. Turbulence statistics obtained in the AMR simulation show good agreement with the ones obtained with the conformal mesh, and the pressure-coefficient distribution along the wing surface matches pressure-scan experimental data obtained in the MTL wind tunnel at KTH. The use of AMR is therefore expected to enable the simulation of high-Reynolds numbers turbulent flows over complex geometries (such as wings), thus allowing the study of pressure-gradient effects at high Reynolds numbers relevant for practical applications.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Adaptive mesh refinement; Adverse pressure gradient; Airfoil; Large-eddy simulation; Turbulent boundary layer

Enhanced secondary motion of the turbulent flow through a porous square duct - Samanta, A.; Vinuesa, Ricardo; Lashgari, I.; Schlatter, Philipp; Brandt, L. (Journal of Fluid Mechanics, 2015)
Direct numerical simulations of the fully developed turbulent flow through a porous square duct are performed to study the effect of the permeable wall on the secondary cross-stream flow. The volume-averaged Navier-Stokes equations are used to describe the flow in the porous phase, a packed bed with porosity εc = 0:95. The porous square duct is computed at Reb ∼ 5000 and compared with the numerical simulations of a turbulent duct with four solid walls. The two boundary layers on the top wall and porous interface merge close to the centre of the duct, as opposed to the channel, because the sidewall boundary layers inhibit the growth of the shear layer over the porous interface. The most relevant feature in the porous duct is the enhanced magnitude of the secondary flow, which exceeds that of a regular duct by a factor of four. This is related to the increased vertical velocity, and the different interaction between the ejections from the sidewalls and the porous medium. We also report a significant decrease in the streamwise turbulence intensity over the porous wall of the duct (which is also observed in a porous channel), and the appearance of short spanwise rollers in the buffer layer, replacing the streaky structures of wall-bounded turbulence. These spanwise rollers most probably result from a Kelvin-Helmholtz type of instability, and their width is limited by the presence of the sidewalls.
CRIS-Team Scopus Importer:2023-03-21
Keywords: porous media; turbulence simulation; turbulent boundary layers

Entropy generation in a boundary layer transitioning under the influence of freestream turbulence - Walsh, Edmond J.; Mc Eligot, Donald M.; Brandt, Luca; Schlatter, Philipp (Journal of Fluids Engineering-Transactions of the Asme, 2011)
The objective of the present research is to develop new fundamental knowledge of the entropy generation process in laminar flow with significant fluctuations (called pre-transition) and during transition prematurely induced by strong freestream turbulence (bypass transition). Results of direct numerical simulations are employed. In the pre-transitional boundary layer, the perturbations by the streaky structures modify the mean velocity profile and induce a "quasi-turbulent" contribution to indirect dissipation. Application of classical laminar theory leads to underprediction of the entropy generated. In the transition region the pointwise entropy generation rate (S‴)+ initially increases near the wall and then decreases to correspond to the distribution predicted for a fully-turbulent boundary layer as the flow progresses downstream. In contrast to a developed turbulent flow, the term for turbulent convection in the turbulence kinetic energy balance is significant and can play an important role in some regions of the transitioning boundary layer. More turbulent energy is produced than dissipated and the excess is convected downstream as the boundary layer grows. Since it is difficult to measure and predict true turbulent dissipation rates (and hence, entropy generation rates) exactly other than by expensive direct numerical simulations, a motivation for this research is to evaluate approximate methods for possible use in experiments and design. These new results demonstrate that an approximate technique, used by many investigators, overestimates the dissipation coefficient Cd by up to seventeen per cent. For better predictions and measurements, an integral approach accounting for the important turbulent energy flux is proposed and validated for the case studied. © 2011 American Society of Mechanical Engineers.
CRIS-Team Scopus Importer:2023-03-21

Entropy generation rate in turbulent spots in a boundary layer subject to freestream turbulence - Rehill, Brendan; Walsh, Ed J.; Nolan, Kevin; Mceligot, Donald M.; Brandt, Luca; Schlatter, Philipp; Henningson, Dan S. (IUTAM Bookseries, 2010)
Turbulent spots are studied in a boundary layer subject to freestream turbulence with the data taken from direct numerical simulations performed by Brandt et al.[2]. Additional simulations of artificially induced turbulent spots are investigated in a laminar and streaky boundary layer. The flow is seperated into turbulent and non-turbulent regions using a threshold of spanwise velocity, w. Mean velocity profiles within the spot show siginificant deviations from fully turbulent profiles. The dissipation coefficient, indicating the evolution of entropy generation within the spot, shows good agreement with previous correlations. © 2010 Springer Science+Business Media B.V.
CRIS-Team Scopus Importer:2023-03-21

Error-driven adaptive mesh refinement for unsteady turbulent flows in spectral-element simulations - Offermans, Nicolas; Massaro, Daniele; Peplinski, Adam; Schlatter, Philipp (Computers & Fluids, 2023)
The simulation of turbulent flows requires high spatial resolution in potentially a priori unknown, solution-dependent locations. To achieve adaptive refinement of the mesh, we rely on error indicators. We assess the differences between an error measure relying on the local convergence properties of the numerical solution and a goal-oriented error measure based on the computation of an adjoint problem. The latter method aims at optimizing the mesh for the calculation of a predefined integral quantity, or functional of interest. This work follows on from a previous study conducted on steady flows in Offermans et al. (2020) and we extend the use of the so-called adjoint error estimator to three-dimensional, turbulent flows. They both represent a way to achieve error control and automatic mesh refinement (AMR) for the numerical approximation of the Navier–Stokes equations, with a spectral element method discretization and non-conforming h-refinement. The current study consists of running the same physical flow case on gradually finer meshes, starting from a coarse initial grid, and to compare the results and mesh refinement patterns when using both error measures. As a flow case, we consider the turbulent flow in a constricted, periodic channel, also known as the periodic hill flow, at four different Reynolds numbers: Re = 700, Re = 1400, Re = 2800 and Re = 5600. Our results show that both error measures allow for effective control of the error, but they adjust the mesh differently. Well-resolved simulations are achieved by automatically focusing refinement on the most critical regions of the domain, while significant saving in the overall number of elements is attained, compared to statically generated meshes. At all Reynolds numbers, we show that relevant physical quantities, such as mean velocity profiles and reattachment/separation points, converge well to reference literature data. At the highest Reynolds number achieved (Re = 5600), relevant quantities, i.e. reattachment and separation locations, are estimated with the same level of accuracy as the reference data while only using one-third of the degrees of freedom of the reference. Moreover, we observe distinct mesh refinement patterns for both error measures. With the spectral error indicator, the mesh resolution is more uniform and turbulent structures are more resolved within the whole domain. On the other hand, the adjoint error estimator tends to focus the refinement within a localized zone in the domain, dependent on the functional of interest, leaving large parts of the domain marginally resolved.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Adaptive mesh refinement; Adjoint error estimator; Direct numerical simulations; Error control; Spectral element method; Spectral error indicator

ESTIMATING UNCERTAINTY OF LOW- AND HIGH-ORDER TURBULENCE STATISTICS IN WALL TURBULENCE - Rezaeiravesh, Saleh; Xavier, Donnatella; Vinuesa, Ricardo; Yao, Jie; Hussain, Fazle; Schlatter, Philipp (12th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2022, 2022)
A framework is introduced for accurate estimation of time-average uncertainties in various types of turbulence statistics. A thorough set of guidelines is provided to adjust the different hyperparameters for estimating uncertainty in sample mean estimators (SMEs). For high-order turbulence statistics, a novel approach is proposed which avoids any linearization and preserves all relevant temporal and spatial correlations and cross-covariances between SMEs. This approach is able to accurately estimate uncertainties in any arbitrary statistical moment. The usability of the approach is demonstrated by applying it to data from direct numerical simulation (DNS) of the turbulent flow over a periodic hill and through a straight circular pipe.
CRIS-Team Scopus Importer:2023-03-21

Evidence of sublaminar drag naturally occurring in a curved pipe - Noorani, A.; Schlatter, Philipp (Physics of Fluids, 2015)
Steady and unsteady flows in a mildly curved pipe for a wide range of Reynolds numbers are examined with direct numerical simulation. It is shown that in a range of Reynolds numbers in the vicinity of Reb ≈ 3400, based on bulk velocity and pipe diameter, a marginally turbulent flow is established in which the friction drag naturally reduces below the laminar solution at the same Reynolds number. The obtained values for friction drag for the laminar and turbulent (sublaminar) flows turn out to be in excellent agreement with experimental measurements in the literature. Our results are also in agreement with Fukagata et al. ["On the lower bound of net driving power in controlled duct flows," Phys. D 238, 1082 (2009)], as the lower bound of net power required to drive the flow, i.e., the pressure drop of the Stokes solution, is still lower than our marginally turbulent flow. A large-scale traveling structure that is thought to be responsible for that behaviour is identified in the instantaneous field. This mode could also be extracted using proper orthogonal decomposition. The effect of this mode is to redistribute the mean flow in the circular cross section which leads to lower gradients at the wall compared to the laminar flow.
CRIS-Team Scopus Importer:2023-03-21

Evolution of turbulence characteristics from straight to curved pipes - Noorani, A.; El Khoury, G. K.; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2013)
Fully developed, statistically steady turbulent flow in straight and curved pipes at moderate Reynolds numbers is studied in detail using direct numerical simulations (DNS) based on a spectral element discretisation. After the validation of data and setup against existing DNS results, a comparative study of turbulent characteristics at different bulk Reynolds numbers Reb = 5300 and 11,700, and various curvature parameters κ = 0, 0.01, 0.1 is presented. In particular, complete Reynolds-stress budgets are reported for the first time. Instantaneous visualisations reveal partial relaminarisation along the inner surface of the curved pipe at the highest curvature, whereas developed turbulence is always maintained at the outer side. The mean flow shows asymmetry in the axial velocity profile and distinct Dean vortices as secondary motions. For strong curvature a distinct bulge appears close to the pipe centre, which has previously been observed in laminar and transitional curved pipes at lower Reb only. On the other hand, mild curvature allows the interesting observation of a friction factor which is lower than in a straight pipe for the same flow rate. All statistical data, including mean profile, fluctuations and the Reynolds-stress budgets, is available for development and validation of turbulence models in curved geometries. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Coiled tube; Curvature effects; Pipe flow; Reynolds-stress budgets; Wall turbulence

Experience and analysis of scalable high-fidelity computational fluid dynamics on modular supercomputing architectures - Karp, Martin; Suarez, Estela; Meinke, Jan H.; Andersson, Måns I.; Schlatter, Philipp; Markidis, Stefano; Jansson, Niclas (International Journal of High Performance Computing Applications, 2024)
The never-ending computational demand from simulations of turbulence makes computational fluid dynamics (CFD) a prime application use case for current and future exascale systems. High-order finite element methods, such as the spectral element method, have been gaining traction as they offer high performance on both multicore CPUs and modern GPU-based accelerators. In this work, we assess how high-fidelity CFD using the spectral element method can exploit the modular supercomputing architecture at scale through domain partitioning, where the computational domain is split between a Booster module powered by GPUs and a Cluster module with conventional CPU nodes. We investigate several different flow cases and computer systems based on the Modular Supercomputing Architecture (MSA). We observe that for our simulations, the communication overhead and load balancing issues incurred by incorporating different computing architectures are seldom worthwhile, especially when I/O is also considered, but when the simulation at hand requires more than the combined global memory on the GPUs, utilizing additional CPUs to increase the available memory can be fruitful. We support our results with a simple performance model to assess when running across modules might be beneficial. As MSA is becoming more widespread and efforts to increase system utilization are growing more important our results give insight into when and how a monolithic application can utilize and spread out to more than one module and obtain a faster time to solution.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Computational fluid dynamics; HPC; modular supercomputing architecture

Experimental characterization of turbulent boundary layers around a NACA 4412 wing profile - Mallor, Fermin; Sanmiguel Vila, Carlos; Hajipour, Majid; Vinuesa, Ricardo; Schlatter, Philipp; Örlü, Ramis (Experimental Thermal and Fluid Science, 2025)
An experimental characterization of the turbulent boundary layers developing around a NACA 4412 wing profile is carried out in the Minimum Turbulence Level (MTL) wind tunnel located at KTH Royal Institute of Technology. The campaign included collecting wall-pressure data via built-in pressure taps, capturing velocity signals in the turbulent boundary layers (TBLs) using hot-wire anemometry (HWA), and conducting direct skin-friction measurements with oil-film interferometry (OFI). The research spanned two chord-based Reynolds numbers (Rec=4×105 and 106) and four angles of attack (5°, 8°, 11° and 14°), encompassing a broad spectrum of flow conditions, from mild to strong adverse-pressure gradients (APGs), including scenarios where the TBL detaches from the wing surface. This dataset offers crucial insights into TBL behavior under varied flow conditions, particularly in the context of APGs. Key features include the quasi-independence of the pressure coefficient distributions from Reynolds number, which aids in distinguishing Reynolds-number effects from those due to APG strengths. The study also reveals changes in TBL dynamics as separation approaches, with energy shifting from the inner to the outer region and the eventual transition to a free-shear flow state post-separation. Additionally, the diagnostic scaling in the outer region under spatial-resolution effects is considered, showing further evidence for its applicability for small L+, however with inconsistent results for larger L+. The findings and database resulting from this campaign may be of special relevance for the development and validation of turbulence models, especially in the context of aeronautical applications.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Adverse-pressure gradient; Hot-wire anemometry; Turbulence scaling; Turbulent boundary layer; Wind-tunnel experiment

Experimental realisation of near-equilibrium adverse-pressure-gradient turbulent boundary layers - Vila, C. Sanmiguel; Vinuesa, Ricardo; Discetti, Stefano; Ianiro, Andrea; Schlatter, Philipp; Orlu, R. (Experimental Thermal and Fluid Science, 2020)
A new experimental database of adverse-pressure-gradient (APG) turbulent boundary layers (TBLs) obtained through hot-wire anemometry and oil-film interferometry covering a momentum–loss Reynolds number 450<Reθ<23450 and Clauser pressure-gradient-parameter range up to β≈2.4 is presented. Both increasing and approximately constant β distributions with the same upstream history are characterised. Turbulence statistics are compared among the different pressure-gradient distributions with additional numerical and experimental zero-pressure-gradient (ZPG) TBL data. Cases at approximately constant β, which can be considered as canonical representations of the boundary layer under a certain pressure-gradient magnitude, exhibit skin-friction and shape-factor curves consistent with the ones proposed by Vinuesa et al. (2017). These curves show a similar scaling behaviour as those proposed by Nagib et al. (2007) for ZPG TBLs. The pre-multiplied power-spectral density is employed to study the differences in the large-scale energy content throughout the boundary layer. Two different large-scale phenomena are identified, the first one related to the pressure gradient and the second one (also present in high-Re ZPG TBLs) due to the Reynolds number. Recently proposed scaling laws by Kitsios et al. (2016) and Maciel et al. (2018) are tested over a wider Reynolds-number range and for different β cases. The mean velocity and streamwise velocity fluctuation profiles are found to be dependent on the upstream development. The mean velocity profile is found to be self-similar only in the outer region, in agreement with classical theory. The mean and higher-order statistics of the new APG TBL database are made available under www.flow.kth.se.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Pressure gradient flows; Turbulent boundary layer; Turbulent flows

Experiments and computations of localized pressure gradients with different history effects - Vinuesa, Ricardo; Rozier, Paul H.; Schlatter, Philipp; Nagib, Hassan M. (AIAA Journal, 2014)
The study of high-Reynolds-number wall-bounded turbulent flows has become a very active area of research in the past decade, where several recent results have challenged current understanding. In this study, four different localized pressure gradient configurations are characterized by computing them using four Reynolds-averaged Navier-Stokes turbulence models (Spalart-Allmaras, κ-ε, shear stress transport, and the Reynolds stress model) and comparing their predictions with experimental measurements of mean flow quantities and wall shear stress. The pressure gradients were imposed on high-Reynolds-number, two-dimensional turbulent boundary layers developing on a flat plate by changing the ceiling geometry of the test section. The computations showed that the shear stress transport model produced the best agreement with the experiments. It was found that what is called "numerical transition" (a procedure by which the laminar boundary conditions are transformed into inflow conditions to characterize the initial turbulent profile) causes the major differences between the various models, thereby highlighting the need for models representative of true transition in computational codes. Also, both experiments and computations confirm the nonuniversality of the von Kármán coefficient κ. Finally, a procedure is demonstrated for simpler two-dimensional computations that can be representative of flows with some mild three-dimensional geometries. Copyright © 2013 by the American Institute of Aeronautics and Astronautics, Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-03-21

Exploring the Ultimate Regime of Turbulent Rayleigh-Bénard Convection Through Unprecedented Spectral-Element Simulations - Jansson, Niclas; Karp, Martin; Perez, Adalberto; Mukha, Timofey; Ju, Yi; Liu, Jiahui; Páll, Szilárd; Laure, Erwin; Weinkauf, Tino; Schumacher, Jörg; Schlatter, Philipp; Markidis, Stefano (Proceedings of the International Conference for High Performance Computing, Networking, Storage and Analysis, SC 2023, 2023)
We detail our developments in the high-fidelity spectral-element code Neko that are essential for unprecedented large-scale direct numerical simulations of fully developed turbulence. Major innovations are modular multi-backend design enabling performance portability across a wide range of GPUs and CPUs, a GPU-optimized preconditioner with task overlapping for the pressure-Poisson equation and in-situ data compression. We carry out initial runs of Rayleigh-Bénard Convection (RBC) at extreme scale on the LUMI and Leonardo supercomputers. We show how Neko is able to strongly scale to 16,384 GPUs and obtain results that are not possible without careful consideration and optimization of the entire simulation workflow. These developments in Neko will help resolving the long-standing question regarding the ultimate regime in RBC.
CRIS-Team Scopus Importer:2023-12-22

Flow features in three-dimensional turbulent duct flows with different aspect ratios - Vinuesa, Ricardo; Schlatter, Philipp; Nagib, Hassan M. (Springer Proceedings in Physics, 2016)
Direct numerical simulations of turbulent duct flows with width-to-height ratios 1, 3, 5, 7 and 10, at a friction Reynolds number Reτ,c ≃ 180, are carried out with the spectral element code Nek5000. The aim of these simulations is to gain insight into the kinematics and dynamics of Prandtl’s secondary flow of second kind, and its impact on the flow physics of wall-bounded turbulence. The secondary flow is characterized in terms of the cross-plane mean kinetic energy K = (V2 + W2)/2, and its variation in the spanwise direction of the flow. Our results show that averaging times of at least 3, 000 time units are required to reach a converged state of the secondary flow, which extends up to z* ≃ 5 h from the side walls. We also show that if the duct is not wide enough to accommodate the whole extent of the secondary flow, then its structure is modified by means of a different spanwise distribution of energy. Future proposed work includes coherent structure eduction, quadrant analysis at the corner, and comparisons with spanwise-periodic channels at comparable Reynolds numbers.
CRIS-Team Scopus Importer:2023-03-21

Flow organization in the wake of a rib in a turbulent boundary layer with pressure gradient - Guemes, A.; Vila, C. Sanmiguel; Orlu, R.; Vinuesa, Ricardo; Schlatter, Philipp; Ianiro, Andrea; Discetti, Stefano (Experimental Thermal and Fluid Science, 2019)
The effect of a streamwise pressure gradient on the wake developed by wall-attached square ribs in a turbulent boundary layer is investigated experimentally. Favourable-, adverse- and zero-pressure-gradient conditions (FPG, APG and ZPG, respectively) are reproduced at matched friction Reynolds number and non-dimensional rib height. Flow-field measurements are carried out by means of Particle Image Velocimetry (PIV). Turbulence statistics are extracted at high resolution using an Ensemble Particle Tracking Velocimetry approach. Modal analysis is performed with Proper Orthogonal Decomposition (POD). We demonstrate that a non-dimensional expression of the pressure gradient and shear stress is needed to quantify the pressure-gradient effects in the wake developing past wall-attached ribs. We suggest the Clauser pressure-gradient parameter β, commonly used in the literature for the characterization of turbulent boundary layers under the effect of a pressure gradient, as a suitable parameter. The results show that, in presence of an adverse pressure gradient, the recirculation region downstream of the rib is increased in size, thus delaying the reattachment, and that the peak of turbulence intensity and the shed eddies are shifted towards larger wall-normal distances than in the ZPG case. The observed changes with respect to the ZPG configuration appear more intense for larger magnitude of β, which are more likely to be obtained in APG than in FPG due to the reduced skin friction and increased displacement thickness.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Pressure gradient flows; Ribs; Turbulent boundary layer

Flow structures on a planar food and drug administration (FDA) nozzle at low and intermediate reynolds number - Corrochano, Adrian; Xavier, Donnatella; Schlatter, Philipp; Vinuesa, Ricardo; Le Clainche, Soledad (Fluids, 2021)
In this paper, we present a general description of the flow structures inside a twodimensional Food and Drug Administration (FDA) nozzle. To this aim, we have performed numerical simulations using the numerical code Nek5000. The topology patters of the solution obtained, identify four different flow regimes when the flow is steady, where the symmetry of the flow breaks down. An additional case has been studied at higher Reynolds number, when the flow is unsteady, finding a vortex street distributed along the expansion pipe of the geometry. Linear stability analysis identifies the evolution of two steady and two unsteady modes. The results obtained have been connected with the changes in the topology of the flow. Finally, higher-order dynamic mode decomposition has been applied to identify the main flow structures in the unsteady flow inside the FDA nozzle. The highest-amplitude dynamic mode decomposition (DMD) modes identified by the method model the vortex street in the expansion of the geometry.
CRIS-Team Scopus Importer:2023-03-21
Keywords: FDA nozzle; Flow structures; Higher order dynamic mode decomposition; Linear stability analysis

Flow topology of rare back flow events and critical points in turbulent channels and toroidal pipes - Chin, C.; Vinuesa, Ricardo; Orlu, R.; Cardesa, J.; Noorani, A.; Schlatter, Philipp; Chong, M. S. (Journal of Physics: Conference Series, 2018)
A study of the back flow events and critical points in the flow through a toroidal pipe at friction Reynolds number Reτ ≈ 650 is performed and compared with the results in a turbulent channel flow at Reτ ≈ 934. The statistics and topological properties of the back flow events are analysed and discussed. Conditionally-averaged flow fields in the vicinity of the back flow event are obtained, and the results for the torus show a similar streamwise wall-shear stress topology which varies considerably for the spanwise wall-shear stress when compared to the channel flow. The comparison between the toroidal pipe and channel flows also shows fewer back flow events and critical points in the torus. This cannot be solely attributed to differences in Reynolds number, but is a clear effect of the secondary flow present in the toroidal pipe. A possible mechanism is the effect of the secondary flow present in the torus, which convects momentum from the inner to the outer bend through the core of the pipe, and back from the outer to the inner bend through the pipe walls. In the region around the critical points, the skin-friction streamlines and vorticity lines exhibit similar flow characteristics with a node and saddle pair for both flows. These results indicate that back flow events and critical points are genuine features of wall-bounded turbulence, and are not artifacts of specific boundary or inflow conditions in simulations and/or measurement uncertainties in experiments.
CRIS-Team Scopus Importer:2023-03-21

Formation of turbulent patterns near the onset of transition in plane Couette flow - Duguet, Y.; Schlatter, Philipp; Henningson, D. S. (Journal of Fluid Mechanics, 2010)
The formation of turbulent patterns in plane Couette flow is investigated near the onset of transition, using numerical simulation in a very large domain of size 800 h 2 h 356 h. Based on a maximum observation time of 20 000 inertial units, the threshold for the appearance of sustained turbulent motion is Rec = 324 1. For Rec < Re 380, turbulent-banded patterns form, irrespective of whether the initial perturbation is a noise or localized disturbance. Measurements of the turbulent fraction versus Re show evidence for a discontinuous phase transition scenario where turbulent spots play the role of the nuclei. Using a smaller computational box, the angle selection of the turbulent bands in the early stages of their development is shown to be related to the amplitude of the initial perturbation. Copyright © Cambridge University Press 2010.
CRIS-Team Scopus Importer:2023-03-21

Fully convolutional networks for velocity-field predictions based on the wall heat flux in turbulent boundary layers - Guastoni, Luca; Balasubramanian, Arivazhagan G.; Foroozan, Firoozeh; Güemes, Alejandro; Ianiro, Andrea; Discetti, Stefano; Schlatter, Philipp; Azizpour, Hossein; Vinuesa, Ricardo (Theoretical and Computational Fluid Dynamics, 2025)
Fully-convolutional neural networks (FCN) were proven to be effective for predicting the instantaneous state of a fully-developed turbulent flow at different wall-normal locations using quantities measured at the wall. In Guastoni et al. (J Fluid Mech 928:A27, 2021. https://doi.org/10.1017/jfm.2021.812), we focused on wall-shear-stress distributions as input, which are difficult to measure in experiments. In order to overcome this limitation, we introduce a model that can take as input the heat-flux field at the wall from a passive scalar. Four different Prandtl numbers Pr=ν/α=(1,2,4,6) are considered (where ν is the kinematic viscosity and α is the thermal diffusivity of the scalar quantity). A turbulent boundary layer is simulated since accurate heat-flux measurements can be performed in experimental settings: first we train the network on aptly-modified DNS data and then we fine-tune it on the experimental data. Finally, we test our network on experimental data sampled in a water tunnel. These predictions represent the first application of transfer learning on experimental data of neural networks trained on simulations. This paves the way for the implementation of a non-intrusive sensing approach for the flow in practical applications.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Machine learning; Turbulence simulation; Turbulent boundary layers

Fully localised edge states in boundary layers - Khapko, Taras; Kreilos, Tobias; Schlatter, Philipp; Duguet, Yohann; Eckhardt, Bruno; Henningson, Dan S. (Proceedings - 15th European Turbulence Conference, ETC 2015, 2015)
Investigation of the laminar–turbulent boundary is performed in a boundary-layer flow. Constant homogeneous suction is applied at the wall in order to prevent the spatial growth of the layer, leading to the parallel Asymptotic Suction Boundary Layer (ASBL). Edge tracking is performed in a large computational domain allowing for full spatial localisation of the structures on the laminar–turbulent separatrix. The obtained dynamics of the state goes through calm and bursting phases. During the latter the structure grows in size, shedding vortices downstream of its core which viscously decay during the calm phases. Comparison with the computation in spatially growing boundary layer is made. The influence of the Reynolds number and the path leading from the edge state to turbulent flow are considered.
CRIS-Team Scopus Importer:2023-03-21

Generating synthetic turbulence with vector autoregression of proper orthogonal decomposition time coefficients - Stanly, Ronith; Du, Shiyu; Xavier, Donnatella; Perez, Adalberto; Mukha, Timofey; Markidis, Stefano; Rezaeiravesh, Saleh; Schlatter, Philipp (Journal of Fluid Mechanics, 2024)
This study introduces vector autoregression (VAR) as a linear procedure that can be used for synthesizing turbulence time series over an entire plane, allowing them to be imposed as an efficient turbulent inflow condition in simulations requiring stationary and cross-correlated turbulence time series. VAR is a statistical tool for modelling and prediction of multivariate time series through capturing linear correlations between multiple time series. A Fourier-based proper orthogonal decomposition (POD) is performed on the two-dimensional (2-D) velocity slices from a precursor simulation of a turbulent boundary layer at a momentum thickness-based Reynolds number,. A subset of the most energetic structures in space are then extracted, followed by applying a VAR model to their complex time coefficients. It is observed that VAR models constructed using time coefficients of 5 and 30 most energetic POD modes per wavenumber (corresponding to and of turbulent kinetic energy, respectively) are able to make accurate predictions of the evolution of the velocity field at for infinite time. Moreover, the 2-D velocity fields from the POD-VAR when used as a turbulent inflow condition, gave a short development distance when compared with other common inflow methods. Since the VAR model can produce an infinite number of velocity planes in time, this enables reaching statistical stationarity without having to run an extremely long precursor simulation or applying ad hoc methods such as periodic time series.
CRIS-Team Scopus Importer:2025-02-04
Keywords: turbulent boundary layers

Global effect of local skin friction drag reduction in spatially developing turbulent boundary layer - Stroh, Alexander; Hasegawa, Y.; Schlatter, Philipp; Frohnapfel, Bettina (Journal of Fluid Mechanics, 2016)
A numerical investigation of two locally applied drag-reducing control schemes is carried out in the configuration of a spatially developing turbulent boundary layer (TBL). One control is designed to damp near-wall turbulence and the other induces constant mass flux in the wall-normal direction. Both control schemes yield similar local drag reduction rates within the control region. However, the flow development downstream of the control significantly differs: persistent drag reduction is found for the uniform blowing case, whereas drag increase is found for the turbulence damping case. In order to account for this difference, the formulation of a global drag reduction rate is suggested. It represents the reduction of the streamwise force exerted by the fluid on a plate of finite length. Furthermore, it is shown that the far-downstream development of the TBL after the control region can be described by a single quantity, namely a streamwise shift of the uncontrolled boundary layer, i.e. a changed virtual origin. Based on this result, a simple model is developed that allows the local drag reduction rate to be related to the global one without the need to conduct expensive simulations or measurements far downstream of the control region.
CRIS-Team Scopus Importer:2023-03-21
Keywords: boundary layer control; drag reduction; turbulence control

Global linear and nonlinear stability of viscous confined plane wakes with co-flow - Tammisola, Outi; Lundell, Fredrik; Schlatter, Philipp; Wehrfritz, Armin; Soderberg, L. Daniel (Journal of Fluid Mechanics, 2011)
The global stability of confined uniform density wakes is studied numerically, using two-dimensional linear global modes and nonlinear direct numerical simulations. The wake inflow velocity is varied between different amounts of co-flow (base bleed). In accordance with previous studies, we find that the frequencies of both the most unstable linear and the saturated nonlinear global mode increase with confinement. For wake Reynolds number Re = 100 we find the confinement to be stabilising, decreasing the growth rate of the linear and the saturation amplitude of the nonlinear modes. The dampening effect is connected to the streamwise development of the base flow, and decreases for more parallel flows at higher Re. The linear analysis reveals that the critical wake velocities are almost identical for unconfined and confined wakes at Re ≈ 400. Further, the results are compared with literature data for an inviscid parallel wake. The confined wake is found to be more stable than its inviscid counterpart, whereas the unconfined wake is more unstable than the inviscid wake. The main reason for both is the base flow development. A detailed comparison of the linear and nonlinear results reveals that the most unstable linear global mode gives in all cases an excellent prediction of the initial nonlinear behaviour and therefore the stability boundary. However, the nonlinear saturated state is different, mainly for higher Re. For Re = 100, the saturated frequency differs less than 5% from the linear frequency, and trends regarding confinement observed in the linear analysis are confirmed. © 2011 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21
Keywords: absolute/convective instability; vortex shedding; wakes

Global linear instability of the rotating-disk flow investigated through simulations - Appelquist, E.; Schlatter, Philipp; Alfredsson, P. H.; Lingwood, R. J. (Journal of Fluid Mechanics, 2015)
Numerical simulations of the flow developing on the surface of a rotating disk are presented based on the linearized incompressible Navier-Stokes equations. The boundary-layer flow is perturbed by an impulsive disturbance within a linear global framework, and the effect of downstream turbulence is modelled by a damping region further downstream. In addition to the outward-travelling modes, inward-travelling disturbances excited at the radial end of the simulated linear region, rend, by the modelled turbulence are included within the simulations, potentially allowing absolute instability to develop. During early times the flow shows traditional convective behaviour, with the total energy slowly decaying in time. However, after the disturbances have reached rend, the energy evolution reaches a turning point and, if the location of rend is at a Reynolds number larger than approximately R=594 (radius non-dimensionalized by √ω∗=, where v is the kinematic viscosity and is the rotation rate of the disk), there will be global temporal growth. The global frequency and mode shape are clearly imposed by the conditions at rend. Our results suggest that the linearized Ginzburg-Landau model by Healey (J. Fluid Mech., vol. 663, 2010, pp. 148-159) captures the (linear) physics of the developing rotating-disk flow, showing that there is linear global instability provided the Reynolds number of rend is sufficiently larger than the critical Reynolds number for the onset of absolute instability.
CRIS-Team Scopus Importer:2023-03-21
Keywords: absolute/convective instability; boundary layer stability; rotating flows

Global stability analysis of a 90°-bend pipe flow - Lupi, Valerio; Canton, Jacopo; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2020)
The present work investigates the stability properties of the flow in a 90°-bend pipe with curvature δ=R/Rc=1/3, with R being the radius of the cross-section of the pipe and Rc the radius of curvature at the pipe centreline. Direct numerical simulations (DNS) for values of the bulk Reynolds number Reb=UbD/ν between 2000 and 3000 are performed. The bulk Reynolds number is based on the bulk velocity Ub, the pipe diameter D, and the kinematic viscosity ν. The flow is found to be steady for Reb⩽2500, with two main pairs of symmetric, counter-rotating vortices in the section of the pipe downstream of the bend. The presence of two recirculation regions is detected inside the bend: one on the outer wall and the other on the inner side. For Reb⩾2550, the flow exhibits a periodic behaviour, oscillating with a fundamental non-dimensional frequency St=fD/Ub=0.23. A global stability analysis is performed in order to determine the cause of the transition from the steady to the periodic regime. The spectrum of the linearised Navier-Stokes operator reveals a pair of complex conjugate eigenvalues with positive real part, hence the transition is ascribed to a Hopf bifurcation occurring at Reb,cr≈2531, a value much lower than the critical Reynolds number for the flow in a torus with the same curvature. The velocity components of the unstable direct and adjoint eigenmodes are investigated, and they display a large spatial separation, most likely due to the non-normality of the linearised Navier-Stokes operator. Thus, the core of the instability, also known in the literature as the wavemaker, is sought performing an analysis of the structural sensitivity of the unstable eigenmode to spatially localised feedbacks. The region located 15° downstream of the bend inlet, on the outer wall, is the most receptive to this kind of perturbations, and thus corresponds to where the instability originates. Since this region coincides with the outer-wall separation bubble, it is concluded that the instability is linked to the strong shear by the backflow phenomena. The present results are relevant for technical applications where bent pipes are frequently used, and their stability properties have hitherto not been studied.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Bent pipe; Global stability; Structural sensitivity

Global Stability Analysis of a Roughness Wake in a Falkner-Skan-Cooke Boundary Layer - Brynjell-Rahkola, Mattias; Schlatter, Philipp; Hanifi, Ardeshir; Henningson, Dan S. (Procedia IUTAM, 2015)
A global stability analysis of a Falkner-Skan-Cooke boundary layer with distributed three-dimensional surface roughness is per- formed using high-order direct numerical simulations. Computations have been performed for different sizes of the roughness elements, and a time-stepping method has been used to find the instability modes. The study shows that a critical roughness height beyond which a global instability is excited does exist. Furthermore, the origins of this instability is examined by means of an energy analysis, which reveals the production and dissipation terms responsible for the instability, as well as the region in space where the instability originates.
CRIS-Team Scopus Importer:2023-03-21
Keywords: energy analysis; Falkner-Skan-Cooke (FSC); global instability; surface roughness

Global stability and optimal perturbation for a jet in cross-flow - Peplinski, Adam; Schlatter, Philipp; Henningson, D. S. (European Journal of Mechanics B-Fluids, 2015)
We study the stability of a jet in cross-flow at low values of the jet to cross-flow velocity ratio R using direct numerical simulations (DNS) and global linear stability analysis adopting a time-stepper method. For the simplified setup without a meshed pipe in the simulations we compare results of a fully-spectral code SIMSON with a spectral-element code Nek5000. We find the use of periodic domains, even with the fringe method, unsuitable due to the large sensitivity of the eigenvalues and due to the large spatial growth of the corresponding eigenmodes. However, we observe a similar sensitivity to reflection from the outflow boundary in the inflow/outflow configuration, and therefore we use an extended domain where reflections are minimal. We apply in our studies both modal and non-modal linear analyses investigating transient effects and their asymptotic fate, and we find a transient wavepacket to develop almost identically in both the globally stable and unstable cases. The final results of the global stability analysis for our numerical setup show the critical value of R, at which the first bifurcation occurs, to lie in the range between 1.5 and 1.6.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Absolute/convective instability; Bifurcation; Direct numerical simulation; Jet in cross-flow; Optimal disturbance

Global stability of 180-bend pipe flow with mesh adaptivity - Massaro, Daniele; Lupi, Valerio; Peplinski, Adam; Schlatter, Philipp (Physical Review Fluids, 2023)
The global stability of the flow in a spatially developing 180∘-bend pipe with curvature δ=R/Rc=1/3 is investigated by performing direct numerical simulations to understand the underlying transitional mechanism. A unique application of the adaptive mesh refinement technique is used during the stability analysis for minimizing the interpolation and quadrature errors. Independent meshes are created for the direct and adjoint solutions, as well as for the base flow extracted via selective frequency damping. The spectrum of the linearized Navier-Stokes operator reveals a pair of complex conjugate eigenvalues, with frequency f≈0.233. Therefore, the transition is attributed to a Hopf bifurcation that takes place at Reb,cr=2528. A structural sensitivity analysis is performed by extracting the wavemaker. We identify the primary source of instability located on the outer wall, θ≈15 downstream of the bend inlet. This region corresponds to the separation bubble on the outer wall. We thus conclude that the instability is caused by the strong shear resulting from the backflow, similar to the 90-bend pipe flow. We believe that understanding the stability mechanism and characterizing the base flow in bent pipes is crucial for studying various biological flows, like blood vessels. Hence, this paper aims to close the knowledge gap between a 90-bend and toroidal pipes by investigating the transition nature in a 18-bend pipe flow.
CRIS-Team Scopus Importer:2023-12-08

Global stability of a jet in crossflow - Bagheri, Shervin; Schlatter, Philipp; Schmid, Peter J.; Henningson, Dan S. (Journal of Fluid Mechanics, 2009)
A linear stability analysis shows that the jet in crossflow is characterized by self-sustained global oscillations for a jet-to-crossflow velocity ratio of 3. A fully three-dimensional unstable steady-state solution and its associated global eigenmodes are computed by direct numerical simulations and iterative eigenvalue routines. The steady flow, obtained by means of selective frequency damping, consists mainly of a (steady) counter-rotating vortex pair (CVP) in the far field and horseshoe-shaped vortices close to the wall. High-frequency unstable global eigenmodes associated with shear-layer instabilities on the CVP and low-frequency modes associated with shedding vortices in the wake of the jet are identified. Furthermore, different spanwise symmetries of the global modes are discussed. This work constitutes the first simulation-based global stability analysis of a fully three-dimensional base flow. © 2009 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21

Hairpin vortices in turbulent boundary layers - Eitel-Amor, G.; Flores, Oscar; Schlatter, Philipp (Journal of Physics: Conference Series, 2014)
The present work addresses the question whether hairpin vortices are a dominant feature of near-wall turbulence and which role they play during transition. First, the parent-offspring mechanism is investigated in temporal simulations of a single hairpin vortex introduced in a mean shear flow corresponding to turbulent channels and boundary layers up to Reτ 590. Using an eddy viscosity computed from resolved simulations, the effect of a turbulent background is also considered. Tracking the vortical structure downstream, it is found that secondary hairpins are created shortly after initialization. Thereafter, all rotational structures decay, whereas this effect is enforced in the presence of an eddy viscosity. In a second approach, a laminar boundary layer is tripped to transition by insertion of a regular pattern of hairpins by means of defined volumetric forces representing an ejection event. The idea is to create a synthetic turbulent boundary layer dominated by hairpin-like vortices. The flow for Reτ < 250 is analysed with respect to the lifetime of individual hairpin-like vortices. Both the temporal and spatial simulations demonstrate that the regeneration process is rather short-lived and may not sustain once a turbulent background has formed. From the transitional flow simulations, it is conjectured that the forest of hairpins reported in former DNS studies is an outer layer phenomenon not being connected to the onset of near-wall turbulence. © Published under licence by IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-03-21

Hairpin vortices in turbulent boundary layers - Eitel-Amor, G.; Orlu, R.; Schlatter, Philipp; Flores, Oscar (Physics of Fluids, 2015)
The present work presents a number of parallel and spatially developing simulations of boundary layers to address the question of whether hairpin vortices are a dominant feature of near-wall turbulence, and which role they play during transition. In the first part, the parent-offspring regeneration mechanism is investigated in parallel (temporal) simulations of a single hairpin vortex introduced in a mean shear flow corresponding to either turbulent channels or boundary layers (Re≳590). The effect of a turbulent background superimposed on the mean flow is considered by using an eddy viscosity computed from resolved simulations. Tracking the vortical structure downstream, it is found that secondary hairpins are only created shortly after initialization, with all rotational structures decaying for later times. For hairpins in a clean (laminar) environment, the decay is relatively slow, while hairpins in weak turbulent environments (10% of t) dissipate after a couple of eddy turnover times. In the second part, the role of hairpin vortices in laminar-turbulent transition is studied using simulations of spatial boundary layers tripped by hairpin vortices. These vortices are generated by means of specific volumetric forces representing an ejection event, creating a synthetic turbulent boundary layer initially dominated by hairpin-like vortices. These hairpins are advected towards the wake region of the boundary layer, while a sinusoidal instability of the streaks near the wall results in rapid development of a turbulent boundary layer. For Re > 400, the boundary layer is fully developed, with no evidence of hairpin vortices reaching into the wall region. The results from both the parallel and spatial simulations strongly suggest that the regeneration process is rather short-lived and may not sustain once a turbulent background is developed. From the transitional flow simulations, it is conjectured that the forest of hairpins reported in former direct numerical simulation studies is reminiscent of the transitional boundary layer and may not be connected to some aspects of the dynamics of the fully developed wall-bounded turbulence.
CRIS-Team Scopus Importer:2023-03-21

Higher-order dynamic mode decomposition on-the-fly: A low-order algorithm for complex fluid flows - Amor, Christian; Schlatter, Philipp; Vinuesa, Ricardo; Le Clainche, Soledad (Journal of Computational Physics, 2023)
This article presents a new method to identify the main patterns describing the flow motion in complex flows. The algorithm is an extension of the higher-order dynamic mode decomposition (HODMD), which compresses the snapshots from the analysed database and progressively updates new compressed snapshots on-the-fly, so it is denoted as HODMD on-the-fly (HODMD-of). This algorithm can be applied in parallel to the numerical simulations (or experiments), and it exhibits two main advantages over offline algorithms: (i) it automatically selects on-the-fly the number of necessary snapshots from the database to identify the relevant dynamics; and (ii) it can be used from the beginning of a numerical simulation (or experiment), since it uses a sliding-window to automatically select, also on-the-fly, the suitable interval to perform the data analysis, i.e. it automatically identifies and discards the transient dynamics. The HODMD-of algorithm is suitable to build reduced order models, which have a much lower computational cost than the original simulation. The performance of the method has been tested in three different cases: the axi-symmetric synthetic jet, the three-dimensional wake of a circular cylinder and the turbulent wake behind a wall-mounted square cylinder. The obtained speed-up factors are around 7 with respect to HODMD; this value depends on the simulation and the configuration of the hyperparameters. HODMD-of also provides a significant reduction of the memory requirements, between 40−80% amongst the two- and three-dimensional cases studied in this paper.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Data-driven methods; Higher-order dynamic mode decomposition; Machine learning; Synthetic jets; Three-dimensional cylinder; Turbulent flows

High-fidelity simulations of the flow around a NACA 4412 wing section at high angles of attack - Mallor, Fermin; Vinuesa, Ricardo; Örlü, Ramis; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2024)
This study uses high-resolution large-eddy simulations (LES) to investigate the turbulent flow around a NACA 4412 wing profile at multiple Reynolds numbers based on chord length and free-stream velocity (Rec=2×105, 4×105 and 106) and angles of attack (AoA=5∘, 8°, 11° and 14°). The introduction of adaptive mesh refinement (AMR) and non-conformal meshing into the spectral-element-method code Nek5000 enabled the simulations at higher AoAs exhibiting flow separation by enabling the use of wider domains, allowing to capture the largest turbulent scales associated with flow separation. The results provide a detailed database – including integral quantities, velocity statistics and spectra – which may be used for the evaluation of lower-fidelity turbulence models. Furthermore, closer inspection of specific turbulent-boundary-layer (TBL) profiles allows us to discern between pressure-gradient (PG) and Reynolds-numbers effects on TBLs, showing that Re balances the PG, by reducing the impact of PG on the flow. Lastly, we assess the influence of flow history on TBLs, showing that a consistent flow history over an extended length is needed for TBLs to exhibit comparable profiles and characteristics.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Adverse-pressure gradient; Flow separation; Large-eddy simulation; Turbulent boundary layers; Wings

High-fidelity simulations of the flow around wings at high reynolds numbers - Vinuesa, Ricardo; Negi, Prabal S.; Hanifi, Ardeshir; Henningson, Dan S.; Schlatter, Philipp (10th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2017, 2017)
Reynolds-number effects in the adverse-pressure-gradient (APG) turbulent boundary layer (TBL) developing on the suction side of a NACA4412 wing section are assessed in the present work. To this end, we conducted a well-resolved large-eddy simulation of the turbulent flow around the NACA4412 airfoil at a Reynolds number based on freestream velocity and chord length of Rec = 1;000;000, with 5° angle of attack. The results of this simulation are used, together with the direct numerical simulation by Hosseini et al. (Int. J. Heat Fluid Flow 61, 2016) of the same wing section at Rec = 400;000, to characterize the effect of Reynolds number on APG TBLs subjected to the same pressure-gradient distribution (defined by the Caluser pressure-gradient parameter β). Our results indicate that the increase in inner-scaled edge velocity U+e, and the decrease in shape factor H, is lower in the APG on the wing than in zero-pressure-gradient (ZPG) TBLs over the same Reynolds-number range. This indicates that the lower-Re boundary layer is more sensitive to the effect of the APG, a conclusion that is supported by the larger values in the outer region of the tangential velocity fluctuation profile in the Rec = 400;000 wing. Future extensions of the present work will be aimed at studying the differences in the outer-region energizing mechanisms due to APGs and increasing Reynolds number.
CRIS-Team Scopus Importer:2023-03-21

High-Order Numerical Simulations of Wind Turbine Wakes - Kleusberg, E.; Mikkelsen, R. F.; Schlatter, Philipp; Ivanell, Stefan; Henningson, D. S. (Journal of Physics: Conference Series, 2017)
Previous attempts to describe the structure of wind turbine wakes and their mutual interaction were mostly limited to large-eddy and Reynolds-averaged Navier-Stokes simulations using finite-volume solvers. We employ the higher-order spectral-element code Nek5000 to study the influence of numerical aspects on the prediction of the wind turbine wake structure and the wake interaction between two turbines. The spectral-element method enables an accurate representation of the vortical structures, with lower numerical dissipation than the more commonly used finite-volume codes. The wind-turbine blades are modeled as body forces using the actuator-line method (ACL) in the incompressible Navier-Stokes equations. Both tower and nacelle are represented with appropriate body forces. An inflow boundary condition is used which emulates homogeneous isotropic turbulence of wind-tunnel flows. We validate the implementation with results from experimental campaigns undertaken at the Norwegian University of Science and Technology (NTNU Blind Tests), investigate parametric influences and compare computational aspects with existing numerical simulations. In general the results show good agreement between the experiments and the numerical simulations both for a single-turbine setup as well as a two-turbine setup where the turbines are offset in the spanwise direction. A shift in the wake center caused by the tower wake is detected similar to experiments. The additional velocity deficit caused by the tower agrees well with the experimental data. The wake is captured well by Nek5000 in comparison with experiments both for the single wind turbine and in the two-turbine setup. The blade loading however shows large discrepancies for the high-turbulence, two-turbine case. While the experiments predicted higher thrust for the downstream turbine than for the upstream turbine, the opposite case was observed in Nek5000.
CRIS-Team Scopus Importer:2023-03-21

High-performance spectral element methods on field-programmable gate arrays : iimplementation, evaluation, and future projection - Karp, Martin; Podobas, Artur; Jansson, Niclas; Kenter, Tobias; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (Proceedings - 2021 IEEE 35th International Parallel and Distributed Processing Symposium, IPDPS 2021, 2021)
Improvements in computer systems have historically relied on two well-known observations: Moore's law and Dennard's scaling. Today, both these observations are ending, forcing computer users, researchers, and practitioners to abandon the general-purpose architectures' comforts in favor of emerging post-Moore systems. Among the most salient of these post-Moore systems is the Field-Programmable Gate Array (FPGA), which strikes a convenient balance between complexity and performance. In this paper, we study modern FPGAs' applicability in accelerating the Spectral Element Method (SEM) core to many computational fluid dynamics (CFD) applications. We design a custom SEM hardware accelerator operating in double-precision that we empirically evaluate on the latest Stratix 10 GX-series FPGAs and position its performance (and power-efficiency) against state-of-the-art systems such as ARM ThunderX2, NVIDIA Pascal/Volta/Ampere Teslaseries cards, and general-purpose manycore CPUs. Finally, we develop a performance model for our SEM-accelerator, which we use to project future FPGAs' performance and role to accelerate CFD applications, ultimately answering the question: what characteristics would a perfect FPGA for CFD applications have?
CRIS-Team Scopus Importer:2023-03-21
Keywords: ARM; CFD; FPGA; HLS; Intel; Nek5000; NVIDIA

History effects and near equilibrium in adverse-pressure-gradient turbulent boundary layers - Bobke, A.; Vinuesa, Ricardo; Orlu, R.; Schlatter, Philipp (Journal of Fluid Mechanics, 2017)
Turbulent boundary layers under adverse pressure gradients are studied using well-resolved large-eddy simulations (LES) with the goal of assessing the influence of the streamwise pressure-gradient development. Near-equilibrium boundary layers were characterized through the Clauser pressure-gradient parameter β. In order to fulfil the near-equilibrium conditions, the free stream velocity was prescribed such that it followed a power-law distribution. The turbulence statistics pertaining to cases with a constant value of β (extending up to approximately 40 boundary-layer thicknesses) were compared with cases with non-constant β distributions at matched values of β and friction Reynolds number Reδ∗. An additional case at matched Reynolds number based on displacement thickness Reδ∗ was also considered. It was noticed that non-constant β cases appear to approach the conditions of equivalent constant β cases after long streamwise distances (approximately 7 boundary-layer thicknesses). The relevance of the constant β cases lies in the fact that they define a 'canonical' state of the boundary layer, uniquely characterized by β and Re. The investigations on the flat plate were extended to the flow around a wing section overlapping in terms of β and Re. Comparisons with the flat-plate cases at matched values of β and Re revealed that the different development history of the turbulent boundary layer on the wing section leads to a less pronounced wake in the mean velocity as well as a weaker second peak in the Reynolds stresses. This is due to the weaker accumulated effect of the β history. Furthermore, a scaling law suggested by Kitsios et al. (Intl J. Heat Fluid Flow, vol. 61, 2016, pp. 129-136), proposing the edge velocity and the displacement thickness as scaling parameters, was tested on two constant-pressure-gradient parameter cases. The mean velocity and Reynolds-stress profiles were found to be dependent on the downstream development. The present work is the first step towards assessing history effects in adverse-pressure-gradient turbulent boundary layers and highlights the fact that the values of the Clauser pressure-gradient parameter and the Reynolds number are not sufficient to characterize the state of the boundary layer.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulent boundary layers; turbulent flows

Identifying an Artificial Turbulent Spot in the Boundary Layer - Rehill, Brendan; Walsh, E. J.; Brandt, Luca; Schlatter, Philipp; Zaki, Tamer A. (Springer Proceedings in Physics, 2012)
An artificial turbulent spot in a boundary layer with zero freestream turbulence and zero pressure gradient is studied through direct numerical simulation. The spot, generated by a vortex pair disturbance, is identified from the surrounding non-turbulent fluid using six different methods of identification. These techniques involved setting thresholds for: instantaneous wall normal velocity, spanwise velocity, turbulent dissipation, λ2-criterion, Q-criterion and the Finite Time Lyapunov Exponent. A sensitivty analysis was performed based on the sensitivity of the maximum spot dimensions to the change in threshold level from it’s original value. The maximum height, width, length and volume of the spot was recorded for changes in threshold level. Based on this analysis the Q-criterion was found to be the most suitable for identifying a turbulent spot in a flow with zero freestream turbulence.
CRIS-Team Scopus Importer:2023-03-21

Identifying Turbulent Spots in Transitional Boundary Layers - Rehill, Brendan; Walsh, Ed J.; Brandt, Luca; Schlatter, Philipp; Zaki, Tamer A.; Mceligot, Donald M. (Journal of Turbomachinery-Transactions of the Asme, 2012)
An artificial turbulent spot is simulated in a zero free-stream turbulence base flow and a base flow with organized streaks. Six identification methods are used in order to isolate the turbulent spot from the surrounding nonturbulent fluid. These are (i) instantaneous wall-normal velocity v, (ii) instantaneous spanwise velocity w, (iii) instantaneous turbulent dissipation, (iv) λ2 criterion, (v) Q criterion, and (vi) gradient of the finite time Lyapunov exponent. All methods are effective in isolating the turbulent spot from the streaks. The robustness of each technique is determined from the sensitivity of the maximum spot dimensions to changes in threshold level. The Q criterion shows the least sensitivity for the zero free-stream turbulence case and the instantaneous turbulent dissipation technique is least sensitive in the organized streaks case. For both cases the v technique was the most sensitive to changes in threshold level. © 2013 American Society of Mechanical Engineers.
CRIS-Team Scopus Importer:2023-03-21

Identifying turbulent spots in transitional boundary layers - Rehill, Brendan; Walsh, Ed J.; Schlatter, Philipp; Brandt, Luca; Zaki, Tamer A.; McEligot, Donald M. (Proceedings of the ASME Turbo Expo, 2011)
An artificial turbulent spot is simulated in a zero free-stream turbulence base flow and a base flow with organised streaks. Six identification methods are used in order to isolate the turbulent spot from the surrounding non-turbulent fluid. These are (i) instantaneous wall-normal velocity, v′, (ii) instantaneous spanwise velocity, w′, (iii) instantaneous turbulent dissipation, (iv) λ2 - criterion, (v) Q - criterion and (vi) gradient of the Finite Time Lyapunov Exponent. All methods are effective in isolating the turbulent spot from the streaks. The robustness of each technique is determined from the sensitivity of the maximum spot dimensions to changes in threshold level. The Q-criterion shows the least sensitivity for the zero free-stream turbulence case and the instantaneous turbulent dissipation technique is least sensitive in the organised streaks case. For both cases the v′ technique was the most sensitive to changes in threshold level. Copyright © 2011 by ASME.
CRIS-Team Scopus Importer:2023-03-21

Identifying well-behaved turbulent boundary layers - Sanmiguel Vila, Carlos; Vinuesa, Ricardo; Discetti, Stefano; Ianiro, Andrea; Schlatter, Philipp; Orlu, Ramis (Springer Proceedings in Physics, 2017)
This paper presents a study focused on the development of zero-pressure-gradient turbulent boundary layers (ZPG TBL) towards well-behaved conditions in the low Reynolds-number range. A new method to assess the length required for the ZPG TBL to exhibit well-behaved conditions is proposed. The proposed method is based on the diagnostic-plot concept (Alfredsson et al., Phys. Fluids, 23:041702, 2011), which only requires mean and turbulence intensity measurements in the outer region of the boundary layer. In contrast to the existing methods which rely on empirical skin-friction curves, shape-factor or wake-parameter, the quantities required by this method are generally much easier to measure. To test the method, the evolution of six different tripping configurations, including weak, late and strong overtripping, are studied in a wind-tunnel experiment to assess the convergence of ZPG TBLs towards well-behaved conditions in the momentum-thickness based Reynolds-number range 500 < Reθ < 4000.
CRIS-Team Scopus Importer:2023-03-21

Impact of corner geometry on the secondary flow in turbulent ducts - Vidal, Alvaro; Vinuesa, Ricardo; Schlatter, Philipp; Nagib, Hassan M. (10th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2017, 2017)
In the present study we perform direct numerical simulations (DNSs) of fully-developed turbulent square ducts with round corners at Reτ,c ∼ 180 and 360, and rectangular ducts of width-toheight ratios of 3 and 5 with rounded side walls at Reτ,c ∼ 180. The friction Reynolds number Reτ,c is based on the centerplane friction velocity and the half-height of the duct. The results are compared with the corresponding duct cases with 90° corners. We focus on the influence of the rounding on the mean cross-stream secondary flow and on further characterizing the mechanisms that produce it. Unexpectedly, the rounded ducts exhibit higher cross-flow rates and their secondary vortices relocate near the transition point between the straight and curved walls. This behavior is associated to the statistically preferential arrangement of sweeping events entering through the curved wall, which trigger an ejection on the adjacent straight wall. We have yet to find effective modifications to the corners or transverse ends of a rectangular duct that would render better rigorous modeling of two-dimensional channel flows.
CRIS-Team Scopus Importer:2023-03-21

Impact simulation and optimisation of elastic fuel tanks reinforced with exoskeleton for aerospace applications - Prus, C.; Vinuesa, Ricardo; Schlatter, Philipp; Tembras, E.; Mestres, E.; Ramirez, J. P. Berro (International Journal of Crashworthiness, 2017)
The main subject of the study is the impact simulation of an elastic fuel tank reinforced with a polymer exoskeleton. Thanks to its lightweight and failure resistance, this type of design shows potential to be used in aerospace applications. The simulation emulates a drop test from the height of 20 m on a rigid surface, in accordance with Military Handbook testing guidelines for fuel tanks. The focus is on providing an example of modelling and solving this type of problems. The computational methods are tested on a generic model of a rectangular prismatic tank with rounded edges. The walls of the tank are made of orthotropic fabric reinforced polymer. The simulation is performed for a 70% and a 100% water-filled tank. All calculations are performed using the Altair HyperWorks 13.0 software suite, in particular, the nonlinear RADIOSS solver and OptiStruct Solver and Optimiser. The fluid inside the tank is modelled using the SPH (Smoothed Particle Hydrodynamics) approach. The model serves as a basis for establishing a design optimisation procedure, aiming at reduction of mass of the tank components while ensuring structural integrity. The main insights of the current study are the successful modelling of the liquid and the air inside the tank by means of smoothed-particle hydrodynamics elements, and the structural optimisation methodology of a composite fuel tank.
CRIS-Team Scopus Importer:2023-03-21
Keywords: fluid–structure interaction; fuel tank; Impact simulation; SPH; structural optimisation

Inflow length and tripping effects in turbulent boundary layers - Orlu, Ramis; Schlatter, Philipp (Journal of Physics: Conference Series, 2011)
A recent assessment of available direct numerical simulation (DNS) data from turbulent boundary layer flows [Schlatter & Örlü, J. Fluid Mech. 659, 116 (2010)] showed surprisingly large differences not only in the skin friction coefficient or shape factor, but also in their predictions of mean and fluctuation profiles far into the sublayer. For the present paper the DNS of a zero pressure-gradient turbulent boundary layer flow by Schlatter et al. [Phys. Fluids 21, 051702 (2009)] serving as the baseline simulation, was re-simulated, however with physically different inflow conditions and tripping effects. The downstream evolution of integral and global quantities as well as mean and fluctuation profiles are presented and results indicate that different inflow conditions and tripping effects explain most of the differences observed when comparing available DNS. It is also found, that if transition is initiated at a low enough Reynolds number (based on the momentum-loss thickness) Re θ < 300, all data agree well for both inner and outer layer for Reθ > 2000; a result that gives a lower limit for meaningful comparisons between numerical and/or wind tunnel experiments.
CRIS-Team Scopus Importer:2023-03-21

Influence of a Large-Eddy-Breakup-Device on the Turbulent Interface of Boundary Layers - Chin, Cheng; Orlu, Ramis; Schlatter, Philipp; Monty, Jason; Hutchins, Nicholas (Flow Turbulence and Combustion, 2017)
The effects of implementing a large-eddy break-up device (LEBU) in a turbulent boundary layer on the interaction with the boundary layer is investigated with particular emphasis on the turbulent/non-turbulent interface (TNTI). The simulation data is taken from a recent well-resolved large eddy simulation (Chin et al. Flow Turb. Combust. 98, 445–460 2017), where the LEBU was implemented at a wall-normal distance of 0.8 δ (local boundary layer thickness) from the wall. A comparison of the TNTI statistics is performed between a zero-pressure-gradient boundary layer with and without the LEBU. The LEBU is found to delay the growth of the turbulent boundary layer and also attenuates the fluctuations of the TNTI. The LEBU appears to alter the structure size at the interface, resulting in a narrower and shorter dominant structure (in an average sense). Further analysis beneath the TNTI using two-point correlations shows that the LEBU affects the turbulent structures in excess of 100 δ downstream of the LEBU.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Large eddy simulation; Large-eddy-break-up device; Turbulent/non-turbulent interface; Wall-bounded turbulence

Influence of corner geometry on the secondary flow in turbulent square ducts - Vidal, A.; Vinuesa, Ricardo; Schlatter, Philipp; Nagib, H. M. (International Journal of Heat and Fluid Flow, 2017)
Direct numerical simulations of fully-developed turbulent flow through a straight square duct with increasing corner rounding radius r were performed to study the influence of corner geometry on the secondary flow. Unexpectedly, the increased rounding of the corners from r=0 to 0.75 does not lead to a monotonic trend towards the pipe case of r=1. Instead, the secondary vortices relocate close to the region of wall-curvature change. This behavior is connected to the inhomogeneous interaction between near-wall bursting events, which are further characterized in this work with the definition of their local preferential direction. We compare our results with those obtained for the flow through a square duct (which corresponds to r=0) and through a round pipe (r=1), focusing on the influence of r on the wall-shear stress distribution and the turbulence statistics along the centerplane and the corner bisector. The former shows that high-speed streaks are preferentially located near the transition between straight and curved surfaces. The Reynolds numbers based on the centerplane friction velocity and duct half-height are Reτ, c ≃ 180 and 350 for the cases under study.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Corner geometry; Direct numerical simulation; Secondary motions; Turbulent duct flow; Wall-bounded turbulence

In-Situ Binary Segmentation of 3D time-dependent Flows into Laminar and Turbulent Regions - Liu, Jiahui; Edwards, Tobias; Durovic, Kristina; Schlatter, Philipp; Weinkauf, Tino (ACM International Conference Proceeding Series, 2024)
The transition from laminar to turbulent flow is a long-standing research subject in the field of fluid mechanics. A basic necessity for such studies is a distinction between laminar and turbulent flow. In particular, a binary segmentation is desired where laminar and turbulent regions behave consistently over time. Previous works in this regard yield inconsistent results, or are restricted to 2D manifolds thereby neglecting the three-dimensional nature of the problem. In this paper, we present a novel use of feature-based methods to segmenting a 3D time-dependent flow into regions of laminar and turbulent behavior. It is based on the extraction of local extrema from a scalar field such as spanwise velocity. It turns out that the existence of many extrema in a region is a good indicator for turbulence. We derive a density function from the extracted extrema using a Kernel Density Estimate (KDE) and threshold it to achieve a binary segmentation into laminar and turbulent regions. We use an in-situ processing approach for data analysis during the simulation run. The two core components of our method exhibit drastically different performance characteristics: the extraction of extrema is embarrassingly parallel, while the KDE is more time-consuming. Hence, we decouple our algorithmic components to achieve a better overall system performance. Our method shows consistent results and enables the domain scientists to study the three-dimensional aspects of the laminar-turbulent transition that were difficult to assess before.
CRIS-Team Scopus Importer:2024-09-06
Keywords: In-situ processing; Kernel density estimate; Laminar-turbulent segmentation; Parallel computing; Visualization

In-Situ Techniques on GPU-Accelerated Data-Intensive Applications - Ju, Yi; Li, Mingshuai; Perez, Adalberto; Bellentani, Laura; Jansson, Niclas; Markidis, Stefano; Schlatter, Philipp; Laure, Erwin (Proceedings 2023 IEEE 19th International Conference on e-Science, e-Science 2023, 2023)
The computational power of High-Performance Computing (HPC) systems is constantly increasing, however, their input/output (IO) performance grows relatively slowly, and their storage capacity is also limited. This unbalance presents significant challenges for applications such as Molecular Dynamics (MD) and Computational Fluid Dynamics (CFD), which generate massive amounts of data for further visualization or analysis. At the same time, checkpointing is crucial for long runs on HPC clusters, due to limited walltimes and/or failures of system components, and typically requires the storage of large amount of data. Thus, restricted IO performance and storage capacity can lead to bottlenecks for the performance of full application workflows (as compared to computational kernels without IO). In-situ techniques, where data is further processed while still in memory rather to write it out over the I/O subsystem, can help to tackle these problems. In contrast to traditional post-processing methods, in-situ techniques can reduce or avoid the need to write or read data via the IO subsystem. They offer a promising approach for applications aiming to leverage the full power of large scale HPC systems. In-situ techniques can also be applied to hybrid computational nodes on HPC systems consisting of graphics processing units (GPUs) and central processing units (CPUs). On one node, the GPUs would have significant performance advantages over the CPUs. Therefore, current approaches for GPU-accelerated applications often focus on maximizing GPU usage, leaving CPUs underutilized. In-situ tasks using CPUs to perform data analysis or preprocess data concurrently to the running simulation, offer a possibility to improve this underutilization.
CRIS-Team Scopus Importer:2023-10-27
Keywords: CPU; GPU; HPC; in-situ

In situ visualization of large-scale turbulence simulations in Nek5000 with ParaView Catalyst - Atzori, Marco; Kopp, Wiebke; Chien, Steven W. D.; Massaro, Daniele; Mallor, Fermin; Peplinski, Adam; Rezaei, Mohamad; Jansson, Niclas; Markidis, Stefano; Vinuesa, Ricardo; Laure, Erwin; Schlatter, Philipp; et al. (Journal of Supercomputing, 2022)
In situ visualization on high-performance computing systems allows us to analyze simulation results that would otherwise be impossible, given the size of the simulation data sets and offline post-processing execution time. We develop an in situ adaptor for Paraview Catalyst and Nek5000, a massively parallel Fortran and C code for computational fluid dynamics. We perform a strong scalability test up to 2048 cores on KTH’s Beskow Cray XC40 supercomputer and assess in situ visualization’s impact on the Nek5000 performance. In our study case, a high-fidelity simulation of turbulent flow, we observe that in situ operations significantly limit the strong scalability of the code, reducing the relative parallel efficiency to only ≈ 21 % on 2048 cores (the relative efficiency of Nek5000 without in situ operations is ≈ 99 %). Through profiling with Arm MAP, we identified a bottleneck in the image composition step (that uses the Radix-kr algorithm) where a majority of the time is spent on MPI communication. We also identified an imbalance of in situ processing time between rank 0 and all other ranks. In our case, better scaling and load-balancing in the parallel image composition would considerably improve the performance of Nek5000 with in situ capabilities. In general, the result of this study highlights the technical challenges posed by the integration of high-performance simulation codes and data-analysis libraries and their practical use in complex cases, even when efficient algorithms already exist for a certain application scenario.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Computational fluid dynamics; High-performance computing; In situ visualization

Intense reynolds-stress events in turbulent ducts - Atzori, Marco; Vinuesa, Ricardo; Lozano-Duran, Adrian; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2021)
The aim of the present work is to investigate the role of intense Reynolds shear-stress events in the generation of the secondary flow in turbulent ducts. We consider the connected regions of flow where the product of the instantaneous fluctuations of two velocity components is higher than a threshold based on the long-time turbulence statistics, in the spirit of the three-dimensional quadrant analysis proposed by Lozano-Durán et al. (J. Fluid Mech., vol. 694, 2012, pp. 100–130). We examine both the geometrical properties of these structures and their contribution to the mean in-plane velocity components, and we perfom a comparison with turbulent channel flow at similar Reynolds number. The contribution to a certain mean quantity is defined as the ensemble average over the detected coherent structures, weighted with their own occupied volume fraction. In the core region of the duct, the contribution of intense events to the wall-normal component of the mean velocity is in very good agreement with that in the channel, despite the presence of the secondary flow in the former. Additionally, the shapes of the three-dimensional objects do not differ significantly in both flows. In the corner region of the duct, the proximity of the walls affects both the geometrical properties of the coherent structures and the contribution to the mean component of the vertical velocity. However, such contribution is less relevant than that of the complementary portion of the flow not included in such objects. Our results show that strong Reynolds shear-stress events are affected by the presence of a corner but, despite the important role of these structures in the dynamics of wall-bounded turbulent flows, their contribution to the secondary flow is relatively low, both in the core and in the corner.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Coherent structures; Direct numerical simulation; Secondary flows; Turbulence

Interaction of noise disturbances and streamwise streaks - Schlatter, Philipp; Deusebio, Enrico; Brandt, Luca; De Lange, Rick (IUTAM Bookseries, 2010)
The evolution of disturbances in boundary layers modified through spanwise periodic, steady streamwise streaks is studied via numerical simulations. The disturbances are introduced via random two- and three-dimensional noise of various amplitudes close to the inlet (Rex ≈ 60000). The aim of the present work is to determine the impact of the interaction of streaks and noise on the arising flow structures and, eventually, on the location and details of the breakdown to turbulence. It is shown that large-scale 2D noise can be controlled via streaks, whereas the more general 3D noise configuration is prone to premature transition due to increased instability of the introduced streaks. It is interesting to note that the latter transition scenario closely resembles the flow structures found in bypass transition. Transition in true bypass transtion forced by ambient free-stream turbulence is also promoted by the addition of streamwise streaks in the laminar part of the boundary layer. © 2010 Springer Science+Business Media B.V.
CRIS-Team Scopus Importer:2023-03-21

Interscale transport mechanisms in turbulent boundary layers - Chan, Chi Ip; Schlatter, Philipp; Chin, R. C. (Journal of Fluid Mechanics, 2021)
The flow physics of turbulent boundary layers is investigated using spectral analysis based on the spanwise scale decomposition of the Reynolds stress transport equation, with data obtained from a direct numerical simulation of the turbulent boundary layer at. Here, we extend the framework of Kawata & Alfredsson (Phys. Rev. Lett., vol. 120, 2018, p. 244501) for plane Couette flows to zero-pressure-gradient boundary layers. The equation contains three fundamental fluxes, which govern the Reynolds stress transport: (i) a scale flux of the interaction between small-scale and large-scale structures, and two spatial fluxes dominated by (ii) pressure and (iii) turbulent transport along the wall-normal direction. The scale flux reveals evidence of the inverse turbulent kinetic energy transfer, from small to large scales, occurring at the near-wall region, whereby for the scale flux of the Reynolds shear stress transport, the inverse transfer extends across the entire boundary layer. The wall-normal fluxes reveal the interactions occurring between scales at the buffer and logarithmic regions. In addition, there is interaction between the large-scale structures and the free stream flow occurring at the edge of the boundary layer, which was not observed in the Couette flow. Flow structures associated with inverse interscale transport of Reynolds shear stress are identified by applying conditional analysis to the spectrally decomposed velocity fields. While the inverse transport is interpreted as the net energy transfer from small-scale ejections and sweeps to the large-scale counterparts, conditional time estimates of the direct and inverse interscale transport reveal that both processes play a substantial role across a broad range of scales.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Navier-Stokes equations; turbulent boundary layers

Investigation of blowing and suction for turbulent flow control on airfoils - Fahland, Georg; Stroh, Alexander; Frohnapfel, Bettina; Atzori, Marco; Vinuesa, Ricardo; Schlatter, Philipp; Gatti, Davide (AIAA Journal, 2021)
An extensive parametric study of turbulent boundary-layer control on airfoils via uniform blowing or suction is presented. The control is applied on either the suction or pressure side of several four-digit NACA-series airfoils. The considered parameter variations include angle of attack, Reynolds number, control intensity, airfoil camber, and airfoil thickness. Two comprehensive metrics, designed to account for the additional energy required by the control, are introduced to evaluate the net aerodynamic performance enhancements. The study confirms previous findings for suction-side boundary-layer control and demonstrates the interesting potential of blowing on the pressure side under various conditions, which achieves a maximum total net drag saving of 14% within the considered parameter space. The broad parameter space covered by the presented Reynolds-average Navier–Stokes simulations allows for more general conclusions than previous studies and can thus provide guidelines for the design of future detailed experimental or numerical studies on similar boundary-layer control schemes.
CRIS-Team Scopus Importer:2023-03-21

Investigation of the Global Instability of the Rotating-disk Boundary Layer - Appelquist, E.; Schlatter, Philipp; Alfredsson, P. H.; Lingwood, R. J. (Procedia IUTAM, 2015)
The development of the flow over a rotating disk is investigated by direct numerical simulations using both the linearized and fully nonlinear incompressible Navier-Stokes equations. These simulations allow investigation of the transition to turbulence of the realistic spatially-developing boundary layer. The current research aims to elucidate further the global linear stability properties of the flow, and relate these to local analysis and discussions in literature. An investigation of the nonlinear upstream (inward) influence is conducted by simulating a small azimuthal section of the disk (1/68). The simulations are initially perturbed by an impulse disturbance where, after the initial transient behaviour, both the linear and nonlinear simulations show a temporally growing upstream mode. This upstream global mode originates in the linear case close to the end of the domain, excited by an absolute instability at this downstream position. In the nonlinear case, it instead originates where the linear region ends and nonlinear harmonics enter the flow field, also where an absolute instability can be found. This upstream global mode can be shown to match a theoretical mode from local linear theory involved in the absolute instability at either the end of the domain (linear case) or where nonlinear harmonics enter the field (nonlinear case). The linear simulation grows continuously in time whereas the nonlinear simulation saturates and the transition to turbulence moves slowly upstream towards smaller radial positions asymptotically approaching a global upstream mode with zero temporal growth rate, which is estimated at a nondimensional radius of 582.
CRIS-Team Scopus Importer:2023-03-21
Keywords: boundary layer flow; direct numerical simulation; rotating disk

Investigations of stability and transition of a jet in crossflow using DNS - Peplinski, A.; Schlatter, Philipp; Henningson, D. S. (Kluwer Academic Publishers, 2015)
We study the stability of a jet in crossflow at low values of the jet-tocrossflow velocity ratio R focusing on direct numerical simulations (DNS) and the global linear stability analysis adopting a time-stepper method. For the simplified setup neglecting a meshed pipe in the simulations, we compare results of the fullyspectral code SIMSON with the spectral-element code Nek5000. We find the calculated critical value R for the first bifurcation to be dependent on the numerical method used. This result is related to a large sensitivity of the eigenvalues and to the large spatial growth of the corresponding eigenmodes, making the use of periodic domains, even with the fringe method, difficult. However, we observe a similar sensitivity to reflection from the outflow boundary in the inflow/outflow configuration as well.We apply in our studies both modal and non-modal analyses investigating transient effects and their asymptotic fate, and we find transient wavepacket that develop almost identically in the stable and unstable cases. Finally, we compare these results with the simulation including the pipe in the computational domain finding the latter one to be much more unstable.
CRIS-Team Scopus Importer:2023-03-21

Investigations of stability and transition of a jet in crossflow using DNS - Peplinski, A.; Schlatter, Philipp; Henningson, D. S. (ERCOFTAC Series, 2015)
CRIS-Team Scopus Importer:2023-03-21

Large-eddy simulation of turbulent flow in a plane asymmetric diffuser by the spectral-element method - Ohlsson, Johan; Schlatter, Philipp; Fischer, Paul F.; Henningson, Dan S. (ERCOFTAC Series, 2010)
LES and no-model LES (coarse-grid DNS) have been performed of turbulent flow in a plane asymmetric diffuser by the Spectral-Element Method (SEM). Mean profile and turbulent stresses compare well to LES results from Herbst et al., however the SEM generally predicts a later (i.e. further downstream) separation. It can be concluded that the use of a high-order method is advantageous for flows featuring pressure-induced separation.
CRIS-Team Scopus Importer:2023-03-21

Large-eddy simulations of adverse pressure gradient turbulent boundary layers - Bobke, Alexandra; Vinuesa, Ricardo; Orlu, Ramis; Schlatter, Philipp (Journal of Physics: Conference Series, 2016)
Adverse pressure-gradient (APG) turbulent boundary layers (TBL) are studied by performing well-resolved large-eddy simulations. The pressure gradient is imposed by defining the free-stream velocity distribution with the description of a power law. Different inflow conditions, box sizes and upper boundary conditions are tested in order to determine the final set-up. The statistics of turbulent boundary layers with two different power-law coefficients and thus magnitudes of adverse pressure gradients are then compared to zero pressure-gradient (ZPG) data. The effect of the APG on TBLs is manifested in the mean flow through a much more prominent wake region and in the Reynolds stresses through the existence of an outer peak. The pre-multiplied energy budgets show that more energy is transported from the near-wall region to farther away from the wall.
CRIS-Team Scopus Importer:2023-03-21

Large scale accumulation patterns of inertial particles in wall-bounded turbulent flow - Sardina, Gaetano; Picano, Francesco; Schlatter, Philipp; Brandt, Luca; Casciola, Carlo Massimo (Flow Turbulence and Combustion, 2011)
Turbulent internal flow in channel and pipe geometry with a diluted second phase of inertial particles is studied numerically. Direct numerical simulations (DNS) are performed at moderate Reynolds number (Re τ ∈≈∈200) in pipe and two channels-a smaller one similar in size to previous studies and a 3∈×∈3-times larger one-and Eulerian statistics pertaining to the particle concentration are evaluated. This simulation box constitutes the largest domain used for particle-laden flows so far. The resulting two-point correlations of the particle concentration show that in the smaller channel the particles organize in thin, streamwise elongated patterns which are very regular and long. The spanwise spacing of these structures is 120 and 160 plus units for the channel and pipe, respectively. Only in the larger box, the streamwise extent is long enough for the particle streaks to decorrelate, thus allowing the particles to move more freely. The influence of the box size on the characteristics of the turbophoresis is clearly shown; a 10% increase of the near-wall correlation is observed for particles with Stokes number St ∈+∈∈=∈50. It is thus shown that the box dimensions are an important factor in correctly assessing the motion of inertial particles, and their relation to the underlying velocity field. In addition the binning size effects on the correlation statistics of particle concentration are exploited. In particular the spanwise correlation peak values appear very sensitive to the adopted binning size, although the position of these peaks is found almost independent. Hence to allow a significant comparison between data of different configurations it is necessary to adopt the same binning spacing in inner variable. © 2011 Springer Science+Business Media B.V.
CRIS-Team Scopus Importer:2023-03-21
Keywords: DNS; Inertial particles; Particle laden flows; Turbophoresis; Turbulence; Wall bounded flows

Large-scale and small-scale contribution to the skin friction reduction in a modified turbulent boundary layer by a large-eddy break-up device - Chan, Chi Ip; Orlu, Ramis; Schlatter, Philipp; Chin, R. C. (Physical Review Fluids, 2022)
The role of streamwise length scales (λx) in turbulent skin friction generation is investigated using a direct numerical simulation data set of an incompressible zero pressure gradient turbulent boundary layer and the spectral analysis based on the Fukagata-Iwamoto-Kasagi (FIK) identity by Fukagata et al. [K. Fukagata et al., Phys. Fluids 14, L73 (2002)1070-663110.1063/1.1516779]. The total skin friction generation associated with motions scaled with local boundary layer thickness δ of λx<3δ and λx>3δ is assessed. The FIK-identity-based spectral analysis is further extended to include the quadrant analysis of Reynolds shear stress. This allows one to relate the turbulent skin friction generation to the quadrant events of Reynolds shear stress, which plays a central role in the momentum transport in turbulent wall-bounded flows. The small-scale ejection and sweep events (λx<3δ) contribute to a significant portion of turbulent skin friction. However, it is found that the large-scale ejection and sweep events with streamwise length scales at λx>3δ are equally important. The turbulent skin friction reduction associated with the modification of large- and small-scale quadrant events is studied, using well-resolved simulation data sets of a large-eddy break-up (LEBU) device in a turbulent boundary layer. The results reveal that LEBUs modify both the large- and small-scale ejection and sweep events, yielding a substantial turbulent skin friction reduction.
CRIS-Team Scopus Importer:2023-03-21

Large-Scale direct numerical simulations of turbulence using GPUs and modern Fortran - Karp, Martin; Massaro, Daniele; Jansson, Niclas; Hart, Alistair; Wahlgren, Jacob; Schlatter, Philipp; Markidis, Stefano (International Journal of High Performance Computing Applications, 2023)
We present our approach to making direct numerical simulations of turbulence with applications in sustainable shipping. We use modern Fortran and the spectral element method to leverage and scale on supercomputers powered by the Nvidia A100 and the recent AMD Instinct MI250X GPUs, while still providing support for user software developed in Fortran. We demonstrate the efficiency of our approach by performing the world’s first direct numerical simulation of the flow around a Flettner rotor at Re = 30,000 and its interaction with a turbulent boundary layer. We present a performance comparison between the AMD Instinct MI250X and Nvidia A100 GPUs for scalable computational fluid dynamics. Our results show that one MI250X offers performance on par with two A100 GPUs and has a similar power efficiency based on readings from on-chip energy sensors.
CRIS-Team Scopus Importer:2023-03-21
Keywords: computational fluid dynamics; direct numerical simulation; Fortran; GPU; high performance computing; spectral element method

Large-scale energy in turbulent boundary layers: Reynolds-number and pressure-gradient effects - Sanmiguel Vila, Carlos; Vinuesa, Ricardo; Discetti, Stefano; Ianiro, Andrea; Schlatter, Philipp; Orlu, Ramis (Springer Proceedings in Physics, 2019)
Adverse-pressure-gradient (APG) turbulent boundary layers (TBLs) are studied using hot-wire measurements which cover a Clauser pressure-gradient-parameter range up to β ≈ 2.4. Constant and non-constant β distributions with the same upstream history are studied. The pre-multiplied power-spectral density is employed to study the differences in the large-scale energy content throughout the boundary layer. Two different large-scale phenomena are identified, the first one due to the pressure gradient and the second one due to the Reynolds number; the latter is also present in high-Re ZPG TBLs. A decomposition of the streamwise velocity fluctuations using a temporal filter shows that the small-scale velocity fluctuations do not scale in APG TBL flows since the effect of the large-scale features extends up to the near-wall region.
CRIS-Team Scopus Importer:2023-03-21

Large-scale friction control in turbulent wall flow - Schlatter, Philipp; Örlü, Ramis; Chin, Cheng; Hutchins, Nicholas; Monty, Jason (9th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2015, 2015)
The present study reconsiders the control scheme proposed by Schoppa & Hussain [Phys Fluids 10:1049-1051 (1998)], using new sets of numerical simulations in a turbulent channel at a friction Reynolds number of 180. In particular, it is aimed at better characterising the physics of the control as well as investigate the optimal parameters. Results indicate that a clear maximum efficiency in drag reduction is reached for the case with a viscous-scaled spanwise wavelength of the vortices of 1200, which yields a drag reduction of 18%, contrary to the smaller wavelength of 400 suggested as the most efficient vortex in Schoppa & Hussain.
CRIS-Team Scopus Importer:2023-03-21

Large-scale simulations of turbulence: HPC and numerical experiments - Schlatter, Philipp; Malm, Johan; Brethouwer, Geert; Johansson, Arne V.; Henningson, Dan S. (Proceedings - 2011 7th IEEE International Conference on eScience, eScience 2011, 2011)
In this paper, we describe some of the methods used at KTH Mechanics in the field of turbulence simulations. High performance computing (HPC) resources, including the dedicated system "Ekman" with 10000 cores at KTH, are employed to perform some of the largest turbulence simulations with up to 10 billion grid points. The results are used to assess the fidelity of such types of simulations by comparing in detail to wind tunnel experiments, excellent agreement is obtained in general. Simulations can thus be considered numerical experiments, and are subject to the same scrutiny as "real" experimental data. Validated simulation data is extremely valuable as it may provide unprecedented insight into the turbulence dynamics. However, given the large size of the computations, the massively parallel simulation codes, post processing tools and storage solutions have to be specifically adapted, making turbulence simulations an interdisplinary area of e-Science. © 2011 IEEE.
CRIS-Team Scopus Importer:2023-03-21
Keywords: boundary layers; direct numerical simulation; turbulence; turbulent separation

Linear disturbances in the rotating-disk flow: A comparison between results from simulations, experiments and theory - Appelquist, E.; Imayama, Shintaro; Alfredsson, P. Henrik; Schlatter, Philipp; Lingwood, R. J. (European Journal of Mechanics B-Fluids, 2016)
The incompressible Navier-Stokes equations have an exact similarity solution for the flow over an infinite rotating disk giving a laminar boundary layer of constant thickness, also known as the von Kármán flow. It is well known now that there is an absolute instability of the boundary layer which is linked to transition to turbulence, but convective routes are also observed. It is these convective modes that we focus on here. A comparison of three different approaches to investigate the convective, so called Type-I, stationary crossflow instability is presented here. The three approaches consist of local linear stability analysis, direct numerical simulations (DNS) and experiments. The 'shooting method' was used to compute the local linear stability whereas linear DNS was performed using a spectral-element method for a full annulus of the disk, a quarter and 1/32 of an annulus, each with one roughness element in the computational domain. These correspond to simulating one, four and 32 roughness elements on the full disk surface and in addition a case with randomly-distributed roughnesses was simulated on the full disk. Two different experimental configurations were used for the comparison: i) a clean-disk condition, i.e. unexcited boundary-layer flow; and ii) a rough-disk condition, where 32 roughness elements were placed on the disk surface to excite the Type-I stationary vortices. Comparisons between theory, DNS and experiments with respect to the structure of the stationary vortices are made. The results show excellent agreement between local linear stability analysis and both DNS and experiments for a fixed azimuthal wavenumber (32 roughnesses). This agreement clearly shows that the three approaches capture the same underlying physics of the setup, and lead to an accurate description of the flow. It also verifies the numerical simulations and shows the robustness of experimental measurements of the flow case. The effects of the azimuthal domain size in the DNS and superposition of multiple azimuthal wavenumbers in the DNS and experiments are discussed.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct numerical simulations; Hot-wire anemometry; Linear stability theory; Rotating-disk boundary layer

Linear stability of buffer layer streaks in turbulent channels with variable density and viscosity - Rinaldi, Enrico; Patel, Ashish; Schlatter, Philipp; Pecnik, Rene (Physical Review Fluids, 2017)
We investigate the stability of streaks in the buffer layer of turbulent channel flows with temperature-dependent density and viscosity by means of linear theory. The adopted framework consists of an extended set of the Orr-Sommerfeld-Squire equations that accounts for density and viscosity nonuniformity in the direction normal to the walls. The base flow profiles for density, viscosity, and velocity are averaged from direct numerical simulations (DNSs) of fully developed turbulent channel flows. We find that the inner scaling based on semilocal quantities provides an effective parametrization of the effect of variable properties on the linearized flow. The spanwise spacing of optimal buffer layer streaks scales to λz,opt≈90 for all cases considered and the maximum energy amplification decreases, compared to the one for a flow with constant properties, if the semilocal Reynolds number Reτ increases away from the walls, consistently with less energetic streaks observed in DNSs of turbulent channels. A secondary stability analysis of the two-dimensional velocity profile formed by the mean turbulent velocity and the nonlinearly saturated optimal streaks predicts a streamwise instability mode with wavelength λx,cr≈230 in semilocal units, regardless of the fluid property distribution across the channel. The threshold for the onset of the secondary instability is reduced, compared to a constant property flow, if Reτ increases away from the walls, which explains the more intense ejection events reported in DNSs. The opposite behavior is predicted by the linear theory for decreasing Reτ, in accord with DNS observations. We finally show that the phase velocity of the critical mode of secondary instability agrees well with the convection velocity calculated by DNSs in the near-wall region for both constant and variable viscosity flows.
CRIS-Team Scopus Importer:2023-03-21

Localized edge states in plane Couette flow - Duguet, Yohann; Schlatter, Philipp; Henningson, Dan S. (Physics of Fluids, 2009)
The dynamics at the threshold of transition in plane Couette flow is investigated numerically in a large spatial domain for a certain type of localized initial perturbation, for Re between 350 and 1000. The corresponding edge state is an unsteady spotlike structure, localized in both streamwise and spanwise directions, which neither grows nor decays in size. We show that the localized nature of the edge state is numerically robust, and is not influenced by the size of the computational domain. The edge trajectory appears to transiently visit localized steady states. This suggests that basic spatiotemporally intermittent features of transition to turbulence, such as the growth of a turbulent spot, can be described as a dynamical system. © 2009 American Institute of Physics.
CRIS-Team Scopus Importer:2023-03-21

Localized edge states in the asymptotic suction boundary layer - Khapko, T.; Kreilos, Tobias; Schlatter, Philipp; Duguet, Y.; Eckhardt, Bruno; Henningson, D. S. (Journal of Fluid Mechanics, 2013)
The dynamics on the laminar-turbulent separatrix is investigated numerically for boundary-layer flows in the subcritical regime. Constant homogeneous suction is applied at the wall, resulting in a parallel asymptotic suction boundary layer (ASBL). When the numerical domain is sufficiently extended in the spanwise direction, the coherent structures found by edge tracking are invariably localized and their dynamics shows bursts that drive a remarkable regular or irregular spanwise dynamics. Depending on the parameters, the asymptotic dynamics on the edge can be either periodic in time or chaotic. A clear mechanism for the regeneration of streaks and streamwise vortices emerges in all cases and is investigated in detail.
CRIS-Team Scopus Importer:2023-03-21
Keywords: boundary layers; instability; nonlinear dynamical systems

Lossy Data Compression Effects on Wall-bounded Turbulence: Bounds on Data Reduction - Otero, Evelyn; Vinuesa, Ricardo; Marin, Oana; Laure, Erwin; Schlatter, Philipp (Flow Turbulence and Combustion, 2018)
Postprocessing and storage of large data sets represent one of the main computational bottlenecks in computational fluid dynamics. We assume that the accuracy necessary for computation is higher than needed for postprocessing. Therefore, in the current work we assess thresholds for data reduction as required by the most common data analysis tools used in the study of fluid flow phenomena, specifically wall-bounded turbulence. These thresholds are imposed a priori by the user in L2-norm, and we assess a set of parameters to identify the minimum accuracy requirements. The method considered in the present work is the discrete Legendre transform (DLT), which we evaluate in the computation of turbulence statistics, spectral analysis and resilience for cases highly-sensitive to the initial conditions. Maximum acceptable compression ratios of the original data have been found to be around 97%, depending on the application purpose. The new method outperforms downsampling, as well as the previously explored data truncation method based on discrete Chebyshev transform (DCT).
CRIS-Team Scopus Importer:2023-03-21
Keywords: Data reduction; Lossy data compression; Orthogonal polynomials; Resilience; Turbulence statistics

Mesh Optimization Using Dual-Weighted Error Estimators: Application to the Periodic Hill - Offermans, N.; Peplinski, A.; Schlatter, Philipp (Springer, 2020)
Simulations have matured to be an important tool in the design and analysis of many modern industrial devices, in particular in the process, vehicle and aeronautical industries. Most of the considered flows are turbulent, for which it is impossible to perform straightforward grid-convergence studies without considering long-term statistics. Therefore, when performing simulations in computational fluid dynamics (CFD), the use of adaptive mesh refinement (AMR) is an effective strategy to increase the reliability of the solution at a reduced computational cost. Such tools allow for error control, reduced simulation time, easier mesh generation, better mesh quality and better resolution of the a priori unknown physics. In the present contribution, the design of an optimal mesh, using AMR, is investigated in Nek5000 [3], a highly scalable code based on the spectral element method (SEM) [9] and aimed at the direct numerical simulation (DNS) of the incompressible Navier–Stokes equations (further discussed in section “Numerical Method”).
CRIS-Team Scopus Importer:2023-03-21

Modal analysis of roughness-induced crossflow vortices in a Falkner-Skan-Cooke boundary layer - Brynjell-Rahkola, Mattias; Schlatter, Philipp; Hanifi, Ardeshir; Henningson, Dan S. (International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2013, 2013)
A three-dimensional global stability analysis using high-order direct numerical simulations is performed to investigate the effect of surface roughness with Reynolds number (based on roughness height) Rek above and below the critical value for transition, on the eigenmodes of a Falkner-Skan-Cooke boundary layer. The surface roughness is introduced with the immersed boundary method and the eigenvalues and eigenfunctions are solved using an iterative time-stepper method. The study reveals a global instability for the case with higher Reynolds number that causes the flow in the non-linear simulations to break down to turbulence shortly downstream of the roughness. Examination of the unstable linear global modes show that these are the same modes that are observed in experiments immediately before breakdown due to secondary instability, which emphasizes the importance of these modes in transition.
CRIS-Team Scopus Importer:2023-03-21

Modal instability of the flow in a toroidal pipe - Canton, Jacopo; Schlatter, Philipp; Orlu, Ramis (Journal of Fluid Mechanics, 2016)
The modal instability encountered by the incompressible flow inside a toroidal pipe is studied, for the first time, by means of linear stability analysis and direct numerical simulation (DNS). In addition to the unquestionable aesthetic appeal, the torus represents the smallest departure from the canonical straight pipe flow, at least for low curvatures. The flow is governed by only two parameters: the Reynolds number and the curvature of the torus δ, i.e. the ratio between pipe radius and torus radius. The absence of additional features, such as torsion in the case of a helical pipe, allows us to isolate the effect that the curvature has on the onset of the instability. Results show that the flow is linearly unstable for all curvatures investigated between 0.002 and unity, and undergoes a Hopf bifurcation at of about 4000. The bifurcation is followed by the onset of a periodic regime, characterised by travelling waves with wavelength O(1) pipe diameters. The neutral curve associated with the instability is traced in parameter space by means of a novel continuation algorithm. Tracking the bifurcation provides a complete description of the modal onset of instability as a function of the two governing parameters, and allows a precise calculation of the critical values of Re and δ. Several different modes are found, with differing properties and eigenfunction shapes. Some eigenmodes are observed to belong to groups with a set of common characteristics, deemed 'families', while others appear as 'isolated'. Comparison with nonlinear DNS shows excellent agreement, confirming every aspect of the linear analysis, its accuracy, and proving its significance for the nonlinear flow. Experimental data from the literature are also shown to be in considerable agreement with the present results.
CRIS-Team Scopus Importer:2023-03-21
Keywords: bifurcation; instability; nonlinear dynamical systems

Modal laminar–turbulent transition delay by means of topology optimization of superhydrophobic surfaces - Nobis, Harrison; Schlatter, Philipp; Wadbro, Eddie; Berggren, Martin; Henningson, Dan S. (Computer Methods in Applied Mechanics and Engineering, 2023)
When submerged under a liquid, the microstructure of a SuperHydrophobic Surface (SHS) traps a lubricating layer of gas pockets, which has been seen to reduce the skin friction of the overlying liquid flow in both laminar and turbulent regimes. More recently, spatially homogeneous SHS have also been shown to delay laminar–turbulent transition in channel flows, where transition is triggered by modal mechanisms. In this study, we investigate, by means of topology optimization, whether a spatially inhomogeneous SHS can be designed to further delay transition in channel flows. Unsteady direct numerical simulations are conducted using the spectral element method in a 3D periodic wall-bounded channel. The effect of the SHS is modelled using a partial slip length on the walls, forming a 2D periodic optimization domain. Following a density-based approach, the optimization procedure uses the adjoint-variable method to compute gradients and a checkpointing strategy to reduce storage requirements. This methodology is adapted to optimizing over an ensemble of initial perturbations. This study presents the first application of topology optimization to laminar–turbulent transition. We show that this method can design surfaces that delay transition significantly compared to a homogeneous counterpart, by inhibiting the growth of secondary instability modes. By optimizing over an ensemble of streamwise phase-shifted perturbations, designs have been found with comparable mean transition time and lower variance.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Channel flow; Direct numerical simulations; Laminar–turbulent transition; Spectral element method; Super-hydrophobic surfaces; Topology optimization

Modeling the Turbulent Wake Behind a Wall-Mounted Square Cylinder - Amor, Christian; Perez, Jose M.; Schlatter, Philipp; Vinuesa, Ricardo; Le Clainche, Soledad (Logic Journal of the Igpl, 2022)
This article introduces some soft computing methods generally used for data analysis and flow pattern detection in fluid dynamics. These techniques decompose the original flow field as an expansion of modes, which can be either orthogonal in time (variants of dynamic mode decomposition), or in space (variants of proper orthogonal decomposition) or in time and space (spectral proper orthogonal decomposition), or they can simply be selected using some sophisticated statistical techniques (empirical mode decomposition). The performance of these methods is tested in the turbulent wake of a wall-mounted square cylinder. This highly complex flow is suitable to show the ability of the aforementioned methods to reduce the degrees of freedom of the original data by only retaining the large scales in the flow. The main result is a reduced-order model of the original flow case, based on a low number of modes. A deep discussion is carried out about how to choose the most computationally efficient method to obtain suitable reduced-order models of the flow. The techniques introduced in this article are data-driven methods that could be applied to model any type of non-linear dynamical system, including numerical and experimental databases.
CRIS-Team Scopus Importer:2023-03-21
Keywords: dynamic mode decomposition (DMD); empirical mode decomposition (EMD); flow structures; proper orthogonal decomposition (POD); reduced-order model; Soft computing; turbulent flow

Mutual inductance instability of the tip vortices behind a wind turbine - Sarmast, Sasan; Dadfar, Reza; Mikkelsen, Robert F.; Schlatter, Philipp; Ivanell, Stefan; Sorensen, Jens N.; Henningson, Dan S. (Journal of Fluid Mechanics, 2014)
Two modal decomposition techniques are employed to analyse the stability of wind turbine wakes. A numerical study on a single wind turbine wake is carried out focusing on the instability onset of the trailing tip vortices shed from the turbine blades. The numerical model is based on large-eddy simulations (LES) of the Navier-Stokes equations using the actuator line (ACL) method to simulate the wake behind the Tjæreborg wind turbine. The wake is perturbed by low-amplitude excitation sources located in the neighbourhood of the tip spirals. The amplification of the waves travelling along the spiral triggers instabilities, leading to breakdown of the wake. Based on the grid configurations and the type of excitations, two basic flow cases, symmetric and asymmetric, are identified. In the symmetric setup, we impose a 120°symmetry condition in the dynamics of the flow and in the asymmetric setup we calculate the full 360°wake. Different cases are subsequently analysed using dynamic mode decomposition (DMD) and proper orthogonal decomposition (POD). The results reveal that the main instability mechanism is dispersive and that the modal growth in the symmetric setup arises only for some specific frequencies and spatial structures, e.g. two dominant groups of modes with positive growth (spatial structures) are identified, while breaking the symmetry reveals that almost all the modes have positive growth rate. In both setups, the most unstable modes have a non-dimensional spatial growth rate close to π/2 and they are characterized by an out-of-phase displacement of successive helix turns leading to local vortex pairing. The present results indicate that the asymmetric case is crucial to study, as the stability characteristics of the flow change significantly compared to the symmetric configurations. Based on the constant non-dimensional growth rate of disturbances, we derive a new analytical relationship between the length of the wake up to the turbulent breakdown and the operating conditions of a wind turbine.
CRIS-Team Scopus Importer:2023-03-21
Keywords: instability; vortex interaction; wakes

Near wall coherence in wall-bounded flows and implications for flow control - Samie, M.; Baars, W. J.; Rouhi, Amirreza; Schlatter, Philipp; Orlu, R.; Marusic; Hutchins, Nicholas (International Journal of Heat and Fluid Flow, 2020)
Opposition-control of the energetic cycle of near wall streaks in wall-bounded turbulence, using numerical approaches, has shown promise for drag reduction. For practical implementation, real-time opposition control is only realizable if there is a degree of coherence between the turbulent velocities passing a sensor and the target point within the flow; for practicality, a sensor (and actuator) should be wall-based to avoid parasitic drag. As such, we here inspect the feasibility of real-time control of the near wall cycle, by considering the coherence between a measurable wall-quantity, being the wall-shear stress fluctuations, and the streamwise and wall-normal velocity fluctuations in a turbulent boundary layer. Synchronized spatial and temporal velocity data from two direct numerical simulations and a fine large eddy simulation at Reτ≈590 and 2000 are employed. This study shows that the spectral energy of the streamwise velocity fluctuations that is stochastically incoherent with wall signals is independent of Reynolds number in the near wall region (up to the viscous-scaled wall-normal height z+≈20). Consequently, the streamwise energy-fraction that is stochastically wall-coherent grows with Reynolds number due to the increasing range of energetic large scales. This thus implies that a wall-based control system has the ability to manipulate a larger portion of the total turbulence energy at off-wall locations, at higher Reynolds numbers, while the efficacy of predicting/targeting the small scales of the near wall cycle remains indifferent with varying Reynolds number. Coherence values of 0.55 and 0.4 were found between the streamwise and wall-normal velocity fluctuations at the near wall peak in the energy spectrogram, respectively, and the streamwise fluctuating friction velocity. These coherence values, which are considerably lower than 1 (maximum possible coherence) suggest that a closed-loop drag reduction scheme targeting near wall cycle streaks alone (based on sensed friction velocity fluctuations) will be of limited success in practice.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Flow control; Turbulent boundary layers; Turbulent flows

Negative streamwise velocities and other rare events near the wall in turbulent flows - Lenaers, Peter; Li, Qiang; Brethouwer, Geert; Schlatter, Philipp; Orlu, Ramis (Journal of Physics: Conference Series, 2011)
Negative streamwise velocities, extreme wall-normal velocites and high flatness values for the wall-normal fluctuations near the wall are investigated for turbulent channel flow simulations at a series of Reynolds numbers up to Reτ = 1000 in this paper. Probability density functions of the wall-shear stress and velocity components are presented, as well as joint probability density functions of the velocity components and the pressure. Backflow occurs more often (0.06% at Reτ = 1000) and further away from the wall into the buffer layer for rising Reynolds number. An oblique vortex outside the viscous sublayer is found to cause this backflow. Extreme v events occur also more often for rising Reynolds number. Positive and negative velocity spikes appear in pairs, located on the two edges of a strong streamwise vortex: the negative spike occurring in a high speed streak indicating a sweeping motion, while the positive spike is located between a high and low speed streak. These extreme v events cause high flatness values near the wall (F(v) = 43 at Reτ = 1000).
CRIS-Team Scopus Importer:2023-03-21

Nek5000 with OpenACC - Gong, Jing; Markidis, Stefano; Schliephake, Michael; Laure, Erwin; Henningson, Dan; Schlatter, Philipp; Peplinski, Adam; Hart, Alistair; Doleschal, Jens; Henty, David; Fischer, Paul (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2015)
Nek5000 is a computational fluid dynamics code based on the spectral element method used for the simulation of incompressible flows. We follow up on an earlier study which ported the simplified version of Nek5000 to a GPU-accelerated system by presenting the hybrid CPU/GPU implementation of the full Nek5000 code using OpenACC. The matrix-matrix multiplication, the Nek5000 gather-scatter operator and a preconditioned Conjugate Gradient solver have implemented using OpenACC for multi-GPU systems.We report an speed-up of 1.3 on single node of a Cray XK6 when using OpenACC directives in Nek5000. On 512 nodes of the Titan supercomputer, the speed-up can be approached to 1.4. A performance analysis of the Nek5000 code using Score-P and Vampir performance monitoring tools shows that overlapping of GPU kernels with host-accelerator memory transfers would considerably increase the performance of the OpenACC version of Nek5000 code.
CRIS-Team Scopus Importer:2023-03-21
Keywords: GPU programming; Nek5000; OpenACC; Spectral element method

Neko: A Modern, Portable, and Scalable Framework for Extreme-Scale Computational Fluid Dynamics - Jansson, Niclas; Karp, Martin; Markidis, Stefano; Schlatter, Philipp (Proceedings - 2024 IEEE International Conference on Cluster Computing Workshops, CLUSTER Workshops 2024, 2024)
Recent trends and advancements in including more diverse and heterogeneous hardware in High-Performance Computing are challenging scientific software developers in their pursuit of good performance and efficient numerical methods. As a result, the well-known maxim 'software outlives hardware' may no longer necessarily hold true, and researchers are today forced to re-factor their codes to leverage these powerful new heterogeneous systems. We present Neko - a portable framework for high-fidelity spectral element flow simulations. Unlike prior works, Neko adopts a modern object-oriented Fortran 2008 approach, allowing multi-tier abstractions of the solver stack and facilitating various hardware backends ranging from general-purpose processors, accelerators down to exotic vector processors and Field Programmable Gate Arrays (FPGAs) via Neko's device abstraction layer. Focusing on Neko's performance and exascale readiness, we outline the optimisation and algorithmic work necessary to ensure scalability and performance portability across a wide range of platforms. Finally, we present performance measurements on a wide range of accelerated computing plat-forms, including the EuroHPC pre-exascale system LUMI and Leonardo, where Neko achieves excellent parallel efficiency for an extreme-scale direct numerical simulation (DNS) of turbu-lent thermal convection using up to 80% of the entire LUMI supercomputer.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Accelerators; Direct numerical simulation; Spectral element method

Neutral stability of the flow in a toroidal pipe - Canton, Jacopo; Örlü, Ramis; Schlatter, Philipp (Proceedings - 15th European Turbulence Conference, ETC 2015, 2015)
This work is concerned with the numerical investigation of the linear stability properties of the viscous, incompressible flow inside a toroidal pipe. A Hopf bifurcation is found and tracked in phase space, showing that the flow is modally unstable even at extremely low curvatures. The bifurcation and the eigenfunctions associated with it are analysed as a function of the two parameters governing the flow, i.e. the Reynolds number, Re, and the curvature, δ. For all curvatures, the critical Reynolds number is found to be about 3000.
CRIS-Team Scopus Importer:2023-03-21

Non-conforming elements in nek5000: Pressure preconditioning and parallel performance - Peplinski, A.; Offermans, N.; Fischer, P. F.; Schlatter, Philipp (Lecture Notes in Computational Science and Engineering, 2020)
Adaptive mesh refinement (AMR) is an important component of modern numerical solvers, as it allows to control the computational error during the simulation, increasing the reliability of the numerical modelling and giving the possibility to study a broad range of different phenomena even without knowing the physics a priori. In this work we present selected aspects of the implementation and parallel performance of a new h-type AMR framework developed for the high-order CFD solver Nek5000; the development was done within the ExaFLOW EU project. We utilise in this case the natural domain decomposition inherent to the spectral element method (SEM), which constitutes the main source of parallelism and provides meshing flexibility that can be exploited in AMR. We use standard libraries for parallel mesh management (p4est) and partitioning (ParMetis) and focus on developing efficient preconditioners for the pressure problem solved on non-conforming meshes. Two different approaches are considered: an additive overlapping Schwarz and a hybrid Schwarz-multigrid method. The strong scaling is shown on the example of the simulation of the turbulent flow around a NACA4412 wing section at Re = 200, 000.
CRIS-Team Scopus Importer:2023-03-21

NON-INTRUSIVE SENSING IN TURBULENT BOUNDARY LAYERS VIA DEEP FULLY-CONVOLUTIONAL NEURAL NETWORKS - Guastoni, Luca; Balasubramanian, Arivazhagan G.; Güemes, Alejandro; Ianiro, Andrea; Discetti, Stefano; Schlatter, Philipp; Azizpour, Hossein; Vinuesa, Ricardo (12th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2022, 2022)
Flow-control techniques are extensively studied in fluid mechanics, as a means to reduce energy losses related to friction, both in fully-developed and spatially-developing flows. These techniques typically rely on closed-loop control systems that require an accurate representation of the state of the flow to compute the actuation. Such representation is generally difficult to obtain without perturbing the flow. For this reason, in this work we propose a fully-convolutional neural-network (FCN) model trained on direct-numerical-simulation (DNS) data to predict the instantaneous state of the flow at different wall-normal locations using quantities measured at the wall. Our model can take as input the heat-flux field at the wall from a passive scalar with Prandtl number Pr = ν/α = 6 (where ν is the kinematic viscosity and α is the thermal diffusivity of the scalar quantity). The heat flux can be accurately measured also in experimental settings, paving the way for the implementation of a non-intrusive sensing of the flow in practical applications.
CRIS-Team Scopus Importer:2023-03-21

Notes on Percolation Analysis of Sampled Scalar Fields - Köpp, Wiebke; Friederici, Anke; Atzori, Marco; Vinuesa, Ricardo; Schlatter, Philipp; Weinkauf, Tino (Mathematics and Visualization, 2021)
Percolation analysis is used to explore the connectivity of randomly connected infinite graphs. In the finite case, a closely related percolation function captures the relative volume of the largest connected component in a scalar field’s superlevel set. While prior work has shown that random scalar fields with little spatial correlation yield a sharp transition in this function, little is known about its behavior on real data. In this work, we explore how different characteristics of a scalar field—such as its histogram or degree of structure—influence the shape of the percolation function. We estimate the critical value and transition width of the percolation function, and propose a corresponding normalization scheme that relates these values to known results on infinite graphs. In our experiments, we find that percolation analysis can be used to analyze the degree of structure in Gaussian random fields. On a simulated turbulent duct flow data set we observe that the critical values are stable and consistent across time. Our normalization scheme indeed aids comparison between data sets and relation to infinite graphs.
CRIS-Team Scopus Importer:2023-03-21

Numerical study of the stabilisation of boundary-layer disturbances by finite amplitude streaks - Schlatter, Philipp; Deusebio, Enrico; De Lange, Rick; Brandt, Luca (International Journal of Flow Control, 2010)
Well-resolved large-eddy simulations of passive control of the laminar-turbulent transition process in flat-plate boundary-layer flows are presented. A specific passive control mechanism is studied, namely the modulation of the laminar boundary-layer profile by a periodic array of steady boundary-layer streaks. This has been shown experimentally to stabilise the exponential growth of Tollmien-Schlichting (TS) waves and delay transition to turbulence. Here we examine the effect of the steady modulations on the amplification of different types of disturbances such as TS-waves, stochastic noise and free-stream turbulence. In our numerical simulations, the streaks are forced at the inflow as optimal solutions to the linear parabolic stability equations (PSE), whereas the additional disturbances are excited via volume forcing active within the computational domain. The simulation results show, in agreement with experimental and theoretical studies, significant damping of unstable two-dimensional TS-waves of various frequencies when introduced into a modulated base flow: The damping characteristics are mainly dependent on the streak amplitude. A new phenomenon is also identified which is characterised by the strong amplification via nonlinear interactions of the second spanwise harmonic of the streak when the streak amplitude is comparable to the TS amplitude. Furthermore, we demonstrate that control by streaks can be effective also in case of stochastic two-dimensional noise. However, as soon as a significant three-dimensionality is dominant, as in e.g. oblique or bypass transition, control by streaks leads often to premature transition. Visualisations of the flow fields are used to highlight the different vortical structures and their interactions that are relevant to the various transition scenarios and the corresponding control by streamwise streaks.
CRIS-Team Scopus Importer:2023-03-21

Numerical study of turbulent-laminar patterns in MHD, rotating and stratified shear flows - Brethouwer, G.; Duguet, Y.; Schlatter, Philipp (ERCOFTAC Series, 2011)
CRIS-Team Scopus Importer:2023-03-21

Oblique laminar-turbulent interfaces in plane shear flows - Duguet, Yohann; Schlatter, Philipp (Physical Review Letters, 2013)
Localized structures such as turbulent stripes and turbulent spots are typical features of transitional wall-bounded flows in the subcritical regime. Based on an assumption for scale separation between large and small scales, we show analytically that the corresponding laminar-turbulent interfaces are always oblique with respect to the mean direction of the flow. In the case of plane Couette flow, the mismatch between the streamwise flow rates near the boundaries of the turbulence patch generates a large-scale flow with a nonzero spanwise component. Advection of the small-scale turbulent fluctuations (streaks) by the corresponding large-scale flow distorts the shape of the turbulence patch and is responsible for its oblique growth. This mechanism can be easily extended to other subcritical flows such as plane Poiseuille flow or Taylor-Couette flow. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-21

On determining characteristic length scales in pressure-gradient turbulent boundary layers - Vinuesa, Ricardo; Bobke, A.; Orlu, R.; Schlatter, Philipp (Physics of Fluids, 2016)
In the present work, we analyze three commonly used methods to determine the edge of pressure gradient turbulent boundary layers: two based on composite profiles, the one by Chauhan et al. ["Criteria for assessing experiments in zero pressure gradient boundary layers," Fluid Dyn. Res. 41, 021404 (2009)] and the one by Nickels ["Inner scaling for wall-bounded flows subject to large pressure gradients," J. Fluid Mech. 521, 217-239 (2004)], and the other one based on the condition of vanishing mean velocity gradient. Additionally, a new method is introduced based on the diagnostic plot concept by Alfredsson et al. ["A new scaling for the streamwise turbulence intensity in wall-bounded turbulent flows and what it tells us about the 'outer' peak," Phys. Fluids 23, 041702 (2011)]. The boundary layers developing over the suction and pressure sides of a NACA4412 wing section, extracted from a direct numerical simulation at chord Reynolds number Rec = 400 000, are used as the test case, besides other numerical and experimental data from favorable, zero, and adverse pressure-gradient flat-plate turbulent boundary layers. We find that all the methods produce robust results with mild or moderate pressure gradients, although the composite-profile techniques require data preparation, including initial estimations of fitting parameters and data truncation. Stronger pressure gradients (with a Rotta-Clauser pressure-gradient parameter β larger than around 7) lead to inconsistent results in all the techniques except the diagnostic plot. This method also has the advantage of providing an objective way of defining the point where the mean streamwise velocity is 99% of the edge velocity and shows consistent results in a wide range of pressure gradient conditions, as well as flow histories. Collapse of intermittency factors obtained from a wide range of pressure-gradient and Re conditions on the wing further highlights the robustness of the diagnostic plot method to determine the boundary layer thickness (equivalent to d99) and the edge velocity in pressure gradient turbulent boundary layers. Published by AIP Publishing.
CRIS-Team Scopus Importer:2023-03-21

On determining characteristic length scales in pressure gradient turbulent boundary layers - Vinuesa, Ricardo; Orlu, Ramis; Schlatter, Philipp (Journal of Physics: Conference Series, 2016)
In the present work we analyze three methods used to determine the edge of pressure gradient turbulent boundary layers: two based on composite profiles, the one by Chauhan et al. (Fluid Dyn. Res. 41:021401, 2009) and the one by Nickels (J. Fluid Mech. 521:217-239, 2004), and the other one based on the condition of vanishing mean velocity gradient. Additionally, a new method is introduced based on the diagnostic plot concept by Alfredsson et al. (Phys. Fluids 23:041702, 2011). The boundary layer developing over the suction side of a NACA4412 wing profile, extracted from a direct numerical simulation at Rec = 400,000, is used as the test case. We find that all the methods produce robust results with mild or moderate pressure gradients, but stronger pressure gradients (with β larger than around 7) lead to inconsistent results in all the techniques except the diagnostic plot. This method also has the advantage of providing an objective way of defining the point where the mean streamwise velocity is 99% of the edge velocity, and shows consistent results in a wide range of pressure gradient conditions, as well as flow histories. Therefore, the technique based on the diagnostic plot is a robust method to determine the boundary layer thickness (equivalent to δ99) and edge velocity in pressure gradient turbulent boundary layers.
CRIS-Team Scopus Importer:2023-03-21

On Large-Scale Friction Control in Turbulent Wall Flow in Low Reynolds Number Channels - Canton, Jacopo; Orlu, Ramis; Chin, Cheng; Hutchins, Nicholas; Monty, Jason; Schlatter, Philipp (Flow Turbulence and Combustion, 2016)
The present study reconsiders the control scheme proposed by Schoppa & Hussain (Phys. Fluids 10, 1049–1051 1998), using a new set of numerical simulations. The computations are performed in a turbulent channel at friction Reynolds numbers of 104 (the value employed in the original study) and 180. In particular, the aim is to better characterise the physics of the control as well as to investigate the optimal parameters. The former purpose lead to a re-design of the control strategy: moving from a numerical imposition of the mean flow to the application of a volume force. A comparison between the two is presented. Results show that the original method only gave rise to transient drag reduction. The forcing method, on the other hand, leads to sustained drag reduction, and thus shows the superiority of the forcing approach for all wavelengths investigated. A clear maximum efficiency in drag reduction is reached for the case with a viscous-scaled spanwise wavelength of the vortices of 1200, which yields a drag reduction of 18 %, as compared to the smaller wavelength of 400 suggested as the most efficient vortex in Schoppa & Hussain. Various turbulence statistics are considered, in an effort to elucidate the causes of the drag-reducing effect. For instance, a region of negative production was found, which is quite unusual for developed turbulent channel flow.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct numerical simulation; Flow control; Skin-friction reduction; Turbulent channel flow

On minimum aspect ratio for duct flow facilities and the role of side walls in generating secondary flows - Vinuesa, Ricardo; Schlatter, Philipp; Nagib, Hassan M. (Journal of Turbulence, 2015)
To the surprise of some of our colleagues, we recently recommended aspect ratios of at least 24 (instead of accepted values over last few decades ranging from 5 to 12) to minimise effects of side walls in turbulent duct flow experiments, in order to approximate the two-dimensional channel flow. Here we compile available results from hydraulics and civil engineering literature, where this was already documented in the 1980s. This is of great importance due to the large amount of computational studies (mainly direct numerical simulations, DNSs) for spanwise-periodic turbulent channel flows, and the extreme complexity of constructing a fully developed duct flow facility with aspect ratio of 24 for high Reynolds numbers with adequate probe resolution. Results from this non-traditional literature for the turbulence community are compared to our recent database of DNS of turbulent duct flows with aspect ratios ranging from 1 to 18 at Reτ, c values of 180 and 330, leading to very good agreement between their experimental and our computational results at these low Reynolds numbers. The DNS results also reveal the complexity of a multitude of streamwise vortical structures in addition to the secondary corner flows (which extend up to z ≃ 5h). These time-dependent and meandering streamwise structures are located at the core of the duct and scale with its half-height. Comparisons of these structures with the vortical motions found in spanwise-periodic channels reveal similitudes in their time-averages and the same rate of decay of their mean kinetic energy ∼ TA-1, with TA being the averaging time. However, differences between the two flows are identified and ideas for their future analysis are proposed.
CRIS-Team Scopus Importer:2023-03-21
Keywords: direct numerical simulation; hydraulics; oil film interferometry; secondary motions; turbulent duct flow; wall turbulence

On minimum aspect ratio for experimental duct flow facilities - Vinuesa, Ricardo; Bartrons, Eduard; Chiu, Daniel; Rüedi, Jean Daniel; Schlatter, Philipp; Obabko, Aleksandr; Nagib, Hassan M. (ERCOFTAC Series, 2016)
To the surprise of some of our colleagues, we recently recommended aspect ratios of at least 24 (instead of accepted values over last few decades ranging from 5 to 12) to minimize effects of sidewalls in turbulent duct flow experiments, in order to approximate the two-dimensional channel flow. Here we compile avail- able results from hydraulics and civil engineering literature, where this was already documented in the 1980s. This is of great importance due to the large amount of computational studies (mainly Direct Numerical Simulations) for spanwise-periodic turbulent channel flows, and the extreme complexity of constructing a fully developed duct flow facility with aspect ratio of 24 for high Reynolds number with adequate probe resolution. Results from this nontraditional literature for the turbulence com- munity are compared to our recent database of DNS of turbulent duct flows with aspect ratios ranging from 1 to 18 and Reτ,c ≃ 180 and 330, leading to very good agreement between their experimental and our computational results.
CRIS-Team Scopus Importer:2023-03-21

On numerical uncertainties in scale-resolving simulations of canonical wall turbulence - Rezaeiravesh, Saleh; Vinuesa, Ricardo; Schlatter, Philipp (Computers & Fluids, 2021)
The present study focuses on applying different metrics to assess accuracy, robustness and sensitivity of scale-resolving simulations of turbulent channel flow, when the numerical parameters are systematically varied. Derived by combining well-established uncertainty quantification techniques and computer experiments, the metrics act as powerful tools for understanding the behavior of flow solvers and exploring the impact of their numerical parameters as well as systematically comparing different solvers. A few examples for uncertain behavior of the solvers, i.e. the behaviors that are unexpected or not fully explainable with our a-priori knowledge, is provided. Two open-source software, Nek5000 and OpenFOAM, are considered with the focus on grid resolution and filtering in Nek5000, and grid resolution and numerical dissipation in OpenFOAM. Considering all metrics as well as the computational efficiency, Nek5000 is shown to outperform OpenFOAM. The propagated uncertainty (a measure of robustness) in the profiles of channel flow quantities of interest (QoIs), together with corresponding Sobol sensitivity indices quantitatively measure the impact and relative contribution of different numerical parameters at different wall-distances. The locations with larger confidence intervals indicate where a QoI is more sensitive to the variation of the numerical parameters. In OpenFOAM, increasing the numerical dissipation at all considered grid resolutions leads to decreasing the uncertainties at the price of losing accuracy. In contrast, the influence of filtering in Nek5000 is found to be more complicated and relying on the grid resolution. In particular, the filter cutoff is found to be more influential than the filter weight, and at high number of Gauss–Lobatto–Legendre (GLL) points per element, it is shown that there exist optimal values for the filter cutoff which result in more accurate QoIs. From the same analysis, it is also concluded that considering the number of GLL points as an indicator of resolution and accuracy in the context of Nek5000 may require additional consideration. The analyses and metrics presented in this study are general and can be applied to any type of flow simulation. They facilitate not only the validation-and-verification process, but also the selection of adequate numerical parameters to achieve accurate and reliable results.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Computer experiments; Nek5000; OpenFOAM; Uncertainty quantification; Wall-resolved turbulence simulation

On stability and transition in bent pipes - Canton, J.; Örlü, R.; Schlatter, Philipp (Springer, 2019)
This work is concerned with the investigation of the instability and transition to turbulence of the viscous, incompressible flow inside curved pipes. For the first time, the impact of the curvature is analysed over the whole parameter space, presenting new results for both the steady flow and the instabilities encountered by this flow.
CRIS-Team Scopus Importer:2023-03-21

On the fluctuating wall-shear stress in zero pressure-gradient turbulent boundary layer flows - Orlu, Ramis; Schlatter, Philipp (Physics of Fluids, 2011)
Recent direct numerical simulation (DNS) results relating to the behavior of the fluctuating wall-shear stress τ+,w,rms in turbulent boundary layer flows are discussed. This new compilation is motivated by a recent article [Wu and Moin, "Transitional and turbulent boundary layer with heat transfer," Phys. Fluids 22, 085105 (2010)], which indicates a need for clarification of the value of τ+,w,rms It is, however, shown here, based on other recent DNS data, that most results, both in boundary layer and channel geometry, yield τ+,w,rms ν0.4 plus a small increase with Reynolds number coming from the growing influence of the outer spectral peak. The observed discrepancy in experimental data is mainly attributed to spatial resolution effects, as originally described by Alfredsson et al. ["The fluctuating wall-shear stress and the velocity field in the viscous sublayer," Phys. Fluids 31, 1026 (1988)]. © 2011 American Institute of Physics.
CRIS-Team Scopus Importer:2023-03-21

On the global nonlinear instability of the rotating-disk flow over a finite domain - Appelquist, E.; Schlatter, Philipp; Alfredsson, P. H.; Lingwood, R. J. (Journal of Fluid Mechanics, 2016)
Direct numerical simulations based on the incompressible nonlinear Navier-Stokes equations of the flow over the surface of a rotating disk have been conducted. An impulsive disturbance was introduced and its development as it travelled radially outwards and ultimately transitioned to turbulence has been analysed. Of particular interest was whether the nonlinear stability is related to the linear stability properties. Specifically three disk-edge conditions were considered; (i) a sponge region forcing the flow back to laminar flow, (ii) a disk edge, where the disk was assumed to be infinitely thin and (iii) a physically realistic disk edge of finite thickness. This work expands on the linear simulations presented by Appelquist et al. (J. Fluid. Mech., vol. 765, 2015, pp. 612-631), where, for case (i), this configuration was shown to be globally linearly unstable when the sponge region effectively models the influence of the turbulence on the flow field. In contrast, case (ii) was mentioned there to be linearly globally stable, and here, where nonlinearity is included, it is shown that both cases (ii) and (iii) are nonlinearly globally unstable. The simulations show that the flow can be globally linearly stable if the linear wavepacket has a positive front velocity. However, in the same flow field, a nonlinear global instability can emerge, which is shown to depend on the outer turbulent region generating a linear inward-travelling mode that sustains a transition front within the domain. The results show that the front position does not approach the critical Reynolds number for the local absolute instability, . Instead, the front approaches and both the temporal frequency and spatial growth rate correspond to a global mode originating at this position.
CRIS-Team Scopus Importer:2023-03-21
Keywords: absolute/convective instability; boundary layer stability; rotating flows

On the identification of well-behaved turbulent boundary layers - Sanmiguel Vila, Carlos; Vinuesa, Ricardo; Discetti, Stefano; Ianiro, Andrea; Schlatter, Philipp; Orlu, R. (Journal of Fluid Mechanics, 2017)
This paper introduces a new method based on the diagnostic plot (Alfredsson et al., Phys. Fluids, vol. 23, 2011, 041702) to assess the convergence towards a well-behaved zero-pressure-gradient (ZPG) turbulent boundary layer (TBL). The most popular and well-understood methods to assess the convergence towards a well-behaved state rely on empirical skin-friction curves (requiring accurate skin-friction measurements), shape-factor curves (requiring full velocity profile measurements with an accurate wall position determination) or wake-parameter curves (requiring both of the previous quantities). On the other hand, the proposed diagnostic-plot method only needs measurements of mean and fluctuating velocities in the outer region of the boundary layer at arbitrary wall-normal positions. To test the method, six tripping configurations, including optimal set-ups as well as both under- and overtripped cases, are used to quantify the convergence of ZPG TBLs towards well-behaved conditions in the Reynolds-number range covered by recent high-fidelity direct numerical simulation data up to a Reynolds number based on the momentum thickness and free-stream velocity of approximately 4000 (corresponding to 2.5 m from the leading edge) in a wind-tunnel experiment. Additionally, recent high-Reynolds-number data sets have been employed to validate the method. The results show that weak tripping configurations lead to deviations in the mean flow and the velocity fluctuations within the logarithmic region with respect to optimally tripped boundary layers. On the other hand, a strong trip leads to a more energized outer region, manifested in the emergence of an outer peak in the velocity-fluctuation profile and in a more prominent wake region. While established criteria based on skin-friction and shape-factor correlations yield generally equivalent results with the diagnostic-plot method in terms of convergence towards a well-behaved state, the proposed method has the advantage of being a practical surrogate that is a more efficient tool when designing the set-up for TBL experiments, since it diagnoses the state of the boundary layer without the need to perform extensive velocity profile measurements.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulent boundary layers; turbulent flows

On the near-wall vortical structures at moderate Reynolds numbers - Schlatter, Philipp; Li, Q.; Orlu, R.; Hussain, F.; Henningson, D. S. (European Journal of Mechanics B-Fluids, 2014)
A recent database from direct numerical simulation (DNS) of a turbulent boundary layer up to Reθ=4300 (Schlatter and Örlü, 2010) is analysed to extract the dominant flow structures in the near-wall region. In particular, the question of whether hairpin vortices are significant features of near-wall turbulence is addressed. A number of different methods based on the λ2 criterion (Jeong and Hussain, 1995) is used to extract turbulent coherent structures: three-dimensional flow visualisation with quantitative estimates of hairpin population, conditional averaging and planar hairpin vortex signatures (HVS). First, visualisations show that during the initial phase of laminar-turbulent transition induced via tripping, hairpin vortices evolving from transitional Λ vortices are numerous and can be considered as the dominant structure of the immediate post-transition stage of the boundary layer. This is in agreement with previous experiments and low-Reynolds-number simulations such as Wu & Moin (2009). When the Reynolds number is increased, the fraction of hairpin vortices decreases to less than 2% for Reθ>4000. Second, conditional ensemble averages (Jeong et al., 1997) find hairpins close to the wall at low Reynolds number, while at a sufficient distance downstream from transition, the flow close to the wall is dominated by single quasi-streamwise vortices; even quantitatively, no major differences between boundary layer and channel can be detected. Moreover, three-dimensional visualisations of the neighbourhood of regions of strong swirling motion in planar cuts through the layer (the HVS) do not reveal hairpin vortices, thereby impairing statistical evidences based on HVS. The present results thus clearly confirm that transitional hairpin vortices do not persist in fully developed turbulent boundary layers, and that their dominant appearance as instantaneous flow structures in the outer boundary-layer region is very unlikely. © 2014 Elsevier Masson SAS. All rights reserved.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct numerical simulation; Hairpin vortices; Turbulent boundary layer; Wall turbulence

On the onset of transition in 90°-bend pipe flow - Lupi, Valerio; Canton, Jacopo; Schlatter, Philipp (11th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2019, 2019)
The present work deals with the global stability analysis of the flow in a 90◦-bend pipe with curvature δ = R/Rc = 0.3, being R the radius of the cross-section of the pipe and Rc the radius of curvature at the pipe centreline. Direct numerical simulations (DNS) for values of the bulk Reynolds number Reb = U——-D/v between 2000 and 3000 are performed. The bulk Reynolds number is based on the bulk velocity Ub, the pipe diameter D, and the kinematic viscosity ν. It is found that the flow is steady for Reb ≤ 2500, and two pairs of symmetric, counter-rotating vortices are observed in the section of the pipe downstream of the bend. Moreover, two recirculation regions are present inside the bend, one on the outer wall and the other on the inner one. For Reb ≥ 2550, the flow becomes periodic, oscillating with a fundamental non-dimensional frequency St = fD/Ub = 0.23. A global stability analysis reveals a pair of complex conjugate eigenvalues with positive real part. The velocity components of the unstable direct and adjoint eigenmodes are investigated, and it is observed that a large spatial separation occurs because of the non-normality of the linearised Navier–Stokes operator. Thus, an analysis of the structural sensitivity of the unstable eigenmode to spatially localised feedbacks is performed, in order to identify the core of the instability, the so-called wavemaker. It is found that the region located 15° downstream of the bend inlet, on the outer wall, is where the instability originates. Since flow separation is observed in this region, it is concluded that the instability is linked with the strong shear by the backflow phenomena.
CRIS-Team Scopus Importer:2023-03-21

On the potential of transfer entropy in turbulent dynamical systems - Massaro, Daniele; Rezaeiravesh, Saleh; Schlatter, Philipp (Scientific Reports, 2023)
Information theory (IT) provides tools to estimate causality between events, in various scientific domains. Here, we explore the potential of IT-based causality estimation in turbulent (i.e. chaotic) dynamical systems and investigate the impact of various hyperparameters on the outcomes. The influence of Markovian orders, i.e. the time lags, on the computation of the transfer entropy (TE) has been mostly overlooked in the literature. We show that the history effect remarkably affects the TE estimation, especially for turbulent signals. In a turbulent channel flow, we compare the TE with standard measures such as auto- and cross-correlation, showing that the TE has a dominant direction, i.e. from the walls towards the core of the flow. In addition, we found that, in generic low-order vector auto-regressive models (VAR), the causality time scale is determined from the order of the VAR, rather than the integral time scale. Eventually, we propose a novel application of TE as a sensitivity measure for controlling computational errors in numerical simulations with adaptive mesh refinement. The introduced indicator is fully data-driven, no solution of adjoint equations is required, with an improved convergence to the accurate function of interest. In summary, we demonstrate the potential of TE for turbulence, where other measures may only provide partial information.
CRIS-Team Scopus Importer:2023-12-22

On the strong scaling of the spectral element solver Nek5000 on petascale systems - Offermans, Nicolas; Marin, Oana; Schanen, Michel; Gong, Jing; Fischer, Paul; Schlatter, Philipp (ACM International Conference Proceeding Series, 2016)
The present work is targeted at performing a strong scaling study of the high-order spectral element uid dynamics solver Nek5000. Prior studies such as [5] indicated a recommendable metric for strong scalability from a theoretical viewpoint, which we test here extensively on three parallel machines with different performance characteristics and interconnect networks, namely Mira (IBM Blue Gene/Q), Beskow (Cray XC40) and Titan (Cray XK7). The test cases considered for the simulations correspond to a turbulent ow in a straight pipe at four different friction Reynolds numbers Reτ = 180, 360, 550 and 1000. Considering the linear model for parallel communication we quantify the machine characteristics in order to better assess the scaling behaviors of the code. Subsequently sampling and profiling tools are used to measure the computation and communication times over a large range of compute cores. We also study the effect of the two coarse grid solvers XXT and AMG on the computational time. Super-linear scaling due to a reduction in cache misses is observed on each computer. The strong scaling limit is attained for roughly 5000 - 10; 000 degrees of freedom per core on Mira, 30; 000 - 50; 0000 on Beskow, with only a small impact of the problem size for both machines, and ranges between 10; 000 and 220; 000 depending on the problem size on Titan. This work aims at being a reference for Nek5000 users and also serves as a basis for potential issues to address as the community heads towards exascale supercomputers.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Benchmarking; Computational fluid dynamics; Nek5000; Scaling

On the use of recurrent neural networks for predictions of turbulent flows - Guastoni, Luca; Srinivasan, Prem A.; Azizpour, Hossein; Schlatter, Philipp; Vinuesa, Ricardo (11th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2019, 2019)
In this paper, the prediction capabilities of recurrent neural networks are assessed in the low-order model of near-wall turbulence by Moehlis et al. (New J. Phys. 6, 56, 2004). Our results show that it is possible to obtain excellent predictions of the turbulence statistics and the dynamic behavior of the flow with properly trained long short-term memory (LSTM) networks, leading to relative errors in the mean and the fluctuations below 1%. We also observe that using a loss function based only on the instantaneous predictions of the flow may not lead to the best predictions in terms of turbulence statistics, and it is necessary to define a stopping criterion based on the computed statistics. Furthermore, more sophisticated loss functions, including not only the instantaneous predictions but also the averaged behavior of the flow, may lead to much faster neural network training.
CRIS-Team Scopus Importer:2023-03-21

OpenACC acceleration for the PN–PN-2 algorithm in Nek5000 - Otero, Evelyn; Gong, Jing; Min, Misun; Fischer, Paul; Schlatter, Philipp; Laure, Erwin (Journal of Parallel and Distributed Computing, 2019)
Due to its high performance and throughput capabilities, GPU-accelerated computing is becoming a popular technology in scientific computing, in particular using programming models such as CUDA and OpenACC. The main advantage with OpenACC is that it enables to simply port codes in their “original” form to GPU systems through compiler directives, thus allowing an incremental approach. An OpenACC implementation is applied to the CFD code Nek5000 for simulation of incompressible flows, based on the spectral-element method. The work follows up previous implementations and focuses now on the PN−PN−2 method for the spatial discretization of the Navier–Stokes equations. Performance results of the ported code show a speed-up of up to 3.1 on multi-GPU for a polynomial order N>11.
CRIS-Team Scopus Importer:2023-03-21
Keywords: GPU programming; High performance computing; Nek5000; OpenACC; Spectral element method

Parallel performance of h-type Adaptive Mesh Refinement for Nek5000 - Peplinski, Adam; Fischer, Paul F.; Schlatter, Philipp (ACM International Conference Proceeding Series, 2016)
We discuss parallel performance of h-type Adaptive Mesh Refinement (AMR) developed for the high-order spectral element solver Nek5000 within CRESTA project. AMR is a desired feature of the future simulation software, as it gives possibility to increase the accuracy of numerical simulations at minimal computational cost by resolving particular region of the domain. At the same time it increases complexity of the communication pattern and introduces load imbalance, that can have negative effect on the code scalability. In this work we concentrate on the parallel performance of different tools required by AMR and the resulting algorithm limitations. Our implementation is based on available libraries for parallel mesh management (p4est) and partitioning (ParMetis) that provide necessary information for grid refinement/coarsening and redistribution performed within nonconforming version of Nek5000. For simplicity we consider advection-diffusion problem instead of the full Navies-Stokes equations and study both strong and weak scalability for the convected-cone problem. It is a synthetic test case allowing to test AMR with frequent dynamic mesh adjustments.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Large-scale scientific computing; Nonconforming methods; Parallel adaptive mesh refinement; Spectral elements

Parametric dependencies of the yawed wind-turbine wake development - Kleusberg, Elektra; Schlatter, Philipp; Henningson, Dan S. (Wind Energy, 2020)
Yaw misalignment is currently being treated as one of the most promising methods for optimizing the power of wind farms. Therefore, detailed knowledge of the impact of yaw on the wake development is necessary for a range of operating conditions. This study numerically investigates the wake development behind a single yawed wind turbine operating at different tip-speed ratios and yaw angles using the actuator-line method in the spectral-element code Nek5000. It is shown that depending on the tip-speed ratio, the blade loading varies along the azimuth, resulting in a wake that is asymmetric in both the horizontal and vertical directions. Large tip-speed ratios as well as large yaw angles are shown to decrease the vertical asymmetry of the yaw-induced counter-rotating vortex pair. Both parameters have the effect that they increase the spanwise force induced by yaw relative to the wake rotation. However, while the strength of the counter-rotating vortex pair in the far wake increases with yaw angle, it is shown to decrease with the tip-speed ratio. The vertical shift in the wake center is found to be highly dependent on the yaw angle and the tip-speed ratio. These detailed insights into the yawed wake are important when optimizing potential downstream turbines.
CRIS-Team Scopus Importer:2023-03-21
Keywords: actuator-line method; CFD; spectral-element method; wake breakdown; wind turbine; yaw

Particle transport in turbulent curved pipe flow - Noorani, Azad; Sardina, Gaetano; Brandt, Luca; Schlatter, Philipp (Journal of Fluid Mechanics, 2016)
Direct numerical simulations (DNS) of particle-laden turbulent flow in straight, mildly curved and strongly bent pipes are performed in which the solid phase is modelled as small heavy spherical particles. A total of seven populations of dilute particles with different Stokes numbers, one-way coupled with their carrier phase, are simulated. The objective is to examine the effect of the curvature on micro-particle transport and accumulation. It is shown that even a slight non-zero curvature in the flow configuration strongly impact the particle concentration map such that the concentration of inertial particles with bulk Stokes number (based on bulk velocity and pipe radius) at the inner bend wall of mildly curved pipe becomes times larger than that in the viscous sublayer of the straight pipe. Near-wall helicoidal particle streaks are observed in the curved configurations with their inclination varying with the strength of the secondary motion of the carrier phase. A reflection layer, as previously observed in particle laden turbulent S-shaped channels, is also apparent in the strongly curved pipe with heavy particles. In addition, depending on the curvature, the central regions of the mean Dean vortices appear to be completely depleted of particles, as observed also in the partially relaminarised region at the inner bend. The turbophoretic drift of the particles is shown to be affected by weak and strong secondary motions of the carrier phase and geometry-induced centrifugal forces. The first-and second-order moments of the velocity and acceleration of the particulate phase in the same configurations are addressed in a companion paper by the same authors. The current data set will be useful for modelling particles advected in wall-bounded turbulent flows where the effects of the curvature are not negligible.
CRIS-Team Scopus Importer:2023-03-21
Keywords: multiphase flow; particle/fluid flow; turbulence simulation

Particle Velocity and Acceleration in Turbulent Bent Pipe Flows - Noorani, Azad; Sardina, Gaetano; Brandt, Luca; Schlatter, Philipp (Flow Turbulence and Combustion, 2015)
We study the dynamics of dilute micro-size inertial particles in turbulent curved pipe flows of different curvature by means of direct numerical simulations with one-way coupled Lagrangian particle tracking. The focus of this work is on the first and second order moments of the velocity and acceleration of the particulate phase, relevant statistics for any modelling effort, whereas the particle distribution is analysed in a previous companion paper. The aim is to understand the role of the cross-stream secondary motions (Dean vortices) on the particle dynamics. We identify the mean Dean vortices associated to the motion of the particles and show that these are moved towards the side-walls and, interestingly, more intense than those of the mean flow. Analysis of the streamwise particle flux reveals a substantial increase due to the secondary motions that brings particles towards the pipe core while moving them towards the outer bend. The in-plane particle flux, most intense in the flow viscous sub-layer along the side walls, increases with particle inertia and pipe curvature. The particle reflections at the outer bend, previously observed also in other strongly curved configurations, locally alter the particle axial and wall-normal velocity and increase turbulent kinetic energy.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Bent pipe; Curvature effect; Gas-solid flow; Particle transport; Particulate dispersion; Secondary motion

Pattern formation in low Reynolds number plane Couette flow - Duguet, Y.; Schlatter, Philipp; Henningson, D. S. (Springer Proceedings in Physics, 2009)
Plane Couette flow is the flow between two counter-sliding plates of velocity U separated by a gap 2h. It has a simple laminar solution with constant shear which is stable for all values of the Reynolds number (v is the kinematic viscosity of the fluid). However, transition to turbulence is observed experimentally above a threshold value of Re between 300 and 400. Whereas featureless turbulence is seen for Re ≥ 400, lower-Re experiments have shown a turbulent regime displaying spatio-temporal intermittency effects, notably the appearance of turbulent stripes, inclined with respect to the direction of the base flow, interspersed with quiescent, nearly laminar regions [1], see Figure 1. It is the ‘fspiral turbulence’ regime, so-called because it has also been identified in Taylor-Couette experiments. Similar patterns have also been numerically reproduced in a minimal-like computational domain (of size 10h in length and 40h in width), oriented against the inclination of one stripe [2]. This reduced computational box allows to understand locally the appearance and teh stability of these localised structures.
CRIS-Team Scopus Importer:2023-03-21

Performance of preconditioners for large-scale simulations using nek5000 - Offermans, N.; Peplinski, A.; Marin, O.; Merzari, E.; Schlatter, Philipp (Lecture Notes in Computational Science and Engineering, 2020)
BoomerAMG, the algebraic multigrid solver from the hypre library, is used to solve a coarse grid problem which is part of the preconditioning strategy for the pressure equation arising from the numerical resolution of the Navier–Stokes equations. A set of optimal parameters for the setup phase is determined and used for selected strong scaling tests on two different supercomputers, namely Mira and Hazel Hen, on up to 131, 072 compute cores. The results are compared to an existing algebraic multigrid solver, designed specifically for the coarse grid problem at hand. It is shown that the BoomerAMG solver is fast and scalable, and that performance depends on the computer architecture. The test cases considered are the turbulent flow past a NACA4412 airfoil and the turbulent flow inside wire-tapped pin bundles.
CRIS-Team Scopus Importer:2023-03-21

Physics-informed neural networks for solving Reynolds-averaged Navier-Stokes equations - Eivazi, Hamidreza; Tahani, Mojtaba; Schlatter, Philipp; Vinuesa, Ricardo (Physics of Fluids, 2022)
Physics-informed neural networks (PINNs) are successful machine-learning methods for the solution and identification of partial differential equations. We employ PINNs for solving the Reynolds-averaged Navier-Stokes equations for incompressible turbulent flows without any specific model or assumption for turbulence and by taking only the data on the domain boundaries. We first show the applicability of PINNs for solving the Navier-Stokes equations for laminar flows by solving the Falkner-Skan boundary layer. We then apply PINNs for the simulation of four turbulent-flow cases, i.e., zero-pressure-gradient boundary layer, adverse-pressure-gradient boundary layer, and turbulent flows over a NACA4412 airfoil and the periodic hill. Our results show the excellent applicability of PINNs for laminar flows with strong pressure gradients, where predictions with less than 1% error can be obtained. For turbulent flows, we also obtain very good accuracy on simulation results even for the Reynolds-stress components.
CRIS-Team Scopus Importer:2023-03-21

Power-Spectral Density in Turbulent Boundary Layers on Wings - Tanarro; Vinuesa, R.; Schlatter, Philipp (Springer, 2020)
Turbulent boundary layers (TBLs) subjected to various amplitudes of adverse pressure gradients (APGs) are of paramount importance in the field of fluid dynamics due to their implications in countless industrial applications in which the flow develops on a curved surface such as wings or nozzles, among others.
CRIS-Team Scopus Importer:2023-03-21

Predicting the temporal dynamics of turbulent channels through deep learning - Borrelli, Giuseppe; Guastoni, Luca; Eivazi, Hamidreza; Schlatter, Philipp; Vinuesa, Ricardo (International Journal of Heat and Fluid Flow, 2022)
The success of recurrent neural networks (RNNs) has been demonstrated in many applications related to turbulence, including flow control, optimization, turbulent features reproduction as well as turbulence prediction and modeling. With this study we aim to assess the capability of these networks to reproduce the temporal evolution of a minimal turbulent channel flow. We first obtain a data-driven model based on a modal decomposition in the Fourier domain (which we denote as FFT-POD) of the time series sampled from the flow. This particular case of turbulent flow allows us to accurately simulate the most relevant coherent structures close to the wall. Long-short-term-memory (LSTM) networks and a Koopman-based framework (KNF) are trained to predict the temporal dynamics of the minimal-channel-flow modes. Tests with different configurations highlight the limits of the KNF method compared to the LSTM, given the complexity of the flow under study. Long-term prediction for LSTM show excellent agreement from the statistical point of view, with errors below 2% for the best models with respect to the reference. Furthermore, the analysis of the chaotic behaviour through the use of the Lyapunov exponents and of the dynamic behaviour through Poincaré maps emphasizes the ability of the LSTM to reproduce the temporal dynamics of turbulence. Alternative reduced-order models (ROMs), based on the identification of different turbulent structures, are explored and they continue to show a good potential in predicting the temporal dynamics of the minimal channel.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Data-driven analysis; Deep-learning; Fourier POD (FFT-POD); Long-short-term-memory (LSTM) networks; Minimal channel flow; Turbulent flows

Predicting the wall-shear stress and wall pressure through convolutional neural networks - Balasubramanian, A. G.; Guastoni, L.; Schlatter, Philipp; Azizpour, H.; Vinuesa, R. (International Journal of Heat and Fluid Flow, 2023)
The objective of this study is to assess the capability of convolution-based neural networks to predict the wall quantities in a turbulent open channel flow, starting from measurements within the flow. Gradually approaching the wall, the first tests are performed by training a fully-convolutional network (FCN) to predict the two-dimensional velocity-fluctuation fields at the inner-scaled wall-normal location ytarget+, using the sampled velocity fluctuations in wall-parallel planes located farther from the wall, at yinput+. The predictions from the FCN are compared against the predictions from a proposed R-Net architecture as a part of the network investigation study. Since the R-Net model is found to perform better than the FCN model, the former architecture is optimized to predict the two-dimensional streamwise and spanwise wall-shear-stress components and the wall pressure from the sampled velocity-fluctuation fields farther from the wall. The data for training and testing is obtained from direct numerical simulation (DNS) of open channel flow at friction Reynolds numbers Reτ=180 and 550. The turbulent velocity-fluctuation fields are sampled at various inner-scaled wall-normal locations, i.e. y+=15,30,50,100,150, along with the wall-shear stress and the wall pressure. At Reτ=550, both FCN and R-Net can take advantage of the self-similarity in the logarithmic region of the flow and predict the velocity-fluctuation fields at y+=50 using the velocity-fluctuation fields at y+=100 as input with about 10% error in prediction of streamwise-fluctuations intensity. Further, the network model trained in this work is also able to predict the wall-shear-stress and wall-pressure fields using the velocity-fluctuation fields at y+=50 with around 10% error in the intensity of the corresponding fluctuations at both Reτ=180 and 550. These results are an encouraging starting point to develop neural-network-based approaches for modelling turbulence near the wall in numerical simulations, especially large-eddy simulations (LESs).
CRIS-Team Scopus Importer:2023-08-11
Keywords: Deep learning; Fully convolutional network; Self-similarity; Turbulent channel flow; Wall-shear stress

Prediction of wall-bounded turbulence from wall quantities using convolutional neural networks - Guastoni, Luca; Encinar, Miguel P.; Schlatter, Philipp; Azizpour, Hossein; Vinuesa, Ricardo (Journal of Physics: Conference Series, 2020)
A fully-convolutional neural-network model is used to predict the streamwise velocity fields at several wall-normal locations by taking as input the streamwise and spanwise wall-shear-stress planes in a turbulent open channel flow. The training data are generated by performing a direct numerical simulation (DNS) at a friction Reynolds number of Reτ = 180. Various networks are trained for predictions at three inner-scaled locations (y+ = 15, 30, 50) and for different time steps between input samples Δt+ s. The inherent non-linearity of the neural-network model enables a better prediction capability than linear methods, with a lower error in both the instantaneous flow fields and turbulent statistics. Using a dataset with higher Δt+ s improves the generalization at all the considered wall-normal locations, as long as the network capacity is sufficient to generalize over the dataset. The use of a multiple-output network, with parallel dedicated branches for two wall-normal locations, does not provide any improvement over two separated single-output networks, other than a moderate saving in training time. Training time can be effectively reduced, by a factor of 4, via a transfer learning method that initializes the network parameters using the optimized parameters of a previously-trained network.
CRIS-Team Scopus Importer:2023-03-21

Predictions of turbulent shear flows using deep neural networks - Srinivasan, P. A.; Guastoni, L.; Azizpour, H.; Schlatter, Philipp; Vinuesa, Ricardo (Physical Review Fluids, 2019)
In the present work, we assess the capabilities of neural networks to predict temporally evolving turbulent flows. In particular, we use the nine-equation shear flow model by Moehlis et al. [New J. Phys. 6, 56 (2004)NJOPFM1367-263010.1088/1367-2630/6/1/056] to generate training data for two types of neural networks: the multilayer perceptron (MLP) and the long short-term memory (LSTM) networks. We tested a number of neural network architectures by varying the number of layers, number of units per layer, dimension of the input, and weight initialization and activation functions in order to obtain the best configurations for flow prediction. Because of its ability to exploit the sequential nature of the data, the LSTM network outperformed the MLP. The LSTM led to excellent predictions of turbulence statistics (with relative errors of 0.45% and 2.49% in mean and fluctuating quantities, respectively) and of the dynamical behavior of the system (characterized by Poincaré maps and Lyapunov exponents). This is an exploratory study where we consider a low-order representation of near-wall turbulence. Based on the present results, the proposed machine-learning framework may underpin future applications aimed at developing accurate and efficient data-driven subgrid-scale models for large-eddy simulations of more complex wall-bounded turbulent flows, including channels and developing boundary layers.
CRIS-Team Scopus Importer:2023-03-21

Preparing scientific application software for exascale computing - Åström, J. A.; Carter, A.; Hetherington, J.; Ioakimidis, K.; Lindahl, E.; Mozdzynski, G.; Nash, R. W.; Schlatter, Philipp; Signell, A.; Westerholm, J. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2013)
Many of the most widely used scientifc application software of today were developed largely during a time when the typical amount of compute cores was calculated in tens or hundreds. Within a not too distant future the number of cores will be calculated in at least hundreds of thousands or even millions. A European collaboration group CRESTA has recently been working on a set of renowned scientific software to investigate and develop these codes towards the realm of exascale computing. The codes are ELMFIRE, GROMACS, IFS, HemeLB, NEK5000, and OpenFOAM. This paper contains a summary of the strategies for their development towards exascale and results achieved during the first year of the collaboration project. © 2013 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Elmfire; Exascale; Gromacs; HemeLB; IFS; NEK5000; OpenFOAM; Optimization; Science Application Software

Pressure fluctuation in high-Reynolds-number turbulent boundary layer: Results from experiments and DNS - Tsuji, Yoshiyuki; Imayama, Shintaro; Schlatter, Philipp; Alfredsson, P. Henrik; Johansson, Arne V.; Marusic, Ivan; Hutchins, Nicholas; Monty, Jason (Journal of Turbulence, 2012)
We have developed a small pressure probe and measured both static pressure and wall pressure simultaneously in turbulent boundary layers up to Reynolds numbers based on the momentum thickness Rθ ≃ 44,620. The measurements were performed at large experimental facilities in Sweden, Australia, and Japan.We find that the measured pressure data are contaminated by the artificial background noise induced by test section and are also affected by the flow boundary conditions. By analyzing data from different wind tunnels acquired at the same Reynolds number, we evaluate the effect of background noises and boundary conditions on the pressure statistics. We also compare the experimental results with results of direct numerical simulations and discuss differences in boundary conditions between real and simulated wind tunnels. © 2012 Taylor & Francis.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Background noise; Direct numerical simulation; Flow boundary conditions; Outer and inner scaling; Static-pressure fluctuation; Turbulent boundary layer; Wall pressure

Pressure fluctuation in high-reynolds number turbulent boundary layer; Results from experiments and numerical simulations - Tsuji, Yoshiyuki; Imayama, Shintaro; Schlatter, Philipp; Alfredsson, P. Henrik; Johansson, Arne V. (7th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2011, 2011)
Pressure fluctuations are measured in zero-pressuregradient boundary layers. Following the previous studies, we developed the small pressure probe and measure both the static pressure inside boundary layer and wall pressure simultaneously in turbulent boundary layers up to Reynolds numbers based on the momentum thickness Rθ ≈ 20000. Discussions are made on the background pressure in the free stream region. It contaminates the physical pressure in the boundary layer. We report on the pressure intensity profile normalized by outer and inner variables. Once the background pressure is subtracted, they are compared with the results of direct numerical simulations.
CRIS-Team Scopus Importer:2023-03-21

Pressure-Gradient Turbulent Boundary Layers Developing Around a Wing Section - Vinuesa, Ricardo; Hosseini, Seyed M.; Hanifi, Ardeshir; Henningson, Dan S.; Schlatter, Philipp (Flow Turbulence and Combustion, 2017)
A direct numerical simulation database of the flow around a NACA4412 wing section at Rec = 400,000 and 5∘ angle of attack (Hosseini et al. Int. J. Heat Fluid Flow 61, 117–128, 2016), obtained with the spectral-element code Nek5000, is analyzed. The Clauser pressure-gradient parameter β ranges from ≃ 0 and 85 on the suction side, and from 0 to − 0.25 on the pressure side of the wing. The maximum Reθ and Reτ values are around 2,800 and 373 on the suction side, respectively, whereas on the pressure side these values are 818 and 346. Comparisons between the suction side with zero-pressure-gradient turbulent boundary layer data show larger values of the shape factor and a lower skin friction, both connected with the fact that the adverse pressure gradient present on the suction side of the wing increases the wall-normal convection. The adverse-pressure-gradient boundary layer also exhibits a more prominent wake region, the development of an outer peak in the Reynolds-stress tensor components, and increased production and dissipation across the boundary layer. All these effects are connected with the fact that the large-scale motions of the flow become relatively more intense due to the adverse pressure gradient, as apparent from spanwise premultiplied power-spectral density maps. The emergence of an outer spectral peak is observed at β values of around 4 for λz ≃ 0.65δ99, closer to the wall than the spectral outer peak observed in zero-pressure-gradient turbulent boundary layers at higher Reθ. The effect of the slight favorable pressure gradient present on the pressure side of the wing is opposite the one of the adverse pressure gradient, leading to less energetic outer-layer structures.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct numerical simulation; Pressure gradient; Turbulent boundary layer; Wing section

Proper orthogonal decomposition on compressed data - Marin, Oana; Merzari, Elia; Schlatter, Philipp; Siegel, Andrew (10th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2017, 2017)
The main approach to identifying coherent structures in a flow field is the Proper Orthogonal Decomposition, due to its simplicity and effectiveness. However it is a data intensive method which becomes more expensive as the data field increases in size. The difficulty pertains mostly when a three-dimensional decomposition is performed, and the limiting factor is storing and loading large data fields of up to billions of gridpoints. This restriction is a conseuqence of the fact that the I/O bandwidth of supercomputers has not been at the same developmental pace as the CPUs. Lossy compression can reduce the size of the data fields and accelerate the computations. The strategy we suggest here relies on data compression via Discrete Chebyshev Transform (or alternatively Discrete Legendre Transform) which leaves invariant the auto-correlation matrix which lies at the core of the POD method. We show that by discarding over 90% of the data we can still retrieve a good proper ortohonal basis of the data set which deviates from the original by 10-2 in the L2 norm.
CRIS-Team Scopus Importer:2023-03-21

Quantification of amplitude modulation in wall-bounded turbulence - Dogan, Eda; Orlu, Ramis; Gatti, Davide; Vinuesa, Ricardo; Schlatter, Philipp (Fluid Dynamics Research, 2019)
Many recent investigations on the scale interactions in wall-bounded turbulent flows focus on describing so-called amplitude modulation, the phenomenon that deals with the influence of large scales in the outer region on the amplitude of the small-scale fluctuations in the near-wall region. The present study revisits this phenomenon regarding two aspects, namely the method for decomposing the scales and the quantification of the modulation. First, the paper presents a summary of the literature that has dealt with either or both aspects. Second, for decomposing the scales, different spectral filters (temporal, spatial or both) and empirical mode decomposition (EMD) are evaluated and compared. The common data set is a well-resolved large-eddy simulation that offers a wide range of Reynolds numbers spanning Re θ = 880-8200. The quantification of the amplitude modulation is discussed for the resulting scale components. Particular focus is given to evaluate the efficacy of the various filters to separate scales for the range of Reynolds numbers of interest. Different to previous studies, the different methods have been evaluated using the same data set, thereby allowing a fair comparison between the various approaches. It is observed that using a spectral filter in the spanwise direction is an effective approach to separate the small and large scales in the flow, even at comparably low Reynolds numbers, whereas filtering in time should be approached with caution in the low-to-moderate Re range. Additionally, using filters in both spanwise and time directions, which would separate both wide and long-living structures from the small and fast scales, gives a cleaner image for the small-scales although the contribution to the scales interaction from that filter implementation has been found negligible. Applying EMD to decompose the scales gives similar results to Fourier filters for the energy content of the scales and thereby for the quantification of the amplitude modulation using the decomposed scales. No direct advantage of EMD over classical Fourier filters could be seen. Potential issues regarding different decomposition methods and different definitions of the amplitude modulation are also discussed.
CRIS-Team Scopus Importer:2023-03-21
Keywords: amplitude modulation; scale interaction; turbulent boundary layer

Quantifying the interaction between large and small scales in wall-bounded turbulent flows: A note of caution - Schlatter, Philipp; Orlu, Ramis (Physics of Fluids, 2010)
Turbulent flow close to solid walls is dominated by an ensemble of fluctuations of large and small spatial scales. Recent work by Mathis et al. [J. Fluid Mech.628, 311 (2009); Phys. Fluids21, 111703 (2009)] introduced and used a decoupling procedure based on the Hilbert transformation applied to the filtered small-scale component of the fluctuating streamwise velocity. This method is employed as a robust tool to quantify a dominant amplitude modulation of the small scales by the large scales found in the outer part of the boundary layer. In the present study, however, we demonstrate by means of experimental and synthetic signals that the correlation coefficient used to quantify the amplitude modulation is related to the skewness of the original signal, and hence, for the Reynolds numbers considered here, may not be an independent tool to unambiguously detect or quantify the effect of large-scale amplitude modulation of the small scales. © 2010 American Institute of Physics.
CRIS-Team Scopus Importer:2023-03-21

RANS Modelling of a NACA4412 Wake Using Wind Tunnel Measurements - Tabatabaei, Narges; Hajipour, Majid; Mallor, Fermin; Orlu, Ramis; Vinuesa, Ricardo; Schlatter, Philipp (Fluids, 2022)
Wake analysis plays a significant role in wind-farm planning through the evaluation of losses and energy yield. Wind-tunnel tests for wake studies have high costs and are time-consuming. Therefore, computational fluid dynamics (CFD) emerges as an efficient alternative. An especially attractive approach is based on the solution of the Reynolds-averaged Navier–Stokes (RANS) equations with two-equation turbulence closure models. The validity of this approach and its inherent limitations, however, remain to be fully understood. To this end, detailed wind-tunnel experiments in the wake of a NACA4412 wing section profile are compared with CFD results. Two-and three-dimensional RANS simulations are carried out for a range of angles of attack up to stall conditions at a chord-and inflow-based Reynolds number of Rec = 4 × 105. Here, we aim to investigate the wake characteristics and self-similar behaviour, both from the experimental and numerical perspectives. The measurements are carried out by means of hot-wire anemometry capturing the wake pattern in several planes. The sensitivity of the CFD model to different configurations of the setup and the considerations required for reliable simulation are discussed. The agreement between CFD, experiments, and the literature is fairly good in many aspects, including the self-similar behaviour and wake parameters, as well as the flow field. Comparison of experiments with URANS/RANS data indicates that the latter is an adequate methodology to characterize wings and their wakes once the CFD setup is designed appropriately and the limitations due to discretization and turbulence modelling are considered.
CRIS-Team Scopus Importer:2023-03-21
Keywords: airfoil wake; RANS modelling; wind tunnel measurement

Rare backflow and extreme wall-normal velocity fluctuations in near-wall turbulence - Lenaers, Peter; Li, Qiang; Brethouwer, Geert; Schlatter, Philipp; Orlu, Ramis (Physics of Fluids, 2012)
Rare negative streamwise velocities and extreme wall-normal velocity fluctuations near the wall are investigated for turbulent channel flow at a series of Reynolds numbers based on friction velocity up to Reτ = 1000. Probability density functions of the wall-shear stress and velocity components are presented as well as joint probability density functions of the velocity components and the pressure. Backflow occurs more often (0.06% at the wall at Reτ = 1000) and further away (up to y+ = 8.5) from the wall for increasing Reynolds number. The regions of backflow are circular with an average diameter, based on ensemble averages, of approximately 20 viscous units independent of Reynolds number. A strong oblique vortex outside the viscous sublayer is found to cause this backflow. Extreme wall-normal velocity events occur also more often for increasing Reynolds number. These extreme fluctuations cause high flatness values near the wall (F(v) = 43 at Reτ = 1000). Positive and negative velocity spikes appear in pairs, located on the two edges of a strong streamwise vortex as documented by Xu et al. [Phys. Fluids8, 1938 (1996)]10.1063/1.868973 for Reτ = 180. The spikes are elliptical and orientated in streamwise direction with a typical length of 25 and a typical width of 7.5 viscous units at y+ ≈ 1. The negative spike occurs in a high-speed streak indicating a sweeping motion, while the positive spike is located in between a high and low-speed streak. The joint probability density functions of negative streamwise and extreme wall-normal velocity events show that these events are largely uncorrelated. The majority of both type of events can be found lying underneath a large-scale structure in the outer region with positive sign, which can be understood by considering the more intense velocity fluctuations due to amplitude modulation of the inner layer by the outer layer. Simulations performed at different resolutions give only minor differences. Results from experiments and recent turbulent boundary layer simulations show similar results indicating that these rare events are universal for wall-bounded flows. In order to detect these rare events in experiments, measurement techniques have to be specifically tuned. © 2012 American Institute of Physics.
CRIS-Team Scopus Importer:2023-03-21

Recurrent bursts via linear processes in turbulent environments - Brethouwer, Geert; Schlatter, Philipp; Duguet, Yohann; Henningson, Dan S.; Johansson, Arne V. (Physical Review Letters, 2014)
Large-scale instabilities occurring in the presence of small-scale turbulent fluctuations are frequently observed in geophysical or astrophysical contexts but are difficult to reproduce in the laboratory. Using extensive numerical simulations, we report here on intense recurrent bursts of turbulence in plane Poiseuille flow rotating about a spanwise axis. A simple model based on the linear instability of the mean flow can predict the structure and time scale of the nearly periodic and self-sustained burst cycles. Poiseuille flow is suggested as a prototype for future studies of low-dimensional dynamics embedded in strongly turbulent environments. © 2014 American Physical Society.
CRIS-Team Scopus Importer:2023-03-21

Recurrent neural networks and Koopman-based frameworks for temporal predictions in a low-order model of turbulence - Eivazi, Hamidreza; Guastoni, Luca; Schlatter, Philipp; Azizpour, Hossein; Vinuesa, Ricardo (International Journal of Heat and Fluid Flow, 2021)
The capabilities of recurrent neural networks and Koopman-based frameworks are assessed in the prediction of temporal dynamics of the low-order model of near-wall turbulence by Moehlis et al. (New J. Phys. 6, 56, 2004). Our results show that it is possible to obtain excellent reproductions of the long-term statistics and the dynamic behavior of the chaotic system with properly trained long-short-term memory (LSTM) networks, leading to relative errors in the mean and the fluctuations below 1%. Besides, a newly developed Koopman-based framework, called Koopman with nonlinear forcing (KNF), leads to the same level of accuracy in the statistics at a significantly lower computational expense. Furthermore, the KNF framework outperforms the LSTM network when it comes to short-term predictions. We also observe that using a loss function based only on the instantaneous predictions of the chaotic system can lead to suboptimal reproductions in terms of long-term statistics. Thus, we propose a model-selection criterion based on the computed statistics which allows to achieve excellent statistical reconstruction even on small datasets, with minimal loss of accuracy in the instantaneous predictions.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Data-driven modeling; Dynamical systems; Koopman operator; Machine learning; Recurrent neural networks

Reduced-order models for flow control: Balanced models and Koopman modes - Rowley, Clarence W.; Mezic, Igor; Bagheri, Shervin; Schlatter, Philipp; Henningson, Dan S. (IUTAM Bookseries, 2010)
This paper addresses recent developments in model-reduction techniques applicable to fluid flows. The main goal is to obtain low-order models tractable enough to be used for analysis and design of feedback laws for flow control, while retaining the essential physics. We first give a brief overview of several model reduction techniques, including Proper Orthogonal Decomposition [3], balanced truncation [8, 9], and the related Eigensystem Realization Algorithm [5, 6], and discuss strengths and weaknesses of each approach. We then describe a new method for analyzing nonlinear flows based on spectral analysis of the Koopman operator, a linear operator defined for any nonlinear dynamical system. We show that, for an example of a jet in crossflow, the resulting Koopman modes decouple the dynamics at different timescales more effectively than POD modes, and capture the relevant frequencies more accurately than linear stability analysis. © 2010 Springer Science+Business Media B.V.
CRIS-Team Scopus Importer:2023-03-21

Reduced-order models to analyse coherent structures in turbulent pipe flow - Abreu, Leandra I.; Cavalieri, André V.G.; Schlatter, Philipp; Vinuesa, Ricardo; Henningson, Dan (11th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2019, 2019)
Fully resolved direct numerical simulations, performed with a high-order spectral-element method, are used to study coherent structures in turbulent pipe flow at friction Reynolds numbers Reτ = 180 and 550 (El Khoury et al., 2013). The database was analysed using spectral proper orthogonal decomposition (SPOD) so as to identify dominant coherent structures, most of which are of streaky shape. As a reduced-order model for such structures, the linearised flow response to harmonic forcing was computed, and the analysed singular modes of the resolvent operator were analysed. For turbulent flows, this approach amounts to considering the non-linear terms in the Navier–Stokes system as an unknown forcing, treated convenienty as external. Resolvent analysis then allows an identification of the optimal forcing and most amplified flow response; the latter may be related to observed relevant structures obtained by SPOD, especially if the gain between forcing and response is much larger than what is found for suboptimal forcings or if the non-linear forcing is white noise. Results from SPOD and resolvent analysis were extracted for several combinations of frequencies, streamwise and azimuthal wavenumbers. For both Reynolds numbers, good agreement between SPOD and resolvent modes was observed for parameter combinations where the lift-up mechanism is present: optimal forcing from resolvent analysis represents streamwise vortices and the associated response are streaky structures.
CRIS-Team Scopus Importer:2023-03-21

Reducing Communication in the Conjugate Gradient Method: A Case Study on High-Order Finite Elements - Karp, Martin; Jansson, Niclas; Podobas, Artur; Schlatter, Philipp; Markidis, Stefano (Proceedings of the Platform for Advanced Scientific Computing Conference, PASC 2022, 2022)
Currently, a major bottleneck for several scientific computations is communication, both communication between different processors, so-called horizontal communication, and vertical communication between different levels of the memory hierarchy. With this bottleneck in mind, we target a notoriously communication-bound solver at the core of many high-performance applications, namely the conjugate gradient method (CG). To reduce the communication we present lower bounds on the vertical data movement in CG and go on to make a CG solver with reduced data movement. Using our theoretical analysis we apply our CG solver on a high-performance discretization used in practice, the spectral element method (SEM). Guided by our analysis, we show that for the Poisson equation on modern GPUs we can improve the performance by 30% by both rematerializing the discrete system and by reformulating the system to work on unique degrees of freedom. In order to investigate how horizontal communication can be reduced, we compare CG to two communication-reducing techniques, namely communication-avoiding and pipelined CG. We strong scale up to 4096 CPU cores and showcase performance improvements of upwards of 70% for pipelined CG compared to standard CG when applied on SEM at scale. We show that in addition to improving the scaling capabilities of the solver, initial measurements indicate that the convergence of SEM is largely unaffected by pipelined CG.
CRIS-Team Scopus Importer:2023-03-21

Reprint of: Influence of corner geometry on the secondary flow in turbulent square ducts - Vidal, A.; Vinuesa, Ricardo; Schlatter, Philipp; Nagib, H. M. (International Journal of Heat and Fluid Flow, 2017)
Direct numerical simulations of fully-developed turbulent flow through a straight square duct with increasing corner rounding radius r were performed to study the influence of corner geometry on the secondary flow. Unexpectedly, the increased rounding of the corners from r=0 to 0.75 does not lead to a monotonic trend towards the pipe case of r=1. Instead, the secondary vortices relocate close to the region of wall-curvature change. This behavior is connected to the inhomogeneous interaction between near-wall bursting events, which are further characterized in this work with the definition of their local preferential direction. We compare our results with those obtained for the flow through a square duct (which corresponds to r=0) and through a round pipe (r=1), focusing on the influence of r on the wall-shear stress distribution and the turbulence statistics along the centerplane and the corner bisector. The former shows that high-speed streaks are preferentially located near the transition between straight and curved surfaces. The Reynolds numbers based on the centerplane friction velocity and duct half-height are Reτ, c ≃ 180 and 350 for the cases under study.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Corner geometry; Direct numerical simulation; Secondary motions; Turbulent duct flow; Wall-bounded turbulence

Resolvent modelling of near-wall coherent structures in turbulent channel flow - Abreu, Leandra; Cavalieri, Andre V. G.; Schlatter, Philipp; Vinuesa, Ricardo; Henningson, Dan S. (International Journal of Heat and Fluid Flow, 2020)
Turbulent channel flow was analysed using direct numerical simulations at friction Reynolds numbers Reτ=180 and 550. The databases were studied using spectral proper orthogonal decomposition (SPOD) to identify dominant near-wall coherent structures, most of which turn out to be streaks and streamwise vortices. Resolvent analysis was used as a theoretical approach to model such structures, as it allows the identification of the optimal forcing and most amplified flow response; the latter may be related to the observed relevant structures obtained by SPOD, especially if the gain between forcing and response is much larger than what is found for suboptimal forcings or if the non-linear forcing is white noise. Results from SPOD and resolvent analysis were compared for several combinations of frequencies and wavenumbers. For both Reynolds numbers, the best agreement between SPOD and resolvent modes was observed for the cases where the lift-up mechanism from resolvent analysis is present, which are also the cases where the optimal resolvent gain is dominant. These results confirm the outcomes in our previous studies (Abreu et al., 2019; Abreu et al., 2020), where we used a DNS database of a pipe flow for the same Reynolds numbers.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Coherent structures; Resolvent analysis; SPOD; Wall-bounded turbulence

Revisiting History Effects in Adverse-Pressure-Gradient Turbulent Boundary Layers - Vinuesa, Ricardo; Orlu, Ramis; Sanmiguel Vila, Carlos; Ianiro, Andrea; Discetti, Stefano; Schlatter, Philipp (Flow Turbulence and Combustion, 2017)
The goal of this study is to present a first step towards establishing criteria aimed at assessing whether a particular adverse-pressure-gradient (APG) turbulent boundary layer (TBL) can be considered well-behaved, i.e., whether it is independent of the inflow conditions and is exempt of numerical or experimental artifacts. To this end, we analyzed several high-quality datasets, including in-house numerical databases of APG TBLs developing over flat-plates and the suction side of a wing section, and five studies available in the literature. Due to the impact of the flow history on the particular state of the boundary layer, we developed three criteria of convergence to well-behaved conditions, to be used depending on the particular case under study. (i) In the first criterion, we develop empirical correlations defining the Reθ-evolution of the skin-friction coefficient and the shape factor in APG TBLs with constant values of the Clauser pressure-gradient parameter β = 1 and 2 (note that β = δ∗/τwdPe/dx, where δ∗ is the displacement thickness, τw the wall-shear stress and dPe/dx the streamwise pressure gradient). (ii) In the second one, we propose a predictive method to obtain the skin-friction curve corresponding to an APG TBL subjected to any streamwise evolution of β, based only on data from zero-pressure-gradient TBLs. (iii) The third method relies on the diagnostic-plot concept modified with the shape factor, which scales APG TBLs subjected to a wide range of pressure-gradient conditions. These three criteria allow to ensure the correct flow development of a particular TBL, and thus to separate history and pressure-gradient effects in the analysis.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Flow history; Numerical simulation; Pressure gradient; Turbulent boundary layer

Reynolds number dependence of large-scale friction control in turbulent channel flow - Canton, Jacopo; Orlu, Ramis; Chin, Cheng; Schlatter, Philipp (Physical Review Fluids, 2016)
The present work investigates the effectiveness of the control strategy introduced by Schoppa and Hussain [Phys. Fluids 10, 1049 (1998)PHFLE61070-663110.1063/1.869789] as a function of Reynolds number (Re). The skin-friction drag reduction method proposed by these authors, consisting of streamwise-invariant, counter-rotating vortices, was analyzed by Canton et al. [Flow, Turbul. Combust. 97, 811 (2016)1386-618410.1007/s10494-016-9723-8] in turbulent channel flows for friction Reynolds numbers (Reτ) corresponding to the value of the original study (i.e., 104) and 180. For these Re, a slightly modified version of the method proved to be successful and was capable of providing a drag reduction of up to 18%. The present study analyzes the Reynolds number dependence of this drag-reducing strategy by performing two sets of direct numerical simulations (DNS) for Reτ=360 and 550. A detailed analysis of the method as a function of the control parameters (amplitude and wavelength) and Re confirms, on the one hand, the effectiveness of the large-scale vortices at low Re and, on the other hand, the decreasing and finally vanishing effectiveness of this method for higher Re. In particular, no drag reduction can be achieved for Reτ=550 for any combination of the parameters controlling the vortices. For low Reynolds numbers, the large-scale vortices are able to affect the near-wall cycle and alter the wall-shear-stress distribution to cause an overall drag reduction effect, in accordance with most control strategies. For higher Re, instead, the present method fails to penetrate the near-wall region and cannot induce the spanwise velocity variation observed in other more established control strategies, which focus on the near-wall cycle. Despite the negative outcome, the present results demonstrate the shortcomings of the control strategy and show that future focus should be on methods that directly target the near-wall region or other suitable alternatives.
CRIS-Team Scopus Importer:2023-03-21

Role of data uncertainties in identifying the logarithmic region of turbulent boundary layers - Vinuesa, Ricardo; Schlatter, Philipp; Nagib, Hassan M. (Experiments in Fluids, 2014)
Composite expansions based on the log-law and the power-law were used to generate synthetic velocity profiles of zero pressure gradient turbulent boundary layers (TBLs) in the range of Reynolds number 800 ≤ R e θ ≤ 860, 000, based on displacement thickness and freestream velocity. Several artificial errors were added to the velocity profiles to simulate typical measurement uncertainties. The effects of the simulated errors were studied by extracting log-law and power-law parameters from all these pseudo-experimental profiles. Various techniques were used to establish a measure of the deviations in the overlap region. When parameters extracted for the log-law and the power-law are associated with similar levels of deviations with respect to their expected values, we consider that the profile leads to ambiguous conclusions. This ambiguity was observed up to R e θ = 16, 000 for a 4 % dispersion in the velocity measurements, up to R e θ = 8.6 × 10 5 for a 400 μm uncertainty in probe position (in air flow at atmospheric pressure), and up to R eθ = 32, 000 for 3 % uncertainty in the determination of uτ. In addition, a new method for the determination of the log-law limits is proposed. The results clearly serve as a further note for caution when identifying either a log or a power-law in TBLs. Together with a number of available studies in the literature, the present results can be seen as a additional reconfirmation of the log-law. © 2014 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-21

Scaling of adverse-pressure-gradient turbulent boundary layers in near-equilibrium conditions - Vinuesa, Ricardo; Bobke, Alexandra; Orlu, Ramis; Schlatter, Philipp (Springer Proceedings in Physics, 2017)
Well-resolved large-eddy simulations are used to study adverse-pressure-gradient (APG) turbulent boundary layers (TBLs) under near-equilibrium conditions. In particular, we focus on two near-equilibrium cases where the power-law freestream velocity distribution is adjusted in order to produce long regions with a constant value of the Clauser pressure-gradient parameter β. In the first case we obtain an APG TBL with a constant value of β ≃ 1 over 37 average boundary-layer thicknesses, and in the second one a constant value of β ≃ 2 for around 28 average boundary-layer thicknesses. The scaling law suggested by Kitsios et al. (Int J Heat Fluid Flow 61:117–128, 2016, [10]), proposing the edge velocity and the displacement thickness as scaling parameters, was tested on the two constant-pressure-gradient parameter cases. The mean velocity and Reynolds-stress profiles were found to be dependent on the downstream development, a conclusion in agreement with classical theory.
CRIS-Team Scopus Importer:2023-03-21

Scaling of small-scale motions in wall-bounded turbulent flows - Wei, Liang; Brethouwer, Geert; Elsinga, Gerrit E.; Schlatter, Philipp; Johansson, Arne V. (International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2013, 2013)
The objective is to investigate flow topology and related Reynolds-number scaling in the eigenframe of the strain-rate tensor for wall-bounded turbulent flows. The databases used in the current study are from direct numerical simulations (DNS) of fully developed channel flow up to friction Reynolds number Ret ≈ 1500, and a spatially developing, zero-pressure-gradient turbulent boundary layer up to Reθ ≈ 4300 (Ret ≈ 1400)., and a spatially developing, zero-pressure-gradient turbulent boundary layer up to Reθ ≈ 4300 (Ret ≈ 1400).. It is found that for all cases considered, the averaged flow patterns in the local strainrate eigenframe appear universal: large scale motions are separated by a shear layer with a pair of vortices. Based on Kolmogorov (η,uη), Taylor (lt) and integral length scales, Reynolds-number scalings of the averaged flow patterns, including the thickness and strength of the shear layer, the distance between the two vortical regions, and the velocity distribution along the most compressing and stretching directions are considered. It is found that the Taylor scaling of the profiles for the thickness of the shear layer seems more suitable than the Kolmogorov scaling, and the integral scaling collapses well away from the shear layer, which confirms that those patterns represent large scales. Generally speaking, the scaling profiles based on the Kolmogorov length and velocity collapse well near the origin, but the Taylor scaling seems best suited in a broader region.
CRIS-Team Scopus Importer:2023-03-21

Scalings of the outer energy source of wall-turbulence - Cimarelli, A.; de Angelis, E.; Schlatter, Philipp; Brethouwer, G.; Talamelli, A.; Casciola, C. M. (ETC 2013 - 14th European Turbulence Conference, 2020)
By means of the multidimensional description given by the Kolmogorov equation we study the energy transfer physics and the production mechanisms of wall-turbulent flows at moderately high Reynolds numbers. Two driving mechanisms are identified for the energy fluxes. The first stronger one, here called driving scale-range (DSR), belongs to the near-wall cycle. As expected, its topology remains unaltered with Reynolds number while its intensity is found to slightly increase with Re. The second mechanism, here called outer scale-range (OSR), takes place in the overlap layer and highlights different features in agreement with the attached eddies hypothesis usually considered to describe the overlap dynamics.
CRIS-Team Scopus Importer:2023-03-21

Secondary flow in spanwise-periodic in-phase sinusoidal channels - Vidal, A.; Nagib, H. M.; Schlatter, Philipp; Vinuesa, Ricardo (Journal of Fluid Mechanics, 2018)
Direct numerical simulations (DNSs) are performed to analyse the secondary flow of Prandtl's second kind in fully developed spanwise-periodic channels with in-plane sinusoidal walls. The secondary flow is characterized for different combinations of wave parameters defining the wall geometry at and 5000, where is the half-height of the channel. The total cross-flow rate in the channel is defined along with a theoretical model to predict its behaviour. Interaction between the secondary flows from opposite walls is observed if, where and are the amplitude and wavelength of the sinusoidal function defining the wall geometry. As the outer-scaled wavelength is reduced, the secondary vortices become smaller and faster, increasing the total cross-flow rate per wall. However, if the inner-scaled wavelength is below 130 viscous units, the cross-flow decays for smaller wavelengths. By analysing cases in which the wavelength of the wall is much smaller than the half-height of the channel, we show that the cross-flow distribution depends almost entirely on the separation between the scales of the instantaneous vortices, where the upper and lower bounds are determined by and, respectively. Therefore, the distribution of the secondary flow relative to the size of the wave at a given can be replicated at higher by decreasing and keeping constant. The mechanisms that contribute to the mean cross-flow are analysed in terms of the Reynolds stresses and using quadrant analysis to evaluate the probability density function of the bursting events. These events are further classified with respect to the sign of their instantaneous spanwise velocities. Sweeping events and ejections are preferentially located in the valleys and peaks of the wall, respectively. The sweeps direct the instantaneous cross-flow from the core of the channel towards the wall, turning in the wall-tangent direction towards the peaks. The ejections drive the instantaneous cross-flow from the near-wall region towards the core. This preferential behaviour is identified as one of the main contributors to the secondary flow.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulence simulation; turbulent flows

Secondary flow in turbulent ducts with increasing aspect ratio - Vinuesa, Ricardo; Schlatter, Philipp; Nagib, H. M. (Physical Review Fluids, 2018)
Direct numerical simulations of turbulent duct flows with aspect ratios 1, 3, 5, 7, 10, and 14.4 at a center-plane friction Reynolds number Re 180, and aspect ratios 1 and 3 at Re 360, were carried out with the spectral-element code nek5000. The aim of these simulations is to gain insight into the kinematics and dynamics of Prandtl's secondary flow of the second kind and its impact on the flow physics of wall-bounded turbulence. The secondary flow is characterized in terms of the cross-plane component of the mean kinetic energy, and its variation in the spanwise direction of the flow. Our results show that averaging times of around 3000 convective time units (based on duct half-height h) are required to reach a converged state of the secondary flow, which extends up to a spanwise distance of around 5h measured from the side walls. We also show that if the duct is not wide enough to accommodate the whole extent of the secondary flow, then its structure is modified as reflected through a different spanwise distribution of energy. Another confirmation of the extent of the secondary flow is the decay rate of kinetic energy of any remnant secondary motions for zc/h>5 (where zc is the spanwise distance from the corner) in aspect ratios 7, 10, and 14.4, which exhibits a decreasing level of energy with increasing averaging time ta, and in its rapid rate of decay given by -1/4ta-1. This is the same rate of decay observed in a spanwise-periodic channel simulation, which suggests that at the core, the kinetic energy of the secondary flow integrated over the cross-sectional area, (K)yz, behaves as a random variable with zero mean, with rate of decay consistent with central limit theorem. Long-time averages of statistics in a region of rectangular ducts extending about the width of a well-designed channel simulation (i.e., extending about 3h on each side of the center plane) indicate that ducts or experimental facilities with aspect ratios larger than 10 may, if properly designed, exhibit good agreement with results obtained from spanwise-periodic channel computations.
CRIS-Team Scopus Importer:2023-03-21

Secondary instability and tertiary states in rotating plane Couette flow - Daly, C. A.; Schneider, Tobias M.; Schlatter, Philipp; Peake, N. (Journal of Fluid Mechanics, 2014)
Recent experimental studies have shown rich transition behaviour in rotating plane Couette flow (RPCF). In this paper we study the transition in supercritical RPCF theoretically by determination of equilibrium and periodic orbit tertiary states via Floquet analysis on secondary Taylor vortex solutions. Two new tertiary states are discovered which we name oscillatory wavy vortex flow (oWVF) and skewed vortex flow (SVF). We present the bifurcation routes and stability properties of these new tertiary states and, in addition, we describe a bifurcation procedure whereby a set of defected wavy twist vortices is approached. Further to this, transition scenarios at flow parameters relevant to experimental works are investigated by computation of the set of stable attractors which exist on a large domain. The physically observed flow states are shown to share features with states in our set of attractors.
CRIS-Team Scopus Importer:2023-03-21
Keywords: bifurcation; nonlinear instability; transition to turbulence

Self-similar transport of inertial particles in a turbulent boundary layer - Sardina, Gaetano; Schlatter, Philipp; Picano, Francesco; Casciola, C. M.; Brandt, Luca; Henningson, D. S. (Journal of Fluid Mechanics, 2012)
Results are presented from a direct numerical simulation of a particle-laden spatially developing turbulent boundary layer up to Re θ = 2500. The peculiar feature of a boundary-layer flow seeded with heavy particles is the variation of the local dimensionless parameters defining the fluid-particle interactions along the streamwise direction. Two different Stokes numbers can be defined, one using inner flow units and the other with outer units. Since these two Stokes numbers exhibit different decay rates in the streamwise direction, we find a decoupled particle dynamics between the inner and the outer region of the boundary layer. Preferential near-wall particle accumulation is similar to that observed in turbulent channel flow, while different behaviour characterizes the outer region. Here the concentration and the streamwise velocity profiles are found to be self-similar and to depend only on the local value of the outer Stokes number and the rescaled wall-normal distance. These new results are powerful in view of engineering and environmental applications and corresponding flow modelling. © 2012 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21
Keywords: boundary layers; multiphase and particle-laden flows; turbulent flows

Self-sustained global oscillations in a jet in crossflow - Schlatter, Philipp; Bagheri, Shervin; Henningson, Dan S. (Theoretical and Computational Fluid Dynamics, 2011)
A jet in crossflow with an inflow ratio of 3, based on the maximum velocity of the parabolic jet profile, is studied numerically. The jet is modeled as an inhomogeneous boundary condition at the crossflow wall. We find two fundamental frequencies, pertaining to self-sustained oscillations in the flow, using full nonlinear direct numerical simulation (DNS) as well as a modal decomposition into global linear eigenmodes and proper orthogonal decomposition (POD) modes; a high frequency which is characteristic for the shear-layer vortices and the upright vortices in the jet wake, and a low frequency which is dominant in the region downstream of the jet orifice. Both frequencies can be related to a region of reversed flow downstream of the jet orifice. This region is observed to oscillate predominantly in the wall-normal direction with the high frequency, and in the spanwise direction with the low frequency. Moreover, the steady-state solution of the governing Navier-Stokes equations clearly shows the horseshoe vortices and the corresponding wall vortices further downstream, and the emergence of a distinct counter-rotating vortex pair high in the free stream. It is thus found that neither the inclusion of the jet pipe nor unsteadiness is necessary to generate the characteristic counter-rotating vortex pair. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Elliptic instability; Global instabilities; Jet in crossflow; Proper orthogonal decomposition

Self-sustained localized structures in a boundary-layer flow - Duguet, Yohann; Schlatter, Philipp; Henningson, Dan S.; Eckhardt, Bruno (Physical Review Letters, 2012)
When a boundary layer starts to develop spatially over a flat plate, only disturbances of sufficiently large amplitude survive and trigger turbulence subcritically. Direct numerical simulation of the Blasius boundary-layer flow is carried out to track the dynamics in the region of phase space separating transitional from relaminarizing trajectories. In this intermediate regime, the corresponding disturbance is fully localized and spreads slowly in space. This structure is dominated by a robust pair of low-speed streaks, whose convective instabilities spawn hairpin vortices evolving downstream into transient disturbances. A quasicyclic mechanism for the generation of offspring is unfolded using dynamical rescaling with the local boundary-layer thickness. © 2012 American Physical Society.
CRIS-Team Scopus Importer:2023-03-21

Separating adverse-pressure-gradient and Reynolds-number effects in turbulent boundary layers - Sanmiguel Vila, Carlos; Vinuesa, Ricardo; Discetti, Stefano; Ianiro, Andrea; Schlatter, Philipp; Orlu, R. (Physical Review Fluids, 2020)
Zero pressure-gradient (ZPG) turbulent boundary layers (TBLs) at high Reynolds numbers (Re) and TBLs with adverse pressure gradients (APGs) share some similarities such as the emergence of an outer peak in the streamwise variance profile related to the enhancement of large-scale energy. Reynolds-number and pressure-gradient effects tend to cause such an energizing of the outer-layer structures, which makes it difficult to distinguish them, mainly because both effects are usually coupled. Using two experimental data sets of ZPG and APG TBLs in which Re and pressure gradient are analyzed independently, the present paper shows that the two effects have different imprints on the flow. In particular, the analysis shows that (1) the small-scale energy in APG TBLs is, contrary to canonical ZPG TBLs, not universal, but is dependent on the APG strength, (2) the APG enhances both the small- and large-scale energy in the outer region, and (3) the outer-peak location and the amplitude of the streamwise variance scale differently for increasing Re and APG magnitude. These findings may have ramifications on the development of turbulence models since the pressure gradient has a direct influence on the near-wall dynamics.
CRIS-Team Scopus Importer:2023-03-21

Separating large-scale superposition and modulation in turbulent channels - Andreolli, Andrea; Gatti, Davide; Vinuesa, Ricardo; Örlü, Ramis; Schlatter, Philipp (Journal of Fluid Mechanics, 2023)
The presence of very-large-scale motions in wall-bounded turbulent flows is commonly associated with their footprint in the form of the superposition of the large scales at the wall and the additional amplitude modulation of small-scale near-wall turbulence. These two phenomena are currently understood to be interlinked, with the superposed large-scale velocity gradient causing the modulation of small-scale activity in the proximity of the wall. To challenge this idea, we devise a numerical strategy that selectively suppresses either superposition or amplitude modulation, in an effort to isolate and study the remaining phenomenon. Results from our direct numerical simulations indicate that a positive correlation between the amplitude of the small scales in the near-wall region and the large-scale signal in the outer flow persists even when near-wall large-scale motions are suppressed -i.e. in absence of superposition. Clearly, this kind of correlation cannot be caused by the near-wall large-scale velocity or its gradients, as both are absent. Conversely, when modulation is blocked, the near-wall footprints of the large scales seem to disappear. This study has been carried out on channel flows at friction Reynolds number in both standard simulation domains and minimal streamwise units (MSUs), where the streamwise fluctuation energy is enhanced. The consistency of the results obtained by the two approaches suggests that MSUs can capture correctly this kind of scale interaction at a much reduced cost.
CRIS-Team Scopus Importer:2023-03-29
Keywords: turbulence theory; turbulent boundary layers

Simulation and validation of a spatially evolving turbulent boundary layer up to Reθ = 8300 - Eitel-Amor, Georg; Orlu, Ramis; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2014)
Results of a finely resolved large-eddy simulation (LES) of a spatially developing zero-pressure-gradient turbulent boundary layer up to a Reynolds number of Reθ = 8300 are presented. The very long computational domain provides substantial assessment for suggested high Reynolds number (Re) trends. Statistics, integral quantities and spectral data are validated using high quality direct numerical simulation (DNS) ranging up to Reθ = 4300 and hot-wire measurements covering the remaining Re-range. The mean velocity, turbulent fluctuations, skin friction, and shape factor show excellent agreement with the reference data. Through utilisation of filtered DNS, subtle differences between the LES and DNS could to a large extent be explained by the reduced spanwise resolution of the LES. Spectra and correlations for the streamwise velocity and the wall-shear stress evidence a clear scale-separation and a footprint of large outer scales on the near-wall small scales. While the inner peak decreases in importance and reduces to 4% of the total energy at the end of the domain, the energy of the outer peak scales in outer units. In the near-wall region a clear k - 1 region emerges. Consideration of the two-dimensional spectra in time and spanwise space reveals that an outer time scale λt ≈ 10δ99 / U∞, with the boundary layer thickness δ99 and free-stream velocity U∞, is the correct scale throughout the boundary layer rather than the transformed streamwise wavelength multiplied by a (scale independent) convection velocity. Maps for the covariance of small scale energy and large scale motions exhibit a stronger linear Re dependence for the amplitude of the off-diagonal peak compared to the diagonal one, thereby indicating that the strength of the amplitude modulation can only qualitatively be assessed through the diagonal peak. In addition, the magnitude of the wall-pressure fluctuations confirms mixed scaling, and pressure spectra at the highest Re give a first indication of a -7/3 wave number dependence. © 2014 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Large-eddy simulation; Numerical simulation; Turbulent boundary layers; Wall turbulence

Simulation of a large-eddy-break-up device (LEBU) in a moderate Reynolds number turbulent boundary layer - Chin, Cheng; Hutchins, Nicholas; Orlu, Ramis; Monty, Jason; Ooi, Andrew; Schlatter, Philipp (9th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2015, 2015)
A well-resolved large eddy simulation (LES) of a large-eddy break-up (LEBU) device in a spatially evolving turbulent boundary layer up to Reθ ∼ 4300 is performed. The LEBU is a flat plate that is implemented via an immersed boundary method. Initial flow visualizations show successful implementation of the LEBU. The LEBU is located at a wall-normal distance of 0.85 (local boundary layer thickness) from the wall and acts to delay the growth of the turbulent boundary layer. The LEBU serves to reduce skin friction drag up to 1605 downstream of the LEBU but no net drag reduction is found. Investigation is performed on the interactions of high and low momentum bulges with the LEBU and the corresponding output is analysed, showing a 'break-up' of these large momentum bulges. In addition, results show an attenuated turbulence intensity profile downstream of the LEBU, which is mainly due to a reduction in energy at spanwise length scales of λz < 200 and >500.
CRIS-Team Scopus Importer:2023-03-21

Simulation of a Large-Eddy-Break-up Device (LEBU) in a Moderate Reynolds Number Turbulent Boundary Layer - Chin, Cheng; Orlu, Ramis; Monty, Jason; Hutchins, Nicholas; Ooi, Andrew; Schlatter, Philipp (Flow Turbulence and Combustion, 2017)
A well-resolved large eddy simulation (LES) of a large-eddy break-up (LEBU) device in a spatially evolving turbulent boundary layer is performed with, Reynolds number, based on free-stream velocity and momentum-loss thickness, of Reθ ≈ 4300. The implementation of the LEBU is via an immersed boundary method. The LEBU is positioned at a wall-normal distance of 0.8 δ (δ denoting the local boundary layer thickness at the location of the LEBU) from the wall. The LEBU acts to delay the growth of the turbulent boundary layer and produces global skin friction reduction beyond 180δ downstream of the LEBU, with a peak local skin friction reduction of approximately 12 %. However, no net drag reduction is found when accounting for the device drag of the LEBU in accordance with the towing tank experiments by Sahlin et al. (Phys. Fluids 31, 2814, 1988). Further investigation is performed on the interactions of high and low momentum bulges with the LEBU and the corresponding output is analysed, showing a ‘break-up’ of these large momentum bulges downstream of the LEBU. In addition, results from the spanwise energy spectra show consistent reduction in energy at spanwise length scales for λz+>1000 independent of streamwise and wall-normal location when compared to the corresponding turbulent boundary layer without LEBU.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Boundary layer; Drag reduction; Large eddy simulation; Large-eddy-break-up device; Wall turbulence

Simulations of heat transfer in a boundary layer subject to free-stream turbulence - Li, Qiang; Schlatter, Philipp; Henningson, Dan S. (6th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2009, 2009)
The ptesenl study investigates the effects or the ambient, free-stream turbulence (FST) on the momentum and heat transfer in a turbulent flat-plate boundary layer via large-eddy simulations (LES) using the ADM-RT model. Due to a FST of 20%, the skin-friction coefficient c/and Stanton number St are substantially elevated up to 15% in the fully turbulent region. The depression of both the mean velocity and temperature profiles in the wake region due to the FST is observed, however, the influence on the wall-normal heat flux in the near-wall region is negligible.
CRIS-Team Scopus Importer:2023-03-21

Simulations of spatially evolving turbulent boundary layers up to Reθ=4300 - Schlatter, Philipp; Li, Qiang; Brethouwer, Geert; Johansson, Arne V.; Henningson, Dan S. (International Journal of Heat and Fluid Flow, 2010)
A well-resolved large-eddy simulation (LES) of a spatially developing turbulent boundary layer under zero-pressure-gradient up to comparably high Reynolds numbers (Reθ=4300) is performed. The laminar inflow is located at Reδ*=450(Reθ≈180), a position where natural transition to turbulence can be expected. The simulation is validated and compared extensively to both numerical data sets, i.e. a recent spatial direct numerical simulation (DNS) up to Reθ=2500 (Schlatter et al., 2009) and available experimental measurements, e.g. the ones obtained by Österlund (1999). The goal is to provide the research community with reliable numerical data for high Reynolds-number wall-bounded turbulence, which can in turn be employed for further model development and validation, but also to contribute to the characterisation and understanding of various aspects of wall turbulence.The results obtained via LES show that good agreement with DNS data at lower Reynolds numbers and experimental data can be obtained for both mean and fluctuating quantities. In addition, turbulence spectra characterising large-scale organisation in the flow have been computed and compared to literature results with good agreement. In particular, the near-wall streaks scaling in inner units and the outer layer large-scale structures can clearly be identified in both spanwise and temporal spectra. © 2010 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-21
Keywords: High Reynolds number; Large-eddy simulation (LES); Turbulent boundary layers

Simulations of turbulent asymptotic suction boundary layers - Bobke, Alexandra; Orlu, Ramis; Schlatter, Philipp (Journal of Turbulence, 2016)
A series of large-eddy simulations of a turbulent asymptotic suction boundary layer (TASBL) was performed in a periodic domain, on which uniform suction was applied over a flat plate. Three Reynolds numbers (defined as ratio of free-stream and suction velocity) of Re = 333, 400 and 500 and a variety of domain sizes were considered in temporal simulations in order to investigate the turbulence statistics, the importance of the computational domain size, the arising flow structures as well as temporal development length required to achieve the asymptotic state. The effect of these two important parameters was assessed in terms of their influence on integral quantities, mean velocity, Reynolds stresses, higher order statistics, amplitude modulation and spectral maps. While the nearwall region up to the buffer region appears to scale irrespective of Re and domain size, the parameters of the logarithmic law (i.e. von Kármán and additive coefficient) decrease with increasing Re, while the wake strength decreases with increasing spanwise domain size and vanishes entirely once the spanwise domain size exceeds approximately two boundary-layer thicknesses irrespective of Re. The wake strength also reduces with increasing simulation time. The asymptotic state of the TASBL is characterised by surprisingly large friction Reynolds numbers and inherits features of wall turbulence at numerically high Re. Compared to a turbulent boundary layer (TBL) or a channel flow without suction, the components of the Reynoldsstress tensor are overall reduced, but exhibit a logarithmic increase with decreasing suction rates, i.e. increasing Re. At the same time, the anisotropy is increased compared to canonical wall-bounded flows without suction. The reduced amplitudes in turbulence quantities are discussed in light of the amplitude modulation due to the weakened larger outer structures. The inner peak in the spectral maps is shifted to higher wavelength and the strength of the outer peak is much less than for TBLs. An additional spatial simulation was performed, in order to relate the simulation results to wind tunnel experiments, which – in accordance with the results fromthe temporal simulation – indicate that a truly TASBL is practically impossible to realise in a wind tunnel. Our unique data set agrees qualitatively with existing literature results for both numerical and experimental studies, and at the same time sheds light on the fact why the asymptotic state could not be established in a wind tunnel experiment, viz. because experimental studies resemble our simulation results from too small simulation boxes or insufficient development times.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Boundary layer; Turbulent asymptotic suction boundary layer; Wall turbulence

Simulation strategies for the Food and Drug Administration nozzle using Nek5000 - Sanchez Abad, Nour; Vinuesa, Ricardo; Schlatter, Philipp; Andersson, Magnus; Karlsson, Matts (AIP Advances, 2020)
Computational fluid dynamics (CFD) is currently a versatile tool used for flow characterization in diverse areas of industry and research; however, its application in medical devices is less developed due to high regulatory standards for safety purposes. In this context, the development of a rigorous and standardized CFD methodology is essential in order to improve the accuracy and ensure the reliability of biomedical applications. To that end, the Food and Drug Administration (FDA) proposed a benchmark model of an idealized medical device to provide a common ground for verification and validation processes. Previous studies have evaluated the potential of conventional turbulence models to predict the relevant flow features in the FDA nozzle but have also been deemed inaccurate or exhibited high dependency on the numerical scheme. Furthermore, validation of computational results relied on previous experiments performed with particle image velocimetry (PIV), which also exhibited noticeable uncertainties. Here, we perform direct numerical simulations (DNSs) of the flow through the FDA nozzle configuration, at Reynolds numbers based on the throat diameter Ret = 500, 2000, 3500, and 5000, using the spectral-element code Nek5000. The predictive capabilities of the synthetic-eddy method and parabolic-inflow conditions at the inlet were tested, and the results were compared with PIV data. Our results highlight the very high sensitivity of this flow case to the inflow conditions and the disturbances at the throat, particularly when predicting the laminar-turbulent jet breakdown. Due to this extreme sensitivity, any benchmark data of this geometry need to include a very detailed characterization of both the conditions at the inflow and the throat, in order to enable relevant comparisons.
CRIS-Team Scopus Importer:2023-03-21

Soft Computing Techniques to Analyze the Turbulent Wake of a Wall-Mounted Square Cylinder - Amor, Christian; Perez, Jose M.; Schlatter, Philipp; Vinuesa, Ricardo; Le Clainche, Soledad (Advances in Intelligent Systems and Computing, 2020)
This paper introduces several methods, generally used in fluid dynamics, to provide low-rank approximations. The algorithm describing these methods are mainly based on singular value decomposition (SVD) and dynamic mode decomposition (DMD) techniques, and are suitable to analyze turbulent flows. The application of these methods will be illustrated in the analysis of the turbulent wake of a wall-mounted cylinder, a geometry modeling a skyscraper. A brief discussion about the large and small size structures of the flow will provide the key ideas to represent the general dynamics of the flow using low-rank approximations. If the flow physics is understood, then it is possible to adapt these techniques, or some other strategies, to solve general complex problems with reduced computational cost. The main goal is to introduce these methods as machine learning strategies that could be potentially used in the field of fluid dynamics, and that can be extended to any other research field.
CRIS-Team Scopus Importer:2023-03-21
Keywords: CFD; Data science; DMD; Fluid dynamics; POD; Soft computing; Turbulence flow

Sources and fluxes of scale energy in the overlap layer of wall turbulence - Cimarelli, Andrea; De Angelis, Elisabetta; Schlatter, Philipp; Brethouwer, G.; Talamelli, A.; Casciola, C. M. (Journal of Fluid Mechanics, 2015)
Direct numerical simulations of turbulent channel flows at friction Reynolds numbers (Re) of 550, 1000 and 1500 are used to analyse the turbulent production, transfer and dissipation mechanisms in the compound space of scales and wall distances by means of the Kolmogorov equation generalized to inhomogeneous anisotropic flows. Two distinct peaks of scale-energy source are identified. The first, stronger one, belongs to the near-wall cycle. Its location in the space of scales and physical space is found to scale in viscous units, while its intensity grows slowly with Re, indicating a near-wall modulation. The second source peak is found further away from the wall in the putative overlap layer, and it is separated from the near-wall source by a layer of significant scale-energy sink. The dynamics of the second outer source appears to be strongly dependent on the Reynolds number. The detailed scale-by-scale analysis of this source highlights well-defined features that are used to make the properties of the outer turbulent source independent of Reynolds number and wall distance by rescaling the problem. Overall, the present results suggest a strong connection of the observed outer scale-energy source with the presence of an outer region of turbulence production whose mechanisms are well separated from the near-wall region and whose statistical features agree with the hypothesis of an overlap layer dominated by attached eddies. Inner-outer interactions between the near-wall and outer source region in terms of scale-energy fluxes are also analysed. It is conjectured that the near-wall modulation of the statistics at increasing Reynolds number can be related to a confinement of the near-wall turbulence production due to the presence of increasingly large production scales in the outer scale-energy source region.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulent boundary layers; turbulent flows

Spanwise-coherent hydrodynamic waves around flat plates and airfoils - Abreu, Leandra; Tanarro, Alvaro; Cavalieri, Andre V. G.; Schlatter, Philipp; Vinuesa, Ricardo; Hanifi, Ardeshir; Henningson, Dan S. (Journal of Fluid Mechanics, 2021)
We investigate spanwise-coherent structures in the turbulent flow around airfoils, motivated by their connection with trailing-edge noise. We analyse well-resolved large-eddy simulations (LES) of the flow around NACA 0012 and NACA 4412 airfoils, both at a Reynolds number of 400 000 based on the chord length. Spectral proper orthogonal decomposition performed on the data reveals that the most energetic coherent structures are hydrodynamic waves, extending over the turbulent boundary layers around the airfoils with significant amplitudes near the trailing edge. Resolvent analysis was used to model such structures, using the mean field as a base flow. We then focus on evaluating the dependence of such structures on the domain size, to ensure that they are not an artefact of periodic boundary conditions in small computational boxes. To this end, we performed incompressible LES of a zero-pressure-gradient turbulent boundary layer, for three different spanwise sizes, with the momentum-thickness Reynolds number matching those near the airfoils trailing edge. The same coherent hydrodynamic waves were observed for the three domains. Such waves are accurately modelled as the most amplified flow response from resolvent analysis. The signature of such wide structures is seen in non-premultiplied spanwise wavenumber spectra, which collapse for the three computational domains. These results suggest that the spanwise-elongated structures are not domain-size dependent for the studied simulations, indicating thus the presence of very wide structures in wall-bounded turbulent flows.
CRIS-Team Scopus Importer:2023-03-21
Keywords: aeroacoustics; hydrodynamic noise

Spatial Averaging Effects in Adverse Pressure Gradient Turbulent Boundary Layers - Mallor, Fermin; Örlü, Ramis; Schlatter, Philipp (Flow Turbulence and Combustion, 2024)
Thermal anemometry sensors for time-resolved velocity measurements average the measured signal over the length of their sensor, thereby attenuating fluctuations stemming from scales smaller than the wire length. Several compensation methods have emerged for wall turbulence, the most prominent ones relying on the small-scale universality in canonical flows or on the reconstruction based on two attenuated variance profiles obtained with sensors of different length. To extend these methods to non-canonical flows, the present work considers various adverse-pressure gradient (APG) turbulent boundary layer (TBL) flows in order to explore how the small-scale energy is affected in the inner and outer layer and how the two prominent correction methods perform as function of wall-distance, wire length and flow condition. Our findings show that the increased levels of small-scale energy in the inner, but also outer layer associated with APG TBLs reduces the applicability of empirical methods based on the universality of small-scale energy. On the other hand, a correction based on the relationship between the spanwise Taylor microscale and the two-point streamwise velocity correlation function, is able to correct the attenuated profiles of non-canonical cases. Combining the strength of both methods, a composite profile for the spanwise Taylor microscale is suggested, which then is used for the correction of probe-length attenuation effects across a multitude of flow conditions.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Adverse pressure gradients; Correction schemes; Hot-wire anemometry; Spatial averaging effects; Turbulent boundary layers

Spatial resolution analysis of planar PIV measurements to characterise vortices in turbulent flows - Rahgozar, Saeed; Maciel, Yvan; Schlatter, Philipp (Journal of Turbulence, 2013)
The effects of spatial resolution of planar particle image velocimetry (PIV) on vortex size, swirling strength, circulation and population density characterisation are analysed using a series of experimental and numerical databases. The databases comprise a PIV database of an adverse-pressure-gradient turbulent boundary layer (APG TBL), a PIV database of a zero-pressure-gradient (ZPG) TBL in streamwise-wall-normal planes and streamwise-wall-normal slices of a direct numerical simulation (DNS) of a ZPG TBL. The effects of interrogation window and mesh sizes on the vortex parameters are analysed in the outer region of these flows using different qualitative and quantitative approaches. The quantitative analysis mainly capitalises on the possibility of mimicking the PIV data-sets with the DNS one. These approaches allow us to not only isolate the effects of mesh size and the interrogation window size but also to deduce the combined effects of other measurement errors in PIV. Typical values of mesh size and interrogation window size (0.01-0.03 of the boundary layer thickness) and typical levels of measurement uncertainties have significant effects on the vortex parameters. Moreover, each PIV error source affects the vortex parameters in different and frequently opposite manners. Hence, an optimal selection of measurement parameters such as the interrogation window size is indispensable in order to minimise the effects of spatial resolution and other measurement errors on the vortex parameters. Guidelines are presented in the Conclusions section of this paper. Finally, it is found that all the vortex parameters, when averaged across the outer region, are reasonably comparable in the ZPG and APG TBLs despite the fact that these are very different flows. © 2013 Taylor & Francis.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct numerical simulation (DNS); Particle image velocimetry (PIV); Spatial resolution; Turbulent flows; Vortex characterisation

Spectral analysis of nonlinear flows - Rowley, Clarence W.; Mezic, Igor; Bagheri, Shervin; Schlatter, Philipp; Henningson, Dan S. (Journal of Fluid Mechanics, 2009)
We present a technique for describing the global behaviour of complex nonlinear flows by decomposing the flow into modes determined from spectral analysis of the Koopman operator, an infinite-dimensional linear operator associated with the full nonlinear system. These modes, referred to as Koopman modes, are associated with a particular observable, and may be determined directly from data (either numerical or experimental) using a variant of a standard Arnoldi method. They have an associated temporal frequency and growth rate and may be viewed as a nonlinear generalization of global eigenmodes of a linearized system. They provide an alternative to proper orthogonal decomposition, and in the case of periodic data the Koopman modes reduce to a discrete temporal Fourier transform. The Arnoldi method used for computations is identical to the dynamic mode decomposition recently proposed by Schmid & Sesterhenn (Sixty-First Annual Meeting of the APS Division of Fluid Dynamics, 2008), so dynamic mode decomposition can be thought of as an algorithm for finding Koopman modes. We illustrate the method on an example of a jet in crossflow, and show that the method captures the dominant frequencies and elucidates the associated spatial structures. © 2009 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21

Spectral proper orthogonal decomposition and resolvent analysis of near-wall coherent structures in turbulent pipe flows - Abreu, Leandra; Cavalieri, Andre V. G.; Schlatter, Philipp; Vinuesa, Ricardo; Henningson, Dan S. (Journal of Fluid Mechanics, 2020)
Direct numerical simulations, performed with a high-order spectral-element method, are used to study coherent structures in turbulent pipe flow at friction Reynolds numbers and. The database was analysed using spectral proper orthogonal decomposition (SPOD) to identify energetically dominant coherent structures, most of which turn out to be streaks and quasi-streamwise vortices. To understand how such structures can be modelled, the linear flow responses to harmonic forcing were computed using the singular value decomposition of the resolvent operator, using the mean field as a base flow. The SPOD and resolvent analysis were calculated for several combinations of frequencies and wavenumbers, allowing the mapping out of similarities between SPOD modes and optimal responses for a wide range of relevant scales in turbulent pipe flows. In order to explore physical reasons behind the agreement between both methods, an indicator of lift-up mechanism in the resolvent analysis was introduced, activated when optimal forcing is dominated by the wall-normal and azimuthal components, and associated response corresponds to streaks of streamwise velocity. Good agreement between leading SPOD and resolvent modes is observed in a large region of parameter space. In this region, a significant gain separation is found in resolvent analysis, which may be attributed to the strong amplification associated with the lift-up mechanism, here understood as nonlinear forcing terms leading to the appearance of streamwise vortices, which in turn form high-amplitude streaks. For both Reynolds numbers, the observed concordances were generally for structures with large energy in the buffer layer. The results highlight resolvent analysis as a pertinent reduced-order model for coherent structures in wall-bounded turbulence, particularly for streamwise elongated structures corresponding to near-wall streamwise vortices and streaks.
CRIS-Team Scopus Importer:2023-03-21
Keywords: pipe flow boundary layer; turbulent boundary layers

Spectra of near-equilibrium adverse-pressure-gradient turbulent boundary layers - Pozuelo, Ramon; Li, Qiang; Schlatter, Philipp; Vinuesa, Ricardo (Physical Review Fluids, 2023)
With the availability of new high-Reynolds-number (Re) databases of turbulent boundary layers (TBLs) it has been possible to identify in detail certain regions of the boundary layer with more complex behavior. In this study we consider a unique database at moderately-high Re, with a nearconstant adverse pressure gradient (APG) [Pozuelo et al., J. Fluid Mech. 939, A34 (2022)0022-112010.1017/jfm.2016.715], and perform spectral analysis of the Reynolds stresses, focusing on the streamwise component. We assess different regions of the APG TBL, comparing this case with the zero-pressure-gradient (ZPG) TBL, and identify the relevant scaling parameters as well as the contribution of the scales of different sizes. The small scales in the near-wall region up to the near-wall spectral peak have been found to scale using viscous units. In APG TBLs, the largest scales close to the wall have a better scaling with the boundary-layer thickness (δ99), and they are significantly affected by the APG. In the overlap and wake regions of the boundary layer, the small energetic scales exhibit a good scaling with the displacement thickness (δ∗) while the larger scales and the outer spectral peak are better scaled with the boundary-layer thickness. Also, note that the wall-normal location of the spectral outer peak scales with the displacement thickness rather than the boundary layer thickness. The various scalings exhibited by the spectra in APG TBLs are reported here, and shed light on the complex phenomena present in these flows of great scientific and technological importance.
CRIS-Team Scopus Importer:2023-03-21

Stability and sensitivity of a cross-flow-dominated Falkner-Skan-Cooke boundary layer with discrete surface roughness - Brynjell-Rahkola, Mattias; Shahriari, Nima; Schlatter, Philipp; Hanifi, Ardeshir; Henningson, Dan S. (Journal of Fluid Mechanics, 2017)
With the motivation of determining the critical roughness size, a global stability and sensitivity analysis of a three-dimensional Falkner-Skan-Cooke (FSC) boundary layer with a cylindrical surface roughness is performed. The roughness size is chosen such that breakdown to turbulence is initiated by a global version of traditional secondary instabilities of the cross-flow (CF) vortices instead of an immediate flow tripping at the roughness. The resulting global eigenvalue spectra of the systems are found to be very sensitive to numerical parameters and domain size. This sensitivity to numerical parameters is quantified using the-pseudospectrum, and the dependency on the domain is analysed through an impulse response, structural sensitivity analysis and an energy budget. It is shown that while the frequencies remain relatively unchanged, the growth rates increase with domain size, which originates from the inclusion of stronger CF vortices in the baseflow. This is reflected in a change in the rate of advective energy transport by the baseflow. It is concluded that the onset of global instability in a FSC boundary layer as the roughness height is increased does not correspond to an immediate flow tripping behind the roughness, but occurs for lower roughness heights if sufficiently long domains are considered. However, the great sensitivity results in an inability to accurately pinpoint the exact parameter values for the bifurcation, and the large spatial growth of the disturbances in the long domains eventually becomes larger than can be resolved using finite-precision arithmetic.
CRIS-Team Scopus Importer:2023-03-21
Keywords: absolute/convective instability; boundary layer stability; transition to turbulence

Stability of a jet in crossflow - Ilak, Milos; Schlatter, Philipp; Bagheri, Shervin; Chevalier, Mattias; Henningson, Dan S. (Physics of Fluids, 2011)
CRIS-Team Scopus Importer:2023-03-21

Stability tools for the spectral-element code Nek5000: Application to Jet-in-Crossflow - Peplinski, A.; Schlatter, Philipp; Fischer, P. F.; Henningson, D. S. (Lecture Notes in Computational Science and Engineering, 2014)
We demonstrate the use of advanced linear stability tools developed for the spectral-element code Nek5000 to investigate the dynamics of nonlinear flows in moderately complex geometries. The aim of stability calculations is to identify the driving mechanism as well as the region most sensitive to the instability: the wavemaker.We concentrate on global linear stability analysis, which considers the linearised Navier–Stokes equations and searches for growing small disturbances, i.e. so-called linear global modes. In the structural sensitivity analysis these modes are associated to the eigenmodes of the direct and adjoint linearised Navier–Stokes operators, and the wavemaker is defined as the overlap of the strongest direct and adjoint eigenmodes. The large eigenvalue problems are solved usingmatrix-freemethods adopting the time-stepping Arnoldi approach.We present here our implementation in Nek5000 with the ARPACK library on a number of test cases.
CRIS-Team Scopus Importer:2023-03-21

Stabilization of the spectral element method in convection dominated flows by recovery of skew-symmetry - Malm, Johan; Schlatter, Philipp; Fischer, Paul F.; Henningson, Dan S. (Journal of Scientific Computing, 2013)
We investigate stability properties of the spectral element method for advection dominated incompressible flows. In particular, properties of the widely used convective form of the nonlinear term are studied. We remark that problems which are usually associated with the nonlinearity of the governing Navier-Stokes equations also arise in linear scalar transport problems, which implicates advection rather than nonlinearity as a source of difficulty. Thus, errors arising from insufficient quadrature of the convective term, commonly referred to as 'aliasing errors', destroy the skew-symmetric properties of the convection operator. Recovery of skew-symmetry can be efficiently achieved by the use of over-integration. Moreover, we demonstrate that the stability problems are not simply connected to underresolution. We combine theory with analysis of the linear advection-diffusion equation in 2D and simulations of the incompressible Navier-Stokes equations in 2D of thin shear layers at a very high Reynolds number and in 3D of turbulent and transitional channel flow at moderate Reynolds number. For the Navier-Stokes equations, where the divergence-free constraint needs to be enforced iteratively to a certain accuracy, small divergence errors can be detrimental to the stability of the method and it is therefore advised to use additional stabilization (e.g. so-called filter-based stabilization, spectral vanishing viscosity or entropy viscosity) in order to assure a stable spectral element method. © 2013 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Over-integration; Skew-symmetry; Spectral element method (SEM); Stability

Stabilization of the spectral-element method in turbulent flow simulations - Ohlsson, J.; Schlatter, Philipp; Fischer, P. F.; Henningson, D. S. (Lecture Notes in Computational Science and Engineering, 2011)
The effect of over-integration and filter-based stabilization in the spectral-element method is investigated. There is a need to stabilize the SEM for flow problems involving non-smooth solutions, e.g., turbulent flow simulations. In model problems such as the Burgers' equation (similar to Kirby and Karniadakis, J. Comput. Phys. 191:249-264, 2003) and the scalar transport equation together with full Navier-Stokes simulations it is noticed that over-integration with the full 3/2-rule is not required for stability. The first additional over-integration nodes are the most efficient to remove aliasing errors. Alternatively, filter-based stabilization can in many cases alone help to stabilize the computation. © 2011 Springer.
CRIS-Team Scopus Importer:2023-03-21

Statistics of particle accumulation in spatially developing turbulent boundary layers - Sardina, Gaetano; Picano, Francesco; Schlatter, Philipp; Brandt, Luca; Casciola, C. M. (Flow Turbulence and Combustion, 2014)
We present the results of a Direct Numerical Simulation of a particle-laden spatially developing turbulent boundary layer up to Re θ = 2500. Two main features differentiate the behavior of inertial particles in a zero-pressure-gradient turbulent boundary layer from the more commonly studied case of a parallel channel flow. The first is the variation along the streamwise direction of the local dimensionless parameters defining the fluid-particle interactions. The second is the coexistence of an irrotational free-stream and a near-wall rotational turbulent flow. As concerns the first issue, an inner and an outer Stokes number can be defined using inner and outer flow units. The inner Stokes number governs the near-wall behavior similarly to the case of channel flow. To understand the effect of a laminar-turbulent interface, we examine the behavior of particles initially released in the free stream and show that they present a distinct behavior with respect to those directly injected inside the boundary layer. A region of minimum concentration occurs inside the turbulent boundary layer at about one displacement thickness from the wall. Its formation is due to the competition between two transport mechanisms: a relatively slow turbulent diffusion towards the buffer layer and a fast turbophoretic drift towards the wall. © 2013 Springer Science+Business Media Dordrecht.
CRIS-Team Scopus Importer:2023-03-21
Keywords: DNS; Inertial particles; Turbophoresis; Turbulent boundary layers; Wall flows

Statistics of particle accumulation in spatially developing turbulent boundary layers - Sardina, Gaetano; Schlatter, Philipp; Brandt, L.; Picano, Francesco; Casciola, C. M.; Henningson, D. S. (Proceedings of the International Symposium on Turbulence, Heat and Mass Transfer, 2012)
A Direct Numerical Simulation of a particle-laden spatially developing turbulent boundary layer up to Re? = 2500 has been performed. The peculiar feature of a boundary layer flow seeded with heavy particles is the variation of the local dimensionless parameters defining the fluid-particle interactions along the streamwise direction. An inner and an outer Stokes number can be defined using inner and outer flow units. These two parameters show different decay rates in the streamwise direction so that it is possible to find a decoupled particle dynamics between the inner and the outer region of the boundary layer. Preferential near-wall particle accumulation is similar to that observed in turbulent channel flow, while a self-similar behavior characterizes the outer region.
CRIS-Team Scopus Importer:2023-03-21

Stochastic and deterministic motion of a laminar-turbulent front in a spanwisely extended Couette flow - Duguet, Yohann; Le Maitre, Olivier; Schlatter, Philipp (Physical Review E, 2011)
We investigate numerically the dynamics of a laminar-turbulent interface in a spanwisely extended and streamwisely minimal plane Couette flow. The chosen geometry allows one to suppress the large-scale secondary flow and to focus on the nucleation of streaks near the interface. It is shown that the resulting spanwise motion of the interface is essentially stochastic and can be modeled as a continuous-time random walk. This model corresponds here to a Gaussian diffusion process. The average speed of the interface and the corresponding diffusion coefficient are determined as functions of the Reynolds number Re, as well as the threshold value above which turbulence contaminates the whole domain. For the lowest values of Re, the stochastic dynamics competes with another deterministic regime of growth of the localized perturbations. The latter is interpreted as a depinning process from the homoclinic snaking region of the system. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2023-03-21

Stochastic motion of a laminar/turbulent interface in a shear flow - Duguet, Yohann; Schlatter, Philipp (Journal of Physics: Conference Series, 2011)
Plane Couette flow is a classical prototype of a shear flow where transition to turbulence is subcritical, i.e. happens despite linear stability of the base flow. In this study we are interested in the spatio-temporal competition between the (active) turbulent phase and the (absorbing) laminar. Our three-dimensional numerical simulations show that the delimiting interface, when parallel to the streamwise direction, moves in a stochastic manner which we model as a continuous-time random walk. Statistical analysis suggests a Gaussian diffusion process and allows us to determine the average speed of this interface as a function of the Reynolds number Re, as well as the threshold in Re above which turbulence contaminates the whole domain. For the lowest value of Re, this stochastic motion competes with another deterministic regime of growth of the localised perturbations. The latter, a rather unexpected regime, is shown to be linked to the recently found localised snaking solutions of the Navier-Stokes equations. An extension of this thinking to more general orientations of the interfaces will be proposed.
CRIS-Team Scopus Importer:2023-03-21

Stripy patterns in low-Re turbulent plane Couette flow - Duguet, Yohann; Schlatter, Philipp; Henningson, Dan S. (IUTAM Bookseries, 2010)
We present for the first time a complete bifurcation diagram of plane Couette flow based on direct numerical simulation of the full Navier-Stokes equations. The use of an unusually large computational domain (800h×2h×356h) is crucial for the determination of transition thresholds, because it allows to reproduce spatiotemporal intermittency structures such as transient spots, turbulent bands, and laminar holes. The threshold in Re (based on the half-gap) is found to be Rec = 324±1, in very good agreement with available experimental data. This work points out that, at the onset of transition in Re, fragmented oblique patterns always emerge from the interaction of growing neighbouring spots. An analogy with thermodynamical phase transition seems relevant to describe the whole transition process. © 2010 Springer Science+Business Media B.V.
CRIS-Team Scopus Importer:2023-03-21

Strong Scaling of OpenACC enabled Nek5000 on several GPU based HPC systems - Vincent, Jonathan; Gong, Jing; Karp, Martin; Peplinski, Adam; Jansson, Niclas; Podobas, Artur; Jocksch, Andreas; Yao, Jie; Hussain, Fazle; Markidis, Stefano; Karlsson, Matts; Pleiter, Dirk; et al. (ACM International Conference Proceeding Series, 2022)
We present new results on the strong parallel scaling for the OpenACC-accelerated implementation of the high-order spectral element fluid dynamics solver Nek5000. The test case considered consists of a direct numerical simulation of fully-developed turbulent flow in a straight pipe, at two different Reynolds numbers Reτ = 360 and Reτ = 550, based on friction velocity and pipe radius. The strong scaling is tested on several GPU-enabled HPC systems, including the Swiss Piz Daint system, TACC's Longhorn, Jülich's JUWELS Booster, and Berzelius in Sweden. The performance results show that speed-up between 3-5 can be achieved using the GPU accelerated version compared with the CPU version on these different systems. The run-time for 20 timesteps reduces from 43.5 to 13.2 seconds with increasing the number of GPUs from 64 to 512 for Reτ = 550 case on JUWELS Booster system. This illustrates the GPU accelerated version the potential for high throughput. At the same time, the strong scaling limit is significantly larger for GPUs, at about 2000 - 5000 elements per rank; compared to about 50 - 100 for a CPU-rank.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Benchmarking; Computational Fluid Dynamics; Nek5000; OpenACC; Scaling

Structure of a turbulent boundary layer studied by DNS - Schlatter, Philipp; Li, Qiang; Brethouwer, Geert; Johansson, Arne V.; Henningson, Dan S. (ERCOFTAC Series, 2011)
CRIS-Team Scopus Importer:2023-03-21

Swirl Switching in bent pipes studied by numerical simulation - Schlatter, Philipp; Hufnagel, Lorenz; Canton, Jacopo; Merzari, Elia; Marin, Oana; Orlu, Ramis (10th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2017, 2017)
Turbulent flow through pipe bends has been extensively studied, but several phenomena still miss an exhaustive explanation. Due to centrifugal forces, the fluid flowing through a curved pipe forms two symmetric, counter-rotating Dean vortices. It has been observed, experimentally and numerically, that these vortices change their size, intensity and location in a quasi-periodic, oscillatory fashion, a phenomenon known as swirl-switching. These oscillations are responsible for failure due to fatigue in pipes, and their origin has been attributed to a recirculation bubble, disturbances coming from the upstream straight section and others. The present study tackles the problem by direct numerical simulations (DNS) of turbulent pipe flow at moderate Reynolds number, analysed, for the first time, with three-dimensional proper orthogonal decomposition (POD) in an effort to distinguish between the spatial and temporal contributions to the oscillations. The simulations are performed at a friction Reynolds number of about 360 with a divergence-free synthetic turbulence inflow, which is crucial to avoid the interference of low-frequency oscillations generated by a standard recycling method. Two different bends are considered, with curvature 0.1 and 0.3, preceded and followed by straight pipe segments. Our results indicate that a single low-frequency, three-dimensional POD mode is responsible for the swirl-switching. This mode represents a travelling wave, and was previously mistaken by 2D POD for two different modes. Low-order reconstruction clearly shows that the upstream turbulent flow does not play a role for the swirl-switching.
CRIS-Team Scopus Importer:2023-03-21

Swirl-switching phenomenon in turbulent flow through toroidal pipes - Noorani, Azad; Schlatter, Philipp (9th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2015, 2015)
Direct numerical simulations (DNS) are performed to investigate turbulent flows in toroidal pipes with mild and strong curvature. By means of proper orthogonal decomposition (POD), dominant structures in the flow field are identified. The most energetic structures in the strongly curved pipes (κ = 0.1 and κ = 0.3) are very similar in both configurations studied here. These modes (shape and frequency) also match the coherent structures responsible for swirl switching phenomenon found earlier in experimental and numerical studies of turbulent flow in spatially developing 90° bends with which the current results are compared. The observed swirl switching in toroidal pipes, which is isolated from any upstream and separation conditions, may challenge the current hyphothesis regarding the origin of swirl switching mechanism.
CRIS-Team Scopus Importer:2023-03-21

Swirl-switching phenomenon in turbulent flow through toroidal pipes - Noorani, A.; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2016)
Direct numerical simulations (DNSs) are performed to investigate turbulent flows in toroidal pipes with two different curvatures. By means of proper orthogonal decomposition (POD), dominant coherent structures in the flow are identified. The most energetic structures in the strongly curved pipes (with curvature κ=0.1 and κ=0.3 and Reb=11,700 based on bulk velocity and diameter) are very similar in structure for both configurations studied. The dominant modes (shape and frequency) appear to match the coherent structures responsible for the swirl switching phenomenon found earlier in experimental and numerical studies of turbulent flow in spatially developing 90° bends, with which the current results are compared. The fact that turbulence in the toroidal pipe features low-frequency coherent structures very similar to swirl switching is relevant as it may challenge the current hypothesis regarding the origin of swirl switching, which is usually connected to the conditions in the upstream straight section. However, the toroidal pipe is homogeneous in the streamwise direction and does as such not feature a straight part.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Coherent motion; Curved pipes; Dean vortices; Pipe flow; Secondary motion; Swirl switching; Wall turbulence

Techniques for Turbulence Tripping of Boundary Layers in RANS Simulations - Tabatabaei, Narges; Vinuesa, Ricardo; Orlu, Ramis; Schlatter, Philipp (Flow Turbulence and Combustion, 2022)
The exact placement of the laminar–turbulent transition has a significant effect on relevant characteristics of the boundary layer and aerodynamics, such as drag, heat transfer and flow separation on e.g. wings and turbine blades. Tripping, which fixes the transition position, has been a valuable aid to wind-tunnel testing during the past 70 years, because it makes the transition independent of the local condition of the free-stream. Tripping helps to obey flow similarity for scaled models and serves as a passive control mechanism. Fundamental fluid-mechanics studies and many engineering developments are based on tripped cases. Therefore, it is essential for computational fluid dynamics (CFD) simulations to replicate the same forced transition, in spite of the advanced improvements in transition modelling. In the last decade, both direct numerical simulation (DNS) and large-eddy simulations (LES) include tripping methods in an effort to avoid the need for modeling the complex mechanisms associated with the natural transition process, which we would like to bring over to Reynolds-averaged Navier–Stokes (RANS) turbulence models. This paper investigates the implementation and performance of such a technique in RANS and specifically in the k- ω SST model. This study assesses RANS tripping with three alternatives: First, a recent approach of turbulence generation, denoted as turbulence-injection method (kI), is evaluated and investigated through different test cases; second, a predefined transition point is used in a traditional transition model (denoted as IM method); and third a novel formulation combining the two previous methods is proposed, denoted γ- kI. The model is compared with DNS, LES and experimental data in a variety of test cases ranging from a turbulent boundary layer on a flat plate to the three-dimensional (3D) flow over a wing section. The desired tripping is achieved at the target location and the simulation results compare very well with the reference results. With the application of the novel model, the challenging transition region can be excluded from a simulation, and consequently more reliable results can be provided.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Boundary layer; CFD RANS; Laminar–turbulent transition; Tripping

Temperature effects in hot-wire measurements on higher-order moments in wall turbulence - Talamelli, Alessandro; Malizia, Fabio; Orlu, Ramis; Cimarelli, Andrea; Schlatter, Philipp (Springer Proceedings in Physics, 2016)
CRIS-Team Scopus Importer:2023-03-21

The effect of lossy data compression in computational fluid dynamics applications: Resilience and data postprocessing - Otero, E.; Vinuesa, R.; Schlatter, Philipp; Marin, O.; Siegel, A.; Laure, E. (Springer, 2019)
The field of computational fluid dynamics (CFD) is data intensive, particularly for high-fidelity simulations. Direct and large-eddy simulations (DNS and LES), which are framed in this high-fidelity regime, require to capture a wide range of flow scales, a fact that leads to a high number of degrees of freedom. Besides the computational bottleneck, brought by the size of the problem, a slightly overlooked issue is the manipulation of the data. High amounts of disk space and also the slow speed of I/O (input/output) impose limitations on large-scale simulations. Typically the computational requirements for proper resolution of the flow structures are far higher than those of post-processing. To mitigate such shortcomings we employ a lossy data compression procedure, and track the reduction that occurs for various levels of truncation of the data set.
CRIS-Team Scopus Importer:2023-03-21

The influence of temperature fluctuations on hot-wire measurements in wall-bounded turbulence - Orlu, Ramis; Malizia, Fabio; Cimarelli, Andrea; Schlatter, Philipp; Talamelli, Alessandro (Experiments in Fluids, 2014)
There are no measurement techniques for turbulent flows capable of reaching the versatility of hot-wire probes and their frequency response. Nevertheless, the issue of their spatial resolution is still a matter of debate when it comes to high Reynolds number near-wall turbulence. Another, so far unattended, issue is the effect of temperature fluctuations - as they are, e.g. encountered in non-isothermal flows - on the low and higher-order moments in wall-bounded turbulent flows obtained through hot-wire anemometry. The present investigation is dedicated to document, understand, and ultimately correct these effects. For this purpose, the response of a hot-wire is simulated through the use of velocity and temperature data from a turbulent channel flow generated by means of direct numerical simulations. Results show that ignoring the effect of temperature fluctuations, caused by temperature gradients along the wall-normal direction, introduces - despite a local mean temperature compensation of the velocity reading - significant errors. The results serve as a note of caution for hot-wire measurements in wall-bounded turbulence, and also where temperature gradients are more prevalent, such as heat transfer measurements or high Mach number flows. A simple correction scheme involving only mean temperature quantities (besides the streamwise velocity information) is finally proposed that leads to a substantial bias error reduction. © 2014 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-21

The influence of thermal boundary conditions on turbulent forced convection pipe flow at two Prandtl numbers - Straub, Steffen; Forooghi, Pourya; Marocco, Luca; Wetzel, Thomas; Vinuesa, Ricardo; Schlatter, Philipp; Frohnapfel, Bettina (International Journal of Heat and Mass Transfer, 2019)
Different types of thermal boundary conditions are conceivable in numerical simulations of convective heat transfer problems. Isoflux, isothermal and a mixed-type boundary condition are compared by means of direct numerical simulations (for the lowest Reynolds number) and well-resolved large-eddy simulations of a turbulent forced convection pipe flow over a range of bulk Reynolds numbers from Reb=5300 to Reb=37700, at two Prandtl numbers, i.e. Pr=0.71 and Pr=0.025. It is found that, while for Pr=0.71 the Nusselt number is hardly affected by the type of thermal boundary condition, for Pr=0.025 the isothermal boundary condition yields ≈20% lower Nusselt numbers compared to isoflux and mixed-type over the whole range of Reynolds numbers. A decomposition of the Nusselt number is derived. In particular, we decompose it into four contributions: laminar, radial and streamwise turbulent heat flux as well as a contribution due to the turbulent velocity field. For Pr=0.71 the contribution due to the radial turbulent heat flux is dominant, whereas for Pr=0.025 the contribution due to the turbulent velocity field is dominant. Only at a moderately high Reynolds number, such as Reb=37700, both turbulent contributions are of similar magnitude. A comparison of first- and second-order thermal statistics between the different types of thermal boundary conditions shows that the statistics are not only influenced in the near-wall region but also in the core region of the flow. Power spectral densities illustrate large thermal structures in low-Prandtl-number fluids as well as thermal structures located right at the wall, only present for the isoflux boundary condition. A database including the first- and second-order statistics together with individual contributions to the budget equations of the temperature variance and turbulent heat fluxes is hosted in the open access repository KITopen (DOI:https://doi.org/10.5445/IR/1000096346).
CRIS-Team Scopus Importer:2023-03-21
Keywords: Forced convection; Low Prandtl number; Pipe; Thermal boundary conditions; Turbulence

The significance of hairpin vortices in turbulent boundary layers - Eitel-Amor, Georg; Örlü, Ramis; Schlatter, Philipp (ETC 2013 - 14th European Turbulence Conference, 2020)
The elementary question whether hairpin vortices constitute an inherent, universal structure of wall turbulence at moderate and high Reynolds numbers (Re) is addressed in this study. The downstream evolution of a single, artificial hairpin vortex is first studied in a mean shear flow to investigate possible decay and package-creation processes under high Re conditions. In a second step, hairpin-dominated flow in a transitional turbulent boundary layer is considered, whereas the lifetime of individual vortices and possible connection mechanisms are evaluated. The statistics obtained from this flow regime will be compared with reference data from turbulent-boundary-layer studies employing different transition mechanisms. Vortex eduction will be applied to comprehend the evolution from a well organized to a more chaotic state. The results could explain discrepancies in boundary-layer data close to transition and will contribute to the discussion about the relevance of hairpin-like structures in fully developed wall turbulence.
CRIS-Team Scopus Importer:2023-03-21

The skin-friction coefficient of a turbulent boundary layer modified by a large-eddy break-up device - Chan, I. C.; Orlu, Ramis; Schlatter, Philipp; Chin, R. C. (Physics of Fluids, 2021)
A computational study based on well-resolved large-eddy simulations is performed to study the skin friction modification by a large-eddy breakup device (LEBU) in a zero-pressure-gradient turbulent boundary layer. The LEBU was modeled using an immersed boundary method. It is observed that the presence of the device leads to the generation of wake vortices, which propagate downstream from the LEBU and toward the wall. A skin friction decomposition procedure is utilized to study different physical mechanisms of the observed skin friction reduction. From the skin friction decomposition, it is found that the skin friction reduction can be characterized by three universal regions of different changes for the skin friction contributions. The first region is predominantly associated with the formation of the wake vortices and the reduction of Reynolds shear stress. In the second region, the mean streamwise velocity fields show that a region of velocity deficit formed downstream of the LEBU propagates toward the wall and leads to turbulence reduction due to wake wall interactions, which also induces a local maximum skin friction reduction. In the third region, the dissipation of wake vortices leads to the regeneration of Reynolds shear stress. A quadrant analysis of the Reynolds shear stress contribution reveals that the LEBU increases the Q2 and Q4 contributions and attenuates the Q1 and Q3 contributions in the first region, followed by an onset of Reynolds shear stress further downstream.
CRIS-Team Scopus Importer:2023-03-21

The spectral-element and pseudo-spectral methods: A comparative study - Ohlsson, J.; Schlatter, Philipp; Mavriplis, C.; Henningson, D. S. (Lecture Notes in Computational Science and Engineering, 2011)
Turbulent and transitional channel flow simulations have been performed in order to assess the differences concerning speed and accuracy in the pseudo-spectral code simson and the spectral-element code nek5000. The results indicate that the pseudo-spectral code is 4-6 times faster than the spectral-element code in fully turbulent channel flow simulations, and up to 10-20 times faster when taking into account the more severe CFL restriction in the spectral-element code. No particular difference concerning accuracy could be noticed either in the turbulent nor the transitional cases, except for the pressure fluctuations at the wall which converge slower for the spectral-element code. © 2011 Springer.
CRIS-Team Scopus Importer:2023-03-21

The three-dimensional structure of swirl-switching in bent pipe flow - Hufnagel, Lorenz; Canton, Jacopo; Orlu, Ramis; Marin, Oana; Merzari, Elia; Schlatter, Philipp (Journal of Fluid Mechanics, 2018)
Swirl-switching is a low-frequency oscillatory phenomenon which affects the Dean vortices in bent pipes and may cause fatigue in piping systems. Despite thirty years worth of research, the mechanism that causes these oscillations and the frequencies that characterise them remain unclear. Here we show that a three-dimensional wave-like structure is responsible for the low-frequency switching of the dominant Dean vortex. The present study, performed via direct numerical simulation, focuses on the turbulent flow through a pipe bend preceded and followed by straight pipe segments. A pipe with curvature 0.3 (defined as ratio between pipe radius and bend radius) is studied for a bulk Reynolds number , corresponding to a friction Reynolds number . Synthetic turbulence is generated at the inflow section and used instead of the classical recycling method in order to avoid the interference between recycling and swirl-switching frequencies. The flow field is analysed by three-dimensional proper orthogonal decomposition (POD) which for the first time allows the identification of the source of swirl-switching: a wave-like structure that originates in the pipe bend. Contrary to some previous studies, the flow in the upstream pipe does not show any direct influence on the swirl-switching modes. Our analysis further shows that a three-dimensional characterisation of the modes is crucial to understand the mechanism, and that reconstructions based on two-dimensional POD modes are incomplete.
CRIS-Team Scopus Importer:2023-03-21
Keywords: pipe flow boundary layer; turbulence simulation; turbulent flows

The vanishing of strong turbulent fronts in bent pipes - Rinaldi, Enrico; Canton, Jacopo; Schlatter, Philipp (Journal of Fluid Mechanics, 2019)
Isolated patches of turbulence in transitional straight pipes are sustained by a strong instability at their upstream front, where the production of turbulent kinetic energy (TKE) is up to five times higher than in the core. Direct numerical simulations presented in this paper show no evidence of such strong fronts if the pipe is bent. We examine the temporal and spatial evolution of puffs and slugs in a toroidal pipe with pipe-to-torus diameter ratio at several subcritical Reynolds numbers. Results show that the upstream overshoot of TKE production is at most one-and-a-half times the value in the core and that the average cross-flow fluctuations at the front are up to three times lower if compared to a straight pipe, while attaining similar values in the core. Localised turbulence can be sustained at smaller energies through a redistribution of turbulent fluctuations and vortical structures by the in-plane Dean motion of the mean flow. This asymmetry determines a strong localisation of TKE production near the outer bend, where linear and nonlinear mechanisms optimally amplify perturbations. We further observe a substantial reduction of the range of Reynolds numbers for long-lived intermittent turbulence, in agreement with experimental data from the literature. Moreover, no occurrence of nucleation of spots through splitting could be detected in the range of parameters considered. Based on the present results, we argue that this mechanism gradually becomes marginal as the curvature of the pipe increases and the transition scenario approaches a dynamical switch from subcritical to supercritical.
CRIS-Team Scopus Importer:2023-03-21
Keywords: nonlinear instability; pipe flow boundary layer; transition to turbulence

The viscous sublayer revisited-exploiting self-similarity to determine the wall position and friction velocity - Alfredsson, P. Henrik; Orlu, Ramis; Schlatter, Philipp (Experiments in Fluids, 2011)
In experiments using hot wires near the wall, it is well known that wall interference effects between the hot wire and the wall give rise to errors, and mean velocity data from the viscous sublayer can usually not be used to determine the wall position, nor the friction velocity from the linear velocity distribution. Here, we introduce a new method that takes advantage of the similarity of the probability density distributions (PDF) or rather the cumulative distribution functions (CDF) in the near-wall region. By using the velocity data in the CDF in a novel way, it is possible to circumvent the problem associated with heat transfer to the wall and to accurately determine both the wall position and the friction velocity. Prior to its exploitation, the self-similarity of the distribution functions of the streamwise velocity fluctuations within the viscous sublayer is established, and it is shown that they can accurately be described by a lognormal distribution. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-21

Topology optimization of heat sinks in a square differentially heated cavity - Saglietti, Clio; Schlatter, Philipp; Wadbro, Eddie; Berggren, Martin; Henningson, Dan S. (International Journal of Heat and Fluid Flow, 2018)
Innovative designs of heat sinks are generated in the present paper through numerical optimization, by applying a material distribution topology optimization approach. The potential of the method is demonstrated in a two-dimensional differentially heated cavity, in which the heat transfer is increased by means of introducing a solid structure that acts as a heat sink. We simulate the heat transfer in the whole system by performing direct numerical simulations of the conjugated problem, i.e. temperature diffusion and convection in the entire domain and momentum conservation in the fluid surrounding the solid. The flow is driven by the buoyancy force, under the Boussinesq approximation, and we describe the presence of solid material as the action of a Brinkman friction force in the Navier–Stokes equations. To obtain a design with a given length scale, we apply regularization techniques by filtering the material distribution. Two different types of filters are applied and compared for obtaining the most realistic solution. Given the large scale of the problem, the optimization is solved with a gradient based method that relies on adjoint sensitivity analysis. The results show the applicability of the method by presenting innovative geometries that are increasing the heat flux. Moreover, the effect of various factors is studied: We investigate the impact of boundary conditions, initial designs, and Rayleigh number. Complex tree-like structures are favored when a horizontal temperature gradient is imposed on the boundary and when we limit the amount of solid volume in the cavity. The choice of the initial design affects the final topology of the generated solid structures, but not their performance for the studied cases. Additionally, when the Rayleigh number increases, the topology of the heat exchanger is able to substantially enhance the convection contribution to the heat transfer.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Conjugate heat transfer; Differentially heated cavity; Direct numerical simulations; Heat sink; Natural convection; Topology optimization

Topology optimization of unsteady flows using the spectral element method - Nobis, Harrison; Schlatter, Philipp; Wadbro, Eddie; Berggren, Martin; Henningson, Dan S. (Computers & Fluids, 2022)
We investigate the applicability of a high-order Spectral Element Method (SEM) to density based topology optimization of unsteady flows in two dimensions. Direct Numerical Simulations (DNS) are conducted relying on Brinkman penalization to describe the presence of solid within the domain. The optimization procedure uses the adjoint-variable method to compute gradients and a checkpointing strategy to reduce storage requirements. A nonlinear filtering strategy is used to both enforce a minimum length scale and to provide smoothing across the fluid–solid interface, preventing Gibbs oscillations. This method has been successfully applied to the design of a channel bend and an oscillating pump, and demonstrates good agreement with body fitted meshes. The precise design of the pump is shown to depend on the initial material distribution. However, the underlying topology and pumping mechanism is the same. The effect of a minimum length scale has been studied, revealing it to be a necessary regularization constraint for the oscillating pump to produce meaningful designs. The combination of SEM and density based optimization offer some unique challenges which are addressed and discussed, namely a lack of explicit boundary tracking exacerbated by the interface smoothing. Nevertheless, SEM can achieve equivalent levels of precision to traditional finite element methods, while requiring fewer degrees of freedom. Hence, the use of SEM addresses the two major bottlenecks associated with optimizing unsteady flows: computation cost and data storage.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct numerical simulations; Length scale control; Non-linear filtering; Spectral element method; Topology optimization; Unsteady

Towards adaptive mesh refinement for the spectral element solver Nek5000 - Offermans, N.; Peplinski, A.; Marin, O.; Fischer, P. F.; Schlatter, Philipp (Springer, 2019)
When performing computational fluid dynamics (CFD) simulations of complex flows, the a priori knowledge of the flow physics and the location of the dominant flow features are usually unknown. For this reason, the development of adaptive remeshing techniques is crucial for large-scale computational problems. Some work has been made recently to provide Nek5000 with adaptive mesh refinement (AMR) capabilities in order to facilitate the generation of the grid and push forward the limit in terms of problem size and complexity [10].
CRIS-Team Scopus Importer:2023-03-21

Towards canonical adverse-pressure-gradient turbulent boundary layers - Örlü, Ramis; Vinuesa, Ricardo; Vila, Carlos Sanmiguel; DIscetti, Stefano; Ianiro, Andrea; Schlatter, Philipp (10th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2017, 2017)
The present investigation focuses on the concerted investigation of pressure gradient and streamwise curvature effects on turbulent boundary layers. In particular, a number of direct and large-eddy simulations covering a wide range of pressure gradient parameters and streamwise histories on flat and curved surfaces is performed and will be compared with wind-tunnel experiments utilising hot-wire anemometry and particle image velocimetry that overlap and extend the Reynolds number range. Results are aimed at isolating the effects of pressure gradients, streamwise curvature and streamwise (pressure gradient) histories as well as Reynolds number, which have traditionally inhibited to draw firm conclusions from the available data.
CRIS-Team Scopus Importer:2023-03-21

Towards large-eddy simulations of high-reynolds number turbulent boundary layers - Schlatter, Philipp; Li, Qiang; Brethouwer, Geert; Johansson, Arne V.; Henningson, Dan S. (6th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2009, 2009)
Well-resolved large-eddy simulations (LES) of a spatially developing turbulent boundary layer under zero pressure gradient up to comparably high Reynolds numbers (Reθ = 4300) are performed. The inflow is located at Reδ∗ = 450 (Reθ ≈ 300), a position where natural transition to turbulence can be expected. Results are validated and compared extensively to both numerical data sets (e.g. an on-going fully-resolved spatial direct numerical simulation (DNS) up to Reθ = 2500) and available experimental measurements, e.g. the ones obtained by Österlund et al. (1999). The goal is to provide the research community with reliable numerical data for high Reynolds-number wall-bounded turbulence, which can in turn be employed for further model development and validation, but also to contribute to the characterisation and understanding of wall turbulence. The results obtained via LES show that good agreement with existing data, both numerically at lower Reynolds numbers and experimentally, can be obtained for both mean and fluctuating quantities. In addition, turbulence spectra characterising large-scale organisation in the flow have been obtained and compared to literature results with good agreement. In particular, the near-wall streaks scaling in inner units and the outer layer, large-scale structures can clearly be identified in both spanwise and temporal spectra. The present contribution focuses on presenting selected results, in an effort to validate the chosen simulation approach and to initiate further studies analysing the simulation data.
CRIS-Team Scopus Importer:2023-03-21

Towards multifidelity models with calibration for turbulent flows - Rezaeiravesh, Saleh; Vinuesa, Ricardo; Schlatter, Philipp (World Congress in Computational Mechanics and ECCOMAS Congress, 2021)
High-fidelity scale-resolving simulations of turbulent flows can be prohibitively expensive, especially at high Reynolds numbers. Therefore, multifidelity models (MFM) can be highly relevant for constructing predictive models for flow quantities of interest (QoIs), uncertainty quantification, and optimization. For numerical simulation of turbulence, there is a hierarchy of methodologies. On the other hand, there are calibration parameters in each of these methods which control the predictive accuracy of the resulting outputs. Compatible with these, the hierarchical MFM strategy which allows for simultaneous calibration of the model parameters as developed by Goh et al. [7] within a Bayesian framework is considered in the present study. The multifidelity model is applied to two cases related to wall-bounded turbulent flows. The examples are the prediction of friction at different Reynolds numbers in turbulent channel flow, and the prediction of aerodynamic coefficients for a range of angles of attack of a standard airfoil. In both cases, based on a few high-fidelity datasets, the MFM leads to accurate predictions of the QoIs as well as an estimation of uncertainty in the predictions.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Calibration; Hierarchical Multifidelity Models; Turbulent Flows; Uncertainty Quantification

Transfer functions for flow predictions in wall-bounded turbulence - Sasaki, Kenzo; Vinuesa, Ricardo; Cavalieri, Andre V. G.; Schlatter, Philipp; Henningson, Dan S. (Journal of Fluid Mechanics, 2019)
Three methods are evaluated to estimate the streamwise velocity fluctuations of a zero-pressure-gradient turbulent boundary layer of momentum-Thickness-based Reynolds number up to , using as input velocity fluctuations at different wall-normal positions. A system identification approach is considered where large-eddy simulation data are used to build single and multiple-input linear and nonlinear transfer functions. Such transfer functions are then treated as convolution kernels and may be used as models for the prediction of the fluctuations. Good agreement between predicted and reference data is observed when the streamwise velocity in the near-wall region is estimated from fluctuations in the outer region. Both the unsteady behaviour of the fluctuations and the spectral content of the data are properly predicted. It is shown that approximately 45Â % of the energy in the near-wall peak is linearly correlated with the outer-layer structures, for the reference case . These identified transfer functions allow insight into the causality between the different wall-normal locations in a turbulent boundary layer along with an estimation of the tilting angle of the large-scale structures. Differences in accuracy of the methods (single-and multiple-input linear and nonlinear) are assessed by evaluating the coherence of the structures between wall-normally separated positions. It is shown that the large-scale fluctuations are coherent between the outer and inner layers, by means of an interactions which strengthens with increasing Reynolds number, whereas the finer-scale fluctuations are only coherent within the near-wall region. This enables the possibility of considering the wall-shear stress as an input measurement, which would more easily allow the implementation of these methods in experimental applications. A parametric study was also performed by evaluating the effect of the Reynolds number, wall-normal positions and input quantities considered in the model. Since the methods vary in terms of their complexity for implementation, computational expense and accuracy, the technique of choice will depend on the application under consideration. We also assessed the possibility of designing and testing the models at different Reynolds numbers, where it is shown that the prediction of the near-wall peak from wall-shear-stress measurements is practically unaffected even for a one order of magnitude change in the corresponding Reynolds number of the design and test, indicating that the interaction between the near-wall peak fluctuations and the wall is approximately Reynolds-number independent. Furthermore, given the performance of such methods in the prediction of flow features in turbulent boundary layers, they have a good potential for implementation in experiments and realistic flow control applications, where the prediction of the near-wall peak led to correlations above 0.80 when wall-shear stress was used in a multiple-input or nonlinear scheme. Errors of the order of 20Â % were also observed in the determination of the near-wall spectral peak, depending on the employed method.
CRIS-Team Scopus Importer:2023-03-21
Keywords: turbulence modelling; turbulent boundary layers

Transitional and turbulent bent pipes - Schlatter, Philipp; Noorani, Azad; Canton, Jacopo; Hufnagel, Lorenz; Orlu, Ramis; Marin, Oana; Merzari, Elia (Springer Proceedings in Physics, 2017)
We review a number of aspects of the transitional and turbulent flow in bent pipes, obtained at KTH using the spectral-element code Nek5000. This flow, sometimes also called Dean flow, is characterised by the appearance of Dean vortices, which arise due to the action of the centrifugal force in the bend. We start with reviewing recent stability analysis in the toroidal flow, and conclude that for all curvatures δ>0 an exponential instability is present at a bulk Reynolds number of about 4000. Further increasing the Reynolds number lets the flow go through a region with potential sub straight and sublaminar drag. An analysis using proper orthogonal decomposition (POD) reveals that wave-like motions are still present in the otherwise turbulent flow. Upon further increasing Re, the in-plane Dean vortices lead to a modulation of turbulence depending on the azimuthal position. The flow is then dominated by low-frequency so-called swirl-switching motion. This motion is studied in both a periodic and spatially developing framework. Finally, the effect of Dean vortices on Lagrangian inertial particles is studied.
CRIS-Team Scopus Importer:2023-03-21

Transition to turbulence in the rotating-disk boundary layer - Appelquist, E.; Schlatter, Philipp; Alfredsson, P. H.; Lingwood, R. J. (ETC 2013 - 14th European Turbulence Conference, 2020)
The development of the flow over a rotating disk is investigated by direct numerical simulations using both the linearised and fully nonlinear Navier-Stokes equations. The nonlinear simulations allow investigation of the transition to turbulence of the realistic spatially-developing boundary layer, and these simulations can be directly validated by physical experiments of the same case. The current research aims to elucidate further the global stability properties of the flow. So far, there are no conclusive simulations available in the literature for the fully nonlinear case for this flow, and since the nonlinearity is particularly relevant for transition to turbulence an increased understanding of this process is expected.
CRIS-Team Scopus Importer:2023-03-21

Transition to turbulence in the rotating-disk boundary-layer flow with stationary vortices - Appelquist, E.; Schlatter, Philipp; Alfredsson, P. H.; Lingwood, R. J. (Journal of Fluid Mechanics, 2018)
This paper proposes a resolution to the conundrum of the roles of convective and absolute instability in transition of the rotating-disk boundary layer. It also draws some comparison with swept-wing flows. Direct numerical simulations based on the incompressible Navier-Stokes equations of the flow over the surface of a rotating disk with modelled roughness elements are presented. The rotating-disk flow has been of particular interest for stability and transition research since the work by Lingwood (J.Â FluidÂ Mech., vol.Â 299, 1995, pp.Â 17-33) where an absolute instability was found. Here stationary disturbances develop from roughness elements on the disk and are followed from the linear stage, growing to saturation and finally transitioning to turbulence. Several simulations are presented with varying disturbance amplitudes. The lowest amplitude corresponds approximately to the experiment by Imayama etÂ al. (J.Â FluidÂ Mech., vol.Â 745, 2014a, pp.Â 132-163). For all cases, the primary instability was found to be convectively unstable, and secondary modes were found to be triggered spontaneously while the flow was developing. The secondary modes further stayed within the domain, and an explanation for this is a proposed globally unstable secondary instability. For the low-amplitude roughness cases, the disturbances propagate beyond the threshold for secondary global instability before becoming turbulent, and for the high-amplitude roughness cases the transition scenario gives a turbulent flow directly at the critical Reynolds number for the secondary global instability. These results correspond to the theory of Pier (J.Â EngngÂ Maths, vol.Â 57, 2007, pp.Â 237-251) predicting a secondary absolute instability. In our simulations, high temporal frequencies were found to grow with a large amplification rate where the secondary global instability occurred. For smaller radial positions, low-frequency secondary instabilities were observed, tripped by the global instability.
CRIS-Team Scopus Importer:2023-03-21
Keywords: absolute/convective instability; nonlinear instability; transition to turbulence

Transport of inertial particles in turbulent boundary layers - Sardina, Gaetano; Brandt, Luca; Schlatter, Philipp; Casciola, Carlo Massimo; Henningson, Dan S. (Journal of Physics: Conference Series, 2011)
A direct numerical simulations (DNS) of a spatially evolving particle-laden turbulent boundary layer has been performed to study turbophoresis effects in presence of changing local Stokes number. The data show a preferential particle localization near the wall at the streamwise position where the local Stokes number St+ assumes a value close to 25, similarly to that found in channel flow. Note that a complete steady state will never been reached for the particle concentration in this kind of flow. The effects of the seeding and of preferential sampling of the fluid velocity will be described as well.
CRIS-Team Scopus Importer:2023-03-21

Turbulence and cyclic bursts in rotating channel flow - Brethouwer, Geert; Wei, Liang; Schlatter, Philipp; Johansson, Arne V. (ETC 2013 - 14th European Turbulence Conference, 2020)
DNS have been performed of turbulent channel flow with spanwise rotation and bulk Reynolds number Re up to 30000. At moderate rotation rates Ro the flow on one side of the channel is approximately laminar, or has turbulent patches or oblique turbulent-laminar patterns. Intense cyclic bursts of turbulence with long time intervals are in some cases observed at sufficiently high Re and Ro. A linear analysis indicates that the turbulence bursts are initiated by a linear instability of plane waves aligned with the rotation axis. This linear instability can develop even if parts of the flow are strongly turbulent.
CRIS-Team Scopus Importer:2023-03-21

Turbulence collapse in a suction boundary layer - Khapko, T.; Schlatter, Philipp; Duguet, Y.; Henningson, D. S. (Journal of Fluid Mechanics, 2016)
Turbulence in the asymptotic suction boundary layer is investigated numerically at the verge of laminarisation using direct numerical simulation. Following an adiabatic protocol, the Reynolds number Re is decreased in small steps starting from a fully turbulent state until laminarisation is observed. Computations in a large numerical domain allow in principle for the possible coexistence of laminar and turbulent regions. However, contrary to other subcritical shear flows, no laminar-turbulent coexistence is observed, even near the onset of sustained turbulence. High-resolution computations suggest a critical Reynolds number Reg ∼ 270, below which turbulence collapses, based on observation times of O(105) inertial time units. During the laminarisation process, the turbulent flow fragments into a series of transient streamwise-elongated structures, whose interfaces do not display the characteristic obliqueness of classical laminar-turbulent patterns. The law of the wall, i.e. logarithmic scaling of the velocity profile, is retained down to Reg, suggesting a large-scale wall-normal transport absent in internal shear flows close to the onset. In order to test the effect of these large-scale structures on the near-wall region, an artificial volume force is added to damp spanwise and wall-normal fluctuations above y+ = 100, in viscous units. Once the largest eddies have been suppressed by the forcing, and thus turbulence is confined to the near-wall region, oblique laminar-turbulent interfaces do emerge as in other wall-bounded flows, however only transiently. These results suggest that oblique stripes at the onset are a prevalent feature of internal shear flows, but will not occur in canonical boundary layers, including the spatially growing ones.
CRIS-Team Scopus Importer:2023-03-21
Keywords: intermittency; turbulent boundary layers; turbulent transition

Turbulence, instabilities and heat transfer in rotating channel flow simulations - Brethouwer, G.; Wei, L.; Schlatter, Philipp; Johansson, A. V. (Proceedings of the International Symposium on Turbulence, Heat and Mass Transfer, 2012)
Direct numerical simulations of fully developed turbulent channel flow rotating about the spanwise direction are performed over a wide range of Reynolds numbers and rotation speeds. A scalar is also included to examine rotation effects on heat transfer. The Reynolds number based on the bulk mean velocity is up to 30 000, which is higher than in previous studies of rotating channel flow. The flow partly or completely relaminarizes on the stable channel side at sufficiently high rotation speeds, leading to distinct turbulent-laminar patterns in certain cases. Strong cyclic bursts of turbulence are observed at higher rotation speeds and sufficiently high Reynolds numbers. Further analysis showed that the burst are caused by plane spanwise waves with a rapidly growing amplitude, which become unstable after some time and break down into intense turbulence. Rotation strongly affects the direction of the turbulent scalar flux and significantly reduces the turbulent Prandtl number.
CRIS-Team Scopus Importer:2023-03-21

Turbulence, instabilities and passive scalars in rotating channel flow - Brethouwer, Geert; Schlatter, Philipp; Johansson, Arne V. (Journal of Physics: Conference Series, 2011)
Fully developed channel flow with a passive scalar rotating about the spanwise axis is studied by direct numerical simulations. The Reynolds number based on the bulk mean velocity Reb is up to 30000, substantially higher than in previous studies, and the rotation rates cover a broad range. Turbulence on the stable channel side is less strongly damped at moderate rotation rates than in channel flow at lower Reb. At high rotation rates and sufficiently high Reb, intermittent strong instabilities occur on the stable side caused by rapidly growing modes resembling two-dimensional Tollmien-Schlichting waves which at some instant become unstable and break down into intense turbulence. The turbulence decays and after some time the waves form again and the process is repeated in a cyclic manner. Rotation also strongly affects the mean passive scalar profiles and turbulent scalar fluxes. Large scalar fluctuations are observed on the border between the stable and unstable channel sides. While in non-rotating channel flow the turbulent Prandtl number of the passive scalar is about one like in other shear flows, it is much smaller in the rotating cases.
CRIS-Team Scopus Importer:2023-03-21

Turbulence in the rotating-disk boundary layer investigated through direct numerical simulations - Appelquist, E.; Schlatter, Philipp; Alfredsson, P. H.; Lingwood, R. J. (European Journal of Mechanics B-Fluids, 2018)
Direct numerical simulations (DNS) are reported for the turbulent rotating-disk boundary layer for the first time. Two turbulent simulations are presented with overlapping small and large Reynolds numbers, where the largest corresponds to a momentum-loss Reynolds number of almost 2000. Simulation data are compared with experimental data from the same flow case reported by Imayama et al. (2014), and also a comparison is made with a numerical simulation of a two-dimensional turbulent boundary layer (2DTBL) over a flat plate reported by Schlatter and Örlü (2010). The agreement of the turbulent statistics between experiments and simulations is in general very good, as well as the findings of a missing wake region and a lower shape factor compared to the 2DTBL. The simulations also show rms-levels in the inner region similar to the 2DTBL. The simulations validate Imayama et al.’s results showing that the rotating-disk turbulent boundary layer in the near-wall region contains shorter streamwise (azimuthal) wavelengths than the 2DTBL, probably due to the outward inclination of the low-speed streaks. Moreover, all velocity components are available from the simulations, and hence the local flow angle, Reynolds stresses and all terms in the turbulent kinetic energy equation are also discussed. However there are in general no large differences compared to the 2DTBL, hence the three-dimensional effects seem to have only a small influence on the turbulence.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Near-wall turbulence; Rotation; Turbulence statistics

Turbulence transition in the asymptotic suction boundary layer - Kreilos, Tobias; Khapko, Taras; Schneider, Tobias M.; Veble, Gregor; Duguet, Yohann; Schlatter, Philipp; Henningson, Dan S.; Eckhardt, Bruno (International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2013, 2013)
We study the transition to turbulence in the asymptotic suction boundary layer (ASBL) by direct numerical simulation. Tracking the motion of trajectories intermediate between laminar and turbulent states we can identify the invariant object inside the laminar-Turbulent boundary, the edge state. In small domains, the flow behaves like a travelling wave over short time intervals. On longer times one notes that the energy shows strong bursts at regular time intervals. During the bursts the streak structure is lost, but it reforms, translated in the spanwise direction by half the domain size. Varying the suction velocity allows to embed the flow into a family of flows that interpolate between plane Couette flow and the ASBL. Near the plane Couette limit, the edge state is a travelling wave. Increasing the suction, the travelling wave and a symmetry-related copy of it undergo a saddle-node infinite-period (SNIPER) bifurcation that leads to bursting and discrete-symmetry shifts. In wider domains, the structures localize in the spanwise direction, and the flow in the active region is similar to the one in small domains. There are still periodic bursts at which the flow structures are shifted, but the shift-distance is no longer connected to a discrete symmetry of the flow geometry. Two different states are found by edge tracking techniques, one where structures are shifted to the same side at every burst and one where they are alternatingly shifted to the left and to the right.
CRIS-Team Scopus Importer:2023-03-21

Turbulent asymptotic suction boundary layers: Effect of domain size and development time - Bobke, Alexandra; Orlu, Ramis; Schlatter, Philipp (Springer Proceedings in Physics, 2016)
CRIS-Team Scopus Importer:2023-03-21

Turbulent asymptotic suction boundary layers studied by simulation - Schlatter, Philipp; Orlu, Ramis (Journal of Physics: Conference Series, 2011)
The turbulent asymptotic suction boundary layer (ASBL) is studied using numerical simulations. Uniform suction is applied on the wall in order to compensate for the momentum loss inflicted by the wall friction. Four Reynolds numbers, defined as the ratio of free-stream velocity and suction rate, Re = 333, 400 and 500, are considered, whereas Re = 280 relaminarised. In agreement with previous studies, suction causes the fluctuation intensities to decrease, and the near-wall anisotropy to increase. The shape of the mean velocity profile is considerably changed yielding a decreased slope in the overlap region. It is shown that even for moderate suction rates large values for the friction Reynolds number Reτ = δ99+ are obtained; at Re = 333 a value of Reτ = 1900 is reached and Re = 400 yields Reτ = 5700. Artificially using smaller computational domains, limiting the size of the largest turbulent structures, gives unexpected results: The mean velocity profile starts to show a distinct wake region which only disappears for large enough domains. Moreover, the boundary layer thickness δ99 strongly depends on the chosen domain size. Spectral maps of the flow are analysed, showing an outer peak appearing at a spanwise size of about 0.6δ99, albeit with considerably lower amplitude compared to cases without suction. Visualisations of the flow are also discussed.
CRIS-Team Scopus Importer:2023-03-21

Turbulent Boundary-Layer Flow: Comparing Experiments with DNS - Örlü, R.; Schlatter, Philipp (Springer Proceedings in Physics, 2012)
CRIS-Team Scopus Importer:2023-03-21

Turbulent boundary layers around wing sections up to Rec=1,000,000 - Vinuesa, Ricardo; Negi, P. S.; Atzori, Marco; Hanifi, Ardeshir; Henningson, D. S.; Schlatter, Philipp (International Journal of Heat and Fluid Flow, 2018)
Reynolds-number effects in the adverse-pressure-gradient (APG) turbulent boundary layer (TBL) developing on the suction side of a NACA4412 wing section are assessed in the present work. To this end, we analyze four cases at Reynolds numbers based on freestream velocity and chord length ranging from Rec=100,000 to 1,000,000, all of them with 5° angle of attack. The results of four well-resolved large-eddy simulations (LESs) are used to characterize the effect of Reynolds number on APG TBLs subjected to approximately the same pressure-gradient distribution (defined by the Clauser pressure-gradient parameter β). Comparisons of the wing profiles with zero-pressure-gradient (ZPG) data at matched friction Reynolds numbers reveal that, for approximately the same β distribution, the lower-Reynolds-number boundary layers are more sensitive to pressure-gradient effects. This is reflected in the values of the inner-scaled edge velocity Ue +, the shape factor H, the components of the Reynolds-stress tensor in the outer region and the outer-region production of turbulent kinetic energy. This conclusion is supported by the larger wall-normal velocities and outer-scaled fluctuations observed in the lower-Rec cases. Thus, our results suggest that two complementing mechanisms contribute to the development of the outer region in TBLs and the formation of large-scale energetic structures: one mechanism associated with the increase in Reynolds number, and another one connected to the APG. Future extensions of the present work will be aimed at studying the differences in the outer-region energizing mechanisms due to APGs and increasing Reynolds number.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Large-eddy simulation; Pressure gradient; Turbulent boundary layer; Wing section

Turbulent boundary layers at moderate Reynolds numbers: Inflow length and tripping effects - Schlatter, Philipp; Orlu, Ramis (Journal of Fluid Mechanics, 2012)
A recent assessment of available direct numerical simulation (DNS) data from turbulent boundary layer flows (Schlatter & Örlü, J. Fluid Mech., vol. 659, 2010, pp. 116-126) showed surprisingly large differences not only in the skin friction coefficient or shape factor, but also in their predictions of mean and fluctuation profiles far into the sublayer. While such differences are expected at very low Reynolds numbers and/or the immediate vicinity of the inflow or tripping region, it remains unclear whether inflow and tripping effects explain the differences observed even at moderate Reynolds numbers. This question is systematically addressed by re-simulating the DNS of a zero-pressure-gradient turbulent boundary layer flow by Schlatter et al. (Phys. Fluids, vol. 21, 2009, art. 051702). The previous DNS serves as the baseline simulation, and the new DNS with a range of physically different inflow conditions and tripping effects are carefully compared. The downstream evolution of integral quantities as well as mean and fluctuation profiles is analysed, and the results show that different inflow conditions and tripping effects do indeed explain most of the differences observed when comparing available DNS at low Reynolds number. It is further found that, if transition is initiated inside the boundary layer at a low enough Reynolds number (based on the momentum-loss thickness) Reθ> 300, all quantities agree well for both inner and outer layer for Reθ> 2000. This result gives a lower limit for meaningful comparisons between numerical and/or wind tunnel experiments, assuming that the flow was not severely over- or understimulated. It is further shown that even profiles of the wall-normal velocity fluctuations and Reynolds shear stress collapse for higher Re θ> irrespective of the upstream conditions. In addition, the overshoot in the total shear stress within the sublayer observed in the DNS of Wu & Moin (Phys. Fluids, vol. 22, 2010, art. 085105) has been identified as a feature of transitional boundary layers. Copyright © 2012 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21
Keywords: transition to turbulence; turbulence simulation; turbulent boundary layers

Turbulent boundary layers in long computational domains - Eitel-Amor, G.; Örlü, R.; Schlatter, Philipp (ERCOFTAC Series, 2015)
CRIS-Team Scopus Importer:2023-03-21

Turbulent boundary layers up to Retheta;=2500 studied through simulation and experiment - Schlatter, Philipp; Orlu, R.; Li, Q.; Brethouwer, G.; Fransson, J. H. M.; Johansson, A. V.; Alfredsson, P. H.; Henningson, D. S. (Physics of Fluids, 2009)
Direct numerical simulations (DNSs) and experiments of a spatially developing zero-pressure-gradient turbulent boundary layer are presented up to Reynolds number Reθ=2500, based on momentum thickness θ and free-stream velocity. For the first time direct comparisons of DNS and experiments of turbulent boundary layers at the same (computationally high and experimentally low) Reθ are given, showing excellent agreement in skin friction, mean velocity, and turbulent fluctuations. These results allow for a substantial reduction of the uncertainty of boundary-layer data, and cross validate the numerical setup and experimental technique. The additional insight into the flow provided by DNS clearly shows large-scale turbulent structures, which scale in outer units growing with Reθ, spanning the whole boundary-layer height. © 2009 American Institute of Physics.
CRIS-Team Scopus Importer:2023-03-21

Turbulent Duct Flow Controlled with Spanwise Wall Oscillations - Straub, Steffen; Vinuesa, Ricardo; Schlatter, Philipp; Frohnapfel, Bettina; Gatti, Davide (Flow Turbulence and Combustion, 2017)
The spanwise oscillation of channel walls is known to substantially reduce the skin-friction drag in turbulent channel flows. In order to understand the limitations of this flow control approach when applied in ducts, direct numerical simulations of controlled turbulent duct flows with an aspect ratio of AR = 3 are performed. In contrast to channel flows, the spanwise extension of the duct is limited. Therefore, the spanwise wall oscillation either directly interacts with the duct side walls or its spatial extent is limited to a certain region of the duct. The present results show that this spanwise limitation of the oscillating region strongly diminishes the drag reduction potential of the control technique. We propose a simple model that allows estimating the achievable drag reduction rates in duct flows as a function of the width of the duct and the spanwise extent of the controlled region.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Control; DNS; Duct flow; Oscillating walls; Secondary flow

Turbulent-laminar coexistence in wall flows with Coriolis, buoyancy or Lorentz forces - Brethouwer, G.; Duguet, Y.; Schlatter, Philipp (Journal of Fluid Mechanics, 2012)
Direct numerical simulations of subcritical rotating, stratified and magneto-hydrodynamic wall-bounded flows are performed in large computational domains, focusing on parameters where laminar and turbulent flow can stably coexist. In most cases, a regime of large-scale oblique laminar-turbulent patterns is identified at the onset of transition, as in the case of pure shear flows. The current study indicates that this oblique regime can be shifted up to large values of the Reynolds number Re by increasing the damping by the Coriolis, buoyancy or Lorentz force. We show evidence for this phenomenon in three distinct flow cases: plane Couette flow with spanwise cyclonic rotation, plane magnetohydrodynamic channel flow with a spanwise or wall-normal magnetic field, and open channel flow under stable stratification. Near-wall turbulence structures inside the turbulent patterns are invariably found to scale in terms of viscous wall units as in the fully turbulent case, while the patterns themselves remain large-scale with a trend towards shorter wavelength for increasing Re. Two distinct regimes are identified: at low Reynolds numbers the patterns extend from one wall to the other, while at large Reynolds number they are confined to the near-wall regions and the patterns on both channel sides are uncorrelated, the core of the flow being highly turbulent without any dominant large-scale structure. © 2012 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21
Keywords: transition to turbulence; turbulent flows

Turbulent pipe flow: New DNS data and large-scale structures - El Khoury, George K.; Schlatter, Philipp; Brethouwer, Geert; Johansson, Arne V. (ETC 2013 - 14th European Turbulence Conference, 2020)
Large-scale fully resolved direct numerical simulations (DNSs) have been performed with a high-order spectral element method to study the flow of an incompressible viscous fluid in a smooth circular pipe of radius R and axial length 25R in the turbulent flow regime at four different friction Reynolds numbers Reτ = 180, 360, 550 and 1000. The new data is compared to other simulation data sets, obtained in pipe, channel and boundary-layer geometry. The pressure is the variable that differs the most between the cases; a significantly higher mean and fluctuating pressure are observed in boundary layers that is linked to a stronger wake region. Critical assessment of the available DNS data is conducted in order to determine which difference or correspondence between the data sets are real and caused by physics, and which discrepancies are likely due to statistical or numerical inaccuracies. Furthermore, two-dimensional spectra of axial/streamwise velocity show an imprint of the large-scale motions from the outer layer in all canonical flows, however with different amplitude.
CRIS-Team Scopus Importer:2023-03-21

Turbulent pipe flow: Statistics, Re-dependence, structures and similarities with channel and boundary layer flows - El Khoury, George K.; Schlatter, Philipp; Brethouwer, Geert; Johansson, Arne V. (Journal of Physics: Conference Series, 2014)
Direct numerical simulation data of fully developed turbulent pipe flow are extensively compared with those of turbulent channel flow and zero-pressure-gradient boundary layer flow for Reτ up to 1000. In the near-wall region, a high degree of similarity is observed in the three flow cases in terms of one-point statistics, probability density functions of the wall-shear stress and pressure, spectra, Reynolds stress budgets and advection velocity of the turbulent structures. This supports the notion that the near-wall region is universal for pipe and channel flow. Probability density functions of the wall shear stress, streamwise turbulence intensities, one-dimensional spanwise/azimuthal spectra of the streamwise velocity and Reynolds-stress budgets are very similar near the wall in the three flow cases, suggesting that the three canonical wall-bounded flows share many features. In the wake region, the mean streamwise velocity and Reynolds stress budgets show some expected differences. © Published under licence by IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-03-21

Turbulent rectangular ducts with minimum secondary flow - Vidal, A.; Vinuesa, Ricardo; Schlatter, Philipp; Nagib, H. M. (International Journal of Heat and Fluid Flow, 2018)
In the present study we perform direct numerical simulations (DNSs) of fully-developed turbulent rectangular ducts with semi-cylindrical side-walls at Reτ c ≃ 180 with width-to-height ratios of 3 and 5. The friction Reynolds number Reτ c is based on the centerplane friction velocity and the half-height of the duct. The results are compared with the corresponding duct cases with straight side-walls (Vinuesa et al., 2014), and also with spanwise-periodic channel and pipe flows. We focus on the influence of the semi-cylindrical side-walls on the mean cross-stream secondary flow and on further characterizing the mechanisms that produce it. The role of the secondary and primary Reynolds-shear stresses in the production of the secondary flow is analyzed by means of quadrant analysis and conditional averaging. Unexpectedly, the ducts with semi-cylindrical side-walls exhibit higher cross-flow rates and their secondary vortices relocate near the transition point between the straight and curved walls. This behavior is associated to the statistically preferential arrangement of sweeping events entering through the curved wall and ejections arising from the adjacent straight wall. Therefore, the configuration with minimum secondary flow corresponds to the duct with straight side-walls and sharp corners. Consequences on experimental facilities and comparisons between experiments and various numerical and theoretical models are discussed revealing the uniqueness of pipe flow.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Direct numerical simulation; Secondary flow; Side-wall geometry; Turbulent duct flow; Wall-bounded turbulence

Uncertainty Quantification of Reduced-Precision Time Series in Turbulent Channel Flow - Karp, Martin; Liu, Felix; Stanly, Ronith; Rezaeiravesh, Saleh; Jansson, Niclas; Schlatter, Philipp; Markidis, Stefano (ACM International Conference Proceeding Series, 2023)
With increased computational power through the use of arithmetic in low-precision, a relevant question is how lower precision affects simulation results, especially for chaotic systems where analytical round-off estimates are non-trivial to obtain. In this work, we consider how the uncertainty of the time series of a direct numerical simulation of turbulent channel flow at Ret = 180 is affected when restricted to a reduced-precision representation. We utilize a non-overlapping batch means estimator and find that the mean statistics can, in this case, be obtained with significantly fewer mantissa bits than conventional IEEE-754 double precision, but that the mean values are observed to be more sensitive in the middle of the channel than in the near-wall region. This indicates that using lower precision in the near-wall region, where the majority of the computational efforts are required, may benefit from low-precision floating point units found in upcoming computer hardware.
CRIS-Team Scopus Importer:2023-12-08

Understanding the Impact of Synchronous, Asynchronous, and Hybrid In-Situ Techniques in Computational Fluid Dynamics Applications - Ju, Yi; Perez, Adalberto; Markidis, Stefano; Schlatter, Philipp; Laure, Erwin (Proceedings - 2022 IEEE 18th International Conference on e-Science, eScience 2022, 2022)
High-Performance Computing (HPC) systems provide input/output (IO) performance growing relatively slowly compared to peak computational performance and have limited storage capacity. Computational Fluid Dynamics (CFD) applications aiming to leverage the full power of Exascale HPC systems, such as the solver Nek5000, will generate massive data for further processing. These data need to be efficiently stored via the IO subsystem. However, limited IO performance and storage capacity may result in performance, and thus scientific discovery, bottlenecks. In comparison to traditional post-processing methods, in-situ techniques can reduce or avoid writing and reading the data through the IO subsystem, promising to be a solution to these problems. In this paper, we study the performance and resource usage of three in-situ use cases: data compression, image generation, and uncertainty quantification. We furthermore analyze three approaches when these in-situ tasks and the simulation are executed synchronously, asynchronously, or in a hybrid manner. In-situ compression can be used to reduce the IO time and storage requirements while maintaining data accuracy. Furthermore, in-situ visualization and analysis can save Terabytes of data from being routed through the IO subsystem to storage. However, the overall efficiency is crucially dependent on the characteristics of both, the in-situ task and the simulation. In some cases, the overhead introduced by the in-situ tasks can be substantial. Therefore, it is essential to choose the proper in-situ approach, synchronous, asynchronous, or hybrid, to minimize overhead and maximize the benefits of concurrent execution.
CRIS-Team Scopus Importer:2023-03-21
Keywords: CFD; HPC; in-situ

Uniform blowing and suction applied to nonuniform adverse-pressure-gradient wing boundary layers - Atzori, Marco; Vinuesa, Ricardo; Stroh, Alexander; Gatti, Davide; Frohnapfel, Bettina; Schlatter, Philipp (Physical Review Fluids, 2021)
A detailed analysis of the effects of uniform blowing, uniform suction, and body-force damping on the turbulent boundary layer developing around a NACA4412 airfoil at moderate Reynolds number is presented. The flow over the suction and the pressure sides of the airfoil is subjected to a nonuniform adverse pressure gradient and a moderate favorable pressure gradient, respectively. We find that the changes in total skin friction due to blowing and suction are not very sensitive to different pressure-gradient conditions or the Reynolds number. However, when blowing and suction are applied to an adverse-pressure-gradient (APG) boundary layer, their impact on properties such as the boundary-layer thickness, the intensity of the wall-normal convection, and turbulent fluctuations are more pronounced. We employ the Fukagata-Iwamoto-Kasagi decomposition [K. Fukagata, Phys. Fluids 14, 73 (2002)10.1063/1.1516779] and spectral analysis to study the interaction between intense adverse pressure gradient and these control strategies. We find that the control modifies skin-friction contributions differently in adverse-pressure-gradient and zero-pressure-gradient boundary layers. In particular, the control strategies modify considerably both the streamwise-development and the pressure-gradient contributions, which have high magnitude when a strong adverse pressure gradient is present. Blowing and suction also impact the convection of structures in the wall-normal direction. Overall, our results suggest that it is not possible to simply separate pressure-gradient and control effects, a fact to take into account in future studies on control design in practical applications.
CRIS-Team Scopus Importer:2023-03-21

Universality and scaling phenomenology of small-scale turbulence in wall-bounded flows - Wei, Liang; Elsinga, Gerrit E.; Brethouwer, Geert; Schlatter, Philipp; Johansson, Arne V. (Physics of Fluids, 2014)
The Reynolds number scaling of flow topology in the eigenframe of the strain-rate tensor is investigated for wall-bounded flows, which is motivated by earlier works showing that such topologies appear to be qualitatively universal across turbulent flows. The databases used in the current study are from direct numerical simulations (DNS) of fully developed turbulent channel flow (TCF) up to friction Reynolds number Reτ ≈ 1500, and a spatially developing, zero-pressure-gradient turbulent boundary layer (TBL) up to ReΘ ≈ 4300 (Ret ≈ 1400). It is found that for TCF and TBL at different Reynolds numbers, the averaged flow patterns in the local strain-rate eigenframe appear the same consisting of a pair of co-rotating vortices embedded in a finite-size shear layer. It is found that the core of the shear layer associated with the intense vorticity region scales on the Kolmogorov length scale, while the overall height of the shear layer and the distance between the vortices scale well with the Taylor micro scale. Moreover, the Taylor micro scale collapses the height of the shear layer in the direction of the vorticity stretching. The outer region of the averaged flow patterns approximately scales with the macro scale, which indicates that the flow patterns outside of the shear layer mainly are determined by large scales. The strength of the shear layer in terms of the peak tangential velocity appears to scale with a mixture of the Kolmogorov velocity and root-mean-square of the streamwise velocity scaling. A quantitative universality in the reported shear layers is observed across both wall-bounded flows for locations above the buffer region. © 2014 AIP Publishing LLC.
CRIS-Team Scopus Importer:2023-03-21

Unsteady aerodynamic effects in pitching airfoils studied through large-eddy simulations - Negi, Prabal S.; Vinuesa, Ricardo; Schlatter, Philipp; Hanifi, Ardeshir; Henningson, Dan S. (10th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2017, 2017)
Wall-resolved large-eddy simulations (LES) are utilized to investigate the flow-physics of an airfoil undergoing pitch oscillations. A relaxation-term (RT) based filtering procedure is employed to add limited high order dissipation to account for the dissipation from the smallest scales which are not resolved. Validation of the procedure is presented for turbulent channel flows and for flow around a wing section. The procedure is then used for the simulation of small-amplitude pitching airfoil at Rec = 100;000 with a reduced frequency k = 0:5. The investigation of the unsteady phenomenon is done in the context of a natural laminar flow airfoil, the performance of which depends critically on the suction side transition characteristics. The dynamic range of the pitch cycle sees the appearance, destabilization and disappearance of a laminar separation bubble at the leading edge. An abrupt change is seen in the lift coefficient, which is linked to a rapid movement of the transition point over the suction side. Destabilization of the laminar separation bubble is the cause of these rapid transition movements which occur near the end of the pitch-up phase of the cycle.
CRIS-Team Scopus Importer:2023-03-21

Unsteady aerodynamic effects in small-amplitude pitch oscillations of an airfoil - Negi, P. S.; Vinuesa, Ricardo; Hanifi, A.; Schlatter, Philipp; Henningson, D. S. (International Journal of Heat and Fluid Flow, 2018)
High-fidelity wall-resolved large-eddy simulations (LES) are utilized to investigate the flow-physics of small-amplitude pitch oscillations of an airfoil at Rec=100,000. The investigation of the unsteady phenomenon is done in the context of natural laminar flow airfoils, which can display sensitive dependence of the aerodynamic forces on the angle of attack in certain “off-design” conditions. The dynamic range of the pitch oscillations is chosen to be in this sensitive region. Large variations of the transition point on the suction-side of the airfoil are observed throughout the pitch cycle resulting in a dynamically rich flow response. Changes in the stability characteristics of a leading-edge laminar separation bubble has a dominating influence on the boundary layer dynamics and causes an abrupt change in the transition location over the airfoil. The LES procedure is based on a relaxation-term which models the dissipation of the smallest unresolved scales. The validation of the procedure is provided for channel flows and for a stationary wing at Rec=400,000.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Dynamic-response; Laminar separation bubble; Local stability; Transition; Unsteady aerodynamics; Wall-resolved les

Using adaptive mesh refinement to simulate turbulent wings at high Reynolds numbers - Tanarro, Álvaro; Mallor, Fermín; Offermans, Nicolas; Peplinski, Adam; Vinuesa, Ricardo; Schlatter, Philipp (11th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2019, 2019)
The implementation of adaptive mesh refinement (AMR) in Nek5000 is used for the first time on the simulation of the flow over wings. This is done by simulating the flow over a NACA4412 profile with 5° angle of attack at chord-based Reynolds number 200,000. The mesh is progressively refined by means of AMR which allows for high resolution near the wall whereas significantly larger elements are used in the far-field. The resultant mesh shows higher resolution than previous conformal meshes, and it allows for larger computational domains, which avoid the use of RANS to determine the boundary condition, all of this with, approximately, 3 times lower total number of grid points. The results of the turbulence statistics show a good agreement with the ones obtained with the conformal mesh. Finally, using AMR on wings leads to simulations at higher Reynolds numbers (i.e. Rec = 850,000) in order to analyse the effect of adverse pressure gradients at high Reynolds numbers.
CRIS-Team Scopus Importer:2023-03-21

Wall accumulation and spatial localization in particle-laden wall flows - Sardina, Gaetano; Schlatter, Philipp; Brandt, Luca; Picano, Francesco; Casciola, C. M. (Journal of Fluid Mechanics, 2012)
We study the two main phenomenologies associated with the transport of inertial particles in turbulent flows, turbophoresis and small-scale clustering. Turbophoresis describes the turbulence-induced wall accumulation of particles dispersed in wall turbulence, while small-scale clustering is a form of local segregation that affects the particle distribution in the presence of fine-scale turbulence. Despite the fact that the two aspects are usually addressed separately, this paper shows that they occur simultaneously in wall-bounded flows, where they represent different aspects of the same process. We study these phenomena by post-processing data from a direct numerical simulation of turbulent channel flow with different populations of inertial particles. It is shown that artificial domain truncation can easily alter the mean particle concentration profile, unless the domain is large enough to exclude possible correlation of the turbulence and the near-wall particle aggregates. The data show a strong link between accumulation level and clustering intensity in the near-wall region. At statistical steady state, most accumulating particles aggregate in strongly directional and almost filamentary structures, as found by considering suitable two-point observables able to extract clustering intensity and anisotropy. The analysis provides quantitative indications of the wall-segregation process as a function of the particle inertia. It is shown that, although the most wall-accumulating particles are too heavy to segregate in homogeneous turbulence, they exhibit the most intense local small-scale clustering near the wall as measured by the singularity exponent of the particle pair correlation function. © 2012 Cambridge University Press.
CRIS-Team Scopus Importer:2023-03-21
Keywords: particle/fluid flow; turbulence simulation; turbulent mixing

WALL-MODELLED LES USING HIGH- AND LOW-ORDER CFD CODES: APPLICATION TO A FLAT-PLATE BOUNDARY LAYER - Mukha, Timofey; Schlatter, Philipp (12th International Symposium on Turbulence and Shear Flow Phenomena, TSFP 2022, 2022)
Results from wall-modelled large-eddy simulations of a zero-pressure-gradient flat-plate turbulent boundary layer in the range Reθ ≈ [4000,12000] are reported. The simulations are performed using a low- and a high-order code: OpenFOAM® and Nek5000, respectively. For the latter, such simulations have previously not been reported in the literature. Structured hexahedral meshes are used, with two levels of refinement. As an important aspect in the wall modelling methodology, we use a temporally varying wall viscosity in order to enforce the wall shear stress. An equivalent inflow generation procedure is used for both codes, allowing for a more fair comparison. Results from Nek5000 simulations are generally more accurate. Both the skin friction and the profiles of velocity statistics are in good agreement with reference data. For Nek5000, this is an important milestone in the development of wall modelling capabilities for this solver. The results from OpenFOAM simulations exhibit a significant over-prediction of the skin friction, which has not been previously reported in the literature. Further investigation of the simulation methodology is necessary to find the cause of the problematic behaviour.
CRIS-Team Scopus Importer:2023-03-21

Wall oscillation induced drag reduction of turbulent boundary layers - Skote, Martin; Mishra, Maneesh; Negi, Prabal Singh; Wu, Yanhua; Lee, Hsiao Mun; Schlatter, Philipp (Springer Proceedings in Physics, 2016)
Spanwise oscillation applied on the wall under a turbulent boundary layer flow is investigated using direct numerical simulation. The temporal wall-forcing produces considerable drag reduction over the region where oscillation occurs. The turbulence fluctuations downstream of the oscillations are presented for the first time. Simulations with identical oscillation parameters have been performed at different Reynolds numbers to investigate the effect on the drag reduction. One of the simulations replicates an earlier experiment to test the fidelity of the current simulations. In addition, we present the future work in this area with an integrated experimental and computational investigation to explore the possibility of applying travelling waves (oscillations in both time and space) as the mode of wall motion for active control of near-wall turbulence.
CRIS-Team Scopus Importer:2023-03-21

Wavepackets in turbulent flow over a NACA 4412 airfoil - Abreu, Leandra I.; Cavalieri, André V.G.; Schlatter, Philipp; Vinuesa, Ricardo; Henningson, Dan (31st Congress of the International Council of the Aeronautical Sciences, ICAS 2018, 2018)
Turbulent flow over a NACA 4412 airfoil with an angle of attack AoA = 5 ◦ was analysed using an incompressible direct numerical simulation (DNS) at chord Reynolds number of Re c = 4 · 10 5 . Snapshots of the flow field were analysed using the method of Spectral Proper Orthogonal Decomposition (SPOD) in frequency domain, in order to extract the dominant coherent structures of the flow. Focus is given to two-dimensional disturbances, known to be most relevant for aeroacoustics. The leading SPOD modes show coherent structures forming a wavepacket, with significant amplitudes in the trailing-edge boundary layer and in the wake. To model coherent structures in the turbulent boundary layer, the optimal harmonic forcing and the associated linear response of the flow were obtained using the singular value decomposition of the linear resolvent operator. The resolvent analysis shows that the leading SPOD modes can be associated to most amplified, linearised flow responses. Furthermore, coherent structures in the wake are modelled as the Kelvin-Helmholtz mode from linear stability theory (LST).
CRIS-Team Scopus Importer:2023-03-21
Keywords: Coherent structures; Reduced order models; Resolvent analysis; SPOD; Wavepackets

Widest scales in turbulent channels - Pozuelo, R.; Cavalieri, A.; Schlatter, Philipp; Vinuesa, R. (Physics of Fluids, 2024)
The widest spanwise scales in turbulent channel flows are studied through the use of three periodic channel-flow simulations at friction Reynolds number Re τ = 550 . The length and height of the channels are the same in all cases ( L x / h = 8 π and L y / h = 2 , respectively), while the width is progressively doubled: L z / h = 4 π , 8 π , 16 π . The effects of increasing the domain width cannot be determined with statistical significance in our simulations, since the difference in the statistics between the simulations is of the same order as the errors of convergence. A channel flow similar to the smaller one [Del Álamo et al., “Scaling of the energy spectra of turbulent channels,” J. Fluid Mech. 500, 135-144 (2004)], which was averaged over a very long time, was used as a reference. The one-dimensional spanwise spectrum of the streamwise velocity is computed with the aim of assessing the domain-size effect on the widest scales. Our results indicate that 90% of the total streamwise energetic fluctuations is recovered without a significant influence of the size of the domain. The remaining 10% of the energy reflects that the widest scales in the outer layer are the ones most significantly affected by the spanwise length of the domain. The power-spectral density for kz = 0 remains constant even if the size of the domain in the spanwise direction is increased up to four times the standard spanwise length, indicating that wide, spanwise coherent structures are not an artifact of domain truncation.
CRIS-Team Scopus Importer:2025-02-04